The distribution of coagulation factors VII and VIII and fibrinogen in adults over 65 years. Results from the Cardiovascular Health Study. - Tracy, R P; Bovill, E G; Fried, L P; Heiss, G; Lee, M H; Polak, J F; Psaty, B M; Savage, P J (Ann Epidemiol, 1992)
The Cardiovascular Health Study (CHS) was designed to examine cardiovascular disease and its risk factors in older adults. We report here the distributions of the coagulation factors fibrinogen, factor VII, and factor VIII in a population-based cohort of men and women 65 years or older. In other studies of middle-aged individuals, these factors were shown to be associated with cardiovascular risk. In the CHS cohort, all three factors were elevated, compared to levels reported in middle-aged individuals, and fibrinogen and factor VIII values were higher in each successive age group; factor VII values, in contrast, declined slightly with age in the CHS cohort. Compared to white subjects, blacks had higher values for fibrinogen and factor VIII and lower values for factor VII. While women had markedly higher values for factor VII and factor VIII than men at all ages in the CHS, mean fibrinogen values were not different between men and women.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Middle Aged; Risk Factors

Hematological and biochemical laboratory values in older Cardiovascular Health Study participants. - Robbins, J; Wahl, P; Savage, P; Enright, P; Powe, N; Lyles, M (J Am Geriatr Soc, 1995)
OBJECTIVE: To define reference hematologic and biochemical lab values in older individuals. DESIGN: Randomly selected, age- and gender-stratified participants. SETTING: Visits by participants to four research clinics. PATIENTS: A total of 5201 participants in the Cardiovascular Health Study, an observational study of older Medicare-eligible individuals living at home. MEASUREMENT: Information about health status, previous illness, and medication use was obtained from participants and/or their MDs. This information was used to define a healthy subset of the population. Blood samples were obtained for Cholesterol, HDL and LDL cholesterol, fasting and 2-hour postload glucose and insulin, fibrinogen, factors VII and VIII, potassium, creatinine, albumin, uric acid, white blood count, hematocrit, hemoglobin, and platelet count. RESULTS: Significant differences were found for age group and/or gender for all mean values. Many tests were significantly different from the generally accepted reference ranges used in clinical laboratories. CONCLUSIONS: In some situations accepted laboratory norms for the general population can not be extrapolated to older adults. There are implications for both research and clinical practice.
Keywords: Age Factors; Aged; Analysis of Variance; California; Cardiovascular Diseases; Cohort Studies; Female; Health Status; Humans; Male; Maryland; Middle Aged; North Carolina; Pennsylvania; Reference Values; Risk Factors; Sex Characteristics

Reduced vital capacity in elderly persons with hypertension, coronary heart disease, or left ventricular hypertrophy. The Cardiovascular Health Study. - Enright, P L; Kronmal, R A; Smith, V E; Gardin, J M; Schenker, M B; Manolio, T A (Chest, 1995)
The Cardiovascular Health Study provided the opportunity to determine the association of subclinical and clinical cardiovascular disease with pulmonary function in a population sample of elderly adults. Included were 2,955 women and 2,246 men over age 64 years who were recruited for this observational study from four communities and completed extensive examinations that included spirometry, echocardiograms, and blood pressure. Current smokers, past smokers with >20 pack-years of smoking, and persons with a history of asthma, chronic bronchitis, or emphysema were excluded from this analysis, leaving 2,784 (55%) of the cohort. Systolic hypertension or coronary artery disease was associated with 40- to 100-mL decrements in FEV1, and 50- to 150-mL decrements in FVC, while a history of congestive heart failure was associated with 200 to 300 mL lower FEV1 and FVC values (p < 0.0001), after correcting for age, height, and waist size. Higher left ventricular (LV) mass was also significantly associated with a decrease in FEV1 and FVC in multivariate models. This relationship was strongest with the end-diastolic LV posterior wall thickness component of LV mass. In summary, FEV1 and FVC are reduced in elderly persons with hypertension, ischemic heart disease, higher disease, higher LV mass, and congestive heart failure, though the magnitude of these associations is relatively small unless heart failure supervenes. Substantial decrements in percent predicted FEV1 and FVC should not be attributed to the presence of uncomplicated ischemic heart disease or hypertension alone.
Keywords: Age Factors; Aged; Aged, 80 and over; Coronary Disease; Female; Forced Expiratory Volume; Humans; Hypertension; Hypertrophy, Left Ventricular; Male; Middle Aged; Ventricular Function, Left; Vital Capacity

Risk factors for abdominal aortic aneurysms in older adults enrolled in The Cardiovascular Health Study. - Alcorn, H G; Wolfson, S K; Sutton-Tyrrell, K; Kuller, L H; O'Leary, D (Arterioscler Thromb Vasc Biol, 1996)
B-mode ultrasound examinations of the abdominal aorta were performed from 1990 to 1992 to evaluate the prevalence of abdominal aortic aneurysm (AAA) in a subgroup of the Pittsburgh cohort (656 participants, aged 65 to 90 years) of the Cardiovascular Health Study (CHS). In this pilot study, we evaluated various definitions of aneurysm and the reproducibility of the measurements. In year 5 (1992 to 1993) of the CHS, the entire cohort (4741 participants) was examined. AAA was defined as an infrarenal aortic diameter of > or= 3.0 cm, or a ratio of infrarenal to suprarenal diameter of > or= 1.2, or a history of AAA repair. For the entire CHS cohort, prevalence of aneurysms was 9.5% (451/4741) overall, with a prevalence among men of 14.2% (278/1956) and prevalence among women of 6.2% (173/2785). Variables significantly related to AAA were older age; male sex; history of angina, coronary heart disease, and myocardial infarction; lower ankle-arm blood pressure ratio; higher maximum carotid stenosis; greater intima-media thickness of the internal carotid artery; higher creatinine; lower HDL levels and higher LDL levels; and cigarette smoking. The study has documented the strong association of cardiovascular risk factors and measures of clinical and subclinical atherosclerosis and cardiovascular disease and prevalence of aneurysms. We used a definition that is more sensitive than previously reported (diameter or ratio), which allowed the detection of smaller aneurysms and possibly those at an earlier stage of development. Follow-up of this cohort may lead to new criteria for determining the risk factors for progression of aneurysms.
Keywords: Aged; Anthropometry; Aortic Aneurysm, Abdominal; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Humans; Male; Middle Aged; Pilot Projects; Prevalence; Reproducibility of Results; Risk Factors; Smoking; Ultrasonography; United States

Carrying the burden of cardiovascular risk in old age: associations of weight and weight change with prevalent cardiovascular disease, risk factors, and health status in the Cardiovascular Health Study. - Harris, T B; Savage, P J; Tell, G S; Haan, M; Kumanyika, S; Lynch, J C (Am J Clin Nutr, 1997)
Measured weight in old age, reported weight at age 50 y, and weight change from age 50 y to old age were studied in association with prevalent cardiovascular disease (CVD), CVD risk factors, and health status in a population of 4954 men and women aged > or = 65 y in the Cardiovascular Health Study (CHS). Heavier weight (i.e., generally weight in the fourth quartile for the cohort) at age 50 y was more closely associated with prevalent CVD than was current weight, with these associations stronger in women than in men. Heavier current weight and heavier weight at age 50 y were associated with cardiovascular risk factors, including higher blood pressure, lower high-density-lipoprotein cholesterol, and higher fasting insulin. Heavier weight at both time points was related to mobility problems in both men and women and to lower current physical activity levels; among women, strong associations were also seen with lower education and current income. Remaining within 10% of reported weight at age 50 y was associated with better health status as measured by reported health, mobility difficulty, number of medications, and prevalent CVD in men. Paradoxically, most cardiovascular risk factors were lowest for weight losers despite an association of weight loss with poorer health. In this cohort of persons aged > or = 65 y, heavier weight was associated with CVD and CVD risk factors, suggesting that prevention of overweight may prove beneficial in improving cardiovascular risk in older persons. Weight stability from age 50 y to old age was associated with better health status than was weight gain or loss.
Keywords: Aged; Blood Pressure; Body Constitution; Body Weight; Cardiovascular Diseases; Cholesterol, LDL; Female; Health Status; Humans; Insulin; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prevalence; Risk Factors; Sex Characteristics

Correlates of performance-based measures of muscle function in the elderly: the Cardiovascular Health Study. - Hirsch, C H; Fried, L P; Harris, T; Fitzpatrick, A; Enright, P; Schulz, R (J Gerontol A Biol Sci Med Sci, 1997)
BACKGROUND: It is unknown how much age-related changes in muscle performance represent normal aging versus the effects of chronic disease and life style. We examined the correlates of four performance measures-gait speed, timed chair stands (TCS), grip strength, and maximal inspiratory pressure (MIP)-using baseline data from the Cardiovascular Health Study (CHS), a population-based study of risk factors for heart disease and stroke in persons > or = age 65. METHODS: We analyzed data from the 5,201 CHS participants. Variables were arranged into nine categories: Personal Characteristics, Anthropometry, Physical Condition, Reported Functional Status, Subjective Health, Psychological Factors, Symptoms, Cognitive Status, Habits and Lifestyle, and Prevalent Disease. Independent correlates were identified using stepwise linear regression. RESULTS: The regression models explained 17.7-25.4% of the observed variability. Although age significantly correlated with each measure, it explained little of the variability (< or = 5.7%). Anthropometric features plus physical condition explained 14.0-17.4% of the variability for grip strength and MIP, but 2.8-12.9% of the variability for gait speed and the log of TCS. Subjective health and psychological factors explained 1.8-9.4% of the variability in gait speed and the log of TCS, but < or = 1.2% of the variability in grip strength and MIP. Variables for prevalent disease explained < or = 1.3% of the variability in each measure. CONCLUSIONS: After age 64, age explained little of the variability in muscle performance in a large sample of mostly functionally intact, community-dwelling older persons. Complex measures such as gait speed were more associated with subjective factors than were direct measures of strength. Prevalent disease contributed surprisingly little to muscle performance.
Keywords: Aging; Anthropometry; Cardiovascular Physiological Phenomena; Female; Gait; Hand Strength; Health Status; Humans; Male; Middle Aged; Motor Activity; Muscles; Pressure; Regression Analysis; Respiration

Does the association of risk factors and atherosclerosis change with age? An analysis of the combined ARIC and CHS cohorts. The Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health Study (CHS) investigators. - Howard, G; Manolio, T A; Burke, G L; Wolfson, S K; O'Leary, D H (Stroke, 1997)
INTRODUCTION: A decrease in the estimated relative risk of cerebrovascular and cardiovascular diseases associated with known disease risk factors has been observed among elderly cohorts, perhaps suggesting that continued risk factor management in the elderly may not be as efficacious as with younger age groups. In this paper, the differential magnitude of the association of risk factors with atherosclerosis across the age spectrum from 45 years to older than 75 years is presented. METHODS: Subclinical atherosclerosis as measured by carotid ultrasonography and risk factor prevalence were assessed using similar methods among participants aged 45 to 64 years in the Atherosclerosis Risk in Communities (ARIC) study and among participants 65 years and older in the Cardiovascular Health Study (CHS). Pooling these two cohorts provided data on the relationship of risk factors and atherosclerosis on nearly 19,000 participants over a broad age range. Regression analyses were used to assess the consistency of the magnitude of the association of risk factors with atherosclerosis across the age spectrum separately for black and white participants in cross-sectional analyses. RESULTS: As expected, each of the risk factors was globally (across all ages) associated with increased atherosclerosis. However, the magnitude of the association did not differ across the age spectrum for hypertension, low density lipoprotein cholesterol (LDL-c), fibrinogen, or body mass index (BMI). For whites, there was a significantly greater impact of smoking and HDL-C among older age strata but a smaller impact of diabetes. For black women, the impact of HDL-C decreased among the older age strata. CONCLUSIONS: These data suggest that most risk factors continue to be associated with increased atherosclerosis at older ages, possibly suggesting a continued value in investigation of strategies to reduce atherosclerosis by controlling risk factors at older ages.
Keywords: African Americans; African Continental Ancestry Group; Aged; Aging; Arteriosclerosis; Body Mass Index; Cardiovascular Physiological Phenomena; Cardiovascular System; Carotid Arteries; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Health Status; Humans; Hypertension; Male; Middle Aged; Regression Analysis; Risk Factors; Sex Factors; Smoking; Tunica Intima; Tunica Media; Ultrasonography

Health status of individuals with mild stroke. - Duncan, P W; Samsa, G P; Weinberger, M; Goldstein, L B; Bonito, A; Witter, D M; Enarson, C; Matchar, D (Stroke, 1997)
BACKGROUND AND PURPOSE: Diminished quality of life and limitations in higher levels of physical functioning are often underestimated in stroke and are not fully captured by measures such as the Barthel Index and the Rankin Outcome Scale. This study used additional measures to assess the health status of 304 persons with mild stroke and to compare these individuals with 184 persons with transient ischemic attack and 654 persons without history of stroke/transient ischemic attack but at elevated risk for stroke (asymptomatic group). METHODS: Subjects were recruited from the Academic Medical Center Consortium (inpatients), the Cardiovascular Health Study (population-based sample of community-dwelling persons 65 years and older), and United HealthCare (inpatients and outpatients typically younger than 65 years). Subjects were interviewed by telephone or in person to assess activities of daily living (Barthel Index), depression (Center for Epidemiological Studies Depression Scale), health status (MOS-36), and utility for current health state. RESULTS: Most respondents were independent on all Barthel items. The stroke group was more impaired on the MOS-36 than the asymptomatic group but similar to the group with transient ischemic attack. Health-related quality of life was lowest for persons with stroke. While symptom status and Barthel Index score were the strongest predictors of health status, the Barthel Index showed a consistent ceiling effect when compared with the physical function subscale of the MOS-36. CONCLUSIONS: The consequences of even mild stroke affect all dimensions of health except pain. Standardized assessment of persons with stroke must evaluate across the entire continuum of health-related functions.
Keywords: Age Distribution; Aged; Cerebrovascular Disorders; European Continental Ancestry Group; Female; Health Status; Humans; Ischemic Attack, Transient; Male; Middle Aged; Social Support

Knowledge of risk among patients at increased risk for stroke. - Samsa, G P; Cohen, S J; Goldstein, L B; Bonito, A J; Duncan, P W; Enarson, C; DeFriese, G H; Horner, R D; Matchar, D B (Stroke, 1997)
BACKGROUND AND PURPOSE: Patients who recognize their increased risk for stroke are more likely to engage in (and comply with) stroke prevention practices than those who do not. We describe perceived risk of stroke among a nationally diverse sample of patients at increased risk for stroke and determine whether patients' knowledge of their stroke risk varied according to patients' demographic and clinical characteristics. METHODS: Respondents were recruited from the Academic Medical Center Consortium (n = 621, five academic medical centers, inpatients of varying age); the Cardiovascular Health Study (n = 321, population-based sample of persons aged 65+ years); and United HealthCare (n = 319, five health plans, inpatients and outpatients typically younger than 65 years). The primary outcome was awareness of being at risk for stroke. RESULTS: Only 41% of respondents were aware of their increased risk for stroke (including less than one half of patients with previous minor stroke). Approximately 74% of patients who recalled being told of their increased stroke risk by a physician acknowledged this risk in comparison with 28% of patients who did not recall being informed by a physician. Younger patients, depressed patients, those in poor current health, and those with a history of TIA were most likely to be aware of their stroke risk. CONCLUSIONS: Over one half of patients at increased risk of stroke are unaware of their risk. Healthcare providers play a crucial role in communicating information about risk, and successful communication encourages adoption of stroke prevention practices. Educational messages should be targeted toward patients least likely to be aware of their risk.
Keywords: Adult; Aged; Aged, 80 and over; Awareness; Cerebrovascular Disorders; Female; Humans; Knowledge; Male; Middle Aged; Multivariate Analysis; Risk Factors

The Sleep Heart Health Study: design, rationale, and methods. - Quan, S F; Howard, B V; Iber, C; Kiley, J P; Nieto, F J; O'Connor, G T; Rapoport, D M; Redline, S; Robbins, J; Samet, J M; Wahl, P W (Sleep, 1997)
The Sleep Heart Health Study (SHHS) is a prospective cohort study designed to investigate obstructive sleep apnea (OSA) and other sleep-disordered breathing (SDB) as risk factors for the development of cardiovascular disease. The study is designed to enroll 6,600 adult participants aged 40 years and older who will undergo a home polysomnogram to assess the presence of OSA and other SDB. Participants in SHHS have been recruited from cohort studies in progress. Therefore, SHHS adds the assessment of OSA to the protocols of these studies and will use already collected data on the principal risk factors for cardiovascular disease as well as follow-up and outcome information pertaining to cardiovascular disease. Parent cohort studies and recruitment targets for these cohorts are the following: Atherosclerosis Risk in Communities Study (1,750 participants), Cardiovascular Health Study (1,350 participants), Framingham Heart Study (1,000 participants), Strong Heart Study (600 participants), New York Hypertension Cohorts (1,000 participants), and Tucson Epidemiologic Study of Airways Obstructive Diseases and the Health and Environment Study (900 participants). As part of the parent study follow-up procedures, participants will be surveyed at periodic intervals for the incidence and recurrence of cardiovascular disease events. The study provides sufficient statistical power for assessing OSA and other SDB as risk factors for major cardiovascular events, including myocardial infarction and stroke.
Keywords: Adult; Aged; Aged, 80 and over; Arteriosclerosis; Cohort Studies; Coronary Disease; Female; Humans; Hypertension; Longitudinal Studies; Male; Middle Aged; Polysomnography; Positive-Pressure Respiration; Prospective Studies; Research Design; Sleep Apnea Syndromes

Factor V Leiden is not a risk factor for arterial vascular disease in the elderly: results from the Cardiovascular Health Study. - Cushman, M; Rosendaal, F R; Psaty, B M; Cook, E F; Valliere, J; Kuller, L H; Tracy, R P (Thromb Haemost, 1998)
Coagulation factor V Leiden is a risk marker for venous thrombosis. For arterial thrombosis no large study to date has included population-based elderly patients. The Cardiovascular Health Study is a longitudinal study of 5,201 men and women over age 65. With 3.4-year follow-up, we studied 373 incident cases of myocardial infarction (MI), angina, stroke. or transient ischemic attack (TIA), and 482 controls. The odds ratios for each event with heterozygous factor V Leiden were: MI, 0.46 (95% CI 0.17 to 1.25); angina, 1.0 (95% CI 0.45 to 2.23); stroke, 0.77 (95% CI 0.35 to 1.70): TIA, 1.33 (95% CI 0.5 to 3.55); any outcome, 0.83 (95% CI 0.48 to 1.44). Adjustment for cardiovascular risk factors did not change relationships. In older adults factor V Leiden is not a risk factor for future arterial thrombosis.
Keywords: Adult; Age Factors; Aged; Arteries; Factor V; Female; Humans; Male; Middle Aged; Mutation; Risk Factors; Thrombosis

Utilities for major stroke: results from a survey of preferences among persons at increased risk for stroke. - Samsa, G P; Matchar, D B; Goldstein, L; Bonito, A; Duncan, P W; Lipscomb, J; Enarson, C; Witter, D; Venus, P; Paul, J E; Weinberger, M (Am Heart J, 1998)
BACKGROUND: Patient beliefs, values, and preferences are crucial to decisions involving health care. In a large sample of persons at increased risk for stroke, we examined attitudes toward hypothetical major stroke. METHODS AND RESULTS: Respondents were obtained from the Academic Medical Center Consortium (n = 621), the Cardiovascular Health Study (n = 321 ), and United Health Care (n = 319). Preferences were primarily assessed by using the time trade off (TTO). Although major stroke is generally considered an undesirable event (mean TTO = 0.30), responses were varied: although 45% of respondents considered major stroke to be a worse outcome than death, 15% were willing to trade off little or no survival to avoid a major stroke. CONCLUSIONS: Providers should speak directly with patients about beliefs, values, and preferences. Stroke-related interventions, even those with a high price or less than dramatic clinical benefits, are likely to be cost-effective if they prevent an outcome (major stroke) that is so undesirable.
Keywords: Adult; Age Distribution; Aged; Aged, 80 and over; Attitude to Health; Female; Health Status; Humans; Intracranial Embolism and Thrombosis; Male; Middle Aged; Quality of Life; Sex Distribution; Surveys and Questionnaires; United States

Analytical and biologic variability in measures of hemostasis, fibrinolysis, and inflammation: assessment and implications for epidemiology. - Sakkinen, P A; Macy, E M; Callas, P W; Cornell, E S; Hayes, T E; Kuller, L H; Tracy, R P (Am J Epidemiol, 1999)
An increasing number of cardiovascular epidemiologic studies are measuring non-traditional risk markers of disease, most of which do not have established biovariability characteristics. When biovariability data have been reported, they usually represent a short time period, and, in any case, there is little consensus on how the information should be used. The authors performed a long-term (6-month) repeated measures study on 26 healthy individuals, and, using a nested analysis of variance (ANOVA) approach, report on the analytical (CVA), intraindividual (CVI), and between individual (CVG) variability of 12 procoagulant, fibrinolysis, and inflammation assays, including total cholesterol for comparison. The results suggest acceptable analytical variability (CVA < or = 1/2 CVI) for all assays. However, there was a large range of intraindividual variation as a proportion of total variance (2-78%), and adjusting for intraindividual and between individual variation in bivariate correlations increased the observed correlation by more than 30 percent for three of these assays. Overall, the assays showed a significant increase in intraindividual variation over 6 months (p < 0.05). While these findings suggest that most of these assays have biovariability characteristics similar to cholesterol, there is variation among assays. Some assays may be better suited to epidemiologic studies, and knowledge of an assay's biovariability data may be useful in interpreting simple statistics, and in designing multivariate models.
Keywords: Adult; Aged; Analysis of Variance; Cardiovascular Diseases; Cholesterol; Epidemiology; Female; Fibrinolysis; Hemostasis; Humans; Inflammation; Male; Middle Aged; Models, Statistical; Multivariate Analysis; Risk Factors

Relation of sleepiness to respiratory disturbance index: the Sleep Heart Health Study. - Gottlieb, D J; Whitney, C W; Bonekat, W H; Iber, C; James, G D; Lebowitz, M; Nieto, F J; Rosenberg, C E (Am J Respir Crit Care Med, 1999)
Obstructive sleep apnea syndrome is a well recognized cause of excessive sleepiness; however, the relation of sleepiness to mild sleep-disordered breathing (SDB), which affects as much as half the adult population, is uncertain. In order to explore this relation, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study, a longitudinal study of the cardiovascular consequences of SDB. The study sample comprises 886 men and 938 women, with a mean age of 65 (SD 11) yr. Sleepiness was quantified using the Epworth Sleepiness Scale (ESS). Sleep-disordered breathing was quantified by the respiratory disturbance index (RDI), defined as the number of apneas plus hypopneas per hour of sleep, measured during in-home polysomnography. When RDI was categorized into four groups (< 5, 5 to < 15, 15 to < 30, >/= 30), a significantly progressive increase in mean ESS score was seen across all four levels of SDB, from 7.2 (4.3) in subjects with RDI < 5 to 9.3 (4.9) in subjects with RDI >/= 30 (p < 0.001). There was no significant modification of this effect by age, sex, body mass index, or evidence of chronic restriction of sleep time or periodic limb movement disorder. The percentage of subjects with excessive sleepiness, defined as an ESS score >/= 11, increased from 21% in subjects with RDI < 5 to 35% in those with RDI >/= 30 (p < 0. 001). We conclude that SDB is associated with excess sleepiness in community-dwelling, middle-aged and older adults, not limited to those with clinically apparent sleep apnea.
Keywords: Aged; Cardiovascular Diseases; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Respiration; Retrospective Studies; Severity of Illness Index; Sleep Apnea Syndromes; Surveys and Questionnaires

Association of sleep-disordered breathing, sleep apnea, and hypertension in a large community-based study. Sleep Heart Health Study. - Nieto, F J; Young, T B; Lind, B K; Shahar, E; Samet, J M; Redline, S; D'Agostino, R B; Newman, A B; Lebowitz, M D; Pickering, T G (JAMA, 2000)
CONTEXT: Sleep-disordered breathing (SDB) and sleep apnea have been linked to hypertension in previous studies, but most of these studies used surrogate information to define SDB (eg, snoring) and were based on small clinic populations, or both. OBJECTIVE: To assess the association between SDB and hypertension in a large cohort of middle-aged and older persons. DESIGN AND SETTING: Cross-sectional analyses of participants in the Sleep Heart Health Study, a community-based multicenter study conducted between November 1995 and January 1998. PARTICIPANTS: A total of 6132 subjects recruited from ongoing population-based studies (aged > or = 40 years; 52.8% female). MAIN OUTCOME MEASURES: Apnea-hypopnea index (AHI, the average number of apneas plus hypopneas per hour of sleep, with apnea defined as a cessation of airflow and hypopnea defined as a > or = 30% reduction in airflow or thoracoabdominal excursion both of which are accompanied by a > or = 4% drop in oxyhemoglobin saturation) [corrected], obtained by unattended home polysomnography. Other measures include arousal index; percentage of sleep time below 90% oxygen saturation; history of snoring; and presence of hypertension, defined as resting blood pressure of at least 140/90 mm Hg or use of antihypertensive medication. RESULTS: Mean systolic and diastolic blood pressure and prevalence of hypertension increased significantly with increasing SDB measures, although some of this association was explained by body mass index (BMI). After adjusting for demographics and anthropometric variables (including BMI, neck circumference, and waist-to-hip ratio), as well as for alcohol intake and smoking, the odds ratio for hypertension, comparing the highest category of AHI (> or = 30 per hour) with the lowest category (< 1.5 per hour), was 1.37 (95% confidence interval [CI], 1.03-1.83; P for trend = .005). The corresponding estimate comparing the highest and lowest categories of percentage of sleep time below 90% oxygen saturation (> or = 12% vs < 0.05%) was 1.46 (95% CI, 1.12-1.88; P for trend <.001). In stratified analyses, associations of hypertension with either measure of SDB were seen in both sexes, older and younger ages, all ethnic groups, and among normal-weight and overweight individuals. Weaker and nonsignificant associations were observed for the arousal index or self-reported history of habitual snoring. CONCLUSION: Our findings from the largest cross-sectional study to date indicate that SDB is associated with systemic hypertension in middle-aged and older individuals of different sexes and ethnic backgrounds.
Keywords: Adult; Aged; Cohort Studies; Cross-Sectional Studies; Female; Humans; Hypertension; Logistic Models; Male; Middle Aged; Obesity; Polysomnography; Sleep Apnea Syndromes; Snoring

Clustering of procoagulation, inflammation, and fibrinolysis variables with metabolic factors in insulin resistance syndrome. - Sakkinen, P A; Wahl, P; Cushman, M; Lewis, M R; Tracy, R P (Am J Epidemiol, 2000)
The known metabolic cardiovascular disease risk factors associated with insulin resistance syndrome (IRS) do not adequately explain the excess cardiovascular disease risk attributed to this syndrome, and abnormalities in hemostatic variables may contribute to this excess risk. Using data from 322 nondiabetic elderly men and women (aged 65-100 years) participating in the Cardiovascular Health Study during 1989-1990, the authors performed factor analysis on 10 metabolic risk factors associated with IRS and 11 procoagulation, inflammation, and fibrinolysis variables to examine the clustering of the metabolic and hemostatic risk markers. Factor analysis of the metabolic variables confirmed four uncorrelated factors: body mass, insulin/glucose, lipids, and blood pressure. Adding the hemostatic variables yielded three new factors interpreted as inflammation, vitamin K-dependent proteins, and procoagulant activity. Plasminogen activator inhibitor-1 clustered with the body mass factor, supporting the hypothesis that obesity is related to impaired fibrinolysis. Fibrinogen clustered with the inflammation summary factor rather than procoagulant activity, supporting the position that fibrinogen principally reflects underlying inflammation rather than procoagulant potential. The authors conclude that should hemostatic variables be shown to contribute to IRS-related cardiovascular disease, apart from plasminogen activator inhibitor-1, they may do so independently of the established metabolic abnormalities.
Keywords: Aged; Aged, 80 and over; Antigens; Blood Coagulation; Cardiovascular Diseases; Cluster Analysis; Factor Analysis, Statistical; Factor VII; Female; Fibrinogen; Fibrinolysis; Humans; Inflammation; Insulin Resistance; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Risk Factors

Does snoring predict sleepiness independently of apnea and hypopnea frequency? - Gottlieb, D J; Yao, Q; Redline, S; Ali, T; Mahowald, M W (Am J Respir Crit Care Med, 2000)
Obstructive apneas and hypopneas during sleep are a well recognized cause of excessive daytime sleepiness. Snoring is also associated with excess sleepiness, although it is not known whether this reflects an independent effect of snoring or whether snoring is simply a marker for obstructive sleep apnea. To further explore the relation of snoring to sleepiness, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study. The study sample comprises 2,737 men and 3,040 women with a mean age of 64 (SD 11) yr. Sleepiness was quantified using the Epworth Sleepiness Scale (ESS). Snoring history was obtained via a self-completion questionnaire. The respiratory disturbance index (RDI), defined as the number of apneas plus hypopneas per hour of sleep, was measured during in-home polysomnography. The ESS score increased progressively with increasing RDI, from a mean of 7.1 (4.2) in subjects with RDI < 1.5 to 8.8 (4.8) in subjects with RDI >/= 15 (p < 0.001). A progressive increase in ESS score was also seen across five categories of snoring frequency, from 6.4 (4.2) in current nonsnorers to 9.3 (4.8) in subjects who snored six to seven nights per week (p < 0.001). The prevalence of excessive daytime sleepiness, defined as an ESS score >/= 11, increased from 15% in never-snorers to 39% in those who snored six to seven nights per week. The relation of snoring to sleepiness was seen at all levels of RDI, with no significant change in the relation of snoring to ESS score after adjustment for RDI in multivariate models. The effects of snoring and RDI on sleepiness were little affected by adjustment for age, sex, race, body mass index, or questionnaire evidence of insufficient sleep time or nocturnal leg jerks or cramps. We conclude that both snoring and RDI are independently associated with excess sleepiness in community-dwelling, middle-aged and older adults.
Keywords: Adult; Aged; Arousal; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Polysomnography; Risk Factors; Sleep Apnea, Obstructive; Snoring; Wakefulness

Effects of varying approaches for identifying respiratory disturbances on sleep apnea assessment. - Redline, S; Kapur, V K; Sanders, M H; Quan, S F; Gottlieb, D J; Rapoport, D M; Bonekat, W H; Smith, P L; Kiley, J P; Iber, C (Am J Respir Crit Care Med, 2000)
Varying approaches to measuring the respiratory disturbance index (RDI) may lead to discrepant estimates of the severity of sleep-disordered breathing (SDB). In this study, we assessed the impact of varying the use of corroborative data (presence and degree of desaturation and/or arousal) to identify hypopneas and apneas. The relationships among 10 RDIs defined by various definitions of apneas and hypopneas were assessed in 5,046 participants in the Sleep Heart Health Study (SHHS) who underwent overnight unattended 12-channel polysomnography (PSG). The magnitude of the median RDI varied 10-fold (i.e., 29.3 when the RDI was based on events identified on the basis of flow or volume amplitude criteria alone to 2.0 for an RDI that required an associated 5% desaturation with events). The correlation between RDIs based on different definitions ranged from 0.99 to 0.68. The highest correlations were among RDIs that required apneas and hypopneas to be associated with some level of desaturation. Lower correlations were observed between RDIs that required desaturation as compared with RDIs defined on the basis of amplitude criteria alone or associated arousal. These data suggest that different approaches for measuring the RDI may contribute to substantial variability in identification and classification of the disorder.
Keywords: Adult; Aged; Aged, 80 and over; Arousal; Diagnosis, Differential; Female; Humans; Lung Volume Measurements; Male; Middle Aged; Observer Variation; Oxygen; Oxyhemoglobins; Polysomnography; Risk Factors; Sleep Apnea Syndromes

Rates of sensor loss in unattended home polysomnography: the influence of age, gender, obesity, and sleep-disordered breathing. - Kapur, V K; Rapoport, D M; Sanders, M H; Enright, P; Hill, J; Iber, C; Romaniuk, J (Sleep, 2000)
OBJECTIVES: To evaluate study failure and sensor loss in unattended home polysomnography and their relationship to age, gender, obesity, and severity of sleep-disordered breathing (SDB). DESIGN: A cross-sectional analysis of data gathered prospectively for the Sleep Heart Health Study (SHHS). SETTING: Unattended polysomnography was performed in participants' homes by the staff of the sites that are involved in SHHS. PARTICIPANTS: 6,802 individuals who met the inclusion criteria (age >40 years, no history of treatment of sleep apnea, no tracheostomy, no current home oxygen therapy) for SHHS. RESULTS: A total of 6802 participants had 7151 studies performed. 6161 of 6802 initial studies (90.6%) were acceptable. Obesity was associated with a decreased likelihood of a successful initial study. After one or more attempts, 6440 participants (94.7%) had studies that were judged as acceptable. The mean duration of scorable signals for specific channels ranged from 5.7 to 6.8 hours. The magnitudes of the effects of age, gender, BMI, and RDI on specific signal durations were not clinically significant. CONCLUSION: Unattended home PSG as performed for SHHS was usually successful. Participant characteristics had very weak associations with duration of scorable signal. This study suggests that unattended home PSG, when performed with proper protocols and quality controls, has reasonable success rates and signal quality for the evaluation of SDB in clinical and research settings.
Keywords: Age Factors; Cross-Sectional Studies; Electroencephalography; Electromyography; Electrooculography; Equipment Failure; Female; Humans; Male; Middle Aged; Obesity; Polysomnography; Prospective Studies; Severity of Illness Index; Sex Factors; Sleep Apnea Syndromes

The association of sleep-disordered breathing and sleep symptoms with quality of life in the Sleep Heart Health Study. - Baldwin, C M; Griffith, K A; Nieto, F J; O'Connor, G T; Walsleben, J A; Redline, S (Sleep, 2001)
This study assessed the extent to which sleep-disordered breathing (SDB), difficulty initiating and maintaining sleep (DIMS), and excessive daytime sleepiness (EDS) were associated with impairment of quality of life (QoL) using the SF-36. Participants (n=5,816; mean age=63 years; 52.5% women) were enrolled in the nation-wide population-based Sleep Heart Health Study (SHHS) implemented to investigate sleep-disordered breathing as a risk factor in the development of cardiovascular disease. Each transformed SF-36 scale was analyzed independently using multiple logistic regression analysis with sleep and other potential confounding variables (e.g., age, ethnicity) included as independent variables. Men (11.6%) were significantly more likely to have SDB compared to women (5.6%), while women (42.4%) were significantly more likely to report DIMS than men (32.5%). Vitality was the sole SF-36 scale to have a linear association with the clinical categories of SDB (mild, moderate, severe SDB). However, individuals with severe SDB indicated significantly poorer QoL on several SF-36 scales. Both DIMS and EDS were strongly associated with reduced QoL even after adjusting for confounding variables for both sexes. Findings suggest 1) mild to moderate SDB is associated with reduced vitality, while severe SDB is more broadly associated with poorer QoL, 2) subjective sleep symptoms are comprehensively associated with poorer QoL, and 3) SF-36 mean score profiles for SDB and sleep symptoms are equivalent to other chronic diseases in the U.S. general population.
Keywords: Adult; Cardiovascular Diseases; Chronic Disease; Circadian Rhythm; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Population Surveillance; Prevalence; Quality of Life; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes; United States

Brachial flow-mediated vasodilator responses in population-based research: methods, reproducibility and effects of age, gender and baseline diameter. - Herrington, D M; Fan, L; Drum, M; Riley, W A; Pusser, B E; Crouse, J R; Burke, G L; McBurnie, M A; Morgan, T M; Espeland, M A (J Cardiovasc Risk, 2001)
BACKGROUND: Brachial artery ultrasound has been proposed as an inexpensive, accurate way to assess cardiovascular risk in populations. However, analysis and interpretation of these data are not uniform. METHODS: We analysed the relationship between relative and absolute changes in brachial artery diameter in response to flow-mediated dilation and age, gender and baseline diameter among 4,040 ultrasound examinations from subjects aged 14 to 98 years. RESULTS: Reproducibility studies demonstrated intra- and interreader and intrasubject correlations from 0.67 to 0.84 for repeated measures of per cent change in diameter. Per cent change in diameter after flow stimulus was 3.58 +/- 0.10% (mean +/- standard deviation). Corresponding values for baseline diameter and absolute change in diameter were 4.43 +/- 0.87 mm and 0.15 +/- 0.01 mm, respectively. Baseline diameter and its variance were inversely related to per cent change in diameter (P< 0.001). In contrast, absolute change in diameter was more uniform throughout the range of baseline diameters. Baseline diameter was directly related, and per cent change in diameter inversely related, to age (P < 0.001 for all three measures). Time to maximum vasodilator response increased with age (P < 0.001). Women (n=2,315) had significantly larger per cent change in diameter than men (n=1,725) (P < 0.001). However, after adjustment for age and baseline diameter, per cent and absolute change were 5% smaller in women than men (P < 0.05 for both). In multivariate analysis, age was overwhelmingly the most important determinant of absolute change in diameter (P < 0.001). CONCLUSIONS: Automated analysis of brachial flow-mediated vasodilator responses is both feasible and reproducible in large-scale clinical and population-based research.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Blood Circulation; Brachial Artery; Female; Humans; Male; Middle Aged; Observer Variation; Population Surveillance; Reproducibility of Results; Sex Factors; Vasodilation; Vasodilator Agents

Echocardiographic features of the right heart in sleep-disordered breathing: the Framingham Heart Study. - Guidry, U C; Mendes, L A; Evans, J C; Levy, D; O'Connor, G T; Larson, M G; Gottlieb, D J; Benjamin, E J (Am J Respir Crit Care Med, 2001)
The effect of sleep-disordered breathing (SDB) on right heart structure and function is controversial. Studies of patients referred for evaluation of possible sleep apnea have yielded conflicting results, and the impact of SDB on the right heart has not been investigated in the general population. We examined the echocardiographic features of subjects with SDB at the Framingham Heart Study site of the Sleep Heart Health Study. Of 1,001 polysomnography subjects, 90 with SDB defined as a respiratory disturbance index (RDI) score > 90th percentile (mean RDI = 42) were compared with 90 low-RDI subjects (mean RDI = 5) matched for age, sex, and body mass index. Right heart measurements, made without knowledge of clinical status, were compared between groups. The majority of the subjects were male (74%). After multivariable adjustment, right ventricle (RV) wall thickness was significantly greater (p = 0.005) in subjects with SDB (0.78 +/- 0.02 cm) than in the low-RDI subjects (0.68 +/- 0.02 cm). Right atrial dimensions, RV dimensions, and RV systolic function were not found to be significantly different between subjects with SDB and the low-RDI subjects. We conclude that in this community-based study of SDB and right heart echocardiographic features, RV wall thickness was increased in subjects with SDB. Whether the RV hypertrophy observed in persons with SDB is associated with increased morbidity and mortality remains unknown.
Keywords: Adult; Age Factors; Aged; Cohort Studies; Cross-Sectional Studies; Data Interpretation, Statistical; Echocardiography; Female; Forced Expiratory Volume; Humans; Hypertrophy, Right Ventricular; Linear Models; Male; Middle Aged; Obesity; Observer Variation; Polysomnography; Prospective Studies; Sex Factors; Sleep Apnea Syndromes; Ventricular Function, Right; Vital Capacity

Relation of sleep-disordered breathing to cardiovascular disease risk factors: the Sleep Heart Health Study. - Newman, A B; Nieto, F J; Guidry, U; Lind, B K; Redline, S; Pickering, T G; Quan, S F (Am J Epidemiol, 2001)
Associations between sleep-disordered breathing and cardiovascular disease (CVD) may be mediated by higher cardiovascular risk factor levels in those with sleep-disordered breathing. The authors examined these relations in the Sleep Heart Health Study, a multiethnic cohort of 6,440 men and women over age 40 years conducted from October 1995 to February 1998 and characterized by home polysomnography. In 4,991 participants who were free of self-reported CVD at the time of the sleep study, moderate levels of sleep-disordered breathing were common, with a median Respiratory Disturbance Index (RDI) of 4.0 (interquartile range, 1.25-10.7). The level of RDI was associated cross-sectionally with age, body mass index, waist-to-hip ratio, hypertension, diabetes, and lipid levels. These relations were more pronounced in those under age 65 years than in those over age 65. Women under age 65 years with RDI in the higher quartiles were more obese than men with similar RDI. Although the pattern of associations was consistent with greater obesity in those with higher RDI, higher body mass index did not explain all of these associations. If sleep-disordered breathing is shown in future follow-up to increase the risk for incident CVD events, part of the risk is likely to be due to the higher cardiovascular risk factors in those with higher RDI.
Keywords: Adult; Aged; Analysis of Variance; Cardiovascular Diseases; Chi-Square Distribution; Cross-Sectional Studies; Female; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Polysomnography; Risk Factors; Sleep Apnea Syndromes; United States

Sleep-disordered breathing and cardiovascular disease: cross-sectional results of the Sleep Heart Health Study. - Shahar, E; Whitney, C W; Redline, S; Lee, E T; Newman, A B; Nieto, F J; O'Connor, G T; Boland, L L; Schwartz, J E; Samet, J M (Am J Respir Crit Care Med, 2001)
Disordered breathing during sleep is associated with acute, unfavorable effects on cardiovascular physiology, but few studies have examined its postulated association with cardiovascular disease (CVD). We examined the cross-sectional association between sleep- disordered breathing and self-reported CVD in 6,424 free-living individuals who underwent overnight, unattended polysomnography at home. Sleep-disordered breathing was quantified by the apnea-hypopnea index (AHI)-the average number of apneas and hypopneas per hour of sleep. Mild to moderate disordered breathing during sleep was highly prevalent in the sample (median AHI: 4.4; interquartile range: 1.3 to 11.0). A total of 1,023 participants (16%) reported at least one manifestation of CVD (myocardial infarction, angina, coronary revascularization procedure, heart failure, or stroke). The multivariable-adjusted relative odds (95% CI) of prevalent CVD for the second, third, and fourth quartiles of the AHI (versus the first) were 0.98 (0.77-1.24), 1.28 (1.02-1.61), and 1.42 (1.13-1.78), respectively. Sleep-disordered breathing was associated more strongly with self-reported heart failure and stroke than with self-reported coronary heart disease: the relative odds (95% CI) of heart failure, stroke, and coronary heart disease (upper versus lower AHI quartile) were 2.38 (1.22-4.62), 1.58 (1.02- 2.46), and 1.27 (0.99-1.62), respectively. These findings are compatible with modest to moderate effects of sleep-disordered breathing on heterogeneous manifestations of CVD within a range of AHI values that are considered normal or only mildly elevated.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Sleep Apnea Syndromes

Anticardiolipin antibodies as a risk factor for venous thromboembolism in a population-based prospective study. - Runchey, Shauna S; Folsom, Aaron R; Tsai, Michael Y; Cushman, Mary; McGovern, Paul D (Br J Haematol, 2002)
Anticardiolipin antibodies, one of the family of 'antiphospholipid' antibodies, increase the risk of venous thromboembolism in the presence of autoimmune disease. Our objective was to determine prospectively whether there is a positive association between anticardiolipin antibodies and venous thromboembolism in ostensibly healthy adults. We conducted a nested case-control study (n = 317 patients and n = 655 control subjects) in a longitudinal study of over 20 000 participants. Baseline (prediagnosis) anticardiolipin IgG and IgM antibodies were assessed by enzyme-linked immunoassays. Venous thromboembolism was validated using standardized criteria for venous thrombosis and pulmonary embolism. There was no association between anticardiolipin antibodies and subsequent venous thromboembolism occurrence, overall or in any subgroup. For example, the multivariate-adjusted relative risk was 0.88 (95% confidence interval, 0.43, 1.78) for greater than versus less than the 95th percentile of anticardiolipin IgG. In conclusion, in this general population sample, an elevated anticardiolipin antibody level was not a risk factor for venous thromboembolism.
Keywords: Aged; Aged, 80 and over; Antibodies, Anticardiolipin; Case-Control Studies; Female; Humans; Immunoglobulin G; Immunoglobulin M; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Reference Values; Risk Factors; Thromboembolism; Venous Thrombosis

Cardiovascular risk factors and venous thromboembolism incidence: the longitudinal investigation of thromboembolism etiology. - Tsai, Albert W; Cushman, Mary; Rosamond, Wayne D; Heckbert, Susan R; Polak, Joseph F; Folsom, Aaron R (Arch Intern Med, 2002)
BACKGROUND: The association between traditional cardiovascular risk factors and risk of venous thromboembolism (VTE) has not been extensively examined in prospective studies. METHODS: To determine whether atherosclerotic risk factors are also associated with increased incidence of VTE, we conducted a prospective study of 19 293 men and women without previous VTE in 6 US communities between 1987 and 1998. RESULTS: There were 215 validated VTE events (1.45 per 1000 person-years) during a median of 8 years of follow-up. The age-adjusted hazard ratio was 1.4 (95% confidence interval [CI], 1.1-1.9) for men vs women, 1.6 (95% CI, 1.2-2.2) for blacks vs whites, and 1.7 (95% CI, 1.5-2.0) per decade of age. Cigarette smoking, hypertension, dyslipidemia, physical inactivity, and alcohol consumption were not associated with risk of VTE. Age-, race-, and sex-adjusted hazard ratios for body mass index categories (calculated as the weight in kilograms divided by the height in meters squared) of less than 25, 25 to less than 30, 30 to less than 35, 35 to less than 40, and 40 or more were 1.0, 1.5, 2.2, 1.5, and 2.7, respectively (P<.001 for the trend). Diabetes was also associated with an increased risk of VTE (adjusted hazard ratio, 1.5 [95% CI, 1.0-2.1]). CONCLUSIONS: Our data showing no relationship of some arterial risk factors with VTE corroborate the view that the etiology of VTE differs from atherosclerotic cardiovascular disease. In addition, the findings suggest a hypothesis that avoidance of obesity and diabetes or vigilance in prophylaxis in patients with those conditions may prevent some venous thromboses.
Keywords: Aged; Arteriosclerosis; Female; Humans; Incidence; Male; Middle Aged; Multivariate Analysis; Proportional Hazards Models; Prospective Studies; Pulmonary Embolism; Risk Factors; United States; Venous Thrombosis

Coagulation factors, inflammation markers, and venous thromboembolism: the longitudinal investigation of thromboembolism etiology (LITE). - Tsai, Albert W; Cushman, Mary; Rosamond, Wayne D; Heckbert, Susan R; Tracy, Russell P; Aleksic, Nena; Folsom, Aaron R (Am J Med, 2002)
PURPOSE: We sought to assess prospectively whether higher levels of blood coagulation factors and inflammation markers are risk factors for venous thromboembolism. SUBJECTS AND METHODS: In two pooled population-based cohort studies, we measured levels of factor VII, factor VIII, von Willebrand factor, fibrinogen, and C-reactive protein, and white blood cell count, in samples obtained from 19,237 adults with no baseline history of venous thromboembolism, cancer, or warfarin use. The endpoint was validated venous thromboembolism during follow-up (median, 7.8 years). RESULTS: A total of 159 venous thromboembolism events occurred. Factor VIII and von Willebrand factor were linearly associated with increased risk of venous thromboembolism (P for trend <0.0001). As compared with those in the lowest quartile, the multivariate-adjusted hazard ratio (HR) of venous thromboembolism was 2.6 (95% confidence interval [CI]: 1.6 to 4.3) for factor VIII levels in the highest quartile and 3.8 (95% CI: 2.0 to 7.2) for the highest fifth percentile. For von Willebrand factor, the hazard ratios in middle-aged subjects were 4.6 (95% CI: 2.2 to 9.2) for the highest quartile and 7.6 (95% CI: 3.1 to 18) for the highest fifth percentile. Factor VII levels above the 95th percentile, as compared with the lowest quartile, also conveyed a higher risk of venous thromboembolism (HR = 2.4; 95% CI: 1.2 to 4.8). In contrast, there was no association of venous thromboembolism with fibrinogen or C-reactive protein levels, or white cell count. CONCLUSIONS: In this prospective study, elevated factor VIII and von Willebrand factor levels were common, independent, and dose-dependent risk factors for venous thromboembolism, and an elevated factor VII level was a possible risk factor. Venous thromboembolism, unlike arterial disease, was not related to inflammatory markers.
Keywords: Aged; Biomarkers; Blood Coagulation Factors; C-Reactive Protein; Cohort Studies; Confidence Intervals; Factor VII; Female; Fibrinogen; Humans; Inflammation Mediators; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Risk Assessment; Risk Factors; Sensitivity and Specificity; Thromboembolism; Venous Thrombosis; von Willebrand Factor

Linearly scaled, rate-invariant normal limits for QT interval: eight decades of incorrect application of power functions. - Rautaharju, Pentti M; Zhang, Zhu-Ming (J Cardiovasc Electrophysiol, 2002)
INTRODUCTION: Normal limits for QT traditionally are derived as mean +/- 2*SD, with rate adjustment done by dividing QT values by power functions such as RR 1/2 (proportional scaling). METHODS AND RESULTS: We evaluated procedures for deriving normal limits by comparing adjusted QT distributions versus heart rate using ECG data of 11,739 normal men and women aged > or = 40 years. QT decreased as predicted by many power functions with heart rate but its SD remained relatively unchanged. Consequently, proportional scaling induced rate-dependent distortion of normal limits. Furthermore, QT distributions by heart rate were variably skewed and non-normal. Therefore, normal limits expressed as mean +/- 2*SD were misleading. Omission of regression intercept was an additional reason for failure of Bazett's and Fridericia's formulas. Regularized normal limits for adjusted QT (Qta) were obtained with linear instead of proportional scaling of type QTa = QT + k1*(1 - RR(k2)), for instance, with k2 = 0.5, k1 = 0.360 for males and 0.353 for females, or with k2 = 0.42, k1 = 0.414 for males and 0.420 for females. With linear scaling, QTa = 460 msec was established as the upper 2% normal limit, with 32 msec as the limit for a significant QTa increase from reference ECG in serial comparison. CONCLUSION: Traditional procedures for establishment of normal limits failed because of proportional scaling, assumption of normal QT distribution, or omission of regression intercept. Percentile distributions of linearly scaled adjusted QT produced regularized rate invariant normal limits within normal sinus rates.
Keywords: Adult; Aged; Aged, 80 and over; Electrocardiography; Female; Heart Rate; Humans; Male; Middle Aged; Prognosis; Reference Values; Sex Characteristics

Measures of cognitive function in persons with varying degrees of sleep-disordered breathing: the Sleep Heart Health Study. - Boland, Lori L; Shahar, Eyal; Iber, Conrad; Knopman, David S; Kuo, Tracy F; Nieto, F Javier (J Sleep Res, 2002)
Epidemiologic literature suggests that persons with clinically diagnosed sleep apnoea frequently have impaired cognitive function, but whether milder degrees of sleep-disordered breathing (SDB) are associated with cognitive dysfunction in the general population is largely unknown. Approximately 1700 subjects free of clinically diagnosed SDB underwent at-home polysomnography (PSG) as part of the Sleep Heart Health Study (SHHS) and completed three cognitive function tests within 1-2 years of their PSG: the Delayed Word Recall Test (DWR), the WAIS-R Digit Symbol Subtest (DSS), and the Word Fluency test (WF). A respiratory disturbance index (RDI) was calculated as the number of apnoeas and hypopnoeas per hour of sleep. After adjustment for age, education, occupation, field centre, diabetes, hypertension, body-mass index, use of CNS medications, and alcohol drinking status, there was no consistent association between the RDI and any of the three cognitive function measures. There was no evidence of a dose-response relation between the RDI and cognitive function scores and the adjusted mean scores by quartiles of RDI never differed from one another by more than 5% for any of the tests. In this sample of free-living individuals with mostly mild to moderate levels of SDB, the degree of SDB appeared to be unrelated to three measures of cognitive performance.
Keywords: Aged; Body Mass Index; Brain; Cognition Disorders; Cohort Studies; Female; Humans; Hypoxia; Male; Middle Aged; Neuropsychological Tests; Oxygen; Polysomnography; Severity of Illness Index; Sleep Apnea, Central

Predictors of sleep-disordered breathing in community-dwelling adults: the Sleep Heart Health Study. - Young, Terry; Shahar, Eyal; Nieto, F Javier; Redline, Susan; Newman, Anne B; Gottlieb, Daniel J; Walsleben, Joyce A; Finn, Laurel; Enright, Paul; Samet, Jonathan M (Arch Intern Med, 2002)
BACKGROUND: Sleep-disordered breathing (SDB) is common, but largely undiagnosed in the general population. Information on demographic patterns of SDB occurrence and its predictive factors in the general population is needed to target high-risk groups that may benefit from diagnosis. METHODS: The sample comprised 5615 community-dwelling men and women aged between 40 and 98 years who were enrolled in the Sleep Heart Health Study. Data were collected by questionnaire, clinical examinations, and in-home polysomnography. Sleep-disordered breathing status was based on the average number of apnea and hypopnea episodes per hour of sleep (apnea-hypopnea index [AHI]). We used multiple logistic regression modeling to estimate cross-sectional associations of selected participant characteristics with SDB defined by an AHI of 15 or greater. RESULTS: Male sex, age, body mass index, neck girth, snoring, and repeated breathing pause frequency were independent, significant correlates of an AHI of 15 or greater. People reporting habitual snoring, loud snoring, and frequent breathing pauses were 3 to 4 times more likely to have an AHI of 15 or greater vs an AHI less than 15, but there were weaker associations for other factors with an AHI of 15 or greater. The odds ratios (95% confidence interval) for an AHI of 15 or greater vs an AHI less than 15 were 1.6 and 1.5, respectively, for 1-SD increments in body mass index and neck girth. As age increased, the magnitude of associations for SDB and body habitus, snoring, and breathing pauses decreased. CONCLUSIONS: A significant proportion of occult SDB in the general population would be missed if screening or case finding were based solely on increased body habitus or male sex. Breathing pauses and obesity may be particularly insensitive for identifying SDB in older people. A better understanding of predictive factors for SDB, particularly in older adults, is needed.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Continental Population Groups; Female; Humans; Male; Middle Aged; Obesity; Predictive Value of Tests; Residence Characteristics; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Snoring

Prospective study of the G20210A polymorphism in the prothrombin gene, plasma prothrombin concentration, and incidence of venous thromboembolism. - Folsom, Aaron R; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Aleksic, Nena (Am J Hematol, 2002)
Case-control studies have indicated increased risk of venous thrombosis associated with the prothrombin gene G20210A polymorphism and with elevated plasma prothrombin levels. We sought to confirm these results in a prospective population-based study of 21,690 persons. We measured G20210A and prothrombin antigen on pre-event blood samples of 302 participants who developed venous thromboembolism (VTE) and 626 participants who remained free of VTE. Approximately 4.0% of cases and 2.4% of controls carried the G20210A polymorphism, but only one of 137 African Americans did. The odds ratio in whites was 1.87 (95% CI = 0.85, 4.11)--higher for those who reported a prior history of VTE (OR = 5.44) than those reporting no VTE history (OR = 1.41) and in those with idiopathic VTE (OR = 2.51) than those with secondary VTE (OR = 1.38). There was no association between venous thromboembolism and plasma prothrombin antigen level. We estimated that the G20210A polymorphism may account for approximately 2.5% of venous thromboembolism events in United States whites.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Case-Control Studies; European Continental Ancestry Group; Genotype; Humans; Incidence; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Prospective Studies; Prothrombin; Recurrence; Research Design; Risk Factors; Thromboembolism; United States

A prospective study of venous thromboembolism in relation to factor V Leiden and related factors. - Folsom, Aaron R; Cushman, Mary; Tsai, Michael Y; Aleksic, Nena; Heckbert, Susan R; Boland, Lori L; Tsai, Albert W; Yanez, N David; Rosamond, Wayne D (Blood, 2002)
The aim of this study was to examine the occurrence of venous thromboembolism (VTE) in relation to factor V-related risk factors. Using a nested case-control design combining 2 population-based prospective studies, we measured factor V Leiden, HR2 haplotype, activated protein C (APC) resistance, and plasma factor V antigen in 335 participants who developed VTE during 8 years of follow-up and 688 controls. The overall odds ratio (OR) of VTE was 3.67 (95% CI, 2.20-6.12) in participants carrying factor V Leiden compared with noncarriers. APC resistance measured after predilution with factor V-deficient plasma conferred an OR of 2.58 (95% CI, 1.62-4.10). All 3 participants homozygous for the HR2 haplotype had a VTE, and the OR of VTE for homozygosity was estimated to be 5.5 (95% CI, 2.45-12.5). Carriers of the HR2 haplotype otherwise were not at increased risk of VTE overall (OR = 1.05; 95% CI, 0.64-1.72), but double heterozygotes for HR2 and factor V Leiden carried an OR of idiopathic VTE of 16.3 (95% CI, 1.7-159) compared with noncarriers. Factor V antigen also was not associated with VTE overall, but for participants with the combination of high factor V antigen plus factor V Leiden the OR of idiopathic VTE was 11.5 (95% CI, 4.2-31.4). In the general population, APC resistance and factor V Leiden were important VTE risk factors; homozygosity for the HR2 haplotype may be a risk factor but was rare; otherwise, HR2 haplotype and factor V antigen were not risk factors except in carriers of factor V Leiden.
Keywords: Activated Protein C Resistance; Aged; Cohort Studies; Continental Population Groups; Factor V; Genotype; Haplotypes; Humans; Incidence; Longitudinal Studies; Middle Aged; Odds Ratio; Prospective Studies; Risk Factors; Thromboembolism; Venous Thrombosis

Protein C, antithrombin, and venous thromboembolism incidence: a prospective population-based study. - Folsom, Aaron R; Aleksic, Nena; Wang, Lu; Cushman, Mary; Wu, Kenneth K; White, Richard H (Arterioscler Thromb Vasc Biol, 2002)
Although deficiencies of protein C and antithrombin, 2 natural plasma anticoagulants, are known risk factors for venous thrombosis, population-based prospective incidence data on these associations are lacking. Venous thromboembolic events have been identified in adults in 2 longitudinal cohort studies, the Atherosclerosis Risk in Communities (ARIC) Study and the Cardiovascular Health Study (CHS). Incidence was examined in relation to prediagnostic plasma levels of protein C (ARIC Study only) and antithrombin. Over a mean of 8.1 years of follow-up, there were 130 incident venous thromboembolic events that were not due to cancer in the ARIC Study. The age-adjusted incidence was elevated 3.36-fold (95% CI 1.24 to 9.11) in the 1.1% of subjects with protein C values <2.0 mg/L compared with subjects with higher values. In contrast, in the ARIC Study and the CHS, there was no association between low plasma antithrombin and venous thromboembolism. In conclusion, in this population-based study, a low protein C, but not antithrombin, level has been determined to be associated with an increased incidence of venous thromboembolism. Attributable risk estimates suggest that low protein C levels account for approximately 2.5% of venous thromboembolic events in the ARIC population.
Keywords: Adult; Aged; Aged, 80 and over; Antithrombins; Arteriosclerosis; Cohort Studies; Humans; Incidence; Longitudinal Studies; Middle Aged; Odds Ratio; Population Surveillance; Prospective Studies; Protein C; Protein C Deficiency; Pulmonary Embolism; Thromboembolism; Venous Thrombosis

The relationship between chronically disrupted sleep and healthcare use. - Kapur, Vishesh K; Redline, Susan; Nieto, F Javier; Young, Terry B; Newman, Anne B; Henderson, Jeffrey A (Sleep, 2002)
STUDY OBJECTIVES: To determine whether chronic sleep deprivation, sleep disruption, sleepiness, insomnia, and OSA are associated with increased healthcare use in a community-based population. DESIGN: Cross-sectional study. SETTING/PARTICIPANTS: 6440 Sleep Heart Health Study (SHHS) participants recruited from ongoing cohort studies. INTERVENTIONS: N/A. MEASUREMENTS: Polysomnography results (Apnea Hypopnea Index (AHI), percent of sleep time with oxyhemoglobin saturation below 90% (CT90), arousal index) as well as data on sleep related symptoms, medication use, and chronic illness. The indirect measure of predicted healthcare utilization was the modified Chronic Disease Score (CDS) calculated from medication data. RESULTS: After adjustment for age, gender, BMI and study site, subjects in the highest quartiles of AHI, CT90 and Epworth score had CDS that were 6%-9% higher than the lowest quartiles. The adjusted mean CDS for subjects with sleep apnea was similar to that for subjects with hypertension, chronic bronchitis or asthma and 18% greater than the mean CDS for subjects without sleep apnea. Among subjects who did not have significant sleep-disordered breathing, complaints of insomnia, sleepiness, fatigue, and not getting enough sleep were associated with increased CDS. CONCLUSIONS: This study demonstrated an association between subjective complaints of daytime sleepiness, inadequate sleep time, insomnia as well as objective measures of severity of SDB, and an indirect measure of healthcare utilization in a community-based sample. Though the percent increases in healthcare utilization observed were modest, the prevalence of these factors in the general population is high, and may therefore be associated with a substantial cost burden to the healthcare system.
Keywords: Adult; Chronic Disease; Cohort Studies; Community Health Services; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Patient Acceptance of Health Care; Polysomnography; Prevalence; Severity of Illness Index; Sleep Apnea, Obstructive; Sleep Deprivation

Short-term variability of respiration and sleep during unattended nonlaboratory polysomnography--the Sleep Heart Health Study. [corrected]. - Quan, Stuart F; Griswold, Michael E; Iber, Conrad; Nieto, F Javier; Rapoport, David M; Redline, Susan; Sanders, Mark; Young, Terry (Sleep, 2002)
STUDY OBJECTIVES: To determine the short-term variability of indices of disturbed respiration and sleep during 2 nights of unattended nonlaboratory polysomnography conducted several months apart. DESIGN: Participants were randomly selected using a block design with stratification on preliminary estimates of 2 criteria: respiratory disturbance index [RDI3% (apnea or hypopnea events associated with > or = 3% O2 desaturation): < 15/hour total sleep time, > or = 15/hour total sleep time] and sleep efficiency (SEff: < 85% and > or = 85%). The RDI and sleep data from initial and repeated polysomnography were compared. SETTING: NA. PARTICIPANTS: A subset of 99 participants in the Sleep Heart Health Study who agreed to have a repeat polysomnogram within 4 months of their original study. INTERVENTIONS: NA. MEASUREMENTS AND RESULTS: Acceptable repeat polysomnograms were obtained in 91 subjects (mean study interval: 77 +/- 18 [sd] days; range: 31-112 days). There was no significant bias in RDI between study nights using several different RDI definitions including RDI3% and RDI4% (apnea or hypopnea events associated with > or = 4% O2 desaturation). Variability between studies estimated using intraclass correlations (ICC) ranged from 0.77 to 0.81. For subjects with a RDI3% < 15, variability increased as a function of increasing RDI, but for those with a RDI3% > or = 15, variability was constant. Body mass index, SEff, gender, or age did not directly predict RDI variability. Using RDI4% cutpoints of < or = 5, < or = 10 and < or = 15 events per hour of sleep demonstrated that 79.1%, 85.7%, and 87.9% of subjects, respectively, had the same classification of SDB status on both nights of study. There also was no significant bias in sleep staging, sleep efficiency, or arousal index between studies. However, variability was greater with ICC values ranging from 0.37 (% time in REM) to 0.76 (arousal index). CONCLUSION: In the Sleep Heart Health Study, accurate estimates of the severity of sleep-disordered breathing and the quality of sleep were obtained from a single night of unattended nonlaboratory polysomnography. These findings may be applicable to other large epidemiologic studies provided that similar recording techniques and quality-assurance procedures are followed.
Keywords: Adult; Aged; Aged, 80 and over; Apnea; Arousal; Body Mass Index; Circadian Rhythm; Electrocardiography; Electromyography; Electrooculography; Female; Humans; Male; Middle Aged; Oxygen Consumption; Polysomnography; Respiration; Sleep Apnea Syndromes; Sleep Stages; Time Factors

Underdiagnosis of sleep apnea syndrome in U.S. communities. - Kapur, Vishesh; Strohl, Kingman P; Redline, Susan; Iber, Conrad; O'Connor, George; Nieto, Javier (Sleep Breath, 2002)
We hypothesize that clinical recognition rates for obstructive sleep apnea-hypoapnea syndrome (OSAHS) are influenced by comorbidity and demographic factors. Data on medical disorders, symptoms of sleep disorders, and cardiovascular risk factors gathered from 15,699 individuals in the Sleep Heart Health Study were compared. Participants were classified into three groups: those with a self-reported physician diagnosis of OSAHS, those with self-reported physician-diagnosed and -treated OSAHS, and those reporting both frequent snoring and daytime sleepiness (two-symptom group). Among all participants, 4.1% reported two symptoms (range across sites: 1.55 to 7.23%), whereas 1.6% reported a physician diagnosis of OSAHS (range: 0.66 to 2.88%) and 0.6% reported physician diagnosis and treatment (range: 0.11 to 0.88%). Recognized OSAHS groups were similar to the two-symptom group in age, having a sleeping partner, measured blood pressure, total cholesterol, and race. In a logistic model that included age along with characteristics found to vary significantly among the three groups (gender, body mass index [BMI], high-density lipoprotein cholesterol levels, hypertension), only male gender and BMI were increased in those with physician-diagnosed and -treated OSAHS. We conclude that disparities (especially in women and in those with lower BMI) exist between current recognition rates for OSAHS and the estimated prevalence by symptom report across the United States.
Keywords: Diagnosis, Differential; Diagnostic Errors; Female; Humans; Male; Middle Aged; Prevalence; Sleep Apnea Syndromes; United States

Diabetes and sleep disturbances: findings from the Sleep Heart Health Study. - Resnick, Helaine E; Redline, Susan; Shahar, Eyal; Gilpin, Adele; Newman, Anne; Walter, Robert; Ewy, Gordon A; Howard, Barbara V; Punjabi, Naresh M (Diabetes Care, 2003)
OBJECTIVE: To test the hypothesis that diabetes is independently associated with sleep-disordered breathing (SDB), and in particular that diabetes is associated with sleep abnormalities of a central, rather than obstructive, nature. RESEARCH DESIGN AND METHODS: Using baseline data from the Sleep Heart Health Study (SHHS), we related diabetes to 1). the respiratory disturbance index (RDI; number of apneas plus hypopneas per h of sleep); 2). obstructive apnea index (OAI; >or=3 apneas/h of sleep associated with obstruction of the upper airway); 3). percent of sleep time < 90% O(2) saturation; 4). central apnea index (CAI; >or=3 apneas [without respiratory effort]/h sleep); 5). occurrence of a periodic breathing (Cheyne Stokes) pattern; and 6) sleep stages. Initial analyses excluding persons with prevalent cardiovascular disease (CVD) were repeated including these participants. RESULTS: Of the 5874 participants included in this report, 692 (11.8%) reported diabetes or were taking oral hypoglycemic medications or insulin and 1002 had prevalent CVD. Among the 4872 persons without CVD, 470 (9.6%) had diabetes. Diabetic participants had worse CVD risk factor profiles than their nondiabetic counterparts, including higher BMI, waist and neck circumferences, triglycerides, higher prevalence of hypertension, and lower HDL cholesterol (P < 0.001, all). Descriptive analyses indicated differences between diabetic and nondiabetic participants in RDI, sleep stages, sleep time <90% O(2) saturation, CAI, and periodic breathing (P < 0.05, all). However, multivariable regression analyses that adjusted for age, sex, BMI, race, and neck circumference eliminated these differences for all sleep measures except percent time in rapid eye movement (REM) sleep (19.0% among diabetic vs. 20.1% among nondiabetic subjects, P < 0.001) and prevalence of periodic breathing (odds ratio [OR] for diabetic subjects versus nondiabetic subjects 1.80, 95% CI 1.02-3.15). Additionally, adjusted analyses showed diabetes was associated with nonstatistically significant elevations in the odds of an increased central breathing index (OR 1.42, 95% CI 0.80-2.55). Addition to the analysis of the 1002 persons with prevalent CVD (including 222 people with diabetes) did not materially change these results. CONCLUSIONS: These data suggest that diabetes is associated with periodic breathing, a respiratory abnormality associated with abnormalities in the central control of ventilation. Some sleep disturbances may result from diabetes through the deleterious effects of diabetes on central control of respiration. The high prevalence of SDB in diabetes, although largely explained by obesity and other confounders, suggests the presence of a potentially treatable risk factor for CVD in the diabetic population.
Keywords: Aged; Diabetes Mellitus; Female; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Fibrin fragment D-dimer and the risk of future venous thrombosis. - Cushman, Mary; Folsom, Aaron R; Wang, Lu; Aleksic, Nena; Rosamond, Wayne D; Tracy, Russell P; Heckbert, Susan R (Blood, 2003)
Plasma D-dimer concentration rises more than 100-fold during acute deep vein thrombosis, but there are no prospective data concerning D-dimer as a risk factor for incident venous thrombosis in a general population. Incident venous thrombosis was ascertained in 2 prospective observational studies, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Of 21 690 participants enrolled between 1987 and 1993, after 8 years of follow-up, D-dimer was measured using baseline stored plasma of 307 participants who developed venous thrombosis and 616 who did not. Relative to the first quintile of the distribution of D-dimer, the age-adjusted odds ratios for future venous thrombosis for the second to fifth quintiles of D-dimer were 1.6, 2.3, 2.3, and 4.2, respectively (P for trend <.0001). Following added adjustment for sex, race, body mass index, factor V Leiden, prothrombin 20210A, and elevated factor VIII coagulant activity (factor VIII:c), these odds ratios were 1.5, 2.1, 1.9, and 3.0, respectively (P for trend <.0001). Among those with idiopathic thrombosis or secondary thrombosis unrelated to cancer, the adjusted fifth quintile odds ratios were 3.5 and 4.8, respectively. By contrast, D-dimer in the fifth versus first quintile was not related to occurrence of cancer-associated thrombosis (odds ratio, 1.1). Odds ratios for elevated D-dimer were consistently elevated in subgroups defined by age, sex, race, duration of follow-up, and thrombosis type (deep vein thrombosis or pulmonary embolus). D-dimer is strongly and positively related to the occurrence of future venous thrombosis.
Keywords: Aged; Body Mass Index; Cohort Studies; Continental Population Groups; Factor V; Factor VIII; Female; Fibrin Fibrinogen Degradation Products; Humans; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Prothrombin; Risk Factors; Venous Thrombosis

Hormone replacement therapy and sleep-disordered breathing. - Shahar, Eyal; Redline, Susan; Young, Terry; Boland, Lori L; Baldwin, Carol M; Nieto, F Javier; O'Connor, George T; Rapoport, David M; Robbins, John A (Am J Respir Crit Care Med, 2003)
Disordered breathing during sleep is more common among postmenopausal women than among their premenopausal counterparts, possibly because of declining levels of estrogen and progesterone. We examined the relationship between the use of replacement hormones and sleep-disordered breathing in a sample of 2,852 noninstitutionalized women, 50 years of age or older, who participated in the Sleep Heart Health Study. The frequency of apneas and hypopneas per hour of sleep (apnea-hypopnea index) was determined by unattended, single-night polysomnography at the participant's home. The prevalence of sleep-disordered breathing (apnea-hypopnea index of 15 or more) among hormone users (61 of 907) was approximately half the prevalence among nonusers (286 of 1,945). Multivariable adjustment for known determinants of the disorder, including age, body mass index, and neck circumference, has attenuated the association, but only moderately (adjusted odds ratio, 0.55; 95% confidence interval, 0.41 to 0.75). The inverse association between hormone use and sleep-disordered breathing was evident in various subgroups and was particularly strong among women 50 to 59 years old (adjusted odds ratio, 0.36; 95% confidence interval, 0.21 to 0.60). If the observed associations are causal, hormone replacement therapy could have a role in preventing or alleviating sleep-disordered breathing.
Keywords: Age Distribution; Aged; Body Mass Index; Causality; Cohort Studies; Confidence Intervals; Estrogen Replacement Therapy; Female; Humans; Logistic Models; Middle Aged; Multivariate Analysis; Odds Ratio; Polysomnography; Postmenopause; Prevalence; Sensitivity and Specificity; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Stages; United States

Hormone replacement therapy and the risk of incident congestive heart failure: the Cardiovascular Health Study. - Rea, Thomas D; Psaty, Bruce M; Heckbert, Susan R; Cushman, Mary; Meilahn, Elaine; Olson, Jean L; Lemaitre, Rozenn N; Smith, Nicholas L; Sotoodehnia, Nona; Chaves, Paulo H M (J Womens Health (Larchmt), 2003)
BACKGROUND: The development of congestive heart failure (CHF) in older persons is related to a variety of mechanisms. Hormone replacement therapy (HRT) affects several of the pathways that may be important in the development of CHF. We hypothesized that HRT would be associated with a decreased risk of incident CHF. METHODS: Using Cox proportional-hazards regression, we assessed the risk of incident CHF (n = 304) associated with time-dependent past and current use of HRT compared to never use. The Cardiovascular Health Study is a prospective cohort study of community-dwelling adults aged 65 years and older. This analysis included female participants without a history of CHF at baseline (n = 3223). RESULTS: At baseline, 62% were never users, 26% were past users, and 12% were current users of HRT. Compared with never users, the multivariable relative risk (RR) of CHF was 1.01 (95% confidence interval [95% CI] 0.76,1.34) for past users and 1.34 (0.93,1.94) for current users. Results were similar among most treatment and clinical subgroups, except that the association of current HRT with CHF appeared to depend on body mass index (BMI) or osteoporosis status. The RR was 0.82 (0.43,1.60) for normal weight women, 1.65 (0.95,2.88) for overweight women, and 2.22 (1.06,4.67) for obese women (p = 0.01 for interaction). Similarly, the RR was 0.15 (0.04,0.65) for women with osteoporosis and 1.82 (1.25,2.65) for women without osteoporosis (p = 0.001 for interaction). CONCLUSIONS: Overall, HRT was not associated with the risk of incident CHF, although BMI and osteoporosis appeared to modify the association of HRT with CHF. The risk of CHF was lower in patients with lower BMI or osteoporosis.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Estrogen Replacement Therapy; Female; Heart Failure; Humans; Incidence; Life Style; Middle Aged; Multivariate Analysis; Obesity; Osteoporosis, Postmenopausal; Proportional Hazards Models; Prospective Studies; Risk; Risk Factors; United States; Women's Health

Prospective study of fibrinolytic markers and venous thromboembolism. - Folsom, Aaron R; Cushman, Mary; Heckbert, Susan R; Rosamond, Wayne D; Aleksic, Nena (J Clin Epidemiol, 2003)
Prior research has conflicted on whether increased levels of plasma fibrinolytic factors may identify patients at risk of venous thromboembolism (VTE). We therefore performed a nested case-control study of VTE within two prospective population-based studies. In 308 participants who developed VTE and 640 controls, we measured PAI-1 antigen, tPA/PAI-1 complex, plasmin-alpha 2-antiplasmin (PAP), and the PAI-1 -675 4G/5G promoter polymorphism on pre-event blood samples. There was no overall association between any of these fibrinolytic variables and VTE, after adjustment for age or for multiple VTE risk factors. There was weak evidence for an interaction of PAP with elevated factor VIIIc and elevated D-dimer in augmenting VTE risk. We conclude that, for the most part, these fibrinolytic markers do not identify healthy subjects at risk for VTE.
Keywords: Aged; alpha-2-Antiplasmin; Antifibrinolytic Agents; Biomarkers; Caenorhabditis elegans Proteins; Case-Control Studies; Female; Fibrinolysin; Fibrinolysis; Humans; Male; Middle Aged; Odds Ratio; Plasminogen Activator Inhibitor 1; Prognosis; Prospective Studies; Protein-Tyrosine Kinases; Risk Factors; Thromboembolism; Venous Thrombosis

Serum homocysteine, thermolabile variant of methylene tetrahydrofolate reductase (MTHFR), and venous thromboembolism: Longitudinal Investigation of Thromboembolism Etiology (LITE). - Tsai, Albert W; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Rosamond, Wayne D; Aleksic, Nena; Yanez, N David; Psaty, Bruce M; Folsom, Aaron R (Am J Hematol, 2003)
We sought to examine prospectively the association of serum homocysteine and the methylene tetrahydrofolate reductase (MTHFR) C677T gene polymorphism with risk of venous thromboembolism (VTE). We studied these relationships in a nested case-control study of 303 VTE cases and 635 matched controls from a population-based cohort of 21,680 adults from six U.S. communities. The highest quintile of serum homocysteine carried a non-statistically significant adjusted odds ratio of 1.55 (95% CI, 0.93-2.58) compared to the lowest quintile in the overall cohort but a significant association among adults aged 45-64 years (OR = 2.05, 95% CI, 1.10-3.83) and an inverse association in those > or = 65 years of age. Carriers of the MTHFR C677T polymorphism were not at higher risk for VTE than those with normal genotype (OR = 0.74, 95% CI = 0.56-0.98). Our prospective data showed, at most, a weak relationship between homocysteine and VTE risk, with associations larger among younger participants. MTHFR C677T was not a risk factor for VTE.
Keywords: Aged; Aging; Animals; Case-Control Studies; Cohort Studies; Factor V; Female; Genotype; Homocysteine; Humans; Longitudinal Studies; Male; Methylenetetrahydrofolate Reductase (NADPH2); Middle Aged; Odds Ratio; Oxidoreductases Acting on CH-NH Group Donors; Polymorphism, Genetic; Prospective Studies; Risk Factors; Venous Thrombosis

Sleep and sleep-disordered breathing in adults with predominantly mild obstructive airway disease. - Sanders, Mark H; Newman, Anne B; Haggerty, Catherine L; Redline, Susan; Lebowitz, Michael; Samet, Jonathan; O'Connor, George T; Punjabi, Naresh M; Shahar, Eyal (Am J Respir Crit Care Med, 2003)
Neither the association between obstructive airways disease (OAD) and sleep apnea-hypopnea (SAH) nor the sleep consequences of each disorder alone and together have been characterized in an adult community setting. Our primary aims were (1) to determine if there is an association between OAD and SAH and (2) identify predictors of oxyhemoglobin desaturation during sleep in persons having OAD with and without SAH. Polysomnography and spirometry results from 5,954 participants in the Sleep Heart Health Study were analyzed. OAD was defined by a FEV1/FVC value less than 70%. Assessment of SAH prevalence in OAD was performed using thresholds of respiratory disturbance index (RDI) greater than 10 and greater than 15. A total of 1,132 participants had OAD that was predominantly mild (FEV1/FVC 63.81 +/- 6.56%, mean +/- SD). SAH was not more prevalent in participants with OAD than in those without OAD (22.32 versus 28.86%, with and without OAD, respectively, at RDI threshold values greater than 10; and 13.97 versus 18.63%, with and without OAD, respectively, at RDI threshold value greater than 15). In the absence of SAH, the adjusted odds ratio for sleep desaturation (> 5% total sleep time with saturation < 90%) was greater than 1.9 when FEV1/FVC was less than 65%. Participants with both OAD and SAH had greater sleep perturbation and desaturation than those with one disorder. Generally mild OAD alone was associated with minimally altered sleep quality. We conclude that (1) there is no association between generally mild OAD and SAH; (2) exclusive of SAH and after adjusting for demographic factors and awake oxyhemoglobin saturation, an FEV1/FVC value less than 65% is associated with increased risk of sleep desaturation; (3) desaturation is greater in persons with both OAD and SAH compared with each of these alone; and (4) individuals with generally mild OAD and without SAH in the community have minimally perturbed sleep.
Keywords: Aged; Cohort Studies; Female; Forced Expiratory Volume; Humans; Male; Middle Aged; Oxyhemoglobins; Polysomnography; Prospective Studies; Pulmonary Disease, Chronic Obstructive; Sleep; Sleep Apnea, Obstructive; Spirometry; Vital Capacity

APOE epsilon4 is associated with obstructive sleep apnea/hypopnea: the Sleep Heart Health Study. - Gottlieb, D J; DeStefano, A L; Foley, D J; Mignot, E; Redline, S; Givelber, R J; Young, T (Neurology, 2004)
BACKGROUND: Obstructive sleep apnea/hypopnea (OSAH) has a strong heritable component, although its genetic basis remains largely unknown. One epidemiologic study found a significant association between the APOE epsilon4 allele and OSAH in middle-aged adults, a finding that was not replicated in a cohort of elderly adults. The objective of this study was to further examine the association of the APOE epsilon4 allele with OSAH in a community-dwelling cohort, exploring age dependency of the association. METHODS: A genetic association study was performed, nested within a prospective cohort study of the cardiovascular consequences of OSAH. Unattended, in-home nocturnal polysomnography was used to measure apnea-hypopnea index (AHI) in 1,775 participants age 40 to 100 years. OSAH was defined as an AHI > or = 15. The relation of APOE genotype to prevalent OSAH was analyzed using generalized estimating equations to account for non-independent observations of individuals from the same sibship. RESULTS: At least one APOE epsilon4 allele was present in 25% of subjects, with 1.3% epsilon4/epsilon4 homozygotes. The prevalence of OSAH was 19%. After adjustment for age, sex, and BMI, the presence of any APOE epsilon4 allele was associated with increased odds of OSAH (OR 1.41, 95% CI 1.06 to 1.87, p = 0.02). The effect was approximately twice as great in subjects <75 (OR 1.61, CI 1.02 to 2.54) as in those > or =75 years old (OR 1.32, CI 0.91 to 1.90). Exploratory analyses revealed that the strongest effect of APOE epsilon4 was in subjects age <65 (OR 3.08, CI 1.43 to 6.64), and was stronger in those with hypertension or cardiovascular disease than in those without. CONCLUSION: The APOE epsilon4 allele is associated with increased risk of OSAH, particularly in individuals under age 65. The mechanisms underlying this association are uncertain. Age-dependency of the APOE-OSAH association may explain previous conflicting results.
Keywords: Adult; Age Distribution; Aged; Aged, 80 and over; Alleles; Apolipoprotein E4; Apolipoproteins E; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Genetic Predisposition to Disease; Genotype; Humans; Hyperlipidemias; Hypertension; Male; Middle Aged; Obesity; Polysomnography; Sleep Apnea, Obstructive; Smoking

Assessment of prolonged QT and JT intervals in ventricular conduction defects. - Rautaharju, Pentti M; Zhang, Zhu-Ming; Prineas, Ron; Heiss, Gerardo (Am J Cardiol, 2004)
The JT interval or Bazett's QTc - QRS has been advocated for detection of prolonged repolarization in ventricular conduction defects (VCDs). However, the use of neither JT nor QTc - QRS has been validated, and normal limits for rate-adjusted JT have not been established for VCDs or for normal ventricular conduction. Functional relations among RR, JT, and QT intervals were evaluated in 11,739 adult men and women with normal ventricular conduction and in 1,251 subjects with major VCD. The results showed that JT adjustment obtained as QTc - QRS retained a strong residual correlation with ventricular rate (r = 0.54), making its use ill-advised. In contrast, QT adjustment as a linear function of the RR interval for VCD as QT(RR,QRS) = QT - 155 x (60/heart rate - 1) - 0.93 x (QRS - 139) + k, with k = -22 ms for men and -34 ms for women, removed the rate dependence and produced upper 2% and 5% normal limits at 460 and 450 ms, respectively, which are identical to those in normal conduction. As an alternative, equally effective linear JT adjustment formulas were derived, including newly required normal standards. Thus, detection of prolonged repolarization in VCD requires the use of the JT interval or a bivariate model for QT with RR and QRS intervals as covariates.
Keywords: Adult; Aged; Aged, 80 and over; Arrhythmias, Cardiac; Bundle-Branch Block; Electrocardiography; Female; Heart Ventricles; Humans; Male; Middle Aged

Associations between gender and measures of daytime somnolence in the Sleep Heart Health Study. - Baldwin, Carol M; Kapur, Vishesh K; Holberg, Catharine J; Rosen, Carol; Nieto, F Javier (Sleep, 2004)
STUDY OBJECTIVES: To examine the relationship of gender to subjective measures of sleepiness, including the Epworth Sleepiness Scale (ESS), in a community-based population. DESIGN: A cross-sectional study. SETTING/PARTICIPANTS: Multicenter Sleep Heart Health Study participants (N = 6.440, 52% women) recruited from ongoing cohort studies. INTERVENTIONS: N/A. MEASUREMENTS: Scores from the ESS, Sleep Heart Health Study daytime sleepiness and feeling unrested questions, polysomnography results (respiratory disturbance index at 4% desaturation), as well as data on difficulty initiating and maintaining sleep, insufficient sleep, sedative use, alcohol use, cardiovascular or respiratory disease, frequent awakening due to leg cramps. RESULTS: Women reported feeling sleepy as often as men did (odds ratio [OR] = 1.06; confidence interval [CI], 0.86-1.32), but women were less likely to have an ESS score > 10 (adjusted OR = 0.77; CI, 0.66-0.90) and more likely to report feeling unrested (adjusted OR = 1.39; CI, 1.14-1.69) than men. In men, the ESS score was more strongly correlated with reports of feeling unrested or sleepy compared to women. CONCLUSIONS: Men and women answer questions on sleepiness differently. Findings indicate that using the ESS to detect subjective sleepiness is more likely to identify men with sleepiness. Since the ESS is more strongly related to other subjective measures in men, the ESS may be a more sensitive measure of subjective sleepiness in men than in women.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Health Status; Humans; Hypertension; Male; Middle Aged; Polysomnography; Severity of Illness Index; Sex Factors

Deep vein thrombosis and pulmonary embolism in two cohorts: the longitudinal investigation of thromboembolism etiology. - Cushman, Mary; Tsai, Albert W; White, Richard H; Heckbert, Susan R; Rosamond, Wayne D; Enright, Paul; Folsom, Aaron R (Am J Med, 2004)
PURPOSE: To determine the incidence of deep vein thrombosis and pulmonary embolism in two cohorts representing regions of the United States. METHODS: The sample comprised 21,680 participants of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. Subjects were aged >/=45 years, resided in six communities, and were followed for 7.6 years. All hospitalizations were identified and thromboses were validated by chart review. RESULTS: The age-standardized incidence of first-time venous thromboembolism was 1.92 per 1000 person-years. Rates were higher in men than women, and increased with age in both sexes. There was no antecedent trauma, surgery, immobilization, or diagnosis of cancer for 48% (175/366) of events. The 28-day case-fatality rate was 11% (29/265) after a first venous thromboembolism and 25% (17/67) for cancer-associated thrombosis. The recurrence rate 2 years after a first venous thromboembolism was 7.7% per year (95% confidence interval [CI]: 4.5% to 10.9% per year). Cancer was the only factor independently associated with 28-day fatality (relative risk [RR] = 5.2; 95% CI: 1.4 to 19.9) or recurrent thrombosis (RR = 9.2; 95% CI: 2.0 to 41.7). CONCLUSION: The incidence of venous thromboembolism in this cohort of middle- and older-aged subjects was similar to that observed in more geographically homogeneous samples. Half of cases were idiopathic. Short-term mortality and 2-year recurrence rates were appreciable, especially among subjects with cancer. Based on this study we estimate that 187,000 cases of first-time venous thromboembolism are diagnosed yearly in the United States among those aged 45 years or older.
Keywords: Aged; Case-Control Studies; Cohort Studies; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Neoplasms; Population Surveillance; Pulmonary Embolism; Recurrence; Risk Factors; Survival Rate; Venous Thrombosis

The effects of age, sex, ethnicity, and sleep-disordered breathing on sleep architecture. - Redline, Susan; Kirchner, H Lester; Quan, Stuart F; Gottlieb, Daniel J; Kapur, Vishesh; Newman, Anne (Arch Intern Med, 2004)
BACKGROUND: Polysomnography is used to assess sleep quality and to gauge the functional effect of sleep disorders. Few population-based data are available to estimate the variation in sleep architecture across the population and the extent to which sleep-disordered breathing (SDB), a common health condition, contributes to poor sleep independent of other factors. The objective of this study was to describe the population variability in sleep quality and to quantify the independent associations with SDB. METHODS: Cross-sectional analyses were performed on data from 2685 participants, aged 37 to 92 years, in a community-based multicenter cohort study. Dependent measures included the percentage time in each sleep stage, the arousal index, and sleep efficiency. Independent measures were age, sex, ethnicity, comorbidity status, and the respiratory disturbance index. RESULTS: Lighter sleep was found in men relative to women and in American Indians and blacks relative to other ethnic groups. Increasing age was associated with impaired sleep in men, with less consistent associations in women. Notably, women had, on average, 106% more slow wave sleep. Sleep-disordered breathing was associated with poorer sleep; however, these associations were generally smaller than associations with sex, ethnicity, and age. Current smokers had lighter sleep than ex-smokers or never smokers. Obesity had little effect on sleep. CONCLUSIONS: Sleep architecture varies with sex, age, ethnicity, and SDB. Individual assessment of the effect of SDB on sleep quality needs to account for other host characteristics. Men, but not women, show evidence of poorer sleep with aging, suggesting important sex differences in sleep physiology.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Comorbidity; Female; Humans; Male; Middle Aged; Multivariate Analysis; Sex Factors; Sleep; Sleep Apnea Syndromes

Polysomnography performed in the unattended home versus the attended laboratory setting--Sleep Heart Health Study methodology. - Iber, Conrad; Redline, Susan; Kaplan Gilpin, Adele M; Quan, Stuart F; Zhang, Lin; Gottlieb, Daniel J; Rapoport, David; Resnick, Helaine E; Sanders, Mark; Smith, Philip (Sleep, 2004)
STUDY OBJECTIVE: To compare polysomnographic recordings obtained in the home and laboratory setting. DESIGN AND SETTING: Multicenter study comparing unsupervised polysomnography performed in the participant's home with polysomnography supervised at an academic sleep disorders center, using a randomized sequence of study setting. Sleep Heart Health Study (SHHS) standardized polysomnographic recording and scoring techniques were used for both settings. PARTICIPANTS: 64 of 76 non-SHHS participants recruited from 7 SHHS field sites who had both a laboratory and home polysomnogram meeting acceptable quality criteria. MEASUREMENTS AND RESULTS: Median sleep duration was greater in the home than in the laboratory (375 vs 318 minutes, respectively, P < .0001) as was sleep efficiency (86% vs 82%, respectively, P < .0024). Very small, but significant increases in percentage of rapid eye movement sleep and decreases in stage 1 sleep were noted in the laboratory. Employing multiple definitions of respiratory disturbance index (RDI), median RDI was similar in both settings (for example, RDI with 3% desaturation: home 12.4, range 0.6-67; laboratory 9.5, range 0.1-93.4, P = .41). Quartile analysis of laboratory RDI showed moderate agreement with home RDI measurements. Based on the mean of laboratory and home RDI and using a cutpoint of 20, there was a biphasic distribution, with the RDI 3% above 20 being more common in the recordings performed in the laboratory than in the home and below 20 being more common in the recordings performed in the home than in the laboratory. These differences could not be attributed to quality of recording, age, sex, or body mass index. CONCLUSIONS: Using SHHS methodology, median RDI was similar in the unattended home and attended laboratory setting with differences of small magnitude in some sleep parameters. Differences in RDI between settings resulted in a rate of disease misclassification that is similar to repeated studies in the same setting.
Keywords: Adult; Aged; Body Mass Index; Clinical Laboratory Techniques; Cohort Studies; Health Status; Home Care Services; Humans; Middle Aged; Polysomnography; Sleep Apnea Syndromes; Sleep, REM

Sleep and reported daytime sleepiness in normal subjects: the Sleep Heart Health Study. - Walsleben, Joyce A; Kapur, Vishesh K; Newman, Anne B; Shahar, Eyal; Bootzin, Richard R; Rosenberg, Carl E; O'Connor, George; Nieto, F Javier (Sleep, 2004)
STUDY OBJECTIVES: To describe the distribution of nocturnal sleep characteristics and reports of daytime sleepiness in a large well-defined group of healthy adults. DESIGN: The Sleep Heart Health Study is a multicenter study examining sleep and cardiopulmonary parameters through nocturnal polysomnography in adults enrolled in geographically distinct cardiovascular cohorts. SETTING: Community setting. PARTICIPANTS: 470 subjects enrolled in the Sleep Heart Health Study (n = 6440) were selected as a 'normative' group based on screening of health conditions and daily habits that could interfere with sleep. MEASUREMENTS AND RESULTS: Home-based nocturnal polysomnography was obtained on all participants and centrally scored for sleep and respiratory parameters. Demographic and health-related data were obtained and updated at the time of the home visit. Sleep efficiency decreased by 1.6% for each 10 years of increased age. Sleep time decreased by 0.1 hours (6.0 minutes) for each 10-year age increase and was longer in women. The arousal index increased by 0.8 for each 10-year increase in age and was lower by 1.4 in women. Women had a lower mean percentage of stage 1 and stage 2 sleep. Mean percentage of slow-wave sleep was higher in women (by 6.7%). Percentage of slow-wave sleep decreased with increased age for men only (by 1.9% for each 10-year age change). CONCLUSIONS: Data suggest a clear lessening in the quantity and quality of sleep with age that appears to be more rapid in males compared to females.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Circadian Rhythm; Cohort Studies; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Sleep; Sleep Stages; Surveys and Questionnaires

Sleep-disordered breathing, glucose intolerance, and insulin resistance: the Sleep Heart Health Study. - Punjabi, Naresh M; Shahar, Eyal; Redline, Susan; Gottlieb, Daniel J; Givelber, Rachel; Resnick, Helaine E (Am J Epidemiol, 2004)
Clinic-based studies suggest that sleep-disordered breathing (SDB) is associated with glucose intolerance and insulin resistance. However, in the available studies, researchers have not rigorously controlled for confounding variables to assess the independent relation between SDB and impaired glucose metabolism. The objective of this study was to determine whether SDB was associated with glucose intolerance and insulin resistance among community-dwelling subjects (n=2,656) participating in the Sleep Heart Health Study (1994-1999). SDB was characterized with the respiratory disturbance index and measurements of oxygen saturation during sleep. Fasting and 2-hour glucose levels measured during an oral glucose tolerance test were used to assess glycemic status. Relative to subjects with a respiratory disturbance index of less than 5.0 events/hour (the reference category), subjects with mild SDB (5.0-14.9 events/hour) and moderate to severe SDB (> or =15 events/hour) had adjusted odds ratios of 1.27 (95% confidence interval: 0.98, 1.64) and 1.46 (95% confidence interval: 1.09, 1.97), respectively, for fasting glucose intolerance (p for trend < 0.01). Sleep-related hypoxemia was also associated with glucose intolerance independently of age, gender, body mass index, and waist circumference. The results of this study suggest that SDB is independently associated with glucose intolerance and insulin resistance and may lead to type 2 diabetes mellitus.
Keywords: Aged; Blood Gas Analysis; Body Constitution; Body Mass Index; Cohort Studies; Confounding Factors, Epidemiologic; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin Resistance; Linear Models; Male; Middle Aged; Multivariate Analysis; Oxyhemoglobins; Polysomnography; Research Design; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes

Sleep-disordered breathing is not associated with the presence of retinal microvascular abnormalities: the Sleep Heart Health Study. - Boland, Lori L; Shahar, Eyal; Wong, Tien Y; Klein, Ronald; Punjabi, Naresh; Robbins, John A; Newman, Anne B (Sleep, 2004)
STUDY OBJECTIVE: Sleep apnea and milder forms of sleep-disordered breathing (SDB) have been associated with overt clinical cardiovascular disease, but it is unknown whether SDB is associated with arterial microvascular pathology. We examined the relation between SDB and retinal microvascular abnormalities. DESIGN: Cross-sectional study. PARTICIPANTS: Subjects were 2,927 men and women, aged 51 to 97 years, who participated in the Sleep Heart Health Study and had retinal photographs taken within approximately 3 years of overnight, unattended, at-home polysomnography. MEASUREMENTS AND RESULTS: A respiratory disturbance index (RDI), calculated as the average number of apneas and hypopneas per hour of sleep, was used as an indicator of SDB in analysis. The overall prevalence of retinopathy was slightly higher in people with higher RDI values (5.4%, 4.9%, 8.6%, and 7.6%, respectively, in increasing quartiles of RDI), but after adjustment for age, body-mass index, hypertension, diabetes, and other factors, the presence of retinopathy was not associated with SDB. With the possible exceptions of microaneurysms and generalized arteriolar narrowing, as measured by lower arteriole-to-venule ratio, specific retinal abnormalities were not associated consistently with the RDI. Relative to the first quartile of RDI, the adjusted odds ratios (95% confidence interval) for the presence of microaneurysm in the second, third, and fourth quartiles of RDI were 1.05 (0.44-2.55), 1.97 (0.89-4.37), and 1.79 (0.78-4.10), respectively. An increase of RDI from 0 to 10 was associated with a predicted decrease in arteriole-to-venule ratio of 0.01. Results were similar when analyses were conducted in normotensive and nondiabetic persons separately. CONCLUSIONS: These data do not demonstrate a notable relation between SDB and retinal abnormalities. However, since this is the first investigation of a link between retinopathy and SDB, similar studies should be conducted in other population samples to demonstrate either consistency or inconsistency of our findings across studies.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Coronary Disease; Cross-Sectional Studies; Female; Humans; Hypoxia; Middle Aged; Polysomnography; Positive-Pressure Respiration; Retina; Retinal Vessels; Sleep Apnea Syndromes

Age-dependent associations between sleep-disordered breathing and hypertension: importance of discriminating between systolic/diastolic hypertension and isolated systolic hypertension in the Sleep Heart Health Study. - Haas, Donald C; Foster, Gregory L; Nieto, F Javier; Redline, Susan; Resnick, Helaine E; Robbins, John A; Young, Terry; Pickering, Thomas G (Circulation, 2005)
BACKGROUND: Sleep-disordered breathing (SDB) is associated with hypertension in the middle-aged. The association is less clear in older persons. Most middle-aged hypertensives have systolic/diastolic hypertension, whereas isolated systolic hypertension (ISH) is common among persons over 60 years. Mechanistically, only systolic/diastolic hypertension is expected to be associated with SDB, but few studies of SDB and hypertension distinguish systolic/diastolic hypertension from ISH. Prior investigations may have underestimated an association between SDB and systolic/diastolic hypertension in the elderly by categorizing individuals with ISH as simply hypertensive. METHODS AND RESULTS: We conducted cross-sectional analyses of 6120 participants in the Sleep Heart Health Study, stratified by age: 40 to 59 (n=2477) and > or =60 years. Outcome measures included apnea-hypopnea index (AHI; average number of apneas plus hypopneas per hour of sleep), systolic/diastolic hypertension (> or =140 and > or =90 mm Hg), and ISH (> or =140 and <90 mm Hg). With adjustment for covariates, ISH was not associated with SDB in either age category. In those aged<60 years, AHI was significantly associated with higher odds of systolic/diastolic hypertension (AHI 15 to 29.9, OR=2.38 [95% CI 1.30 to 4.38]; AHI > or =30, OR=2.24 [95% CI 1.10 to 4.54]). Among those aged > or =60 years, no adjusted association between AHI and systolic/diastolic hypertension was found. CONCLUSIONS: SDB is associated with systolic/diastolic hypertension in those aged <60 years. No association was found between SDB and systolic/diastolic hypertension in those aged > or =60 years or between SDB and ISH in either age category. These findings have implications for SDB screening and treatment. Distinguishing between hypertensive subtypes reveals a stronger association between SDB and hypertension for those aged <60 years than previously reported.
Keywords: Adult; Age Factors; Aged; Antihypertensive Agents; Cross-Sectional Studies; Diastole; Female; Humans; Hypertension; Male; Middle Aged; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Central; Systole

Alcohol use and risk of ischemic stroke among older adults: the cardiovascular health study. - Mukamal, Kenneth J; Chung, Hyoju; Jenny, Nancy S; Kuller, Lewis H; Longstreth, W T; Mittleman, Murray A; Burke, Gregory L; Cushman, Mary; Beauchamp, Norman J; Siscovick, David S (Stroke, 2005)
BACKGROUND AND PURPOSE: The association of light to moderate alcohol consumption with risk of ischemic stroke remains uncertain, as are the roles of potentially mediating factors and modification by apolipoprotein E (apoE) genotype. METHODS: We studied the prospective association of alcohol consumption and risk of ischemic stroke among 4410 participants free of cardiovascular disease at baseline in the Cardiovascular Health Study, a population-based cohort study of older adults from 4 US communities. Participants reported their consumption of alcoholic beverages yearly. RESULTS: During an average follow-up period of 9.2 years, 434 cases of incident ischemic stroke occurred. Compared with long-term abstainers, the multivariate relative risks of ischemic stroke were 0.85 (95% CI, 0.63 to 1.13), 0.75 (95% CI, 0.53 to 1.06), 0.82 (95% CI, 0.51 to 1.30), and 1.03 (95% CI, 0.68 to 1.57) among consumers of <1, 1 to 6, 7 to 13, and > or =14 drinks per week (P quadratic trend 0.06). ApoE genotype appeared to modify the alcohol-ischemic stroke relationship (P interaction 0.08), with generally lower risks among drinkers than abstainers in apoE4-negative participants but higher risks among drinkers than abstainers among apoE4-positive participants. We could not identify candidate mediators among lipid, inflammatory, and prothrombotic factors. CONCLUSIONS: In this study of older adults, the association of alcohol use and risk of ischemic stroke was U-shaped, with modestly lower risk among consumers of 1 to 6 drinks per week. However, apoE genotype may modify this association, and even moderate alcohol intake may be associated with an increased risk of ischemic stroke among apoE4-positive older adults.
Keywords: Aged; Alcohol Drinking; Apolipoproteins E; Brain Infarction; Brain Ischemia; Cohort Studies; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Inflammation; Ischemia; Lipids; Male; Middle Aged; Multivariate Analysis; Myocardial Infarction; Prospective Studies; Risk; Risk Factors; Stroke; Substance-Related Disorders; Thrombosis; Time Factors; Vascular Diseases

Association of sleep time with diabetes mellitus and impaired glucose tolerance. - Gottlieb, Daniel J; Punjabi, Naresh M; Newman, Ann B; Resnick, Helaine E; Redline, Susan; Baldwin, Carol M; Nieto, F Javier (Arch Intern Med, 2005)
BACKGROUND: Experimental sleep restriction causes impaired glucose tolerance (IGT); however, little is known about the metabolic effects of habitual sleep restriction. We assessed the cross-sectional relation of usual sleep time to diabetes mellitus (DM) and IGT among participants in the Sleep Heart Health Study, a community-based prospective study of the cardiovascular consequences of sleep-disordered breathing. METHODS: Participants were 722 men and 764 women, aged 53 to 93 years. Usual sleep time was obtained by standardized questionnaire. Diabetes mellitus was defined as a serum glucose level of 126 mg/dL or more (> or =7.0 mmol/L) fasting or 200 mg/dL or more (> or =11.1 mmol/L) 2 hours following standard oral glucose challenge or medication use for DM. Impaired glucose tolerance was defined as a 2-hour postchallenge glucose level of 140 mg/dL or more (> or =7.8 mmol/L) and less than 200 mg/dL. The relation of sleep time to DM and IGT was examined using categorical logistic regression with adjustment for age, sex, race, body habitus, and apnea-hypopnea index. RESULTS: The median sleep time was 7 hours per night, with 27.1% of subjects sleeping 6 hours or less per night. Compared with those sleeping 7 to 8 hours per night, subjects sleeping 5 hours or less and 6 hours per night had adjusted odds ratios for DM of 2.51 (95% confidence interval, 1.57-4.02) and 1.66 (95% confidence interval, 1.15-2.39), respectively. Adjusted odds ratios for IGT were 1.33 (95% confidence interval, 0.83-2.15) and 1.58 (95% confidence interval, 1.15-2.18), respectively. Subjects sleeping 9 hours or more per night also had increased odds ratios for DM and IGT. These associations persisted when subjects with insomnia symptoms were excluded. CONCLUSIONS: A sleep duration of 6 hours or less or 9 hours or more is associated with increased prevalence of DM and IGT. Because this effect was present in subjects without insomnia, voluntary sleep restriction may contribute to the large public health burden of DM.
Keywords: Age Factors; Aged; Aged, 80 and over; Blood Glucose; Diabetes Mellitus; Disease Progression; Female; Glucose Intolerance; Humans; Male; Middle Aged; Odds Ratio; Prevalence; Prospective Studies; Sleep; Surveys and Questionnaires; Time Factors; United States

beta(2)-Adrenergic receptor polymorphisms and determinants of cardiovascular risk: the Cardiovascular Health Study. - Hindorff, Lucia A; Heckbert, Susan R; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Herrington, David M; Edwards, Karen L; Tracy, Russell P (Am J Hypertens, 2005)
BACKGROUND: Common Arg16Gly and Gln27Glu polymorphisms of the beta(2)-adrenergic receptor (beta(2)AR) have been associated with hypertension and coronary disease. This analysis of older adults in the Cardiovascular Health Study examined whether these polymorphisms were associated with blood pressure (BP), subclinical atherosclerosis, and, among treated hypertensive individuals, differences in coronary disease risk according to antihypertensive drug class. METHODS: Altogether, 5249 participants (4441 white and 808 African American, median follow-up time 10.2 years) were genotyped for both polymorphisms. Ankle-arm index (AAI), carotid intima-media thickness (IMT), and brachial flow-mediated dilation were measured cross-sectionally. All estimates were adjusted for ethnicity. RESULTS: Relative to Gln27 homozygotes, carrying the Glu27 allele was not associated with new-onset hypertension (hazard ratio [HR] = 1.01, 95% confidence interval [CI] = 0.87 to 1.16), BP control (odds ratio [OR] = 0.97, 95% CI = 0.89 to 1.06), AAI (mean difference 0.0042 +/- 0.0052), carotid IMT (mean difference 0.0044 +/- 0.02 mm), or brachial flow-mediated dilation (mean difference in baseline diameter -0.028 +/- 0.036 mm; the most marked of three measures). Among treated hypertensive individuals, coronary disease risk was similar in Glu27 carriers relative to Gln27 homozygotes in subgroups defined by use of beta-blockers (HR = 1.09, 95% CI = 0.64 to 1.87) or other antihypertensive medications (HR = 1.00, 95% CI = 0.78 to 1.28). Results were similar for the Arg16Gly polymorphism. CONCLUSIONS: The association of beta(2)AR genotype with coronary disease previously reported in this older adult population is not likely to be explained by BP levels, subclinical atherosclerosis, or antihypertensive treatment. Other measures of vascular response, gene-gene or gene-environment interactions, or characteristics developing earlier in life may mediate the association between beta(2)AR genotype and coronary disease and merit further research.
Keywords: African Americans; Antihypertensive Agents; Arteriosclerosis; Coronary Artery Disease; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Factors

Cardiovascular risk factors for retinal vein occlusion and arteriolar emboli: the Atherosclerosis Risk in Communities & Cardiovascular Health studies. - Wong, Tien Yin; Larsen, Emily K Marino; Klein, Ronald; Mitchell, Paul; Couper, David J; Klein, Barbara E K; Hubbard, Larry D; Siscovick, David S; Sharrett, A Richey (Ophthalmology, 2005)
OBJECTIVE: To examine the associations of retinal vein occlusion and arteriolar emboli with cardiovascular disease. DESIGN: Population-based cross-sectional study. PARTICIPANTS: Pooled from the Atherosclerosis Risk in Communities Study (n = 12,642; mean age, 60 years) and the Cardiovascular Health Study (n = 2824; mean age, 79 years). METHODS: Retinal vein occlusion and arteriolar emboli were identified from a single nonmydriatic retinal photograph using a standardized protocol. Photographs were also graded for arteriovenous nicking and focal arteriolar narrowing. All participants had a comprehensive systemic evaluation, including standardized carotid ultrasonography. MAIN OUTCOME MEASURES: Retinal vein occlusion and arteriolar emboli. RESULTS: Prevalences of retinal vein occlusion and arteriolar emboli were 0.3% (n = 39 cases) and 0.2% (n = 34 cases), respectively. After adjusting for age, retinal vein occlusion was associated with hypertension (odds ratio [OR], 2.96; 95% confidence interval [CI], 1.43-6.14), systolic blood pressure (BP) (OR, 4.12; 95% CI, 1.40-12.16; highest quartile vs. lowest), diastolic BP (OR, 2.64; 95% CI, 1.07-6.46; highest quartile vs. lowest), carotid artery plaque (OR, 5.62; 95% CI, 2.60-12.16), body mass index (OR, 3.88; 95% CI, 1.23-12.18; highest quartile vs. lowest), plasma fibrinogen (OR, 3.29; 95% CI, 1.08-10.02; highest quartile vs. lowest), arteriovenous nicking (OR, 4.09; 95% CI, 2.00-8.36), and focal arteriolar narrowing (OR, 5.17; 95% CI, 2.59-10.29). After adjusting for age, retinal arteriolar emboli were associated with hypertension (OR, 3.14; 95% CI, 1.44-6.84), systolic BP (OR, 3.46; 95% CI, 1.13-10.65; highest quartile vs. lowest), prevalent coronary heart disease (OR, 2.33; 95% CI, 1.01-5.42), carotid artery plaque (OR, 4.62; 95% CI, 1.85-11.57), plasma lipoprotein (a) (OR, 3.69; 95% CI, 1.20-11.41; highest quartile vs. lowest), plasma fibrinogen (OR, 3.09; 95% CI, 0.98-9.76; highest quartile vs. lowest), and current cigarette smoking (OR, 3.08; 95% CI, 1.47-6.47). Approximately a quarter of participants with retinal vein occlusion and arteriolar emboli had evidence of carotid artery plaque as defined from ultrasound. CONCLUSIONS: Retinal vein occlusion and retinal arteriolar emboli are associated with carotid artery disease, hypertension, and other cardiovascular risk factors.
Keywords: Aged; Aged, 80 and over; Arterioles; Blood Pressure; Cardiovascular Diseases; Carotid Stenosis; Coronary Artery Disease; Cross-Sectional Studies; Embolism; Female; Fibrinogen; Humans; Hypertension; Lipoprotein(a); Male; Meta-Analysis as Topic; Middle Aged; Retinal Artery; Retinal Vein Occlusion; Risk Factors

Common promoter polymorphisms of inflammation and thrombosis genes and longevity in older adults: the cardiovascular health study. - Reiner, Alexander P; Diehr, Paula; Browner, Warren S; Humphries, Stephen E; Jenny, Nancy S; Cushman, Mary; Tracy, Russell P; Walston, Jeremy; Lumley, Thomas; Newman, Anne B; Kuller, Lewis H; Psaty, Bruce M (Atherosclerosis, 2005)
Inflammatory response genes may influence life span or quality at advanced ages. Using data from the population-based cardiovascular health study (CHS) cohort, we examined the associations between promoter polymorphisms of several inflammation and thrombosis genes with longevity. We ascertained genotypes for interleukin (IL)-6 -174 G/C, beta-fibrinogen -455 G/A, plasminogen activator inhibitor (PAI)-1 -675 4G/5G, and thrombin-activatable fibrinolysis inhibitor (TAFI) -438 G/A in 2224 men and women > or = 65 years old at baseline. During 10 years of follow-up, men with the TAFI -438 A/A genotype had decreased mortality due to all causes, and lived, on average, 0.9 more years of life, or 1.1 more years of healthy life, than men with the -438 G allele. The effects of TAFI -438 G/A in women were smaller and not statistically significant. PAI-1 4G/4G genotype appeared to be associated with lower non-cardiovascular mortality in men, but with greater cardiovascular mortality in women. In exploratory analyses, we observed a possible interaction among anti-inflammatory drugs, interleukin-6 -174 C/C genotype, and longevity. These findings suggest that modulators of fibrinolytic activity may have a generalized influence on aging, and merit further investigation in studies of genetic determinants of human longevity.
Keywords: Aged; Aging; Carboxypeptidase B2; Cause of Death; Cohort Studies; Female; Genotype; Health Status; Humans; Inflammation; Longevity; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Prospective Studies; Risk Factors; Thrombosis

Haptoglobin phenotype, sleep-disordered breathing, and the prevalence of cardiovascular disease: the Sleep Heart Health Study. - Levy, Andrew P; Zhang, Lin; Miller-Lotan, Rachel; Redline, Susan; O'Connor, George T; Quan, Stuart F; Resnick, Helaine E (Sleep, 2005)
BACKGROUND: Diabetes is an independent risk factor for cardiovascular disease, and there is growing evidence that sleep-disordered breathing also may increase the risk of cardiovascular disease. The mechanism responsible for increased susceptibility of people with diabetes to cardiovascular disease is thought to share several features with sleep-disordered breathing, notably increased oxidative stress. We recently demonstrated that a particular haptoglobin phenotype that is associated with differential antioxidant activity is an independent risk factor for cardiovascular disease in individuals with diabetes. We therefore sought to determine whether sleep-disordered breathing and cardiovascular disease are more strongly associated among people with the unfavorable haptoglobin phenotype. METHODS: We tested this hypothesis in 2612 middle-aged and older participants from the Sleep Heart Health Study. Haptoglobin phenotyping was performed by gel electrophoresis. Respiratory disturbance index was assessed by standard methods. Logistic regression analysis was performed to estimate the association between haptoglobin phenotype and cardiovascular disease, adjusting for known cardiovascular risk factors (age, sex, diabetes, smoking, lipid levels, and hypertension). Possible modification by haptoglobin phenotype of the association of sleep-disordered breathing with cardiovascular disease prevalence was explored by examining interaction terms. RESULTS: We found no significant association between haptoglobin phenotype and prevalent cardiovascular disease in this cohort, nor were significant interactions found between haptoglobin phenotype and sleep-disordered breathing on the prevalence of cardiovascular disease. CONCLUSIONS: Sleep-disordered breathing did not appear to interact with haptoglobin phenotype in modifying the association with prevalent cardiovascular disease in the Sleep Heart Health Study. These findings could be due to the absence of association or to survivor bias in these cross-sectional analyses.
Keywords: Aged; Angioplasty, Balloon, Coronary; Coronary Artery Bypass; Cross-Sectional Studies; Female; Haptoglobins; Humans; Male; Middle Aged; Myocardial Infarction; Oxidative Stress; Phenotype; Polysomnography; Prevalence; Sleep Apnea Syndromes

Polysomnographic predictors of blood pressure and hypertension: is one index best? - Redline, Susan; Min, Nancy I; Shahar, Eyal; Rapoport, David; O'Connor, George (Sleep, 2005)
STUDY OBJECTIVES: Numerous indexes derived from polysomnography are available to characterize sleep-disordered breathing, with no consensus over which measures best predict clinical outcomes. This study addresses the relative merits of using alternative polysomnography indexes by characterizing the consistency and strength of the association of each index with blood pressure and hypertension. DESIGN: Cross-sectional analyses of the association of alternative polysomnography indexes with blood pressure and hypertension were performed in construction and validation data sets. Linear and logistic regression models were used to identify the best variable sets. PATIENTS: Data were obtained from 6433 men and women (age 62.9 +/- 11.0 years, 52.8% women) who participated in the Sleep Heart Health Study. RESULTS: In multivariable models, most indexes showed weak linear associations with systolic, with slightly stronger associations for diastolic blood pressure, and the log odds of hypertension. No single index showed consistent superiority over others. Systolic blood pressure, diastolic blood pressure, and hypertension each were associated with distinct sets of polysomnography variables. Slightly more-consistent associations were demonstrated for indexes that included hypopneas that were linked with either a 3% or 4% desaturation level than indexes that did not require hypopneas to have linked desaturation. For indexes that combined apneas and hypopneas, there was no evidence that linking obstructive apneas to desaturation or arousal altered prediction compared with counting all apneas. CONCLUSION: In summary, using a rigorous cross-validation assessment, we did not identify a clear superiority of any single index for blood pressure or hypertension prediction. Detailed analyses of alternative definitions of the respiratory disturbance index support current scoring guidelines, where desaturation criteria are recommended for hypopneas but not apneas.
Keywords: Blood Pressure; Cross-Sectional Studies; Female; Humans; Hypertension; Male; Middle Aged; Polysomnography; Predictive Value of Tests; Reproducibility of Results; Severity of Illness Index; Sleep Apnea, Obstructive

Predictors of heartburn during sleep in a large prospective cohort study. - Fass, Ronnie; Quan, Stuart F; O'Connor, George T; Ervin, Ann; Iber, Conrad (Chest, 2005)
BACKGROUND AND AIMS: Nocturnal gastroesophageal reflux, which may result in nocturnal heartburn, has been demonstrated to be associated with a more severe form of gastroesophageal reflux disease (GERD). The aim of this study was to determine the clinical predictors of heartburn during sleep in a large prospective cohort study. METHODS: Study subjects were members of the parent cohorts from which the Sleep Heart Health Study (SHHS) recruited participants. SHHS is a multicenter, longitudinal, cohort study of the cardiovascular consequences of sleep-disordered breathing. As part of the recruitment process, parent cohort members completed a questionnaire that permitted an assessment of the relationships between heartburn during sleep, and patient demographics, sleep abnormalities, medical history, and social habits in nine community-based parent cohorts across the United States. All variables, significant at the p < 0.05 level, were included as independent variables in multivariate logistic regression models with heartburn during sleep status included as the dependent variable RESULTS: A total of 15,314 subjects completed the questions about heartburn during sleep, and of these, 3,806 subjects (24.9%) reported having this symptom. In four increasingly comprehensive multivariate models, increased body mass index (BMI), carbonated soft drink consumption, snoring and daytime sleepiness (Epworth sleepiness scale score), insomnia, hypertension, asthma, and usage of benzodiazepines were strong predictors of heartburn during sleep. In contrast, college education decreased the risk of reporting heartburn during sleep. CONCLUSIONS: Heartburn during sleep is very common in the general population. Reports of this type of symptom of GERD are strongly associated with increased BMI, carbonated soft drink consumption, snoring and daytime sleepiness, insomnia, hypertension, asthma, and usage of benzodiazepines. Overall, heartburn during sleep may be associated with sleep complaints and excessive daytime sleepiness.
Keywords: Aged; Body Mass Index; Carbonated Beverages; Cohort Studies; Educational Status; Female; Gastroesophageal Reflux; Heartburn; Humans; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Sleep; Surveys and Questionnaires

Progression and regression of sleep-disordered breathing with changes in weight: the Sleep Heart Health Study. - Newman, Anne B; Foster, Greg; Givelber, Rachel; Nieto, F Javier; Redline, Susan; Young, Terry (Arch Intern Med, 2005)
BACKGROUND: The relationship of weight changes to the incidence, progression, and remission of sleep-disordered breathing (SDB) is not well defined. This study aims to determine the relationship between change in weight and progression or remission of SDB by polysomnography. METHODS: We performed a longitudinal cohort study of the cardiovascular consequences of sleep apnea in diverse US communities. Sleep apnea and polysomnographic indicators of SDB were assessed 5 years apart. RESULTS: A total of 2968 men and women (mean age, 62 years) participated in the study. Men were more likely to have an increase in Respiratory Disturbance Index (RDI) with a given increase in weight than were women, and this was not explained by differences in starting weight, waist circumference, age, or ethnicity. In a linear regression analysis, both men and women had a greater increase in RDI with weight gain than a decrease in RDI with weight loss. In a categorical analysis of larger degrees of change, this sex difference was also evident. Associations were similar in diverse ethnic groups. However, SDB progressed over time, even in those with stable weight. CONCLUSION: Modest changes in weight were related to an increase or decrease in SDB, and this association was stronger in men than in women.
Keywords: Body Weights and Measures; Causality; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Humans; Linear Models; Male; Middle Aged; Obesity; Odds Ratio; Sex Distribution; Sleep Apnea Syndromes; United States; Weight Gain; Weight Loss

Sleepiness in patients with moderate to severe sleep-disordered breathing. - Kapur, Vishesh K; Baldwin, Carol M; Resnick, Helaine E; Gottlieb, Daniel J; Nieto, F Javier (Sleep, 2005)
BACKGROUND: Population-based studies suggest that complaints of sleepiness are absent in many individuals with sleep-disordered breathing. We investigated the prevalence of sleepiness as well as factors associated with sleepiness in individuals with moderate to severe sleep-disordered breathing (apnea-hypopnea index > or = 15). DESIGN: Cross-sectional study. SETTING: The Sleep Heart Health Study. PARTICIPANTS: Sleep Heart Health Study participants (N = 6440). MEASUREMENTS AND RESULTS: Sleepiness was defined as an Epworth Sleepiness Scale score >10 or a report of at least frequently feeling unrested or sleepy. Forty-six percent of participants with moderate to severe sleep-disordered breathing (n = 1149) reported sleepiness. Characteristics associated with sleepiness after adjustment for confounders included presence of respiratory disease, shorter self-reported weekday and weekend sleep, sleep durations, complaints of insufficient sleep, complaints of sleep maintenance insomnia, early morning awakening, habitual snoring, and complaints of awakening with leg cramps or leg jerks. Some respiratory polysomnography measures were associated with sleepiness, but sleep-stage percentages and measures of sleep disruption were not. CONCLUSIONS: In this community-based cohort, subjective sleepiness is absent in many individuals with significant sleep-disordered breathing. Comorbid conditions, including respiratory disease, sleep restriction, insomnia, and nocturnal leg complaints, are important risk factors for sleepiness in individuals with moderate to severe sleep-disordered breathing.
Keywords: Aged; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Oxygen; Polysomnography; Prevalence; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Arousal Disorders; Sleep Stages; Surveys and Questionnaires

Survival following dementia onset: Alzheimer's disease and vascular dementia. - Fitzpatrick, Annette L; Kuller, Lewis H; Lopez, Oscar L; Kawas, Claudia H; Jagust, William (J Neurol Sci, 2005)
Survival following the onset of dementia has been reported to vary from 3 to over 9 years. We examined mortality in 3602 participants of the Cardiovascular Health (CHS) Cognition Study in four US communities evaluated for dementia incidence between 1992 and 1999 and followed for 6.5 years. By June 2000, 33 of 62 (53.2%) participants who developed vascular dementia (VaD) had died compared to 79 of 245 (32.2%) with Alzheimer's disease (AD), 66 of 151 (43.7%) with both AD and VaD, and 429 of 2318 (18.5%) with normal cognition. Using Cox proportional hazards regression with a time-dependent covariate for dementia status adjusted for age, gender and race, individuals with VaD were more than four times as likely to die during follow-up than those with normal cognition (HR: 4.4, 95% CI: 3.1-6.3). The hazard ratios were 2.1 (95% CI: 1.6-2.7) for AD and 2.5 (95% CI: 1.9-3.3) for both types. Adjusted accelerated life models estimated median survival from dementia onset to death as 3.9 years for those with VaD, 7.1 years for AD, 5.4 years for mixed dementia, and 11.0 years for matched controls with normal cognition. While persons with VaD died primarily from cerebrovascular disease, those with AD/mixed dementia died more frequently from dementia/failure to thrive.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Capillaries; Cerebral Amyloid Angiopathy; Cerebrovascular Circulation; Cerebrovascular Disorders; Female; Frontal Lobe; Humans; Male; Middle Aged; Prospective Studies

Association of nocturnal arrhythmias with sleep-disordered breathing: The Sleep Heart Health Study. - Mehra, Reena; Benjamin, Emelia J; Shahar, Eyal; Gottlieb, Daniel J; Nawabit, Rawan; Kirchner, H Lester; Sahadevan, Jayakumar; Redline, Susan (Am J Respir Crit Care Med, 2006)
RATIONALE: Sleep-disordered breathing recurrent intermittent hypoxia and sympathetic nervous system activity surges provide the milieu for cardiac arrhythmia development. OBJECTIVE: We postulate that the prevalence of nocturnal cardiac arrhythmias is higher among subjects with than without sleep-disordered breathing. METHODS: The prevalence of arrhythmias was compared in two samples of participants from the Sleep Heart Health Study frequency-matched on age, sex, race/ethnicity, and body mass index: (1) 228 subjects with sleep-disordered breathing (respiratory disturbance index>or=30) and (2) 338 subjects without sleep-disordered breathing (respiratory disturbance index<5). RESULTS: Atrial fibrillation, nonsustained ventricular tachycardia, and complex ventricular ectopy (nonsustained ventricular tachycardia or bigeminy or trigeminy or quadrigeminy) were more common in subjects with sleep-disordered breathing compared with those without sleep-disordered breathing: 4.8 versus 0.9% (p=0.003) for atrial fibrillation; 5.3 versus 1.2% (p=0.004) for nonsustained ventricular tachycardia; 25.0 versus 14.5% (p=0.002) for complex ventricular ectopy. Compared with those without sleep-disordered breathing and adjusting for age, sex, body mass index, and prevalent coronary heart disease, individuals with sleep-disordered breathing had four times the odds of atrial fibrillation (odds ratio [OR], 4.02; 95% confidence interval [CI], 1.03-15.74), three times the odds of nonsustained ventricular tachycardia (OR, 3.40; 95% CI, 1.03-11.20), and almost twice the odds of complex ventricular ectopy (OR, 1.74; 95% CI, 1.11-2.74). A significant relation was also observed between sleep-disordered breathing and ventricular ectopic beats/h (p<0.0003) considered as a continuous outcome. CONCLUSIONS: Individuals with severe sleep-disordered breathing have two- to fourfold higher odds of complex arrhythmias than those without sleep-disordered breathing even after adjustment for potential confounders.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Circadian Rhythm; Electrocardiography; Female; Follow-Up Studies; Humans; Male; Middle Aged; Odds Ratio; Polysomnography; Prevalence; Retrospective Studies; Risk Factors; Severity of Illness Index; Sleep; Sleep Apnea, Obstructive

The association of race with frailty: the cardiovascular health study. - Hirsch, Calvin; Anderson, Melissa L; Newman, Anne; Kop, Willem; Jackson, Sharon; Gottdiener, John; Tracy, Russell; Fried, Linda P (Ann Epidemiol, 2006)
PURPOSE: Frailty, which has been conceptualized as a state of decreased physiologic reserve contributing to functional decline, has a prevalence among older African Americans that is twice that in older whites. This study assesses the independent contribution of race to frailty. METHODS: We evaluated 786 African-American and 4491 white participants of the Cardiovascular Health Study (CHS). Frailty is defined as meeting three or more of five criteria derived from CHS measures: lowest quintile for grip strength, self-reported exhaustion, unintentional weight loss of 10 lbs or greater in 1 year, slowest quintile for gait speed, and lowest quintile for physical activity. Controlling for age, sex, comorbidity, socioeconomic factors, and race, multinomial logistic regression estimated the odds ratio (OR) of prefrail (one or two criteria) to not frail and frail to not frail. RESULTS: Among African Americans, 8.7% of men and 15.0% of women were frail compared with 4.6% and 6.8% of white men and women, respectively. In adjusted models, nonobese African Americans had a fourfold greater odds of frailty compared with whites. The increased OR of frailty associated with African-American race was less pronounced among those who were obese or disabled. CONCLUSION: African-American race is associated independently with frailty.
Keywords: African Americans; Aged; Asthenia; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Frail Elderly; Health Status; Humans; Male; Middle Aged; Motor Activity; Odds Ratio; United States; Weight Loss

Association of usual sleep duration with hypertension: the Sleep Heart Health Study. - Gottlieb, Daniel J; Redline, Susan; Nieto, F Javier; Baldwin, Carol M; Newman, Anne B; Resnick, Helaine E; Punjabi, Naresh M (Sleep, 2006)
STUDY OBJECTIVES: Limited experimental data suggest that sleep restriction acutely elevates blood pressure; however, little is known about the relationship between usual sleep duration and hypertension. This study assesses the relationship between usual sleep duration and hypertension in a community-based cohort. DESIGN: Cross-sectional observational study. SETTING: The Sleep Heart Health Study, a community-based prospective study of the cardiovascular consequences of sleep-disordered breathing. PARTICIPANTS: Two thousand eight hundred thirteen men and 3097 women, aged 40 to 100 years. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: Usual weekday and weekend sleep durations were obtained by questionnaire, and their weighted average were categorized as less than 6, 6 to less than 7, 7 to less than 8, 8 to less than 9, and 9 or more hours per night. Hypertension was defined as a systolic blood pressure of 140 mm Hg or greater, a diastolic blood pressure of 90 mm Hg or greater, or use of medication to treat hypertension. The relationship between sleep duration and hypertension was examined using categorical logistic regression with adjustment for age, sex, race, apnea-hypopnea index, and body mass index. Compared to subjects sleeping 7 to less than 8 hours per night, those sleeping less than 6 and between 6 and 7 hours per night had adjusted odds ratios for hypertension of 1.66 (95% confidence interval 1.35-2.04) and 1.19 (1.02-1.39), respectively, whereas those sleeping between 8 and 9 and 9 or more hours per night had adjusted odds ratios for hypertension of 1.19 (1.04-1.37) and 1.30 (1.04-1.62), respectively (p < .0001 for association of sleep duration with hypertension). These associations persisted when analyses were further adjusted for caffeine and alcohol consumption, current smoking, insomnia symptoms, depression symptoms, sleep efficiency, and prevalent diabetes mellitus or cardiovascular disease. CONCLUSIONS: Usual sleep duration above or below the median of 7 to less than 8 hours per night is associated with an increased prevalence of hypertension, particularly at the extreme of less than 6 hours per night.
Keywords: Adult; Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Health Surveys; Humans; Hypertension; Male; Middle Aged; Odds Ratio; Prospective Studies; Sleep; Sleep Apnea, Obstructive; Sleep Deprivation; Statistics as Topic

Cigarette smoking and nocturnal sleep architecture. - Zhang, Lin; Samet, Jonathan; Caffo, Brian; Punjabi, Naresh M (Am J Epidemiol, 2006)
Cigarette smoking has been associated with a high prevalence of sleep-related complaints. However, its effects on sleep architecture have not been fully examined. The primary objective of this investigation was to assess the impact of cigarette smoking on sleep architecture. Polysomnography was used to characterize sleep architecture among 6,400 participants of the Sleep Heart Health Study (United States, 1994-1999). Sleep parameters included total sleep time, latency to sleep onset, sleep efficiency, and percentage of time in each sleep stage. The study sample consisted of 2,916 never smokers, 2,705 former smokers, and 779 current smokers. Compared with never smokers, current smokers had a longer initial sleep latency (5.4 minutes, 95% confidence interval (CI): 2.9, 7.9) and less total sleep time (14.0 minutes, 95% CI: 6.4, 21.7). Furthermore, relative to never smokers, current smokers also had more stage 1 sleep (relative proportion = 1.24, 95% CI: 1.14, 1.33) and less slow wave sleep (relative proportion = 0.86, 95% CI: 0.78, 0.95). Finally, no differences in sleep architecture were noted between former and never smokers. The results of this study show that cigarette smoking is independently associated with disturbances in sleep architecture, including a longer latency to sleep onset and a shift toward lighter stages of sleep. Nicotine in cigarette smoke and acute withdrawal from it may contribute to disturbances in sleep architecture.
Keywords: Aged; Arousal; Chi-Square Distribution; Female; Humans; Male; Middle Aged; Polysomnography; Prevalence; Regression Analysis; Risk Factors; Sleep Stages; Sleep Wake Disorders; Smoking; United States

Lipoprotein subclass and particle size differences in Afro-Caribbeans, African Americans, and white Americans: associations with hepatic lipase gene variation. - Miljkovic-Gacic, Iva; Bunker, Clareann H; Ferrell, Robert E; Kammerer, Candace M; Evans, Rhobert W; Patrick, Alan L; Kuller, Lewis H (Metabolism, 2006)
Despite a higher prevalence of coronary heart disease risk factors, men of African origin have less coronary atherosclerosis, as measured by coronary calcification, than whites. In part, this is thought to be because of the less atherogenic lipoprotein profile observed in men of African origin, characterized by lower triglycerides and higher high-density lipoprotein (HDL) cholesterol. We hypothesized that the -514C>T polymorphism in the hepatic lipase gene (LIPC) plays a significant role in determining a less atherogenic lipoprotein profile observed in men of African origin. Previously conducted studies of the LIPC -514C>T polymorphism in African Americans may have been confounded by a higher level of European admixture; in addition, the results from these studies do not necessarily apply to other African populations because gene-environment interactions may differ. Thus, we compared nuclear magnetic resonance spectroscopy-measured lipoprotein subclass patterns and LIPC -514C>T genotypes in population-based samples of older white American (n = 532) and African American (n = 97) men from the Cardiovascular Health Study to those among older, less admixed, Afro-Caribbean men (n = 205) from the Tobago Health Study. Men of African origin had a more favorable lipoprotein profile than whites. In addition, levels of low-density lipoprotein cholesterol, total cholesterol, and triglyceride, and large and small very low-density lipoprotein, small low-density lipoprotein, as well as very low-density lipoprotein particle size, were remarkably lower in Afro-Caribbean men than in either African American or white men. The frequency of the LIPC -514T allele was much higher in Afro-Caribbeans (0.57) and in African Americans (0.49) than in whites (0.20). The -514T allele in both populations of African origin, but not in whites, was associated with elevated large HDL and greater HDL size. Our findings indicate that the higher frequency of the LIPC -514T allele found in men of African origin living in different environments significantly contributes to the more favorable distribution of HDL subclasses compared with whites.
Keywords: Adult; African Americans; Age Factors; Aged; Alleles; Body Mass Index; Cardiovascular Diseases; Caribbean Region; Cohort Studies; DNA; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Humans; Lipase; Lipoproteins; Lipoproteins, HDL; Lipoproteins, LDL; Liver; Longitudinal Studies; Male; Middle Aged; Particle Size; Trinidad and Tobago; United States

Obstructive sleep apnea and plasma natriuretic peptide levels in a community-based sample. - Patwardhan, Anjali A; Larson, Martin G; Levy, Daniel; Benjamin, Emelia J; Leip, Eric P; Keyes, Michelle J; Wang, Thomas J; Gottlieb, Daniel J; Vasan, Ramachandran S (Sleep, 2006)
STUDY OBJECTIVES: We hypothesized that alterations in cardiac hemodynamics associated with obstructive sleep apnea-hypopnea (OSAH) would be reflected in higher natriuretic peptide levels. We examined the association of OSAH with natriuretic peptides in a community-based sample. DESIGN: Cross-sectional, retrospective, observational study. SETTING: Framingham Heart Study Offspring Cohort and Sleep Heart Health Study. PARTICIPANTS: Community-based sample of 623 individuals. MEASUREMENTS: Full-montage home polysomnography was used to determine apnea-hypopnea index (AHI) and percentage of time with an oxyhemoglobin saturation < 90% (PctLt90). Sensitive immunoradiometric assays were used to measure plasma B-type (BNP) and N-terminal pro-atrial natriuretic peptide (NT-ANP). Multivariable regression was used to examine the relations between natriuretic peptides and indicators of OSAH, adjusting for age, sex, body mass index, and clinical covariates. RESULTS: No statistically significant relations between OSAH indices and BNP were observed in the multivariable model. Compared with an AHI < 5, relative levels of 1.20, 0.88, and 0.91 were observed forAHI categories 5-15, 15-30, >30 events per hour, respectively. For NT-ANP, no significant relations were seen with AHI in the multivariable model (relative levels of 0.98, 0.91, and 0.90). An inverse association was observed between NT-ANP and PctLt90 in age- and sex-adjusted models (relative levels of 0.93, 0.87, and 0.80), although this association became statistically nonsignificant after adjusting for body mass index. CONCLUSION: Lack of association of natriuretic peptides with OSAH indices suggests that undiagnosed OSAH may not be associated with major alterations in left ventricular function, as reflected in morning natriuretic peptide levels.
Keywords: Atrial Fibrillation; Body Mass Index; Cohort Studies; Female; Humans; Hypertension; Male; Middle Aged; Myocardial Infarction; Natriuretic Peptides; Obesity; Polysomnography; Prevalence; Residence Characteristics; Severity of Illness Index; Sleep Apnea, Obstructive

Obstructive sleep apnea-hypopnea and neurocognitive functioning in the Sleep Heart Health Study. - Quan, Stuart F; Wright, Ron; Baldwin, Carol M; Kaemingk, Kristine L; Goodwin, James L; Kuo, Tracy F; Kaszniak, Alfred; Boland, Lori L; Caccappolo, Elise; Bootzin, Richard R (Sleep Med, 2006)
BACKGROUND AND PURPOSE: Obstructive sleep apnea-hypopnea (OSAH) is associated with sleep fragmentation and nocturnal hypoxemia. In clinical samples, patients with OSAH frequently are found to have deficits in neuropsychological function. However, the nature and severity of these abnormalities in non-clinical populations is less well defined. PATIENTS AND METHODS: One hundred and forty-one participants from the Tucson, AZ and New York, NY field centers of the Sleep Heart Health Study completed a battery of neuropsychological tests for 9-40 months (mean=24 months, SD=7 months) after an unattended home polysomnogram. Sixty-seven participants had OSAH (AHI>10) and 74 did not have OSAH (control (CTL), apnea-hypopnea index (AHI)<5). In addition to the individual tests, composite variables representing attention, executive function, MotorSpeed and processing speed were constructed from the neuropsychological test battery. RESULTS: There were no significant differences in any individual neuropsychological test or composite variable between the OSAH and CTL groups. However, when time spent with O(2) saturations less than 85% was dichotomized into those participants in the top quartile of the distribution and those in the lower three quartiles, motor speed was significantly impaired in those who were more hypoxemic. In addition, poorer motor speed (model adjusted R(2)=0.242, P<0.001) and processing speed performance (model adjusted R(2)=0.122, P<0.001) were associated with more severe oxygen desaturation even after controlling for degree of daytime sleepiness, age, gender and educational level. CONCLUSIONS: Mild to moderate OSAH has little impact on the selected measures of attention, executive function, motor speed and processing speed. However, hypoxemia adversely affects both motor and processing speed. These results suggest that in middle-aged to elderly adults the neuropsychological effects of clinically unrecognized mild to moderate OSAH are neither global nor large.
Keywords: Brain; Cognition Disorders; Continuous Positive Airway Pressure; Demography; Disorders of Excessive Somnolence; Electromyography; Electrooculography; Female; Health Status; Humans; Hypoxia; Male; Middle Aged; Neuropsychological Tests; Oxygen; Polysomnography; Severity of Illness Index; Sleep Apnea, Obstructive; Surveys and Questionnaires

Sleep apnea in patients on conventional thrice-weekly hemodialysis: comparison with matched controls from the Sleep Heart Health Study. - Unruh, Mark L; Sanders, Mark H; Redline, Susan; Piraino, Beth M; Umans, Jason G; Hammond, Terese C; Sharief, Imran; Punjabi, Naresh M; Newman, Anne B (J Am Soc Nephrol, 2006)
Sleep-disordered breathing (SDB) has been noted commonly in hemodialysis (HD) patients, but it is not known whether this is related directly to the treatment of kidney failure with HD or to the higher prevalence of obesity and older age. Forty-six HD patients were compared with 137 participants from the Sleep Heart Health Study (SHHS) who were matched for age, gender, body mass index (BMI), and race. Home unattended polysomnography was performed and scored using similar protocols. The study sample was 62.7 +/- 10.1 yr, was predominantly male (72%) and white (63%), and had an average BMI of 28 +/- 5.3 kg/m(2). The HD sample had a higher systolic BP (137 versus 121 mmHg; P < 0.01) and a higher prevalence of diabetes (33 versus 9%; P < 0.01) and cardiovascular disease (33 versus 13%; P < 0.01) compared with the SHHS sample. The HD group had significantly less sleep time (320 versus 379 min; P < 0.0001) but similar sleep efficiency. HD patients had a higher frequency of arousals per hour (25.1 versus 17.1; P < 0.0001) and apnea-hypopneas per hour (27.2 versus 15.2; P < 0.0001) and greater percentage of the total sleep time below an oxygen saturation of 90% (7.2 versus 1.8; P < 0.0001). HD patients were more likely to have severe SDB (>30 respiratory events per hour) compared with the SHHS sample (odds ratio 4.07; 95% confidence interval 1.83 to 9.07). There was a strong association of HD with severe SDB and nocturnal hypoxemia independent of age, BMI, and the higher prevalence of chronic disease. The potential mechanisms for the higher likelihood of SDB in the HD population must be identified to provide specific prevention and therapy.
Keywords: Blood Pressure; Body Mass Index; Cardiovascular Diseases; Case-Control Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Kidney Failure, Chronic; Male; Middle Aged; Prevalence; Renal Dialysis; Severity of Illness Index; Sleep Apnea Syndromes

ABO blood group, other risk factors and incidence of venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Ohira, T; Cushman, M; Tsai, M Y; Zhang, Y; Heckbert, S R; Zakai, N A; Rosamond, W D; Folsom, A R (J Thromb Haemost, 2007)
BACKGROUND: Numerous case-control studies have reported higher prevalence of non-O blood type among venous thromboembolism (VTE) patients than controls, but potential mechanisms or effect modifiers for the association are not fully established. PATIENTS/METHODS: Using a nested case-control design combining the Atherosclerosis Risk in Communities and the Cardiovascular Health Study cohort, ABO blood type and other VTE risk factors were measured on pre-event blood samples of 492 participants who subsequently developed VTE and 1008 participants who remained free of VTE. RESULTS: A total of 64.4% of cases and 52.5% of controls had non-O blood type. Among controls, mean values of factor VIIIc (FVIIIc) and von Willebrand factor among the non-O blood type group were higher than among the O group. Compared with O blood type, the age-adjusted odds ratio (OR) of VTE for non-O blood type was 1.64 (95% CI, 1.32-2.05) and was similar for the two parent studies and race groups. Further adjustment for sex, race, body mass index, diabetes mellitus and FVIIIc reduced the OR: 1.31 (95% CI, 1.02-1.68). Factor V Leiden (FV Leiden) appeared to modify the non-O blood type association with VTE in a supra-additive fashion, with an age-, sex- and race-adjusted OR of 6.77 (95% CI, 3.65-12.6) for having both risk factors. CONCLUSIONS: Non-O blood type was independently associated with risk of VTE, and added to the risk associated with FV Leiden.
Keywords: ABO Blood-Group System; Aged; Case-Control Studies; Diabetes Complications; Factor V; Factor VIII; Female; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Thromboembolism; Venous Thrombosis; von Willebrand Factor

Alcohol consumption and type 2 diabetes among older adults: the Cardiovascular Health Study. - Djoussé, Luc; Biggs, Mary L; Mukamal, Kenneth J; Siscovick, David S (Obesity (Silver Spring), 2007)
OBJECTIVE: The objective was to examine the role of total and beverage-specific alcohol consumption on the incidence of type 2 diabetes mellitus (DM) among elderly men and women. RESEARCH METHODS AND PROCEDURES: We studied prospectively 4655 participants of the Cardiovascular Health Study who were free of DM at baseline. Alcohol consumption was obtained at baseline and during follow-up examinations. DM was defined using fasting glucose and/or use of hypoglycemic medications. We used Cox proportional hazard models to estimate adjusted relative risks of diabetes across alcohol categories. RESULTS: During a mean follow-up of 6.3 years, 234 incident cases of DM were documented. Compared with never drinkers, hazard ratios [95% confidence interval (CI)] for DM were 0.7 (0.3 to 1.4), 0.5 (0.3 to 0.9), 0.6 (0.4 to 1.1), and 0.8 (0.4 to 1.3) for former drinkers and current drinkers of <1, 1 to 6, and 7+ drinks per week, respectively, for men after adjustment for age, BMI, education, and smoking. Corresponding values for women were 1.2 (0.6 to 2.3), 0.7 (0.4 to 1.1), 0.6 (0.3 to 1.1), and 0.4 (0.2 to 1.0), respectively. A reduced risk of DM was observed with all types of beverage consumed. Similar findings were observed when we repeated the above analyses using simple or weighted cumulative alcohol update and covariates over time. DISCUSSION: Light to moderate alcohol consumption was associated with a lower incidence of DM among elderly people, irrespective of the type of beverage consumed.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Diabetes Mellitus, Type 2; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Medicare; Middle Aged; Risk; Smoking; Temperance; United States

The association of alpha-fibrinogen Thr312Ala polymorphism and venous thromboembolism in the LITE study. - Rasmussen-Torvik, Laura J; Cushman, Mary; Tsai, Michael Y; Zhang, Yan; Heckbert, Susan R; Rosamond, Wayne D; Folsom, Aaron R (Thromb Res, 2007)
INTRODUCTION: The alpha-fibrinogen Thr312Ala variant has been shown to influence clot structure through increased factor XIII cross-linking and formation of thicker fibrin fibers. However, the effect of this common variant on risk of venous thromboembolism (VTE) is unclear. This paper reports the association between the Thr312Ala variant and VTE in the LITE study. MATERIALS AND METHODS: 506 cases and 1014 controls frequency matched on age, sex, race, and study were drawn from two prospective studies and included in the analysis. Logistic regression was used to examine the association between Thr312Ala and VTE. RESULTS: In a logistic regression model minimally adjusted for the matching variables, the Thr312Ala TA and AA genotypes were associated with a significantly higher risk of VTE than the TT genotype (TA OR and 95% confidence interval 1.27 [1.01-1.60], AA OR 1.49 [1.00-2.22]). Associations were similar in analyses of PE and DVT considered separately and across racial and study subgroups. The association between alpha-fibrinogen Thr312Ala and VTE was modified by both BMI and the FXIII Val34Leu variant; the combination of elevated BMI or FXIII Val34Leu with alpha-fibrinogen Thr312Ala conveyed lower odds of VTE than would be expected by an additive or multiplicative model of individual risk factors. CONCLUSIONS: These results suggest that alpha-fibrinogen Thr312Ala is involved in the pathogenesis of VTE and that its action may be modified by other VTE risk factors.
Keywords: African Continental Ancestry Group; Aged; Case-Control Studies; European Continental Ancestry Group; Female; Fibrinogen; Genotype; Humans; Logistic Models; Male; Middle Aged; Mutation, Missense; Polymorphism, Genetic; Venous Thromboembolism

Association of physical activity with sleep-disordered breathing. - Quan, Stuart F; O'Connor, George T; Quan, Jason S; Redline, Susan; Resnick, Helaine E; Shahar, Eyal; Siscovick, David; Sherrill, Duane L (Sleep Breath, 2007)
This study was performed to determine whether there is a protective association between participation in vigorous or vigorous/moderately vigorous physical activity and the prevalence of sleep-disordered breathing (SDB). Polysomnographic and questionnaire data from the baseline examination of 4,275 participants in the Sleep Heart Health Study (SHHS) were analyzed in relation to information on amount of physical activity and other potentially relevant factors collected from five SHHS parent cohorts (Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, Framingham Heart Study, Strong Heart Study, and Tucson Epidemiologic Study of Airways Obstructive Diseases). Logistic regression models were fitted to determine if amount and strenuousness of physical activity was associated with the presence of SDB. At least 3 h per week of vigorous physical activity reduced the odds of SDB, defined as a respiratory disturbance index (RDI) of at least 15 apneas/hypopneas per hour (Adjusted OR, 0.68; 95%CI, 0.51-0.91). A qualitatively similar but slightly weaker association was observed when SDB was defined as a RDI > or = 10 per hour (Adjusted OR, 0.81; 95%CI, 0.64-1.02). These findings remained after adjustment for sleepiness and restricting analyses to participants with good health. Three or more hours of moderately vigorous or vigorous physical activity also appeared to confer some protection against SDB, but these associations were weaker. Gender- and obesity-stratified analyses suggested that the protective association between physical activity and SDB occurred primarily in men and those who were obese. A program of regular vigorous physical activity of at least 3 h per week may be a useful adjunctive treatment modality for SDB, but this association needs confirmation with a prospective clinical trial.
Keywords: Adult; Cardiac Rehabilitation; Cardiovascular Diseases; Cohort Studies; Exercise; Female; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Polysomnography; Pulmonary Disease, Chronic Obstructive; Pulmonary Ventilation; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive; Sleep Stages; Weight Loss

Ethnic-specific prevalence of peripheral arterial disease in the United States. - Allison, Matthew A; Ho, Elena; Denenberg, Julie O; Langer, Robert D; Newman, Anne B; Fabsitz, Richard R; Criqui, Michael H (Am J Prev Med, 2007)
BACKGROUND: Individuals diagnosed with peripheral arterial disease (PAD) are at increased risk for future functional limitations as well as cardiovascular morbidity and mortality. The aim of this study was to estimate the age-, gender-, and ethnic-specific burden of PAD in the United States for the year 2000. METHODS: Data were collected from seven community-based studies that assessed subjects for the presence of PAD using the ankle-brachial index (ABI). Using standardized weighting criteria, age-, gender-, and ethnic-specific prevalence rates were computed and then multiplied by the corresponding 2000 Census population totals to estimate the burden of PAD in the United States for that year. Evidence-based adjustments for studies which did not consider possible subclavian stenosis, prior revascularization for PAD, or both were employed. RESULTS: In 2000, it is conservatively estimated that at least 6.8 million (5.8%) individuals aged 40 years or older had PAD based on an ABI of less than 0.9 or previous revascularization for PAD, and that that there are an additional 1.7 million Americans with PAD but "normal" ABIs. Including this group gives a total of 8.5 million (7.2%) individuals with PAD. CONCLUSIONS: Roughly one in 16 individuals residing in the United States in 2000 who were aged 40 years and older had PAD. Clinicians are encouraged to screen for the presence of PAD using the ABI.
Keywords: Adult; Aged; Aged, 80 and over; Databases as Topic; Female; Humans; Male; Middle Aged; Peripheral Vascular Diseases; United States

Genome-wide association of sleep and circadian phenotypes. - Gottlieb, Daniel J; O'Connor, George T; Wilk, Jemma B (BMC Med Genet, 2007)
BACKGROUND: Numerous studies suggest genetic influences on sleepiness and circadian rhythms. The Sleep Heart Health Study collected questionnaire data on sleep habits and sleepiness from 2848 Framingham Heart Study Offspring Cohort participants. More than 700 participants were genotyped using the Affymetrix 100K SNP GeneChip, providing a unique opportunity to assess genetic linkage and association of these traits. METHODS: Sleepiness (defined as the Epworth Sleepiness Scale score), usual bedtime and usual sleep duration were assessed by self-completion questionnaire. Standardized residual measures adjusted for age, sex and BMI were analyzed. Multipoint variance components linkage analysis was performed. Association of SNPs to sleep phenotypes was analyzed with both population-based and family-based association tests, with analysis limited to 70,987 autosomal SNPs with minor allele frequency > or =10%, call rate > or =80%, and no significant deviation from Hardy-Weinberg equilibrium (p > or = 0.001). RESULTS: Heritability of sleepiness was 0.29, bedtime 0.22, and sleep duration 0.17. Both genotype and sleep phenotype data were available for 749 subjects. Linkage analysis revealed five linkage peaks of LOD >2: four to usual bedtime, one to sleep duration. These peaks include several candidate sleep-related genes, including CSNK2A2, encoding a known component of the circadian molecular clock, and PROK2, encoding a putative transmitter of the behavioral circadian rhythm from the suprachiasmatic nucleus. Association tests identified an association of usual bedtime with a non-synonymous coding SNP in NPSR1 that has been shown to encode a gain of function mutation of the neuropeptide S receptor, whose endogenous ligand is a potent promoter of wakefulness. Each copy of the minor allele of this SNP was associated with a 15 minute later mean bedtime. The lowest p value was for association of sleepiness with a SNP located in an intron of PDE4D, which encodes a cAMP-specific phosphodiesterase widely expressed in human brain. Full association results are posted at http://www.ncbi.nlm.nih.gov/projects/gap/cgi-bin/study.cgi?id=phs000007 webcite. CONCLUSION: This analysis confirms prior reports of significant heritability of sleepiness, usual bedtime, and usual sleep duration. Several genetic loci with suggestive linkage to these traits are identified, including linkage peaks containing circadian clock-related genes. Association tests identify NPSR1 and PDE4D as possible mediators of bedtime and sleepiness.
Keywords: Adult; Alleles; Cardiovascular Diseases; Circadian Rhythm; Cohort Studies; Female; Gene Frequency; Genetic Linkage; Genome, Human; Genotype; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Sleep; Surveys and Questionnaires

Inflammation biomarkers and near-term death in older men. - Jenny, Nancy Swords; Yanez, N David; Psaty, Bruce M; Kuller, Lewis H; Hirsch, Calvin H; Tracy, Russell P (Am J Epidemiol, 2007)
Associations of C-reactive protein (CRP) and fibrinogen with death may weaken over time. Combining both markers may improve prediction of death in older adults. In 5,828 Cardiovascular Health Study participants (United States, 1989-2000), 383 deaths (183 cardiovascular disease (CVD)) in years 1-3 (early) and 914 deaths (396 CVD) in years 4-8 (late) occurred. For men, when comparing highest to lowest quartiles, hazard ratios for early death were 4.1 (95% confidence interval (CI): 2.7, 6.3) for CRP and 4.1 (95% CI: 2.7, 6.4) for fibrinogen in models adjusted for CVD risk. For early CVD death, hazard ratios were 4.3 (95% CI: 2.2, 8.4) and 3.4 (95% CI: 1.8, 6.3), respectively. When comparing men in the highest quartiles of both biomarkers with those in the lowest, hazard ratios were 9.6 (95% CI: 4.3, 21.1) for early death and 13.5 (95% CI: 3.2, 56.5) for early CVD death. Associations were weaker for late deaths. For women, CRP (hazard ratio = 2.3, 95% CI: 1.4, 3.9), but not fibrinogen (hazard ratio = 1.3, 95% CI: 0.8, 2.2), was associated with early death. Results were similar for CVD death. Neither was associated with late deaths. CRP and fibrinogen were more strongly associated with death in older men than women and more strongly associated with early than late death. Combining both markers may identify older men at greatest risk of near-term death.
Keywords: Age Distribution; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Diabetes Complications; Epidemiologic Studies; Female; Fibrinogen; Follow-Up Studies; Humans; Hypercholesterolemia; Hypertension; Inflammation; Male; Middle Aged; Obesity; Population Surveillance; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Factors; Sex Distribution; Smoking; Time Factors; United States

Relationship between reported and measured sleep times: the sleep heart health study (SHHS). - Silva, Graciela E; Goodwin, James L; Sherrill, Duane L; Arnold, Jean L; Bootzin, Richard R; Smith, Terry; Walsleben, Joyce A; Baldwin, Carol M; Quan, Stuart F (J Clin Sleep Med, 2007)
STUDY OBJECTIVE: Subjective and objective assessments of sleep may be discrepant due to sleep misperception and measurement effects, the latter of which may change the quality and quantity of a person's usual sleep. This study compared sleep times from polysomnography (PSG) with self-reports of habitual sleep and sleep estimated on the morning after a PSG in adults. DESIGN: Total sleep time and sleep onset latency obtained from unattended home PSGs were compared to sleep times obtained from a questionnaire completed before the PSG and a Morning Survey completed the morning after the PSG. PARTICIPANTS: A total of 2,113 subjects who were > or = 40 years of age were included in this analysis. MEASURES AND RESULTS: Subjects were 53% female, 75% Caucasian, and 38% obese. The mean habitual sleep time (HABTST), morning estimated sleep time (AMTST), and PSG total sleep times (PSGTST) were 422 min, 379 min, and 363 min, respectively. The mean habitual sleep onset latency, morning estimated sleep onset latency, and PSG sleep onset latency were 17.0 min, 21.8 min, and 16.9 min, respectively. Models adjusting for related demographic factors showed that HABTST and AMTST differ significantly from PSGTST by 61 and 18 minutes, respectively. Obese and higher educated people reported less sleep time than their counterparts. Similarly, small but significant differences were seen for sleep latency. CONCLUSIONS: In a community population, self-reported total sleep times and sleep latencies are overestimated even on the morning following overnight PSG.
Keywords: Adult; Attitude to Health; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Psychometrics; Sleep Initiation and Maintenance Disorders; Sleep Stages; Surveys and Questionnaires; Time Factors; Wakefulness

Risk factors for intracerebral hemorrhage in a pooled prospective study. - Sturgeon, Jared D; Folsom, Aaron R; Longstreth, W T; Shahar, Eyal; Rosamond, Wayne D; Cushman, Mary (Stroke, 2007)
BACKGROUND AND PURPOSE: Few prospective studies have reported risk factors for intracerebral hemorrhage (ICH), and results are inconsistent. We studied risk factors for ICH in a pooled cohort of the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS). METHODS: The ARIC cohort was recruited in 1987 to 1989 and involves 15 792 men and women, aged 45 to 64 years at baseline, sampled from 4 US communities. The CHS cohort was recruited in 1989 to 1993 and involves 5888 men and women, aged 65 or over at baseline, sampled from 4 US communities. Baseline measurements included many potential vascular risk factors. The cohorts were followed for incident stroke events. RESULTS: Over 263 489 person-years of follow-up, 135 incident ICH events occurred. In a multivariable model, age, African-American ethnicity (versus Whites), and hypertension were positively associated with incident ICH, whereas low-density lipoprotein cholesterol and triglycerides were inversely related to incident ICH. Participants with systolic blood pressure >or=160 mm Hg or diastolic blood pressure >/=110 mm Hg had 5.55 (95% CI 3.07 to 10.0) times the rate of ICH as nonhypertensives. Sex, smoking, alcohol intake, body mass index, waist-to-hip ratio, waist circumference, and diabetes were not related to ICH. CONCLUSIONS: In this pooled cohort the risk factors for ICH were older age, African-American ethnicity, hypertension, lower LDL-C, and lower triglycerides.
Keywords: African Americans; Age Distribution; Cerebral Hemorrhage; Cholesterol, LDL; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Male; Middle Aged; Multivariate Analysis; Predictive Value of Tests; Prevalence; Prospective Studies; Risk Factors; Stroke; Triglycerides

Age-specific prevalence and years of healthy life in a system with three health states. - Diehr, Paula; Yanez, David; Derleth, Ann; Newman, Anne B (Stat Med, 2008)
Consider a 3-state system with one absorbing state, such as Healthy, Sick, and Dead. Over time, the prevalence of the Healthy state will approach an 'equilibrium' value that is independent of the initial conditions. We derived this equilibrium prevalence (Prev:Equil) as a function of the local transition probabilities. We then used Prev:Equil to estimate the expected number of years spent in the healthy state over time. This estimate is similar to the one calculated by multi-state life table methods, and has the advantage of having an associated standard error. In longitudinal data for older adults, the standard error was accurate when a valid survival table was known from other sources, or when the available data set was sufficient to estimate survival accurately. Performance was better with fewer waves of data. If validated in other situations, these estimates of prevalence and years of healthy life (YHL) and their standard errors may be useful when the goal is to compare YHL for different populations.
Keywords: Age Factors; Biometry; Health Status; Humans; Life Tables; Longitudinal Studies; Middle Aged; Models, Statistical; Probability; Quality-Adjusted Life Years

Ankle brachial index combined with Framingham Risk Score to predict cardiovascular events and mortality: a meta-analysis. - Fowkes, F G R; Murray, G D; Butcher, I; Heald, C L; Lee, R J; Chambless, L E; Folsom, A R; Hirsch, A T; Dramaix, M; deBacker, G; Wautrecht, J-C; Kornitzer, M; et al. (JAMA, 2008)
CONTEXT: Prediction models to identify healthy individuals at high risk of cardiovascular disease have limited accuracy. A low ankle brachial index (ABI) is an indicator of atherosclerosis and has the potential to improve prediction. OBJECTIVE: To determine if the ABI provides information on the risk of cardiovascular events and mortality independently of the Framingham risk score (FRS) and can improve risk prediction. DATA SOURCES: Relevant studies were identified. A search of MEDLINE (1950 to February 2008) and EMBASE (1980 to February 2008) was conducted using common text words for the term ankle brachial index combined with text words and Medical Subject Headings to capture prospective cohort designs. Review of reference lists and conference proceedings, and correspondence with experts was conducted to identify additional published and unpublished studies. STUDY SELECTION: Studies were included if participants were derived from a general population, ABI was measured at baseline, and individuals were followed up to detect total and cardiovascular mortality. DATA EXTRACTION: Prespecified data on individuals in each selected study were extracted into a combined data set and an individual participant data meta-analysis was conducted on individuals who had no previous history of coronary heart disease. RESULTS: Sixteen population cohort studies fulfilling the inclusion criteria were included. During 480,325 person-years of follow-up of 24,955 men and 23,339 women, the risk of death by ABI had a reverse J-shaped distribution with a normal (low risk) ABI of 1.11 to 1.40. The 10-year cardiovascular mortality in men with a low ABI (< or = 0.90) was 18.7% (95% confidence interval [CI], 13.3%-24.1%) and with normal ABI (1.11-1.40) was 4.4% (95% CI, 3.2%-5.7%) (hazard ratio [HR], 4.2; 95% CI, 3.3-5.4). Corresponding mortalities in women were 12.6% (95% CI, 6.2%-19.0%) and 4.1% (95% CI, 2.2%-6.1%) (HR, 3.5; 95% CI, 2.4-5.1). The HRs remained elevated after adjusting for FRS (2.9 [95% CI, 2.3-3.7] for men vs 3.0 [95% CI, 2.0-4.4] for women). A low ABI (< or = 0.90) was associated with approximately twice the 10-year total mortality, cardiovascular mortality, and major coronary event rate compared with the overall rate in each FRS category. Inclusion of the ABI in cardiovascular risk stratification using the FRS would result in reclassification of the risk category and modification of treatment recommendations in approximately 19% of men and 36% of women. CONCLUSION: Measurement of the ABI may improve the accuracy of cardiovascular risk prediction beyond the FRS.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Ankle; Atherosclerosis; Blood Pressure; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Confidence Intervals; Female; Global Health; Humans; Male; Middle Aged; Odds Ratio; Predictive Value of Tests; Risk Assessment; Risk Factors; Severity of Illness Index

Association of restless legs syndrome and cardiovascular disease in the Sleep Heart Health Study. - Winkelman, John W; Shahar, Eyal; Sharief, Imran; Gottlieb, Daniel J (Neurology, 2008)
OBJECTIVE: We evaluated the cross-sectional association between restless legs syndrome (RLS) and prevalent cardiovascular disease (CVD) in a large community-based sample of middle-aged and elderly subjects. METHODS: This is a cross-sectional observational study of 1,559 men and 1,874 women (mean age of 67.9 years) who were enrolled in the Sleep Heart Health Study, a community-based study of the cardiovascular consequences of sleep-disordered breathing. RLS was defined by positive responses on a self-administered questionnaire to the four diagnostic criteria, with symptoms occurring at least five times per month and associated with at least moderate distress. Coronary artery disease (CAD) was determined by self-report of doctor-diagnosed angina, myocardial infarction, or coronary revascularization procedure. Total CVD included CAD or history of physician-diagnosed stroke or heart failure. The relation of RLS to prevalent CAD and CVD was examined by multivariable logistic regression models RESULTS: RLS was present in 6.8% of women (n = 128) and 3.3% of men (n = 51). After adjustment for age, sex, race, body mass index, diabetes mellitus, systolic blood pressure, antihypertensive medication use, total:high-density lipoprotein cholesterol ratio, and smoking history, the ORs for CAD were 2.05 (95% CI 1.38 to 3.04) and for CVD were 2.07 (1.43 to 3.00) for subjects with RLS compared to those without RLS. The associations of RLS with CAD and CVD were stronger in those with RLS symptoms at least 16 times per month and were stronger in those with severe than in those with moderately bothersome symptoms. CONCLUSIONS: Restless legs syndrome (RLS) is associated with prevalent coronary artery disease and cardiovascular disease. This association appears stronger in those with greater frequency or severity of RLS symptoms.
Keywords: Aged; Body Mass Index; Cardiovascular Diseases; Cross-Sectional Studies; Evaluation Studies as Topic; Female; Health Surveys; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Prevalence; Restless Legs Syndrome; Surveys and Questionnaires

Chronic kidney disease increases risk for venous thromboembolism. - Wattanakit, Keattiyoat; Cushman, Mary; Stehman-Breen, Catherine; Heckbert, Susan R; Folsom, Aaron R (J Am Soc Nephrol, 2008)
Chronic kidney disease (CKD) is associated with increased risk for cardiovascular disease morbidity and mortality, but its association with incident venous thromboembolism (VTE) in non-dialysis-dependent patients has not been evaluated in a community-based population. With the use of data from the Longitudinal Investigation of Thromboembolism Etiology (LITE) study, 19,073 middle-aged and elderly adults were categorized on the basis of estimated GFR, and cystatin C (available in 4734 participants) was divided into quintiles. During a mean follow-up time of 11.8 yr, 413 participants developed VTE. Compared with participants with normal kidney function, relative risk for VTE was 1.28 (95% confidence interval [CI] 1.02 to 1.59) for those with mildly decreased kidney function and 2.09 (95% CI 1.47 to 2.96) for those with stage 3/4 CKD, when adjusted for age, gender, race, and center. After additional adjustment for cardiovascular disease risk factors, an increased risk for VTE was still observed in participants with stage 3/4 CKD, with a multivariable adjusted relative risk of 1.71 (95% CI 1.18 to 2.49). There was no significant association between cystatin C and VTE. In conclusion, middle-aged and elderly patients with CKD (stages 3 through 4) are at increased risk for incident VTE, suggesting that VTE prophylaxis may be particularly important in this population.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Diabetic Nephropathies; Factor VIII; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney Failure, Chronic; Longitudinal Studies; Male; Middle Aged; Risk Factors; Thromboembolism; Venous Thrombosis

Common genetic variants associated with plasma fibrin D-dimer concentration in older European- and African-American adults. - Lange, L A; Reiner, A P; Carty, C L; Jenny, N S; Cushman, M; Lange, E M (J Thromb Haemost, 2008)
BACKGROUND AND OBJECTIVES: D-dimer is a hemostasis marker that reflects ongoing fibrin formation and degradation. There is significant inter-individual and inter-population variability in D-dimer concentration, but whether genetic factors underlie these differences is largely unknown. We hypothesized that common coagulation gene variants contribute to differences in circulating D-dimer concentration. METHODS: The setting was European-American (EA; n = 1858) and African-American (AA; n = 327) unrelated older adults from the Cardiovascular Health Study (CHS), in which we genotyped SNPs in 42 genes related to blood coagulation and fibrinolysis. RESULTS: Several fibrinogen gene polymorphisms, including the Thr312Ala Aalpha chain variant and the FGG-10034 C/T variant, were associated with approximately 20% higher plasma D-dimer levels in EA (false discovery rate < 5% for covariate-adjusted model). There was also some evidence that a Pro41Leu variant of the PLAU gene encoding urinary plasminogen activator and non-coding polymorphism of the plasminogen activator inhibitor type 1 gene (SERPINE1) were associated with higher plasma D-dimer in EA. There were no significant associations between the studied coagulation or fibrinolysis gene SNPs and plasma D-dimer levels in the smaller AA sample. However, each standard deviation increase in European ancestry assessed by ancestry-informative gene markers was associated with approximately 10% lower mean D-dimer levels in AA. CONCLUSIONS: Together, common coagulation/fibrinolysis gene SNPs explained only approximately 2% of the variance in plasma D-dimer levels in EA. These findings suggest that the association of D-dimer with risk of vascular outcomes may be mediated largely by environmental factors, other genes, and/or genetic interactions.
Keywords: Africa; African Americans; Aged; Aged, 80 and over; Blood Coagulation; Europe; European Continental Ancestry Group; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Fibrinolysis; Genotype; Humans; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; Prospective Studies; United States; Urokinase-Type Plasminogen Activator

Effect of sleep disordered breathing on the sleep of bed partners in the Sleep Heart Health Study. - Sharief, Imran; Silva, Graciela E; Goodwin, James L; Quan, Stuart F (Sleep, 2008)
OBJECTIVE: To study the sleep quality of bed partners of persons with sleep disordered breathing in a non-clinical population based sample in a home environment. DESIGN: Cross-sectional study in a community sample. METHODS: 110 pairs of subjects living in the same household from the Tucson, Minnesota, and Pittsburgh sites of the Sleep Heart Health Study (SHHS) were included if both partners had an in-home, unattended polysomnogram (PSG) performed as a part of SHHS exam cycle 2. Sleep disordered breathing (SDB) was considered present if the respiratory disturbance index (RDI) was > or =10 events/h and no SDB if RDI was <5 events/h. Pairs were classified according to their SDB status and assigned to one of 3 groups: 1) NoSDB-NoSDB (n = 46), 2) NoSDB-SDB (n = 42), and 3) SDB-SDB (n = 22). RESULTS: There were no differences between the NoSDB-NoSDB and the SDB-SDB partners in their demographic, PSG, or quality of life variables. However, within the NoSDB-SDB group, NoSDB in comparison to their SDB partners weighed less (mean BMI: 26 vs. 29 kg/m2, P < 0.0003), had decreased stage 2% (55 vs. 64, P < 0.0001), increased stage 3 and 4% (21 vs. 11, P <0.0005) and a lower arousal index (13.8 vs. 20 events/h, P < 0.0001). When comparing the NoSDB subjects from the NoSDB-SDB group to subjects in the NoSDB-NoSDB group and to subjects in the SDB-SDB group, significant differences were seen for RDI and BMI but not for any other parameter. CONCLUSION: In a non-clinical population based sample, the sleep quality of bed partners of SDB subjects without SDB is better than their SDB bed partner. However, their sleep quality was not different in comparison to the sleep of those without SDB who also had a bed partner without SDB.
Keywords: Aged; Arousal; Cohort Studies; Female; Humans; Male; Middle Aged; Polysomnography; Quality of Life; Sleep Apnea, Obstructive; Snoring; Spouses

Fasting glycemia in sleep disordered breathing: lowering the threshold on oxyhemoglobin desaturation. - Stamatakis, Katherine; Sanders, Mark H; Caffo, Brian; Resnick, Helaine E; Gottlieb, Dan J; Mehra, Reena; Punjabi, Naresh M (Sleep, 2008)
STUDY OBJECTIVES: Commonly used definitions of sleep-disordered breathing (SDB) are based on identifying discrete events of breathing abnormalities during sleep that are accompanied by an oxyhemoglobin desaturation (delta SaO2) of at least 4%. However, it is not known whether disordered breathing events with oxyhemoglobin desaturation less than 4% are associated with clinical sequelae such as abnormalities in fasting glycemia. DESIGN: Cross-sectional study. SUBJECTS AND SETTING: Participants from the Sleep Heart Health Study (SHHS) with a fasting glucose measurement made within a year of the baseline polysomnogram. MEASUREMENTS AND RESULTS: SDB severity was defined using the apnea-hypopnea index (AHI) and the hypopnea index (HI) by counting events with different levels of oxyhemoglobin desaturation (0.0%-1.9%, 2.0%-2.9%, 3.0%-3.9%, > or = 4.0%). Fasting glucose levels were used to classify individuals into normal (<100 mg/dL), impaired (100-125 mg/dL), and diabetic (> or = 126 mg/dL) groups. Ordinal logistic regression was used to determine the adjusted relative odds of an abnormal glucose value across quartiles of the hypopnea index, independent of factors such as age, body mass index, waist circumference, and usual sleep duration. The prevalence of impaired and diabetic fasting glucose in the analytical sample was 32.9% and 5.8%, respectively. The covariate-adjusted relative odds of impaired or diabetic fasting glucose in the highest versus the lowest AHI quartile was 1.35 (95% CI: 1.04-1.76) for events with a delta SaO2 > or = 4.0%, 1.72 (95% CI: 1.20-2.48) for events with a delta SaO2 between 3.0%-3.9%, 1.41 (95% CI: 1.07-1.86) for events with a delta SaO2 between 2.0%-2.9%, and 1.07 (95% CI: 0.84-1.37) for events with a delta SaO2 between 0.0%-1.9%. The corresponding odds ratios for the HI were 1.47 (95% CI: 1.13-1.92), 2.25 (95% CI: 1.59-3.19), 1.44 (95% CI: 1.09-1.90), and 1.15 (95% CI: 0.90-1.47), respectively. CONCLUSIONS: The results of this study indicate that SDB events accompanied by oxyhemoglobin desaturation of between 2% to 4% are associated with fasting hyperglycemia. These findings suggest that milder degrees of SDB may predispose to adverse metabolic outcomes.
Keywords: Aged; Blood Glucose; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Male; Middle Aged; Odds Ratio; Oxygen; Oxyhemoglobins; Polysomnography; Reference Values; Sleep Apnea, Obstructive

Hemostatic and inflammatory risk factors for intracerebral hemorrhage in a pooled cohort. - Sturgeon, Jared D; Folsom, Aaron R; Longstreth, W T; Shahar, Eyal; Rosamond, Wayne D; Cushman, Mary (Stroke, 2008)
BACKGROUND AND PURPOSE: The purpose of this study was to identify novel risk factors for intracerebral hemorrhagic stroke (ICH). METHODS: Risk factors were assessed at baseline in a pooled cohort of the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS) involving 21,680 adults aged 45 or over. Over 263,489 person-years of follow-up, we identified 135 incident ICH events. RESULTS: In multivariable models, for each SD higher baseline level of fibrinogen, the relative rate of incident ICH increased 35% (95% CI, 17% to 55%). Fibrinogen was more strongly related to ICH in ARIC than in CHS. In multivariable models, those with von Willebrand factor levels above the median were 1.72 (95% CI, 0.97 to 3.03) times more likely to have an incident ICH as those below the median. Factor VIII was significantly positively related to ICH in ARIC (relative rate per standard deviation of 1.31; 95% CI, 1.07 to 1.62), but not in CHS. There was no relation in multivariable models between lipoprotein (a), Factor VII, white blood cell count, or C-reactive protein and ICH. CONCLUSIONS: Greater plasma fibrinogen and, to some degree, von Willebrand factor were associated with increased rates of ICH in these prospective studies, whereas Factor VIII was related to ICH in younger ARIC study participants only.
Keywords: Age Distribution; Aged; Biomarkers; C-Reactive Protein; Cerebral Hemorrhage; Cohort Studies; Factor VIII; Female; Fibrinogen; Follow-Up Studies; Humans; Leukocyte Count; Lipoprotein(a); Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Stroke; United States; Vasculitis; von Willebrand Factor

High-density lipoprotein cholesterol and venous thromboembolism in the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Chamberlain, Alanna M; Folsom, Aaron R; Heckbert, Susan R; Rosamond, Wayne D; Cushman, Mary (Blood, 2008)
We determined prospectively the risk of venous thromboembolism (VTE) in relation to baseline high-density lipoprotein cholesterol (HDL-c) in 19 049 participants of the Longitudinal Investigation of Thromboembolism Etiology (LITE), which was composed of 14 490 participants of the Atherosclerosis Risk in Communities (ARIC) study and 4559 participants of the Cardiovascular Health Study (CHS). In addition, we determined the risk of VTE in relation to baseline subfractions of HDL (HDL(2) and HDL(3)) and apolipoprotein A-I (apoA-I) in 14 488 participants of the ARIC study. Age-adjusted incidence rates of VTE by HDL-c quartile ranged from 1.64 to 1.91 per 1000 person-years in men and 1.40 to 1.94 per 1000 person-years in women; however, there was no apparent trend of VTE incidence across HDL-c quartiles for either sex. The multivariate adjusted hazard ratios of VTE by HDL-c quartiles (with quartile 4 as the reference) were nonsignificant for both sexes and ranged between 0.91 and 0.99 for men and 0.78 and 1.22 for women. Results did not differ in separate evaluations of idiopathic and secondary VTE. In the ARIC study, there was no trend of VTE hazard ratios across quartiles of HDL(2), HDL(3), or apoA-I. Low HDL-c does not appear to be an important VTE risk factor.
Keywords: Aged; Apolipoprotein A-I; Cholesterol, HDL; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; United States; Venous Thromboembolism

Insulin-like growth factors, their binding proteins, and prostate cancer risk: analysis of individual patient data from 12 prospective studies. - Roddam, Andrew W; Allen, Naomi E; Appleby, Paul; Key, Timothy J; Ferrucci, Luigi; Carter, H Ballentine; Metter, E Jeffrey; Chen, Chu; Weiss, Noel S; Fitzpatrick, Annette; Hsing, Ann W; Lacey, James V; et al. (Ann Intern Med, 2008)
BACKGROUND: Some, but not all, published results have shown an association between circulating blood levels of some insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) and the subsequent risk for prostate cancer. PURPOSE: To assess the association between levels of IGFs and IGFBPs and the subsequent risk for prostate cancer. DATA SOURCES: Studies identified in PubMed, Web of Science, and CancerLit. STUDY SELECTION: The principal investigators of all studies that published data on circulating concentrations of sex steroids, IGFs, or IGFBPs and prostate cancer risk using prospectively collected blood samples were invited to collaborate. DATA EXTRACTION: Investigators provided individual participant data on circulating concentrations of IGF-I, IGF-II, IGFBP-II, and IGFBP-III and participant characteristics to a central data set in Oxford, United Kingdom. DATA SYNTHESIS: The study included data on 3700 men with prostate cancer and 5200 control participants. On average, case patients were 61.5 years of age at blood collection and received a diagnosis of prostate cancer 5 years after blood collection. The greater the serum IGF-I concentration, the greater the subsequent risk for prostate cancer (odds ratio [OR] in the highest vs. lowest quintile, 1.38 [95% CI, 1.19 to 1.60]; P < 0.001 for trend). Neither IGF-II nor IGFBP-II concentrations were associated with prostate cancer risk, but statistical power was limited. Insulin-like growth factor I and IGFBP-III were correlated (r = 0.58), and although IGFBP-III concentration seemed to be associated with prostate cancer risk, this was secondary to its association with IGF-I levels. Insulin-like growth factor I concentrations seemed to be more positively associated with low-grade than high-grade disease; otherwise, the association between IGFs and IGFBPs and prostate cancer risk had no statistically significant heterogeneity related to stage or grade of disease, time between blood collection and diagnosis, age and year of diagnosis, prostate-specific antigen level at recruitment, body mass index, smoking, or alcohol intake. LIMITATIONS: Insulin-like growth factor concentrations were measured in only 1 sample for each participant, and the laboratory methods to measure IGFs differed in each study. Not all patients had disease stage or grade information, and the diagnosis of prostate cancer may differ among the studies. CONCLUSION: High circulating IGF-I concentrations are associated with a moderately increased risk for prostate cancer.
Keywords: Aged; Humans; Insulin-Like Growth Factor Binding Protein 2; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor Binding Proteins; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Male; Middle Aged; Prospective Studies; Prostatic Neoplasms; Risk Factors; Somatomedins

Knee height and arm span: a reflection of early life environment and risk of dementia. - Huang, T L; Carlson, M C; Fitzpatrick, A L; Kuller, L H; Fried, L P; Zandi, P P (Neurology, 2008)
OBJECTIVES: To determine if anthropometric measures, as markers of early life environment, are associated with risk of dementia, Alzheimer disease (AD), and vascular dementia (VaD). METHODS: A total of 2,798 subjects were followed as part of the Cardiovascular Health Cognition Study for an average of 5.4 years; 480 developed dementia. Knee height was measured 3 years prior to and arm span 4 years after the study's baseline. Cox proportional hazard models were used to examine their association with subsequent risk of dementia, AD, and VaD. RESULTS: Among women, greater knee height and arm span were associated with lower risks of dementia (knee height: HR per 1-inch increase 0.84; 95% CI 0.74-0.96; arm span: HR per 1-inch increase 0.93; 95% CI 0.88-0.98) and AD (knee height: HR per 1-inch increase 0.78; 95% CI 0.65-0.93; arm span: HR per 1-inch increase 0.90; 95% CI 0.85-0.96). Women in the lowest quartile of arm span had approximately 1.5 times greater risk of dementia (HR 1.45; 95% CI 1.03-2.05) and AD (HR 1.70; 95% CI 1.10-2.62) than other women. Among men, only arm span was associated with lower risks of dementia (HR per 1-inch increase 0.94; 95% CI 0.89-1.00) and AD (HR per 1-inch increase 0.92; 95% CI 0.84-1.00). For each gender, knee height was not associated with VaD, while arm span was associated with a nonsignificant lower risk of VaD. CONCLUSIONS: Our findings with knee height and arm span are consistent with previous reports and suggest early life environment may play an important role in the determination of future dementia risk.
Keywords: Aged; Aged, 80 and over; Aging; Anthropometry; Arm; Body Height; Brain; Child; Child, Preschool; Dementia; Environment; Female; Follow-Up Studies; Humans; Infant; Infant, Newborn; Knee; Male; Middle Aged; Prospective Studies; Risk Factors; Sex Characteristics; Skeleton

Left ventricular morphology and systolic function in sleep-disordered breathing: the Sleep Heart Health Study. - Chami, Hassan A; Devereux, Richard B; Gottdiener, John S; Mehra, Reena; Roman, Mary J; Benjamin, Emelia J; Gottlieb, Daniel J (Circulation, 2008)
BACKGROUND: Whether sleep-disordered breathing (SDB) is a risk factor for left ventricular (LV) hypertrophy and dysfunction is controversial. We assessed the relation of SDB to LV morphology and systolic function in a community-based sample of middle-aged and older adults. METHODS AND RESULTS: The present study was a cross-sectional observational study of 2058 Sleep Heart Health Study participants (mean age 65+/-12 years; 58% women; 44% ethnic minorities) who had technically adequate echocardiograms. A polysomnographically derived apnea-hypopnea index (AHI) and hypoxemia index (percent of sleep time with oxyhemoglobin saturation < 90%) were used to quantify SDB severity. LV mass index was significantly associated with both AHI and hypoxemia index after adjustment for age, sex, ethnicity, study site, body mass index, current and prior smoking, alcohol consumption, systolic blood pressure, antihypertensive medication use, diabetes mellitus, and prevalent myocardial infarction. Adjusted LV mass index was 41.3 (SD 9.90) g/m(2.7) in participants with AHI < 5 (n=957) and 44.1 (SD 9.90) g/m(2.7) in participants with AHI > or = 30 (n=84) events per hour. Compared with participants with AHI < 5, those with AHI > or = 30 had an adjusted odds ratio of 1.78 (95% confidence interval 1.14 to 2.79) for LV hypertrophy. A higher AHI and higher hypoxemia index were also associated with larger LV diastolic dimension and lower LV ejection fraction, with a trend toward lower LV fractional shortening. LV wall thickness was significantly associated with the hypoxemia index but not with AHI. Left atrial diameter was not associated with either SDB measure. CONCLUSIONS: In a community-based cohort, SDB is associated with echocardiographic evidence of increased LV mass and reduced LV systolic function.
Keywords: Aged; Echocardiography; Female; Humans; Hypertrophy, Left Ventricular; Hypoxia; Male; Middle Aged; Odds Ratio; Sleep Apnea Syndromes; Systole; Ventricular Dysfunction, Left

Metabolic syndrome, endothelial dysfunction, and risk of cardiovascular events: the Northern Manhattan Study (NOMAS). - Suzuki, Takeki; Hirata, Kumiko; Elkind, Mitchell S V; Jin, Zhezhen; Rundek, Tanja; Miyake, Yumiko; Boden-Albala, Bernadette; Di Tullio, Marco R; Sacco, Ralph; Homma, Shunichi (Am Heart J, 2008)
BACKGROUND: Metabolic syndrome (MetS) predisposes to cardiovascular disease. Endothelial dysfunction is thought to be an important factor in the pathogenesis of atherosclerosis. We tested the hypothesis that both MetS and endothelial dysfunction are vascular risk factors and provide additive prognostic values in predicting cardiovascular events in a multiethnic community sample. METHODS: The study population consisted of 819 subjects (467 female, mean age 66.5 +/- 8.8 years, 66% Hispanic) enrolled in the NOMAS. Metabolic syndrome was defined using the revised Adult Treatment Panel III criteria. Brachial artery flow-mediated dilation (FMD) was measured using high-resolution ultrasound. Endothelial dysfunction was defined as FMD <8.44% (lower 3 quartiles). Cox proportional hazards models were used to assess the effect of MetS and endothelial dysfunction on risk of cardiovascular events. RESULTS: During 81 +/- 21 months of follow-up, events occurred in 84 subjects. Metabolic syndrome was independently associated with cardiovascular events in a multivariate model, including cardiovascular risk factors (adjusted hazard ratio 2.08, 95% CI 1.27-3.40). Subjects with both MetS and endothelial dysfunction were at higher risk for cardiovascular events than those with either one of them alone (adjusted hazard ratio 2.60, 95% CI 1.14-5.92). CONCLUSIONS: Metabolic syndrome is associated with incident cardiovascular events. Combined use of MetS and FMD identifies those who are at higher risk of cardiovascular events. Metabolic syndrome and noninvasive FMD testing can be used concurrently for cardiovascular risk prediction.
Keywords: Adult; Aged; Brachial Artery; Endothelium, Vascular; Female; Humans; Kaplan-Meier Estimate; Male; Metabolic Syndrome; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Stroke; Vascular Diseases

No advantage of A beta 42-lowering NSAIDs for prevention of Alzheimer dementia in six pooled cohort studies. - Szekely, C A; Green, R C; Breitner, J C S; Østbye, T; Beiser, A S; Corrada, M M; Dodge, H H; Ganguli, M; Kawas, C H; Kuller, L H; Psaty, B M; Resnick, S M; et al. (Neurology, 2008)
INTRODUCTION: Observational studies show reduced incidence of Alzheimer dementia (AD) in users of nonsteroidal anti-inflammatory drugs (NSAIDs). One hypothesis holds that the subset of NSAIDs known as selective A beta(42)-lowering agents (SALAs) is responsible for this apparent reduction in AD risk. METHODS: We pooled individual-level data from six prospective studies to obtain a sufficient sample to examine AD risk in users of SALA vs non-SALA NSAIDs. RESULTS: Of 13,499 initially dementia-free participants (70,863 person-years), 820 developed incident AD. Users of NSAIDs (29.6%) showed reduced risk of AD (adjusted hazard ratio [aHR] 0.77, 95% CI 0.65-0.91). The point estimates were similar for SALAs (aHR 0.87, CI 0.72-1.04) and non-SALAs (aHR 0.75, CI 0.56-1.01). Because 573 NSAID users (14.5%) reported taking both a SALA and non-SALA, we examined their use alone and in combination. Resulting aHRs were 0.82 (CI 0.67-0.99) for SALA only, 0.60 (CI 0.40-0.90) for non-SALA only, and 0.87 (CI 0.57-1.33) for both NSAIDs (Wald test for differences, p = 0.32). The 40.7% of participants who used aspirin also showed reduced risk of AD, even when they used no other NSAIDs (aHR 0.78, CI 0.66-0.92). By contrast, there was no association with use of acetaminophen (aHR 0.93, CI 0.76-1.13). CONCLUSIONS: In this pooled dataset, nonsteroidal anti-inflammatory drug (NSAID) use reduced the risk of Alzheimer dementia (AD). However, there was no apparent advantage in AD risk reduction for the subset of NSAIDs shown to selectively lower A beta(42), suggesting that all conventional NSAIDs including aspirin have a similar protective effect in humans.
Keywords: Acetaminophen; Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics, Non-Narcotic; Anti-Inflammatory Agents, Non-Steroidal; Aspirin; Cohort Studies; Female; Humans; Male; Middle Aged; Neuroprotective Agents; Peptide Fragments; Proportional Hazards Models; Prospective Studies; Risk Factors

Polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha are associated with C-reactive protein. - Reiner, Alexander P; Barber, Mathew J; Guan, Yongtao; Ridker, Paul M; Lange, Leslie A; Chasman, Daniel I; Walston, Jeremy D; Cooper, Gregory M; Jenny, Nancy S; Rieder, Mark J; Durda, J Peter; Smith, Joshua D; et al. (Am J Hum Genet, 2008)
Data from the Pharmacogenomics and Risk of Cardiovascular Disease (PARC) study and the Cardiovascular Health Study (CHS) provide independent and confirmatory evidence for association between common polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha and plasma C-reactive protein (CRP) concentration. Analyses with the use of imputation-based methods to combine genotype data from both studies and to test untyped SNPs from the HapMap database identified several SNPs within a 5 kb region of HNF1A intron 1 with the strongest evidence of association with CRP phenotype.
Keywords: Aged; Bayes Theorem; C-Reactive Protein; Female; Hepatocyte Nuclear Factor 1-alpha; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Pravastatin; Simvastatin

Power spectral analysis of EEG activity during sleep in cigarette smokers. - Zhang, Lin; Samet, Jonathan; Caffo, Brian; Bankman, Isaac; Punjabi, Naresh M (Chest, 2008)
BACKGROUND: Research on the effects of cigarette smoking on sleep architecture is limited. The objective of this investigation was to examine differences in sleep EEG between smokers and nonsmokers. METHODS: Smokers and nonsmokers who were free of all medical comorbidities were matched on different factors, including age, gender, race, body mass index, and anthropometric measures. Home polysomnography was conducted using a standard recording montage. Sleep architecture was assessed using visual sleep-stage scoring. The discrete fast Fourier transform was used to calculate the EEG power spectrum for the entire night within contiguous 30-s epochs of sleep for the following frequency bandwidths: delta (0.8 to 4.0 Hz); theta (4.1 to 8.0 Hz); alpha (8.1 to 13.0 Hz); and beta (13.1 to 20.0 Hz). RESULTS: Conventional sleep stages were similar between the two groups. However, spectral analysis of the sleep EEG showed that, compared to nonsmokers, smokers had a lower percentage of EEG power in the delta-bandwidth (59.7% vs 62.6%, respectively; p < 0.04) and higher percentage of EEG power in alpha-bandwidth (15.6% vs 12.5%, respectively; p < 0.001). Differences in the EEG power spectrum between smokers and nonsmokers were greatest in the early part of the sleep period and decreased toward the end. Subjective complaints of lack of restful sleep were also more prevalent in smokers than in nonsmokers (22.5% vs 5.0%, respectively; p < 0.02) and were explained, in part, by the differences in EEG spectral power. CONCLUSIONS: Cigarette smokers manifest disturbances in the sleep EEG that are not evident in conventional measures of sleep architecture. Nicotine in cigarette smoke and withdrawal from it during sleep may contribute to these changes and the subjective experience of nonrestorative sleep.
Keywords: Electroencephalography; Female; Humans; Logistic Models; Male; Middle Aged; Polysomnography; Sleep; Smoking; Spectroscopy, Fourier Transform Infrared

Prevalence, prognosis, and implications of isolated minor nonspecific ST-segment and T-wave abnormalities in older adults: Cardiovascular Health Study. - Kumar, Anita; Prineas, Ronald J; Arnold, Alice M; Psaty, Bruce M; Furberg, Curt D; Robbins, John; Lloyd-Jones, Donald M (Circulation, 2008)
BACKGROUND: The prevalence and prognostic significance of isolated minor nonspecific ST-segment and T-wave abnormalities (NSSTTAs) in older adults are poorly understood. METHODS AND RESULTS: Cardiovascular Health Study participants free of both clinical cardiovascular disease and major ECG abnormalities were included. We examined the prospective association of isolated minor NSSTTAs (defined by Minnesota Codes 4-3, 4-4, 5-3, and 5-4) with total, cardiovascular, and coronary mortality and incident nonfatal myocardial infarction. Among 3224 participants (61.9% women; mean age, 72 years), 233 (7.2%) had isolated NSSTTAs at baseline. Covariates associated with isolated NSSTTAs included older age, nonwhite race (20.5% of blacks versus 4.8% of whites; P<0.001), diabetes, and higher blood pressure and body mass index but not the presence of subclinical cardiovascular disease. After 39 518 person-years of follow-up, the presence of isolated NSSTTAs was associated with significantly increased risk for coronary heart disease mortality (multivariable-adjusted hazards ratio, 1.76; 95% CI, 1.18 to 2.61) but not with incident nonfatal myocardial infarction (multivariable-adjusted hazards ratio, 0.71; 95% CI, 0.43 to 1.17). The association of isolated NSSTTAs with coronary death was independent of subclinical atherosclerosis and left ventricular mass measures. In secondary analyses, among those with cardiac death, there was a significantly higher rate of primary arrhythmic death (32.3% versus 15.4%; P=0.02) in participants with isolated NSSTTAs versus those without NSSTTAs. CONCLUSIONS: Isolated NSSTTAs are common in older Americans and are associated with significantly increased risk for coronary death. However, isolated NSSTTAs are not associated with incident nonfatal myocardial infarction, suggesting that they are associated particularly with increased risk for primary arrhythmic death.
Keywords: Age Factors; Aged; Arrhythmias, Cardiac; Cardiovascular Diseases; Cohort Studies; Electrocardiography; Female; Health Status; Humans; Male; Middle Aged; Prevalence; Prognosis; Prospective Studies

PROC, PROCR and PROS1 polymorphisms, plasma anticoagulant phenotypes, and risk of cardiovascular disease and mortality in older adults: the Cardiovascular Health Study. - Reiner, A P; Carty, C L; Jenny, N S; Nievergelt, C; Cushman, M; Stearns-Kurosawa, D J; Kurosawa, S; Kuller, L H; Lange, L A (J Thromb Haemost, 2008)
BACKGROUND AND OBJECTIVES: Genes encoding protein C anticoagulant pathways are candidates for atherothrombotic and other aging-related disorders. METHODS: Using a tagSNP approach, and data from the Cardiovascular Health Study (CHS), we assessed associations of common polymorphisms of PROC, PROS1 and PROCR with: (i) plasma protein C, soluble protein C endothelial receptor (sEPCR) and protein S levels measured in a subsample of 336 participants at study entry; and (ii) risk of incident clinical outcomes [coronary heart disease (CHD), stroke, and mortality] in 4547 participants during follow-up. Secondarily, we explored associations between plasma protein C, protein S and sEPCR levels and other candidate genes involved in thrombosis, inflammation, and aging. RESULTS: The PROCR Ser219Gly polymorphism (rs867186) was strongly associated with higher sEPCR levels, explaining 75% of the phenotypic variation. The PROCR Ser219Gly variant was also associated with higher levels of circulating protein C antigen. An IL10 polymorphism was associated with higher free protein S levels. The minor alleles of PROC rs2069901 and PROS1 rs4857343 were weakly associated with lower protein C and free protein S levels, respectively. There was no association between PROCR Ser219Gly and risk of CHD, stroke, or mortality. The minor allele of another common PROCR tagSNP, rs2069948, was associated with lymphoid PROCR mRNA expression and with increased risk of incident stroke and all-cause mortality, and decreased healthy survival during follow-up. CONCLUSIONS: A common PROCR variant may be associated with decreased healthy survival in older adults. Additional studies are warranted to establish the role of PROCR variants in ischemic and aging-related disorders.
Keywords: Aged; Aged, 80 and over; Aging; Antigens, CD; Blood Coagulation Factor Inhibitors; Cardiovascular Diseases; Coronary Disease; Endothelial Protein C Receptor; Female; Humans; Inflammation; Male; Middle Aged; Mortality; Polymorphism, Genetic; Protein C; Protein S; Receptors, Cell Surface; Risk; Stroke; Thrombosis

Relation of sleep-disordered breathing to carotid plaque and intima-media thickness. - Wattanakit, Keattiyoat; Boland, Lori; Punjabi, Naresh M; Shahar, Eyal (Atherosclerosis, 2008)
BACKGROUND: Sleep-disordered breathing (SDB) is associated with clinical cardiovascular disease (CVD), but its relation to subclinical atherosclerosis remains to be determined. METHODS: We analyzed the cross-sectional associations of SDB, measured by the respiratory disturbance index (RDI), a hypoxemia index, and an arousal index, with carotid plaque and carotid intima-media thickness (IMT), measured by ultrasound. The sample included 985 participants in the Sleep Heart Health Study (mean age-62, median RDI-8.7) with no history of coronary heart disease and stroke, of whom 396 had evidence of a carotid plaque. RESULTS: As compared with the first quartile of the RDI (0-1.2), the crude odds ratio for carotid plaque was 1.14, 1.27, and 1.48 for the second (1.3-4.1), third (4.2-10.7), and fourth (>10.7) quartile, respectively. After adjustment for CVD risk factors, the corresponding odds ratios were reduced (1.00, 1.04, 1.07, and 1.25). Similarly, the unadjusted mean carotid IMT increased with RDI, but adjusted means (mm) were similar (0.84, 0.85, 0.84, 0.85). Spline regression models did not show monotonicity of the dose-response functions at the right end of the RDI distribution. Neither the hypoxemia index nor the arousal index was associated with carotid plaque or carotid IMT. CONCLUSION: The results of this study suggest that crude, positive associations between SDB and subclinical atherosclerosis can be attributed to confounding by CVD risk factors.
Keywords: Aged; Carotid Arteries; Carotid Artery Diseases; Female; Humans; Male; Middle Aged; Odds Ratio; Risk Factors; Sleep Apnea Syndromes; Tunica Intima; Tunica Media; Ultrasonography

Sleep disordered breathing and hypertension: does self-reported sleepiness modify the association? - Kapur, Vishesh K; Resnick, Helaine E; Gottlieb, Daniel J (Sleep, 2008)
STUDY OBJECTIVES: Epidemiologic studies that demonstrate increased risk of hypertension in persons with sleep disordered breathing indicate that only a minority of these persons report significant subjective sleepiness. Studies also suggest that presence of self-reported sleepiness may identify a subset of persons with sleep disordered breathing who are at greatest risk of cardiovascular sequelae, including hypertension. We explore whether self-reported sleepiness modifies the relationship between sleep disordered breathing and prevalent hypertension. DESIGN: Cross-sectional. SETTING: Multicenter study. PARTICIPANTS: 6046 subjects from the Sleep Heart Health Study. MEASUREMENTS: Polysomnography, systolic and diastolic blood pressure, antihypertensive medication use, questionnaire determined excessive sleepiness and Epworth Sleepiness Scale, and covariates. RESULTS: The odds of hypertension at higher apnea hypopnea index categories were larger in participants identified as sleepy based on responses to a frequency of sleepiness question or the Epworth score. For example, for those with AHI > or =30 compared to AHI <1.5, the adjusted odds ratio for hypertension was 2.83 (1.33-6.04) among those reporting sleepiness > or =5 days per month, but only 1.22 (0.89-1.68) among those reporting less frequent daytime sleepiness. In adjusted logistic regression models, there was statistical evidence for effect modification by frequency of sleepiness (P = 0.033) of the association between apnea hypopnea index and hypertension. In adjusted models that included the Epworth score as a continuous variable, the interaction term fell slightly short of statistical significance (beta = 0.010, P = 0.07). CONCLUSION: This study finds that the association of sleep disordered breathing with hypertension is stronger in individuals who report daytime sleepiness than in those who do not.
Keywords: Aged; Antihypertensive Agents; Comorbidity; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Health Surveys; Humans; Hypertension; Male; Middle Aged; Odds Ratio; Oxygen; Polysomnography; Sleep Apnea, Obstructive; United States

Sleep-disordered breathing and cardiovascular disease: an outcome-based definition of hypopneas. - Punjabi, Naresh M; Newman, Anne B; Young, Terry B; Resnick, Helaine E; Sanders, Mark H (Am J Respir Crit Care Med, 2008)
RATIONALE: Epidemiologic studies on the consequences of sleep-disordered breathing invariably use the apnea-hypopnea index as the primary measure of disease severity. Although hypopneas constitute a majority of disordered breathing events, significant controversy remains about the best criteria used to define these events. OBJECTIVES: The current investigation sought to assess the most appropriate definition for hypopneas that would be best correlated with cardiovascular disease. METHODS: A community sample of middle-aged and older adults was recruited as part of the Sleep Heart Health Study. Full-montage polysomnography was conducted and hypopneas were defined using different thresholds of oxyhemoglobin desaturation with and without arousals. Prevalent cardiovascular disease was assessed based on self-report. Logistic regression analysis was used to characterize the independent association between the hypopnea index and prevalent cardiovascular disease. MEASUREMENTS AND MAIN RESULTS: Using a sample of 6,106 adults with complete data on cardiovascular disease status and polysomnography, the current study found that hypopneas associated with an oxyhemoglobin desaturation of 4% or more were associated with prevalent cardiovascular disease independent of confounding covariates. The adjusted prevalent odds ratios for quartiles of the hypopnea index using a 4% desaturation criterion were as follows: 1.00 (<1.10 events/h), 1.10 (1.01-3.20 events/h), 1.33 (3.21-7.69 events/h), and 1.41 (>7.69 events/h). Hypopnea measures based on less than 4% oxyhemoglobin desaturation or presence of arousals showed no association with cardiovascular disease. CONCLUSIONS: Hypopneas comprise a significant component of sleep-disordered breathing in the general community. By varying the criteria for defining hypopneas, this study demonstrates that hypopneas with a desaturation of at least 4% are independently associated with cardiovascular disease. In contrast, no association was observed between cardiovascular disease and hypopneas associated with milder desaturations or arousals.
Keywords: Aged; Apnea; Cardiovascular Diseases; Cohort Studies; Female; Humans; Male; Middle Aged; Odds Ratio; Oxyhemoglobins; Polysomnography; Sleep Apnea Syndromes; Terminology as Topic

Sleep-disordered breathing and impaired glucose metabolism in normal-weight and overweight/obese individuals: the Sleep Heart Health Study. - Seicean, Sinziana; Kirchner, H Lester; Gottlieb, Daniel J; Punjabi, Naresh M; Resnick, Helaine; Sanders, Mark; Budhiraja, Rohit; Singer, Mendel; Redline, Susan (Diabetes Care, 2008)
OBJECTIVE: To characterize the association between sleep-disordered breathing (SDB) and impaired fasting glucose (IFG), impaired glucose tolerance (IGT), combined IFG and IGT, and occult diabetes in individuals of different body habitus. RESEARCH DESIGN AND METHODS: Cross-sectional analysis of 2,588 participants (aged 52-96 years; 46% men) without known diabetes. SDB was defined as respiratory disturbance index >or=10 events/h. IFG, IGT, occult diabetes, and body weight were classified according to recent accepted guidelines. Participants with and without SDB were compared on prevalence and odds ratios for measures of impaired glucose metabolism (IGM), adjusting for age, sex, race, BMI, and waist circumference. RESULTS: SDB was observed in 209 nonoverweight and 1,036 overweight/obese participants. SDB groups had significantly higher adjusted prevalence and adjusted odds of IFG, IFG plus IGT, and occult diabetes. The adjusted odds ratio for all subjects was 1.3 (95% CI 1.1-1.6) for IFG, 1.2 (1.0-1.4) for IGT, 1.4 (1.1-2.7) for IFG plus IGT, and 1.7 (1.1-2.7) for occult diabetes. CONCLUSIONS: SDB was associated with occult diabetes, IFG, and IFG plus IGT, after adjusting for age, sex, race, BMI, and waist circumference. The magnitude of these associations was similar in nonoverweight and overweight participants. The consistency of associations across all measures of IGM and body habitus groups and the significant association between SDB and IFG plus IGT, a risk factor for rapid progression to diabetes, cardiovascular disease, and mortality, suggests the importance of SDB as a risk factor for clinically important levels of metabolic dysfunction.
Keywords: Aged; Aged, 80 and over; Body Weight; Cardiovascular Diseases; Cross-Sectional Studies; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Male; Middle Aged; Obesity; Overweight; Polysomnography; Reference Values; Sleep Wake Disorders

Subjective and objective sleep quality in patients on conventional thrice-weekly hemodialysis: comparison with matched controls from the sleep heart health study. - Unruh, Mark L; Sanders, Mark H; Redline, Susan; Piraino, Beth M; Umans, Jason G; Chami, Hassan; Budhiraja, Rohit; Punjabi, Naresh M; Buysse, Daniel; Newman, Anne B (Am J Kidney Dis, 2008)
BACKGROUND: Studies examining sleep in the hemodialysis (HD) population have largely lacked an adequate comparison group. It therefore is uncertain whether poor sleep quality in the HD population reflects age, chronic health conditions, or effects of conventional HD therapy. STUDY DESIGN: Cross-sectional matched-group study. SETTING & PARTICIPANTS: Forty-six in-center HD patients were compared with 137 community participants participating in the Sleep Heart Health Study matched for age, sex, body mass index, and race. PREDICTOR: HD patients compared with community-dwelling non-HD participants. OUTCOMES & MEASUREMENTS: Home unattended polysomnography was performed and scored by using similar protocols. Sleep habits and sleepiness were assessed by using the Sleep Habits Questionnaire and Epworth Sleepiness Scale. RESULTS: Average age of study samples was 63 years, 72% were white, and average body mass index was 28 +/- 5 kg/m(2). HD patients were significantly more likely than community participants to have short sleep (odds ratio, 3.27; 95% confidence interval, 1.16 to 9.25) and decreased sleep efficiency (odds ratio, 5.5; 95% confidence interval, 1.5 to 19.6). HD patients reported more difficulty getting back to sleep (odds ratio, 2.25; 95% confidence interval, 1.11 to 4.60) and waking up too early (odds ratio, 2.39; 95% confidence interval, 1.01 to 5.66). There was no association between polysomnography sleep time and self-reported sleep time (r = 0.09; P = 0.6) or between the Epworth Sleepiness Scale and severity of sleep apnea (r = 0.10; P = 0.5) in the HD population. LIMITATIONS: The study was limited to participants older than 45 years. CONCLUSIONS: Kidney failure treated with thrice-weekly HD is significantly associated with poor subjective and objective sleep quality.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Pennsylvania; Polysomnography; Prognosis; Renal Dialysis; Retrospective Studies; Risk Factors; Severity of Illness Index; Sleep; Sleep Apnea Syndromes; Surveys and Questionnaires

Total insulinlike growth factor 1 and insulinlike growth factor binding protein levels, functional status, and mortality in older adults. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis; Strickler, Howard D; Rohan, Thomas E; Xue, XiaoNan; Kritchevsky, Stephen B; Newman, Anne B; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To assess the association between total insulinlike growth factor (IGF)-1, IGF binding protein-1 (IGFBP-1), and IGFBP-3 levels and functioning and mortality in older adults. DESIGN: Cohort study. SETTING/PARTICIPANTS: One thousand one hundred twenty-two individuals aged 65 and older without prior cardiovascular disease events participating in the Cardiovascular Health Study. MEASUREMENTS: Baseline fasting plasma levels of IGF-1, IGFBP-1, and IGFBP-3 (defined as tertiles, T1-T3) were examined in relationship to handgrip strength, time to walk 15 feet, development of new difficulties with activities of daily living (ADLs), and mortality. RESULTS: Higher IGFBP-1 predicted worse handgrip strength (P-trend(T1-T3)<.01) and slower walking speed (P-trend(T1-T3)=.03), lower IGF-1 had a borderline significant association with worse handgrip strength (P-trend(T1-T3)=.06), and better grip strength was observed in the middle IGFBP-3 tertile than in the low or high tertiles (P=.03). Adjusted for age, sex, and race, high IGFBP-1 predicted greater mortality (P-trend(T1-T3)<.001, hazard ratio (HR)(T3vsT1)=1.48, 95% confidence interval (CI)=1.15-1.90); this association was borderline significant after additional confounder adjustment (P-trend(T1-T3)=.05, HR(T3vsT1)=1.35, 95% CI=0.98-1.87). High IGFBP-1 was associated with greater risk of incident ADL difficulties after adjustment for age, sex, race, and other confounders (P-trend(T1-T3)=.04, HR(T3vsT1)=1.40, CI=1.01-1.94). Neither IGF-1 nor IGFBP-3 level predicted mortality or incident ADL difficulties. CONCLUSION: In adults aged 65 and older, high IGFBP-1 levels were associated with greater risk of mortality and poorer functional ability, whereas IGF-1 and IGFBP-3 had little association with these outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Enzyme-Linked Immunosorbent Assay; Fasting; Female; Follow-Up Studies; Hand Strength; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Survival Rate; United States; Walking

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Brachial artery diameter, blood flow and flow-mediated dilation in sleep-disordered breathing. - Chami, Hassan A; Keyes, Michelle J; Vita, Joseph A; Mitchell, Gary F; Larson, Martin G; Fan, Shuxia; Vasan, Ramachandran S; O'Connor, George T; Benjamin, Emelia J; Gottlieb, Daniel J (Vasc Med, 2009)
Clinic-based, case-control studies linked sleep-disordered breathing (SDB) to markers of endothelial dysfunction. We attempted to validate this association in a large community-based sample, and evaluate the relation of SDB to arterial diameter and peripheral blood flow. This community-based, cross-sectional observational study included 327 men and 355 women, aged 42-83 years, from the Framingham Heart Study site of the Sleep Heart Health Study. The polysomnographically derived apnea-hypopnea index and the hypoxemia index (percent sleep time with oxyhemoglobin saturation below 90%) were used to quantify the severity of SDB. Brachial artery ultrasound measurements included baseline diameter, percent flow-mediated dilation, and baseline and hyperemic flow velocity and volume. The baseline brachial artery diameter was significantly associated with both the apnea-hypopnea index and the hypoxemia index. The association was diminished by adjustment for body mass index, but remained significant for the apnea-hypopnea index. Age-, sex-, race- and body mass index-adjusted mean diameters were 4.32, 4.33, 4.33, 4.56, 4.53 mm for those with apnea-hypopnea index < 1.5, 1.5-4.9, 5-14.9, 15-29.9, >/= 30, respectively; p = 0.03. Baseline flow measures were associated with the apnea-hypopnea index but this association was non-significant after adjusting for body mass index. No significant association was observed between measures of SDB and percent flow-mediated dilation or hyperemic flow in any model. In conclusion, this study supports a moderate association of SDB and larger baseline brachial artery diameter, which may reflect SDB-induced vascular remodeling. This study does not support a link between SDB and endothelial dysfunction as measured by brachial artery flow-mediated dilation.
Keywords: Adult; Aged; Aged, 80 and over; Blood Flow Velocity; Brachial Artery; Cross-Sectional Studies; Female; Humans; Hyperemia; Hypoxia; Laser-Doppler Flowmetry; Male; Middle Aged; Polysomnography; Regional Blood Flow; Severity of Illness Index; Sleep Apnea Syndromes; Ultrasonography; Vasodilation

Coagulation factors IX through XIII and the risk of future venous thrombosis: the Longitudinal Investigation of Thromboembolism Etiology. - Cushman, Mary; O'Meara, Ellen S; Folsom, Aaron R; Heckbert, Susan R (Blood, 2009)
Higher levels of procoagulant factors and factor XII deficiency may be risk factors for first venous thromboembolism (VTE). We studied associations of coagulation factors IX through XIII with risk of future VTE in 2 general population samples. Using a nested case-control study combining the 21 860 participants of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study, we determined antigenic levels of these coagulation factors in primarily pre-event blood samples from 462 participants who subsequently developed VTE and 1047 participants who remained free of VTE. Only elevated levels of factors IX and XI were associated with increased risk of VTE after adjustment for age, sex, race, and study. For factor IX, the odds ratio (OR) was 1.4 (95% confidence interval [CI], 1.0-2.0) comparing the top to bottom quintile. The OR for factor XI was higher: 2.0 (95% CI, 1.4-2.9). With further adjustment for body mass index and diabetes, only elevated factor XI remained associated with VTE risk: OR 1.8 (95% CI, 1.3-2.7). Associations were similar by study and whether the thrombosis was idiopathic or secondary. Factor XII deficiency was not related to VTE risk. Among these procoagulant factors, only elevated factor XI was a risk factor for VTE.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Factor IX; Factor X; Factor XI; Factor XII; Factor XIII; Female; Humans; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Risk Factors; Venous Thromboembolism

Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium: Design of prospective meta-analyses of genome-wide association studies from 5 cohorts. - Psaty, Bruce M; O'Donnell, Christopher J; Gudnason, Vilmundur; Lunetta, Kathryn L; Folsom, Aaron R; Rotter, Jerome I; Uitterlinden, André G; Harris, Tamara B; Witteman, Jacqueline C M; Boerwinkle, Eric (Circ Cardiovasc Genet, 2009)
BACKGROUND: The primary aim of genome-wide association studies is to identify novel genetic loci associated with interindividual variation in the levels of risk factors, the degree of subclinical disease, or the risk of clinical disease. The requirement for large sample sizes and the importance of replication have served as powerful incentives for scientific collaboration. Methods- The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium was formed to facilitate genome-wide association studies meta-analyses and replication opportunities among multiple large population-based cohort studies, which collect data in a standardized fashion and represent the preferred method for estimating disease incidence. The design of the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium includes 5 prospective cohort studies from the United States and Europe: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. With genome-wide data on a total of about 38 000 individuals, these cohort studies have a large number of health-related phenotypes measured in similar ways. For each harmonized trait, within-cohort genome-wide association study analyses are combined by meta-analysis. A prospective meta-analysis of data from all 5 cohorts, with a properly selected level of genome-wide statistical significance, is a powerful approach to finding genuine phenotypic associations with novel genetic loci. CONCLUSIONS: The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and collaborating non-member studies or consortia provide an excellent framework for the identification of the genetic determinants of risk factors, subclinical-disease measures, and clinical events.
Keywords: Adult; Aged; Aging; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Diseases; Humans; Male; Meta-Analysis as Topic; Middle Aged; Phenotype; Research Design; Risk Factors

Common coding variants of the HNF1A gene are associated with multiple cardiovascular risk phenotypes in community-based samples of younger and older European-American adults: the Coronary Artery Risk Development in Young Adults Study and The Cardiovascula - Reiner, Alexander P; Gross, Myron D; Carlson, Christopher S; Bielinski, Suzette J; Lange, Leslie A; Fornage, Myriam; Jenny, Nancy S; Walston, Jeremy; Tracy, Russell P; Williams, O Dale; Jacobs, David R; Nickerson, Deborah A (Circ Cardiovasc Genet, 2009)
BACKGROUND: The transcription factor hepatocyte nuclear factor (HNF)-1 alpha regulates the activity of a number of genes involved in innate immunity, blood coagulation, lipid and glucose transport and metabolism, and cellular detoxification. Common polymorphisms of the HNF-1 alpha gene (HNF1A) were recently associated with plasma C-reactive protein and gamma-glutamyl transferase concentration in middle-aged to older European Americans (EA). METHODS AND RESULTS: We assessed whether common variants of HNF1A are associated with C-reactive protein, gamma-glutamyl transferase, and other atherosclerotic and metabolic risk factors, in the large, population-based Coronary Artery Risk Development in Young Adults Study of healthy young EA (n=2154) and African American (AA; n=2083) adults. The minor alleles of Ile27Leu (rs1169288) and Ser486Asn (rs2464196) were associated with 0.10 to 0.15 standard deviation units lower C-reactive protein and gamma-glutamyl transferase levels in EA. The same HNF1A coding variants were associated with higher low-density lipoprotein cholesterol, apolipoprotein B, creatinine, and fibrinogen in EA. We replicated the associations between HNF1A coding variants and C-reactive protein, fibrinogen, low-density lipoprotein cholesterol, and renal function in a second population-based sample of EA adults 65 years and older from the Cardiovascular Health Study. The HNF1A Ser486Asn and/or Ile27Leu variants were also associated with increased risk of subclinical coronary atherosclerosis in Coronary Artery Risk Development in Young Adults and with incident coronary heart disease in Cardiovascular Health Study. The Ile27Leu and Ser486Asn variants were 3-fold less common in AA than in EA. There was little evidence of association between HNF1A genotype and atherosclerosis-related phenotypes in AA. CONCLUSIONS: Common polymorphisms of HNF1A seem to influence multiple phenotypes related to cardiovascular risk in the general population of younger and older EA adults.
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; gamma-Glutamyltransferase; Genetic Predisposition to Disease; Genotype; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Common hemostasis and inflammation gene variants and venous thrombosis in older adults from the Cardiovascular Health Study. - Reiner, A P; Lange, L A; Smith, N L; Zakai, N A; Cushman, M; Folsom, A R (J Thromb Haemost, 2009)
BACKGROUND/OBJECTIVES: Age-related changes in blood coagulation and fibrinolysis are associated with increased risk of thrombotic events. Inherited deficiencies of coagulation proteins, such as factor V (FV) Leiden and prothrombin G20210A, explain a small fraction of venous thromboembolic disease (VTE). Additional genetic factors are likely to underlie the etiology of VTE, some of which may become manifest at older ages. METHODS: We tested 290 common SNPs within 51 thrombosis and inflammation genes for association with VTE in the Cardiovascular Health Study, a large, prospective cohort of older adults followed for up to 12 years. RESULTS: There were 184 VTE events that occurred at mean age of 78 years. TagSNPs within four genes encoding FXIII subunit A (F13A), FVII activating protease (HABP2), protease activated receptor-1 (F2R) and the urokinase receptor (PLAUR) showed the strongest evidence for association with VTE, with each gene having a global P-value < 0.05 and at least one tagSNP false discovery rate (FDR) q-value < 0.05. The rs3024409 variant allele of F13A1 was associated with 1.66-fold increased risk of VTE, while the minor alleles of HABP2 rs6585234 and rs3862019, F2R rs253061 and rs153311, and PLAUR rs344782 were each associated with lower risk of VTE (hazard ratios in the range of 0.49-0.66). Consistent with the observed protective association for VTE risk, the HABP2 rs3862019 variant allele was also associated with lower activity levels of coagulation factors FVIII, FIX, FX and plasminogen. We also confirm previously reported associations between common variants of the coagulation FII, FV, FVIII, FXI, alpha-fibrinogen and protein C genes and risk of VTE. CONCLUSIONS: These findings suggest that several novel common coagulation gene variants may be related to risk of VTE in older adults. Further studies in older adults are needed to validate these findings and assess functional molecular mechanisms.
Keywords: Aged; Alleles; Factor V; Factor VIII; Female; Hemostasis; Humans; Inflammation; Male; Middle Aged; Models, Genetic; Plasminogen; Prothrombin; Risk; Serine Endopeptidases; Venous Thrombosis

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genetic variations in nitric oxide synthase 1 adaptor protein are associated with sudden cardiac death in US white community-based populations. - Kao, W H Linda; Arking, Dan E; Post, Wendy; Rea, Thomas D; Sotoodehnia, Nona; Prineas, Ronald J; Bishe, Bryan; Doan, Betty Q; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Coresh, Josef; et al. (Circulation, 2009)
BACKGROUND: The ECG QT interval is associated with risk of sudden cardiac death (SCD). A previous genome-wide association study demonstrated that allelic variants (rs10494366 and rs4657139) in the nitric oxide synthase 1 adaptor protein (NOS1AP), which encodes a carboxy-terminal PDZ ligand of neuronal nitric oxide synthase, are associated with the QT interval in white adults. The present analysis was conducted to validate the association between NOS1AP variants and the QT interval and to examine the association with SCD in a combined population of 19 295 black and white adults from the Atherosclerosis Risk In Communities Study and the Cardiovascular Health Study. METHODS AND RESULTS: We examined 19 tagging single-nucleotide polymorphisms in the genomic blocks containing rs10494366 and rs4657139 in NOS1AP. SCD was defined as a sudden pulseless condition of cardiac origin in a previously stable individual. General linear models and Cox proportional hazards regression models were used. Multiple single-nucleotide polymorphisms in NOS1AP, including rs10494366, rs4657139, and rs16847548, were significantly associated with adjusted QT interval in whites (P<0.0001). In whites, after adjustment for age, sex, and study, the relative hazard of SCD associated with each C allele at rs16847548 was 1.31 (95% confidence interval 1.10 to 1.56, P=0.002), assuming an additive model. In addition, a downstream neighboring single-nucleotide polymorphism, rs12567209, which was not correlated with rs16847548 or QT interval, was also independently associated with SCD in whites (relative hazard 0.57, 95% confidence interval 0.39 to 0.83, P=0.003). Adjustment for QT interval and coronary heart disease risk factors attenuated but did not eliminate the association between rs16847548 and SCD, and such adjustment had no effect on the association between rs12567209 and SCD. No significant associations between tagging single-nucleotide polymorphisms in NOS1AP and either QT interval or SCD were observed in blacks. CONCLUSIONS: In a combined analysis of 2 population-based prospective cohort studies, sequence variations in NOS1AP were associated with baseline QT interval and the risk of SCD in white US adults.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Death, Sudden, Cardiac; Electrocardiography; European Continental Ancestry Group; Genotype; Humans; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomewide association studies of stroke. - Ikram, M Arfan; Seshadri, Sudha; Bis, Joshua C; Fornage, Myriam; DeStefano, Anita L; Aulchenko, Yurii S; Debette, Stephanie; Lumley, Thomas; Folsom, Aaron R; van den Herik, Evita G; Bos, Michiel J; Beiser, Alexa; et al. (N Engl J Med, 2009)
BACKGROUND: The genes underlying the risk of stroke in the general population remain undetermined. METHODS: We carried out an analysis of genomewide association data generated from four large cohorts composing the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, including 19,602 white persons (mean [+/-SD] age, 63+/-8 years) in whom 1544 incident strokes (1164 ischemic strokes) developed over an average follow-up of 11 years. We tested the markers most strongly associated with stroke in a replication cohort of 2430 black persons with 215 incident strokes (191 ischemic strokes), another cohort of 574 black persons with 85 incident strokes (68 ischemic strokes), and 652 Dutch persons with ischemic stroke and 3613 unaffected persons. RESULTS: Two intergenic single-nucleotide polymorphisms on chromosome 12p13 and within 11 kb of the gene NINJ2 were associated with stroke (P<5x10(-8)). NINJ2 encodes an adhesion molecule expressed in glia and shows increased expression after nerve injury. Direct genotyping showed that rs12425791 was associated with an increased risk of total (i.e., all types) and ischemic stroke, with hazard ratios of 1.30 (95% confidence interval [CI], 1.19 to 1.42) and 1.33 (95% CI, 1.21 to 1.47), respectively, yielding population attributable risks of 11% and 12% in the discovery cohorts. Corresponding hazard ratios were 1.35 (95% CI, 1.01 to 1.79; P=0.04) and 1.42 (95% CI, 1.06 to 1.91; P=0.02) in the large cohort of black persons and 1.17 (95% CI, 1.01 to 1.37; P=0.03) and 1.19 (95% CI, 1.01 to 1.41; P=0.04) in the Dutch sample; the results of an underpowered analysis of the smaller black cohort were nonsignificant. CONCLUSIONS: A genetic locus on chromosome 12p13 is associated with an increased risk of stroke.
Keywords: African Continental Ancestry Group; Aged; Chromosomes, Human, Pair 12; Cohort Studies; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors; Stroke

Lack of association of soluble endothelial protein C receptor and PROCR 6936A/G polymorphism with the risk of venous thromboembolism in a prospective study. - Yamagishi, Kazumasa; Cushman, Mary; Heckbert, Susan R; Tsai, Michael Y; Folsom, Aaron R (Br J Haematol, 2009)
Prior case-control studies reported that levels of the soluble form of the endothelial protein C receptor (sEPCR) were strongly controlled by the PROCR 6963A/G polymorphism and higher levels were a risk factor for venous thromboembolism (VTE). We sought to prospectively examine the association of sEPCR and the 6963A/G polymorphism with the incidence of VTE. The Longitudinal Investigation of Thromboembolism Etiology (LITE) pooled data from the Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) Study on men and women aged > or =45 years. A nested case-control study of 458 incident VTE and 1038 controls was performed. sEPCR levels were distributed trimodally according to 6963A/G polymorphism. Adjusting for age, sex and race, there was no overall association between sEPCR level and VTE: odds ratio (OR) [95% confidence interval] for highest versus lowest quartile = 1.17[0.86-1.59]. However, higher sEPCR was associated with VTE in non-whites (OR = 1.84[1.05-3.22]) and women (OR = 1.51[1.01-2.26]). The 6963A/G polymorphism was not associated with VTE risk (OR = 0.93[0.70-1.25]). In conclusion, sEPCR levels and the PROCR 6963A/G polymorphism were not associated overall with increased risk of VTE.
Keywords: Antigens, CD; Case-Control Studies; Endothelial Protein C Receptor; Female; Genotype; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Polymorphism, Genetic; Prospective Studies; Receptors, Cell Surface; Risk; Venous Thromboembolism

Longitudinal evaluation of sleep-disordered breathing and sleep symptoms with change in quality of life: the Sleep Heart Health Study (SHHS). - Silva, Graciela E; An, Ming-Wen; Goodwin, James L; Shahar, Eyal; Redline, Susan; Resnick, Helaine; Baldwin, Carol M; Quan, Stuart F (Sleep, 2009)
STUDY OBJECTIVES: Findings from population studies evaluating the progression and incidence of sleep disordered breathing have shown evidence of a longitudinal increase in the severity of sleep disordered breathing. The present study evaluates the association among changes in sleep disordered breathing, sleep symptoms, and quality of life over time. DESIGN: Prospective cohort study. Data were from the Sleep Heart Health Study. SETTING: Multicenter study. PARTICIPANTS: Three thousand seventy-eight subjects aged 40 years and older from the baseline and follow-up examination cycles were included. MEASUREMENTS: The primary outcomes were changes in the Physical Component Summary and Mental Component Summary scales obtained from the Medical Outcomes Study Short-Form Health Survey. The primary exposure was change in the respiratory disturbance index obtained from unattended overnight polysomnograms performed approximately 5 years apart. Other covariates included measures of excessive daytime sleepiness and difficulty initiating and maintaining sleep. RESULTS: Mean respiratory disturbance index increased from 8.1 +/- 11 SD at baseline to 10.9 +/- 14 (P < 0.0001) at follow-up. The mean Physical Component Summary and Mental Component Summary scores were 48.5 and 54.1 at baseline and 46.3 and 54.8 at follow-up. No associations between change in respiratory disturbance index and changes in Physical Component Summary or Mental Component Summary scores were seen. However, worsening of difficulty initiating and maintaining sleep and excessive daytime sleepiness were significantly associated with lower quality of life. CONCLUSIONS: A slight increase in severity of sleep disordered breathing was seen over 5 years; this was not associated with worsening of quality of life. However, subjective symptoms of quality of sleep and daytime sleepiness were associated with declining quality of life.
Keywords: Aged; Attitude to Health; Cohort Studies; Comorbidity; Disease Progression; Disorders of Excessive Somnolence; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Quality of Life; Sleep Apnea, Obstructive; Sleep Initiation and Maintenance Disorders

Meta-analysis: retinal vessel caliber and risk for coronary heart disease. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; Dejong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Ann Intern Med, 2009)
BACKGROUND: Retinal vessel caliber may be a novel marker of coronary heart disease (CHD) risk. However, the sex-specific effect, magnitude of association, and effect independent of traditional CHD disease risk factors remain unclear. PURPOSE: To determine the association between retinal vessel caliber and risk for CHD. DATA SOURCES: Relevant studies in any language identified through MEDLINE (1950 to June 2009) and EMBASE (1950 to June 2009) databases. STUDY SELECTION: Studies were included if they examined a general population, measured retinal vessel caliber from retinal photographs, and documented CHD risk factors and incident CHD events. DATA EXTRACTION: 6 population-based prospective cohort studies provided data for individual participant meta-analysis. DATA SYNTHESIS: Proportional hazards models, adjusted for traditional CHD risk factors, were constructed for retinal vessel caliber and incident CHD in women and men. Among 22,159 participants who were free of CHD and followed for 5 to 14 years, 2219 (10.0%) incident CHD events occurred. Retinal vessel caliber changes (wider venules and narrower arterioles) were each associated with an increased risk for CHD in women (pooled multivariable-adjusted hazard ratios, 1.16 [95% CI, 1.06 to 1.26] per 20-microm increase in venular caliber and 1.17 [CI, 1.07 to 1.28] per 20-microm decrease in arteriolar caliber) but not in men (1.02 [CI, 0.94 to 1.10] per 20-microm increase in venular caliber and 1.02 [CI, 0.95 to 1.10] per 20-microm decrease in arteriolar caliber). Women without hypertension or diabetes had higher hazard ratios. LIMITATION: Error in the measurement of retinal vessel caliber and Framingham variables was not taken into account. CONCLUSION: Retinal vessel caliber changes were independently associated with an increased risk for CHD events in women.
Keywords: Adult; Aged; Arterioles; Biomarkers; Coronary Disease; Female; Humans; Male; Middle Aged; Proportional Hazards Models; Retinal Vessels; Risk Factors; Sex Factors; Venules

Midlife and late-life obesity and the risk of dementia: cardiovascular health study. - Fitzpatrick, Annette L; Kuller, Lewis H; Lopez, Oscar L; Diehr, Paula; O'Meara, Ellen S; Longstreth, W T; Luchsinger, José A (Arch Neurol, 2009)
BACKGROUND: While high adiposity in middle age appears to be related to greater dementia risk, studies exploring this association in the elderly are conflicting. OBJECTIVE: To evaluate associations between midlife and late-life obesity and risk of dementia. DESIGN: Prospective study with mean follow-up of 5.4 years (1992-1994 through 1999). SETTING: Community-dwelling sample in 4 US sites recruited from Medicare eligibility files. PARTICIPANTS: A total of 2798 adults without dementia (mean age, 74.7 years; 59.1% women) participating in the Cardiovascular Health Study who underwent magnetic resonance imaging were measured for height and weight at baseline at age 65 years or older (late life), and self-reported weight at age 50 years (midlife). Body mass index (BMI) (calculated as weight in kilograms divided by height in meters squared) was calculated at both times. MAIN OUTCOME MEASURES: Dementia, Alzheimer disease, and vascular dementia classified by a multidisciplinary committee using standardized criteria. RESULTS: Classification resulted in 480 persons with incident dementia, 245 with Alzheimer disease (no vascular dementia), and 213 with vascular dementia (with or without Alzheimer disease). In evaluations of midlife obesity, an increased risk of dementia was found for obese (BMI >30) vs normal-weight (BMI 20-25) persons, adjusted for demographics (hazard ratio [HR], 1.39; 95% confidence interval [CI], 1.03-1.87) and for cardiovascular risk factors (1.36; 0.94-1.95). The risk estimates were reversed in assessments of late-life BMI. Underweight persons (BMI <20) had an increased risk of dementia (1.62; 1.02-2.64), whereas being overweight (BMI >25-30) was not associated (0.92; 0.72-1.18) and being obese reduced the risk of dementia (0.63; 0.44-0.91) compared with those with normal BMI. CONCLUSION: These results help explain the "obesity paradox" as differences in dementia risk across time are consistent with physical changes in the trajectory toward disability.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Anthropometry; Body Mass Index; Dementia, Vascular; Evaluation Studies as Topic; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Obesity; Prospective Studies; Risk; Survival Analysis

Multiple independent genetic factors at NOS1AP modulate the QT interval in a multi-ethnic population. - Arking, Dan E; Khera, Amit; Xing, Chao; Kao, W H Linda; Post, Wendy; Boerwinkle, Eric; Chakravarti, Aravinda (PLoS One, 2009)
Extremes of electrocardiographic QT interval are associated with increased risk for sudden cardiac death (SCD); thus, identification and characterization of genetic variants that modulate QT interval may elucidate the underlying etiology of SCD. Previous studies have revealed an association between a common genetic variant in NOS1AP and QT interval in populations of European ancestry, but this finding has not been extended to other ethnic populations. We sought to characterize the effects of NOS1AP genetic variants on QT interval in the multi-ethnic population-based Dallas Heart Study (DHS, n = 3,072). The SNP most strongly associated with QT interval in previous samples of European ancestry, rs16847548, was the most strongly associated in White (P = 0.005) and Black (P = 3.6 x 10(-5)) participants, with the same direction of effect in Hispanics (P = 0.17), and further showed a significant SNP x sex-interaction (P = 0.03). A second SNP, rs16856785, uncorrelated with rs16847548, was also associated with QT interval in Blacks (P = 0.01), with qualitatively similar results in Whites and Hispanics. In a previously genotyped cohort of 14,107 White individuals drawn from the combined Atherosclerotic Risk in Communities (ARIC) and Cardiovascular Health Study (CHS) cohorts, we validated both the second locus at rs16856785 (P = 7.63 x 10(-8)), as well as the sex-interaction with rs16847548 (P = 8.68 x 10(-6)). These data extend the association of genetic variants in NOS1AP with QT interval to a Black population, with similar trends, though not statistically significant at P<0.05, in Hispanics. In addition, we identify a strong sex-interaction and the presence of a second independent site within NOS1AP associated with the QT interval. These results highlight the consistent and complex role of NOS1AP genetic variants in modulating QT interval.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; African Americans; Aged; Death, Sudden, Cardiac; Electrocardiography; Ethnic Groups; European Continental Ancestry Group; Female; Genome-Wide Association Study; Heart Diseases; Heart Rate; Hispanic Americans; Humans; Linear Models; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Sex Factors; Young Adult

NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

Peak thrombin generation and subsequent venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE) study. - Lutsey, P L; Folsom, A R; Heckbert, S R; Cushman, M (J Thromb Haemost, 2009)
BACKGROUND: Thrombin is an enzyme that is essential for the acceleration of the coagulation cascade and the conversion of fibrinogen to clottable fibrin. OBJECTIVES: We evaluated the relationship of basal peak thrombin generation with the risk of future venous thromboembolism (VTE), and determined whether associations were independent of other coagulation markers. METHODS: The Longitudinal Investigation of Thromboembolism Etiology (LITE) study investigated VTE in two prospective population-based cohorts: the Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS). Peak thrombin generation was measured on stored plasma in a nested case-control sample (434 cases and 1004 controls). Logistic regression was used to estimate the relationship of peak thrombin generation with VTE, adjusted for age, sex, race, center, and body mass index. Mediation was evaluated by additionally adjusting for factor VIII and D-dimer. RESULTS: Relative to the first quartile of peak thrombin generation, the odds ratio (OR) of VTE for those above the median was 1.74 [95% confidence interval (CI) 1.28-2.37]. The association was modestly attenuated by adjustment for FVIII and D-dimer (OR 1.47, 95% CI 1.05-2.05). Associations appeared to be stronger for idiopathic than for secondary VTE. Elevated peak thrombin generation more than added to the VTE risk associated with FV Leiden or low activated partial thromboplastin time. CONCLUSIONS: In this prospective study of two independent cohorts, elevated basal peak thrombin generation was associated with subsequent risk of VTE, independently of established VTE risk factors.
Keywords: Adult; Aged; Biomarkers; Blood Coagulation Factors; Case-Control Studies; Ethnic Groups; Factor VIII; Female; Fibrin Fibrinogen Degradation Products; Humans; Male; Middle Aged; Partial Thromboplastin Time; Prospective Studies; Risk Factors; Thrombin; United States; Venous Thromboembolism

Polysomnographic and health-related quality of life correlates of restless legs syndrome in the Sleep Heart Health Study. - Winkelman, John W; Redline, Susan; Baldwin, Carol M; Resnick, Helaine E; Newman, Anne B; Gottlieb, Daniel J (Sleep, 2009)
STUDY OBJECTIVES: Sleep disturbance is the primary clinical morbidity of restless legs syndrome (RLS). To date, sleep disturbance in RLS has been measured in (1) clinical samples with polysomnography (PSG) or (2) population-based samples by self-report. The objective of this study was to analyze sleep by PSG in a population-based sample with symptoms of RLS. DESIGN: Cross-sectional observational study. SETTING: Community-based. PARTICIPANTS: 3433 older men and women. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: RLS was evaluated using an 8-item self-administered questionnaire based on NIH diagnostic criteria and required symptoms occurring > or = five times per month and associated with at least moderate distress. Health-related quality of life (HRQOL) was determined using the SF-36. Unattended, in-home PSG was performed. Data were assessed using general linear models with adjustment for demographic, health-related variables, and apnea-hypopnea index (AHI). Subjects with RLS had longer adjusted mean sleep latency (39.8 vs 26.4 min, P < 0.0001) and higher arousal index (20.1 vs 18.0, P = 0.0145) than those without RLS. Sleep latency increased progressively as the frequency of RLS symptoms increased from 5-15 days per month to 6-7 days per week. No differences in sleep stage percentages were observed between participants with and without RLS. Subjects with RLS also reported poorer HRQOL in all physical domains as well as in the Mental Health and Vitality domains. CONCLUSIONS: These novel PSG data from a nonclinical, community-based sample of individuals with RLS document sleep disturbance in the home even in individuals with intermittent symptoms.
Keywords: Adult; Aged; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Polysomnography; Prospective Studies; Quality of Life; Restless Legs Syndrome; Sleep Initiation and Maintenance Disorders; Statistics as Topic

Prediction of incident stroke events based on retinal vessel caliber: a systematic review and individual-participant meta-analysis. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; de Jong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Am J Epidemiol, 2009)
The caliber of the retinal vessels has been shown to be associated with stroke events. However, the consistency and magnitude of association, and the changes in predicted risk independent of traditional risk factors, are unclear. To determine the association between retinal vessel caliber and the risk of stroke events, the investigators combined individual data from 20,798 people, who were free of stroke at baseline, in 6 cohort studies identified from a search of the Medline (National Library of Medicine, Bethesda, Maryland) and EMBASE (Elsevier B.V., Amsterdam, the Netherlands) databases. During follow-up of 5-12 years, 945 (4.5%) incident stroke events were recorded. Wider retinal venular caliber predicted stroke (pooled hazard ratio = 1.15, 95% confidence interval: 1.05, 1.25 per 20-micron increase in caliber), but the caliber of retinal arterioles was not associated with stroke (pooled hazard ratio = 1.00, 95% confidence interval: 0.92, 1.08). There was weak evidence of heterogeneity in the hazard ratio for retinal venular caliber, which may be attributable to differences in follow-up strategies across studies. Inclusion of retinal venular caliber in prediction models containing traditional stroke risk factors reassigned 10.1% of people at intermediate risk into different, mostly lower, risk categories.
Keywords: Aged; Fluorescein Angiography; Humans; Middle Aged; Predictive Value of Tests; Proportional Hazards Models; Retinal Artery; Retinal Vein; Retinal Vessels; Risk Factors; Stroke

Prospective study of sleep-disordered breathing and hypertension: the Sleep Heart Health Study. - O'Connor, George T; Caffo, Brian; Newman, Anne B; Quan, Stuart F; Rapoport, David M; Redline, Susan; Resnick, Helaine E; Samet, Jonathan; Shahar, Eyal (Am J Respir Crit Care Med, 2009)
RATIONALE: Cross-sectional epidemiologic studies show an association between sleep-disordered breathing and hypertension, but only one cohort study has examined sleep-disordered breathing as a risk factor for incident hypertension. OBJECTIVES: To examine whether sleep-disordered breathing increases the risk of incident hypertension among persons 40 years of age and older. METHODS: In a prospective cohort study, we analyzed data from 2,470 participants who at baseline did not have hypertension, defined as blood pressure of at least 140/90 mm Hg or taking antihypertensive medication. The apnea-hypopnea index (AHI), the number of apneas plus hypopneas per hour of sleep, was measured by overnight in-home polysomnography. We estimated odds ratios for developing hypertension during 5 years of follow-up according to baseline AHI. MEASUREMENTS AND MAIN RESULTS: The odds ratios for incident hypertension increased with increasing baseline AHI; however, this relationship was attenuated and not statistically significant after adjustment for baseline body-mass index. Although not statistically significant, the observed association between a baseline AHI greater than 30 and future hypertension (odds ratio, 1.51; 95% confidence interval, 0.93-2.47) does not exclude the possibility of a modest association. CONCLUSIONS: Among middle-aged and older persons without hypertension, much of the relationship between AHI and risk of incident hypertension was accounted for by obesity. After adjustment for body mass index, the AHI was not a significant predictor of future hypertension, although a modest influence of an AHI greater than 30 on hypertension could not be excluded.
Keywords: Adult; Blood Pressure; Confidence Intervals; Cross-Sectional Studies; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Male; Middle Aged; Odds Ratio; Polysomnography; Prognosis; Prospective Studies; Risk Factors; Sleep Apnea Syndromes; Time Factors; United States

Replication of findings on the association of genetic variation in 24 hemostasis genes and risk of incident venous thrombosis. - Smith, N L; Wiggins, K L; Reiner, A P; Lange, L A; Cushman, M; Heckbert, S R; Lumley, T; Rice, K M; Folsom, A R; Psaty, B M (J Thromb Haemost, 2009)
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Case-Control Studies; Cohort Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Haplotypes; Hemostasis; Humans; Incidence; Male; Menopause; Middle Aged; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk; Thrombophilia; Venous Thrombosis; Young Adult

Sleep-disordered breathing and mortality: a prospective cohort study. - Punjabi, Naresh M; Caffo, Brian S; Goodwin, James L; Gottlieb, Daniel J; Newman, Anne B; O'Connor, George T; Rapoport, David M; Redline, Susan; Resnick, Helaine E; Robbins, John A; Shahar, Eyal; Unruh, Mark L; et al. (PLoS Med, 2009)
BACKGROUND: Sleep-disordered breathing is a common condition associated with adverse health outcomes including hypertension and cardiovascular disease. The overall objective of this study was to determine whether sleep-disordered breathing and its sequelae of intermittent hypoxemia and recurrent arousals are associated with mortality in a community sample of adults aged 40 years or older. METHODS AND FINDINGS: We prospectively examined whether sleep-disordered breathing was associated with an increased risk of death from any cause in 6,441 men and women participating in the Sleep Heart Health Study. Sleep-disordered breathing was assessed with the apnea-hypopnea index (AHI) based on an in-home polysomnogram. Survival analysis and proportional hazards regression models were used to calculate hazard ratios for mortality after adjusting for age, sex, race, smoking status, body mass index, and prevalent medical conditions. The average follow-up period for the cohort was 8.2 y during which 1,047 participants (587 men and 460 women) died. Compared to those without sleep-disordered breathing (AHI: <5 events/h), the fully adjusted hazard ratios for all-cause mortality in those with mild (AHI: 5.0-14.9 events/h), moderate (AHI: 15.0-29.9 events/h), and severe (AHI: >or=30.0 events/h) sleep-disordered breathing were 0.93 (95% CI: 0.80-1.08), 1.17 (95% CI: 0.97-1.42), and 1.46 (95% CI: 1.14-1.86), respectively. Stratified analyses by sex and age showed that the increased risk of death associated with severe sleep-disordered breathing was statistically significant in men aged 40-70 y (hazard ratio: 2.09; 95% CI: 1.31-3.33). Measures of sleep-related intermittent hypoxemia, but not sleep fragmentation, were independently associated with all-cause mortality. Coronary artery disease-related mortality associated with sleep-disordered breathing showed a pattern of association similar to all-cause mortality. CONCLUSIONS: Sleep-disordered breathing is associated with all-cause mortality and specifically that due to coronary artery disease, particularly in men aged 40-70 y with severe sleep-disordered breathing. Please see later in the article for the Editors' Summary.
Keywords: Aged; Coronary Artery Disease; Female; Humans; Hypoxia; Male; Middle Aged; Odds Ratio; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Survival Analysis

Age and cystatin C in healthy adults: a collaborative study. - Odden, Michelle C; Tager, Ira B; Gansevoort, Ron T; Bakker, Stephan J L; Katz, Ronit; Fried, Linda F; Newman, Anne B; Canada, Robert B; Harris, Tamara; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G (Nephrol Dial Transplant, 2010)
BACKGROUND: Kidney function declines with age, but a substantial portion of this decline has been attributed to the higher prevalence of risk factors for kidney disease at older ages. The effect of age on kidney function has not been well described in a healthy population across a wide age spectrum. METHODS: The authors pooled individual-level cross-sectional data from 18 253 persons aged 28-100 years in four studies: the Cardiovascular Health Study; the Health, Aging and Body Composition Study; the Multi-Ethnic Study of Atherosclerosis and the Prevention of Renal and Vascular End-Stage Disease cohort. Kidney function was measured by cystatin C. Clinical risk factors for kidney disease included diabetes, hypertension, obesity, smoking, coronary heart disease, cerebrovascular disease, peripheral arterial disease and heart failure. RESULTS: Across the age range, there was a strong, non-linear association of age with cystatin C concentration. This association was substantial, even among participants free of clinical risk factors for kidney disease; mean cystatin C levels were 46% higher in participants 80 and older compared with those <40 years (1.06 versus 0.72 mg/L, P < 0.001). Participants with one or more risk factors had higher cystatin C concentrations for a given age, and the age association was slightly stronger (P < 0.001 for age and risk factor interaction). CONCLUSIONS: There is a strong, non-linear association of age with kidney function, even in healthy individuals. An important area for research will be to investigate the mechanisms that lead to deterioration of kidney function in apparently healthy persons.
Keywords: Adult; Aged; Aged, 80 and over; Cross-Sectional Studies; Cystatin C; Humans; Kidney; Middle Aged; Reference Values

Association of genome-wide variation with the risk of incident heart failure in adults of European and African ancestry: a prospective meta-analysis from the cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Smith, Nicholas L; Felix, Janine F; Morrison, Alanna C; Demissie, Serkalem; Glazer, Nicole L; Loehr, Laura R; Cupples, L Adrienne; Dehghan, Abbas; Lumley, Thomas; Rosamond, Wayne D; Lieb, Wolfgang; Rivadeneira, Fernando; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Although genetic factors contribute to the onset of heart failure (HF), no large-scale genome-wide investigation of HF risk has been published to date. We have investigated the association of 2,478,304 single-nucleotide polymorphisms with incident HF by meta-analyzing data from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Eligible participants for these analyses were of European or African ancestry and free of clinical HF at baseline. Each study independently conducted genome-wide scans and imputed data to the approximately 2.5 million single-nucleotide polymorphisms in HapMap. Within each study, Cox proportional hazards regression models provided age- and sex-adjusted estimates of the association between each variant and time to incident HF. Fixed-effect meta-analyses combined results for each single-nucleotide polymorphism from the 4 cohorts to produce an overall association estimate and P value. A genome-wide significance P value threshold was set a priori at 5.0x10(-7). During a mean follow-up of 11.5 years, 2526 incident HF events (12%) occurred in 20 926 European-ancestry participants. The meta-analysis identified a genome-wide significant locus at chromosomal position 15q22 (1.4x10(-8)), which was 58.8 kb from USP3. Among 2895 African-ancestry participants, 466 incident HF events (16%) occurred during a mean follow-up of 13.7 years. One genome-wide significant locus was identified at 12q14 (6.7x10(-8)), which was 6.3 kb from LRIG3. CONCLUSIONS: We identified 2 loci that were associated with incident HF and exceeded genome-wide significance. The findings merit replication in other community-based settings of incident HF.
Keywords: African Americans; Aged; Aged, 80 and over; Cohort Studies; Endopeptidases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Ubiquitin-Specific Proteases

Associations of PM10 with sleep and sleep-disordered breathing in adults from seven U.S. urban areas. - Zanobetti, Antonella; Redline, Susan; Schwartz, Joel; Rosen, Dennis; Patel, Sanjay; O'Connor, George T; Lebowitz, Michael; Coull, Brent A; Gold, Diane R (Am J Respir Crit Care Med, 2010)
RATIONALE: Sleep-disordered breathing (SDB), the recurrent episodic disruption of normal breathing during sleep, affects as much as 17% of U.S. adults, and may be more prevalent in poor urban environments. SDB and air pollution have been linked to increased cardiovascular diseases and mortality, but the association between pollution and SDB is poorly understood. OBJECTIVES: We used data from the Sleep Heart Health Study (SHHS), a U.S. multicenter cohort study assessing cardiovascular and other consequences of SDB, to examine whether particulate air matter less than 10 μm in aerodynamic diameter (PM(10)) was associated with SDB among persons 39 years of age and older. METHODS: Using baseline data from SHHS urban sites, outcomes included the following: the respiratory disturbance index (RDI); percentage of sleep time at less than 90% O(2) saturation; and sleep efficiency, measured by overnight in-home polysomnography. We applied a fixed-effect model containing a city effect, controlling for potential predictors. In all models we included both the 365-day moving averages of PM(10) and temperature (long-term effects) and the differences between the daily measures of these two predictors and their 365-day average (short-term effects). MEASUREMENTS AND MAIN RESULTS: In summer, increases in RDI or percentage of sleep time at less than 90% O(2) saturation, and decreases in sleep efficiency, were all associated with increases in short-term variation in PM(10). Over all seasons, we found that increased RDI was associated with an 11.5% (95% confidence interval: 1.96, 22.01) increase per interquartile range increase (25.5°F) in temperature. CONCLUSIONS: Reduction in air pollution exposure may decrease the severity of SDB and nocturnal hypoxemia and may improve cardiac risk.
Keywords: Adult; Aged; Aged, 80 and over; Air Pollutants; Air Pollution; Cities; Cohort Studies; Female; Humans; Male; Middle Aged; Multicenter Studies as Topic; Particle Size; Particulate Matter; Polysomnography; Seasons; Severity of Illness Index; Sleep; Sleep Apnea Syndromes; Temperature; United States; Urban Health

Common genetic variants associate with serum phosphorus concentration. - Kestenbaum, Bryan; Glazer, Nicole L; Köttgen, Anna; Felix, Janine F; Hwang, Shih-Jen; Liu, Yongmei; Lohman, Kurt; Kritchevsky, Stephen B; Hausman, Dorothy B; Petersen, Ann-Kristin; Gieger, Christian; Ried, Janina S; et al. (J Am Soc Nephrol, 2010)
Phosphorus is an essential mineral that maintains cellular energy and mineralizes the skeleton. Because complex actions of ion transporters and regulatory hormones regulate serum phosphorus concentrations, genetic variation may determine interindividual variation in phosphorus metabolism. Here, we report a comprehensive genome-wide association study of serum phosphorus concentration. We evaluated 16,264 participants of European ancestry from the Cardiovascular Heath Study, Atherosclerosis Risk in Communities Study, Framingham Offspring Study, and the Rotterdam Study. We excluded participants with an estimated GFR <45 ml/min per 1.73 m(2) to focus on phosphorus metabolism under normal conditions. We imputed genotypes to approximately 2.5 million single-nucleotide polymorphisms in the HapMap and combined study-specific findings using meta-analysis. We tested top polymorphisms from discovery cohorts in a 5444-person replication sample. Polymorphisms in seven loci with minor allele frequencies 0.08 to 0.49 associate with serum phosphorus concentration (P = 3.5 x 10(-16) to 3.6 x 10(-7)). Three loci were near genes encoding the kidney-specific type IIa sodium phosphate co-transporter (SLC34A1), the calcium-sensing receptor (CASR), and fibroblast growth factor 23 (FGF23), proteins that contribute to phosphorus metabolism. We also identified genes encoding phosphatases, kinases, and phosphodiesterases that have yet-undetermined roles in phosphorus homeostasis. In the replication sample, five of seven top polymorphisms associate with serum phosphorous concentrations (P < 0.05 for each). In conclusion, common genetic variants associate with serum phosphorus in the general population. Further study of the loci identified in this study may help elucidate mechanisms of phosphorus regulation.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Fibroblast Growth Factors; Gene Frequency; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Male; Middle Aged; Phosphorus; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing; Sex Factors; Sodium-Phosphate Cotransporter Proteins, Type IIa

Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

Common variants in the calcium-sensing receptor gene are associated with total serum calcium levels. - O'Seaghdha, Conall M; Yang, Qiong; Glazer, Nicole L; Leak, Tennille S; Dehghan, Abbas; Smith, Albert V; Kao, W H Linda; Lohman, Kurt; Hwang, Shih-Jen; Johnson, Andrew D; Hofman, Albert; Uitterlinden, André G; et al. (Hum Mol Genet, 2010)
Serum calcium levels are tightly regulated. We performed genome-wide association studies (GWAS) in population-based studies participating in the CHARGE Consortium to uncover common genetic variations associated with total serum calcium levels. GWAS of serum calcium concentrations was performed in 20 611 individuals of European ancestry for ∼2.5 million genotyped and imputed single-nucleotide polymorphisms (SNPs). The SNP with the lowest P-value was rs17251221 (P = 2.4 * 10(-22), minor allele frequency 14%) in the calcium-sensing receptor gene (CASR). This lead SNP was associated with higher serum calcium levels [0.06 mg/dl (0.015 mmol/l) per copy of the minor G allele] and accounted for 0.54% of the variance in serum calcium concentrations. The identification of variation in CASR that influences serum calcium concentration confirms the results of earlier candidate gene studies. The G allele of rs17251221 was also associated with higher serum magnesium levels (P = 1.2 * 10(-3)), lower serum phosphate levels (P = 2.8 * 10(-7)) and lower bone mineral density at the lumbar spine (P = 0.038), but not the femoral neck. No additional genomic loci contained SNPs associated at genome-wide significance (P < 5 * 10(-8)). These associations resemble clinical characteristics of patients with familial hypocalciuric hypercalcemia, an autosomal-dominant disease arising from rare inactivating mutations in the CASR gene. We conclude that common genetic variation in the CASR gene is associated with similar but milder features in the general population.
Keywords: Adult; Calcium; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing

C-reactive protein concentration and risk of coronary heart disease, stroke, and mortality: an individual participant meta-analysis. - Kaptoge, Stephen; Di Angelantonio, Emanuele; Lowe, Gordon; Pepys, Mark B; Thompson, Simon G; Collins, Rory; Danesh, John (Lancet, 2010)
BACKGROUND: Associations of C-reactive protein (CRP) concentration with risk of major diseases can best be assessed by long-term prospective follow-up of large numbers of people. We assessed the associations of CRP concentration with risk of vascular and non-vascular outcomes under different circumstances. METHODS: We meta-analysed individual records of 160 309 people without a history of vascular disease (ie, 1.31 million person-years at risk, 27 769 fatal or non-fatal disease outcomes) from 54 long-term prospective studies. Within-study regression analyses were adjusted for within-person variation in risk factor levels. RESULTS: Log(e) CRP concentration was linearly associated with several conventional risk factors and inflammatory markers, and nearly log-linearly with the risk of ischaemic vascular disease and non-vascular mortality. Risk ratios (RRs) for coronary heart disease per 1-SD higher log(e) CRP concentration (three-fold higher) were 1.63 (95% CI 1.51-1.76) when initially adjusted for age and sex only, and 1.37 (1.27-1.48) when adjusted further for conventional risk factors; 1.44 (1.32-1.57) and 1.27 (1.15-1.40) for ischaemic stroke; 1.71 (1.53-1.91) and 1.55 (1.37-1.76) for vascular mortality; and 1.55 (1.41-1.69) and 1.54 (1.40-1.68) for non-vascular mortality. RRs were largely unchanged after exclusion of smokers or initial follow-up. After further adjustment for fibrinogen, the corresponding RRs were 1.23 (1.07-1.42) for coronary heart disease; 1.32 (1.18-1.49) for ischaemic stroke; 1.34 (1.18-1.52) for vascular mortality; and 1.34 (1.20-1.50) for non-vascular mortality. INTERPRETATION: CRP concentration has continuous associations with the risk of coronary heart disease, ischaemic stroke, vascular mortality, and death from several cancers and lung disease that are each of broadly similar size. The relevance of CRP to such a range of disorders is unclear. Associations with ischaemic vascular disease depend considerably on conventional risk factors and other markers of inflammation. FUNDING: British Heart Foundation, UK Medical Research Council, BUPA Foundation, and GlaxoSmithKline.
Keywords: Alcohol Drinking; Biomarkers; Blood Pressure; Body Mass Index; C-Reactive Protein; Cholesterol; Coronary Disease; Databases, Factual; Diabetes Mellitus; Female; Fibrinogen; Humans; Interleukin-6; Leukocyte Count; Lung Diseases; Male; Middle Aged; Motor Activity; Neoplasms; Regression Analysis; Risk Assessment; Risk Factors; Serum Albumin; Sex Factors; Smoking; Stroke; Triglycerides

Diabetes mellitus, fasting blood glucose concentration, and risk of vascular disease: a collaborative meta-analysis of 102 prospective studies. - Sarwar, N; Gao, P; Seshasai, S R Kondapally; Gobin, R; Kaptoge, S; Di Angelantonio, E; Ingelsson, E; Lawlor, D A; Selvin, E; Stampfer, M; Stehouwer, C D A; Lewington, S; et al. (Lancet, 2010)
BACKGROUND: Uncertainties persist about the magnitude of associations of diabetes mellitus and fasting glucose concentration with risk of coronary heart disease and major stroke subtypes. We aimed to quantify these associations for a wide range of circumstances. METHODS: We undertook a meta-analysis of individual records of diabetes, fasting blood glucose concentration, and other risk factors in people without initial vascular disease from studies in the Emerging Risk Factors Collaboration. We combined within-study regressions that were adjusted for age, sex, smoking, systolic blood pressure, and body-mass index to calculate hazard ratios (HRs) for vascular disease. FINDINGS: Analyses included data for 698 782 people (52 765 non-fatal or fatal vascular outcomes; 8.49 million person-years at risk) from 102 prospective studies. Adjusted HRs with diabetes were: 2.00 (95% CI 1.83-2.19) for coronary heart disease; 2.27 (1.95-2.65) for ischaemic stroke; 1.56 (1.19-2.05) for haemorrhagic stroke; 1.84 (1.59-2.13) for unclassified stroke; and 1.73 (1.51-1.98) for the aggregate of other vascular deaths. HRs did not change appreciably after further adjustment for lipid, inflammatory, or renal markers. HRs for coronary heart disease were higher in women than in men, at 40-59 years than at 70 years and older, and with fatal than with non-fatal disease. At an adult population-wide prevalence of 10%, diabetes was estimated to account for 11% (10-12%) of vascular deaths. Fasting blood glucose concentration was non-linearly related to vascular risk, with no significant associations between 3.90 mmol/L and 5.59 mmol/L. Compared with fasting blood glucose concentrations of 3.90-5.59 mmol/L, HRs for coronary heart disease were: 1.07 (0.97-1.18) for lower than 3.90 mmol/L; 1.11 (1.04-1.18) for 5.60-6.09 mmol/L; and 1.17 (1.08-1.26) for 6.10-6.99 mmol/L. In people without a history of diabetes, information about fasting blood glucose concentration or impaired fasting glucose status did not significantly improve metrics of vascular disease prediction when added to information about several conventional risk factors. INTERPRETATION: Diabetes confers about a two-fold excess risk for a wide range of vascular diseases, independently from other conventional risk factors. In people without diabetes, fasting blood glucose concentration is modestly and non-linearly associated with risk of vascular disease. FUNDING: British Heart Foundation, UK Medical Research Council, and Pfizer.
Keywords: Adult; Aged; Blood Glucose; Coronary Disease; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Humans; Male; Middle Aged; Risk Factors; Stroke

Differential white blood cell count and type 2 diabetes: systematic review and meta-analysis of cross-sectional and prospective studies. - Gkrania-Klotsas, Effrossyni; Ye, Zheng; Cooper, Andrew J; Sharp, Stephen J; Luben, Robert; Biggs, Mary L; Chen, Liang-Kung; Gokulakrishnan, Kuppan; Hanefeld, Markolf; Ingelsson, Erik; Lai, Wen-An; Lin, Shih-Yi; et al. (PLoS One, 2010)
OBJECTIVE: Biological evidence suggests that inflammation might induce type 2 diabetes (T2D), and epidemiological studies have shown an association between higher white blood cell count (WBC) and T2D. However, the association has not been systematically investigated. RESEARCH DESIGN AND METHODS: Studies were identified through computer-based and manual searches. Previously unreported studies were sought through correspondence. 20 studies were identified (8,647 T2D cases and 85,040 non-cases). Estimates of the association of WBC with T2D were combined using random effects meta-analysis; sources of heterogeneity as well as presence of publication bias were explored. RESULTS: The combined relative risk (RR) comparing the top to bottom tertile of the WBC count was 1.61 (95% CI: 1.45; 1.79, p = 1.5*10(-18)). Substantial heterogeneity was present (I(2) = 83%). For granulocytes the RR was 1.38 (95% CI: 1.17; 1.64, p = 1.5*10(-4)), for lymphocytes 1.26 (95% CI: 1.02; 1.56, p = 0.029), and for monocytes 0.93 (95% CI: 0.68; 1.28, p = 0.67) comparing top to bottom tertile. In cross-sectional studies, RR was 1.74 (95% CI: 1.49; 2.02, p = 7.7*10(-13)), while in cohort studies it was 1.48 (95% CI: 1.22; 1.79, p = 7.7*10(-5)). We assessed the impact of confounding in EPIC-Norfolk study and found that the age and sex adjusted HR of 2.19 (95% CI: 1.74; 2.75) was attenuated to 1.82 (95% CI: 1.45; 2.29) after further accounting for smoking, T2D family history, physical activity, education, BMI and waist circumference. CONCLUSIONS: A raised WBC is associated with higher risk of T2D. The presence of publication bias and failure to control for all potential confounders in all studies means the observed association is likely an overestimate.
Keywords: Adult; Aged; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Leukocyte Count; Male; Middle Aged; Prospective Studies

European ancestry as a risk factor for atrial fibrillation in African Americans. - Marcus, Gregory M; Alonso, Alvaro; Peralta, Carmen A; Lettre, Guillaume; Vittinghoff, Eric; Lubitz, Steven A; Fox, Ervin R; Levitzky, Yamini S; Mehra, Reena; Kerr, Kathleen F; Deo, Rajat; Sotoodehnia, Nona; et al. (Circulation, 2010)
BACKGROUND: Despite a higher burden of standard atrial fibrillation (AF) risk factors, African Americans have a lower risk of AF than whites. It is unknown whether the higher risk is due to genetic or environmental factors. Because African Americans have varying degrees of European ancestry, we sought to test the hypothesis that European ancestry is an independent risk factor for AF. METHODS AND RESULTS: We studied whites (n=4543) and African Americans (n=822) in the Cardiovascular Health Study (CHS) and whites (n=10 902) and African Americans (n=3517) in the Atherosclerosis Risk in Communities (ARIC) Study (n=3517). Percent European ancestry in African Americans was estimated with 1747 ancestry informative markers from the Illumina custom ITMAT-Broad-CARe array. Among African Americans without baseline AF, 120 of 804 CHS participants and 181 of 3517 ARIC participants developed incident AF. A meta-analysis from the 2 studies revealed that every 10% increase in European ancestry increased the risk of AF by 13% (hazard ratio, 1.13; 95% confidence interval, 1.03 to 1.23; P=0.007). After adjustment for potential confounders, European ancestry remained a predictor of incident AF in each cohort alone, with a combined estimated hazard ratio for each 10% increase in European ancestry of 1.17 (95% confidence interval, 1.07 to 1.29; P=0.001). A second analysis using 3192 ancestry informative markers from a genome-wide Affymetrix 6.0 array in ARIC African Americans yielded similar results. CONCLUSIONS: European ancestry predicted risk of incident AF. Our study suggests that investigating genetic variants contributing to differential AF risk in individuals of African versus European ancestry will be informative.
Keywords: African Americans; Aged; Atrial Fibrillation; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Risk Factors

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Fucosyltransferase 2 (FUT2) non-secretor status is associated with Crohn's disease. - McGovern, Dermot P B; Jones, Michelle R; Taylor, Kent D; Marciante, Kristin; Yan, Xiaofei; Dubinsky, Marla; Ippoliti, Andy; Vasiliauskas, Eric; Berel, Dror; Derkowski, Carrie; Dutridge, Deb; Fleshner, Phil; et al. (Hum Mol Genet, 2010)
Genetic variation in both innate and adaptive immune systems is associated with Crohn's disease (CD) susceptibility, but much of the heritability to CD remains unknown. We performed a genome-wide association study (GWAS) in 896 CD cases and 3204 healthy controls all of Caucasian origin as defined by multidimensional scaling. We found supportive evidence for 21 out of 40 CD loci identified in a recent CD GWAS meta-analysis, including two loci which had only nominally achieved replication (rs4807569, 19p13; rs991804, CCL2/CCL7). In addition, we identified associations with genes involved in tight junctions/epithelial integrity (ASHL, ARPC1A), innate immunity (EXOC2), dendritic cell biology [CADM1 (IGSF4)], macrophage development (MMD2), TGF-beta signaling (MAP3K7IP1) and FUT2 (a physiological trait that regulates gastrointestinal mucosal expression of blood group A and B antigens) (rs602662, P=3.4x10(-5)). Twenty percent of Caucasians are 'non-secretors' who do not express ABO antigens in saliva as a result of the FUT2 W134X allele. We demonstrated replication in an independent cohort of 1174 CD cases and 357 controls between the four primary FUT2 single nucleotide polymorphisms (SNPs) and CD (rs602662, combined P-value 4.90x10(-8)) and also association with FUT2 W143X (P=2.6x10(-5)). Further evidence of the relevance of this locus to CD pathogenesis was demonstrated by the association of the original four SNPs and CD in the recently published CD GWAS meta-analysis (rs602662, P=0.001). These findings strongly implicate this locus in CD susceptibility and highlight the role of the mucus layer in the development of CD.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Cohort Studies; Crohn Disease; Female; Fucosyltransferases; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Genetic ancestry in lung-function predictions. - Kumar, Rajesh; Seibold, Max A; Aldrich, Melinda C; Williams, L Keoki; Reiner, Alex P; Colangelo, Laura; Galanter, Joshua; Gignoux, Christopher; Hu, Donglei; Sen, Saunak; Choudhry, Shweta; Peterson, Edward L; et al. (N Engl J Med, 2010)
BACKGROUND: Self-identified race or ethnic group is used to determine normal reference standards in the prediction of pulmonary function. We conducted a study to determine whether the genetically determined percentage of African ancestry is associated with lung function and whether its use could improve predictions of lung function among persons who identified themselves as African American. METHODS: We assessed the ancestry of 777 participants self-identified as African American in the Coronary Artery Risk Development in Young Adults (CARDIA) study and evaluated the relation between pulmonary function and ancestry by means of linear regression. We performed similar analyses of data for two independent cohorts of subjects identifying themselves as African American: 813 participants in the Health, Aging, and Body Composition (HABC) study and 579 participants in the Cardiovascular Health Study (CHS). We compared the fit of two types of models to lung-function measurements: models based on the covariates used in standard prediction equations and models incorporating ancestry. We also evaluated the effect of the ancestry-based models on the classification of disease severity in two asthma-study populations. RESULTS: African ancestry was inversely related to forced expiratory volume in 1 second (FEV(1)) and forced vital capacity in the CARDIA cohort. These relations were also seen in the HABC and CHS cohorts. In predicting lung function, the ancestry-based model fit the data better than standard models. Ancestry-based models resulted in the reclassification of asthma severity (based on the percentage of the predicted FEV(1)) in 4 to 5% of participants. CONCLUSIONS: Current predictive equations, which rely on self-identified race alone, may misestimate lung function among subjects who identify themselves as African American. Incorporating ancestry into normative equations may improve lung-function estimates and more accurately categorize disease severity. (Funded by the National Institutes of Health and others.)
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; Female; Forced Expiratory Volume; Genetic Markers; Genotype; Humans; Linear Models; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Reference Values; Respiratory Function Tests; Vital Capacity; Young Adult

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Genome-wide association studies of serum magnesium, potassium, and sodium concentrations identify six Loci influencing serum magnesium levels. - Meyer, Tamra E; Verwoert, Germaine C; Hwang, Shih-Jen; Glazer, Nicole L; Smith, Albert V; van Rooij, Frank J A; Ehret, Georg B; Boerwinkle, Eric; Felix, Janine F; Leak, Tennille S; Harris, Tamara B; Yang, Qiong; et al. (PLoS Genet, 2010)
Magnesium, potassium, and sodium, cations commonly measured in serum, are involved in many physiological processes including energy metabolism, nerve and muscle function, signal transduction, and fluid and blood pressure regulation. To evaluate the contribution of common genetic variation to normal physiologic variation in serum concentrations of these cations, we conducted genome-wide association studies of serum magnesium, potassium, and sodium concentrations using approximately 2.5 million genotyped and imputed common single nucleotide polymorphisms (SNPs) in 15,366 participants of European descent from the international CHARGE Consortium. Study-specific results were combined using fixed-effects inverse-variance weighted meta-analysis. SNPs demonstrating genome-wide significant (p<5 x 10(-8)) or suggestive associations (p<4 x 10(-7)) were evaluated for replication in an additional 8,463 subjects of European descent. The association of common variants at six genomic regions (in or near MUC1, ATP2B1, DCDC5, TRPM6, SHROOM3, and MDS1) with serum magnesium levels was genome-wide significant when meta-analyzed with the replication dataset. All initially significant SNPs from the CHARGE Consortium showed nominal association with clinically defined hypomagnesemia, two showed association with kidney function, two with bone mineral density, and one of these also associated with fasting glucose levels. Common variants in CNNM2, a magnesium transporter studied only in model systems to date, as well as in CNNM3 and CNNM4, were also associated with magnesium concentrations in this study. We observed no associations with serum sodium or potassium levels exceeding p<4 x 10(-7). Follow-up studies of newly implicated genomic loci may provide additional insights into the regulation and homeostasis of human serum magnesium levels.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Magnesium; Male; Middle Aged; Polymorphism, Single Nucleotide; Potassium; Sodium

Genome-wide association study identifies GPC5 as a novel genetic locus protective against sudden cardiac arrest. - Arking, Dan E; Reinier, Kyndaron; Post, Wendy; Jui, Jonathan; Hilton, Gina; O'Connor, Ashley; Prineas, Ronald J; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Rea, Thomas; Sotoodehnia, Nona; et al. (PLoS One, 2010)
BACKGROUND: Existing studies indicate a significant genetic component for sudden cardiac arrest (SCA) and genome-wide association studies (GWAS) provide an unbiased approach for identification of novel genes. We performed a GWAS to identify genetic determinants of SCA. METHODOLOGY/PRINCIPAL FINDINGS: We used a case-control design within the ongoing Oregon Sudden Unexpected Death Study (Oregon-SUDS). Cases (n = 424) were SCAs with coronary artery disease (CAD) among residents of Portland, OR (2002-07, population approximately 1,000,000) and controls (n = 226) were residents with CAD, but no history of SCA. All subjects were of White-European ancestry and GWAS was performed using Affymetrix 500K/5.0 and 6.0 arrays. High signal markers were genotyped in SCA cases (n = 521) identified from the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS) (combined n = 19,611). No SNPs reached genome-wide significance (p<5x10(-8)). SNPs at 6 loci were prioritized for follow-up primarily based on significance of p<10(-4) and proximity to a known gene (CSMD2, GPR37L1, LIN9, B4GALNT3, GPC5, and ZNF592). The minor allele of GPC5 (GLYPICAN 5, rs3864180) was associated with a lower risk of SCA in Oregon-SUDS, an effect that was also observed in ARIC/CHS whites (p<0.05) and blacks (p<0.04). In a combined Cox proportional hazards model analysis that adjusted for race, the minor allele exhibited a hazard ratio of 0.85 (95% CI 0.74 to 0.98; p<0.01). CONCLUSIONS/SIGNIFICANCE: A novel genetic locus for SCA, GPC5, was identified from Oregon-SUDS and successfully validated in the ARIC and CHS cohorts. Three other members of the Glypican family have been previously implicated in human disease, including cardiac conditions. The mechanism of this specific association requires further study.
Keywords: Aged; Alleles; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Ethnic Groups; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glypicans; Heart Diseases; Humans; Male; Middle Aged; Models, Genetic; Oligonucleotide Array Sequence Analysis; Oregon; Polymorphism, Single Nucleotide

Genomic variation associated with mortality among adults of European and African ancestry with heart failure: the cohorts for heart and aging research in genomic epidemiology consortium. - Morrison, Alanna C; Felix, Janine F; Cupples, L Adrienne; Glazer, Nicole L; Loehr, Laura R; Dehghan, Abbas; Demissie, Serkalem; Bis, Joshua C; Rosamond, Wayne D; Aulchenko, Yurii S; Wang, Ying A; Haritunians, Talin; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Prognosis and survival are significant concerns for individuals with heart failure (HF). To better understand the pathophysiology of HF prognosis, the association between 2,366,858 single-nucleotide polymorphisms (SNPs) and all-cause mortality was evaluated among individuals with incident HF from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Participants were 2526 individuals of European ancestry and 466 individuals of African ancestry who experienced an incident HF event during follow-up in the respective cohorts. Within each study, the association between genetic variants and time to mortality among individuals with HF was assessed by Cox proportional hazards models that included adjustment for sex and age at the time of the HF event. Prospective fixed-effect meta-analyses were conducted for the 4 study populations of European ancestry (N=1645 deaths) and for the 2 populations of African ancestry (N=281 deaths). Genome-wide significance was set at P=5.0x10(-7). Meta-analytic findings among individuals of European ancestry revealed 1 genome-wide significant locus on chromosome 3p22 in an intron of CKLF-like MARVEL transmembrane domain containing 7 (CMTM7, P=3.2x10(-7)). Eight additional loci in individuals of European ancestry and 4 loci in individuals of African ancestry were identified by high-signal SNPs (P<1.0x10(-5)) but did not meet genome-wide significance. CONCLUSIONS: This study identified a novel locus associated with all-cause mortality among individuals of European ancestry with HF. This finding warrants additional investigation, including replication, in other studies of HF.
Keywords: African Americans; Aged; Aged, 80 and over; Chemokines; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Failure; Humans; Introns; Male; MARVEL Domain-Containing Proteins; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Independent susceptibility markers for atrial fibrillation on chromosome 4q25. - Lubitz, Steven A; Sinner, Moritz F; Lunetta, Kathryn L; Makino, Seiko; Pfeufer, Arne; Rahman, Rosanna; Veltman, Caroline E; Barnard, John; Bis, Joshua C; Danik, Stephan P; Sonni, Akshata; Shea, Marisa A; et al. (Circulation, 2010)
BACKGROUND: Genetic variants on chromosome 4q25 are associated with atrial fibrillation (AF). We sought to determine whether there is more than 1 susceptibility signal at this locus. METHODS AND RESULTS: Thirty-four haplotype-tagging single-nucleotide polymorphisms (SNPs) at the 4q25 locus were genotyped in 790 case and 1177 control subjects from Massachusetts General Hospital and tested for association with AF. We replicated SNPs associated with AF after adjustment for the most significantly associated SNP in 5066 case and 30 661 referent subjects from the German Competence Network for Atrial Fibrillation, Atherosclerosis Risk In Communities Study, Cleveland Clinic Lone AF Study, Cardiovascular Health Study, and Rotterdam Study. All subjects were of European ancestry. A multimarker risk score composed of SNPs that tagged distinct AF susceptibility signals was constructed and tested for association with AF, and all results were subjected to meta-analysis. The previously reported SNP, rs2200733, was most significantly associated with AF (minor allele odds ratio 1.80, 95% confidence interval 1.50 to 2.15, P=1.2 x 10(-20)) in the discovery sample. Adjustment for rs2200733 genotype revealed 2 additional susceptibility signals marked by rs17570669 and rs3853445. A graded risk of AF was observed with an increasing number of AF risk alleles at SNPs that tagged these 3 susceptibility signals. CONCLUSIONS: We identified 2 novel AF susceptibility signals on chromosome 4q25. Consideration of multiple susceptibility signals at chromosome 4q25 identifies individuals with an increased risk of AF and may localize regulatory elements at the locus with biological relevance in the pathogenesis of AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Lipoprotein-associated phospholipase A(2) and risk of coronary disease, stroke, and mortality: collaborative analysis of 32 prospective studies. - Thompson, Alexander; Gao, Pei; Orfei, Lia; Watson, Sarah; Di Angelantonio, Emanuele; Kaptoge, Stephen; Ballantyne, Christie; Cannon, Christopher P; Criqui, Michael; Cushman, Mary; Hofman, Albert; Packard, Chris; et al. (Lancet, 2010)
BACKGROUND: Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), an inflammatory enzyme expressed in atherosclerotic plaques, is a therapeutic target being assessed in trials of vascular disease prevention. We investigated associations of circulating Lp-PLA(2) mass and activity with risk of coronary heart disease, stroke, and mortality under different circumstances. METHODS: With use of individual records from 79 036 participants in 32 prospective studies (yielding 17 722 incident fatal or non-fatal outcomes during 474 976 person-years at risk), we did a meta-analysis of within-study regressions to calculate risk ratios (RRs) per 1 SD higher value of Lp-PLA(2) or other risk factor. The primary outcome was coronary heart disease. FINDINGS: Lp-PLA(2) activity and mass were associated with each other (r=0.51, 95% CI 0.47-0.56) and proatherogenic lipids. We noted roughly log-linear associations of Lp-PLA(2) activity and mass with risk of coronary heart disease and vascular death. RRs, adjusted for conventional risk factors, were: 1.10 (95% CI 1.05-1.16) with Lp-PLA(2) activity and 1.11 (1.07-1.16) with Lp-PLA(2) mass for coronary heart disease; 1.08 (0.97-1.20) and 1.14 (1.02-1.27) for ischaemic stroke; 1.16 (1.09-1.24) and 1.13 (1.05-1.22) for vascular mortality; and 1.10 (1.04-1.17) and 1.10 (1.03-1.18) for non-vascular mortality, respectively. RRs with Lp-PLA(2) did not differ significantly in people with and without initial stable vascular disease, apart from for vascular death with Lp-PLA(2) mass. Adjusted RRs for coronary heart disease were 1.10 (1.02-1.18) with non-HDL cholesterol and 1.10 (1.00-1.21) with systolic blood pressure. INTERPRETATION: Lp-PLA(2) activity and mass each show continuous associations with risk of coronary heart disease, similar in magnitude to that with non-HDL cholesterol or systolic blood pressure in this population. Associations of Lp-PLA(2) mass and activity are not exclusive to vascular outcomes, and the vascular associations depend at least partly on lipids. FUNDING: UK Medical Research Council, GlaxoSmithKline, and British Heart Foundation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Blood Pressure; Coronary Disease; Female; Humans; Linear Models; Lipids; Male; Middle Aged; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Systole

A meta-analysis of four genome-wide association studies of survival to age 90 years or older: the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. - Newman, Anne B; Walter, Stefan; Lunetta, Kathryn L; Garcia, Melissa E; Slagboom, P Eline; Christensen, Kaare; Arnold, Alice M; Aspelund, Thor; Aulchenko, Yurii S; Benjamin, Emelia J; Christiansen, Lene; D'Agostino, Ralph B; et al. (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Genome-wide association studies (GWAS) may yield insights into longevity. METHODS: We performed a meta-analysis of GWAS in Caucasians from four prospective cohort studies: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Longevity was defined as survival to age 90 years or older (n = 1,836); the comparison group comprised cohort members who died between the ages of 55 and 80 years (n = 1,955). In a second discovery stage, additional genotyping was conducted in the Leiden Longevity Study cohort and the Danish 1905 cohort. RESULTS: There were 273 single-nucleotide polymorphism (SNP) associations with p < .0001, but none reached the prespecified significance level of 5 x 10(-8). Of the most significant SNPs, 24 were independent signals, and 16 of these SNPs were successfully genotyped in the second discovery stage, with one association for rs9664222, reaching 6.77 x 10(-7) for the combined meta-analysis of CHARGE and the stage 2 cohorts. The SNP lies in a region near MINPP1 (chromosome 10), a well-conserved gene involved in regulation of cellular proliferation. The minor allele was associated with lower odds of survival past age 90 (odds ratio = 0.82). Associations of interest in a homologue of the longevity assurance gene (LASS3) and PAPPA2 were not strengthened in the second stage. CONCLUSION: Survival studies of larger size or more extreme or specific phenotypes may support or refine these initial findings.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Cohort Studies; Confidence Intervals; Female; Genome-Wide Association Study; Genotype; Humans; Longevity; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide

A novel approach to prediction of mild obstructive sleep disordered breathing in a population-based sample: the Sleep Heart Health Study. - Caffo, Brian; Diener-West, Marie; Punjabi, Naresh M; Samet, Jonathan (Sleep, 2010)
This manuscript considers a data-mining approach for the prediction of mild obstructive sleep disordered breathing, defined as an elevated respiratory disturbance index (RDI), in 5,530 participants in a community-based study, the Sleep Heart Health Study. The prediction algorithm was built using modern ensemble learning algorithms, boosting in specific, which allowed for assessing potential high-dimensional interactions between predictor variables or classifiers. To evaluate the performance of the algorithm, the data were split into training and validation sets for varying thresholds for predicting the probability of a high RDI (≥7 events per hour in the given results). Based on a moderate classification threshold from the boosting algorithm, the estimated post-test odds of a high RDI were 2.20 times higher than the pre-test odds given a positive test, while the corresponding post-test odds were decreased by 52% given a negative test (sensitivity and specificity of 0.66 and 0.70, respectively). In rank order, the following variables had the largest impact on prediction performance: neck circumference, body mass index, age, snoring frequency, waist circumference, and snoring loudness.
Keywords: Age Factors; Aged; Algorithms; Body Mass Index; Cohort Studies; Female; Humans; Male; Middle Aged; Predictive Value of Tests; Risk Factors; ROC Curve; Sleep Apnea Syndromes; Snoring; Waist Circumference

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

Obstructive sleep apnea-hypopnea and incident stroke: the sleep heart health study. - Redline, Susan; Yenokyan, Gayane; Gottlieb, Daniel J; Shahar, Eyal; O'Connor, George T; Resnick, Helaine E; Diener-West, Marie; Sanders, Mark H; Wolf, Philip A; Geraghty, Estella M; Ali, Tauqeer; Lebowitz, Michael; et al. (Am J Respir Crit Care Med, 2010)
RATIONALE: Although obstructive sleep apnea is associated with physiological perturbations that increase risk of hypertension and are proatherogenic, it is uncertain whether sleep apnea is associated with increased stroke risk in the general population. OBJECTIVES: To quantify the incidence of ischemic stroke with sleep apnea in a community-based sample of men and women across a wide range of sleep apnea. METHODS: Baseline polysomnography was performed between 1995 and 1998 in a longitudinal cohort study. The primary exposure was the obstructive apnea-hypopnea index (OAHI) and outcome was incident ischemic stroke. MEASUREMENTS AND MAIN RESULTS: A total of 5,422 participants without a history of stroke at the baseline examination and untreated for sleep apnea were followed for a median of 8.7 years. One hundred ninety-three ischemic strokes were observed. In covariate-adjusted Cox proportional hazard models, a significant positive association between ischemic stroke and OAHI was observed in men (P value for linear trend: P = 0.016). Men in the highest OAHI quartile (>19) had an adjusted hazard ratio of 2.86 (95% confidence interval, 1.1-7.4). In the mild to moderate range (OAHI, 5-25), each one-unit increase in OAHI in men was estimated to increase stroke risk by 6% (95% confidence interval, 2-10%). In women, stroke was not significantly associated with OAHI quartiles, but increased risk was observed at an OAHI greater than 25. CONCLUSIONS: The strong adjusted association between ischemic stroke and OAHI in community-dwelling men with mild to moderate sleep apnea suggests that this is an appropriate target for future stroke prevention trials.
Keywords: Aged; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Proportional Hazards Models; Prospective Studies; Severity of Illness Index; Sex Factors; Sleep Apnea, Obstructive; Stroke

Prevalence of asymptomatic carotid artery stenosis in the general population: an individual participant data meta-analysis. - de Weerd, Marjolein; Greving, Jacoba P; Hedblad, Bo; Lorenz, Matthias W; Mathiesen, Ellisiv B; O'Leary, Daniel H; Rosvall, Maria; Sitzer, Matthias; Buskens, Erik; Bots, Michiel L (Stroke, 2010)
BACKGROUND AND PURPOSE: In the discussion on the cost-effectiveness of screening, precise estimates of severe asymptomatic carotid stenosis are vital. Accordingly, we assessed the prevalence of moderate and severe asymptomatic carotid stenosis by age and sex using pooled cohort data. METHODS: We performed an individual participant data meta-analysis (23 706 participants) of 4 population-based studies (Malmö Diet and Cancer Study, Tromsø, Carotid Atherosclerosis Progression Study, and Cardiovascular Health Study). Outcomes of interest were asymptomatic moderate (> or =50%) and severe carotid stenosis (> or =70%). RESULTS: Prevalence of moderate asymptomatic carotid stenosis ranged from 0.2% (95% CI, 0.0% to 0.4%) in men aged <50 years to 7.5% (5.2% to 10.5%) in men aged > or =80 years. For women, this prevalence increased from 0% (0% to 0.2%) to 5.0% (3.1% to 7.5%). Prevalence of severe asymptomatic carotid stenosis ranged from 0.1% (0.0% to 0.3%) in men aged <50 years to 3.1% (1.7% to 5.3%) in men aged > or =80. For women, this prevalence increased from 0% (0.0% to 0.2%) to 0.9% (0.3% to 2.4%). CONCLUSIONS: The prevalence of severe asymptomatic carotid stenosis in the general population ranges from 0% to 3.1%, which is useful information in the discussion on the cost-effectiveness of screening.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Carotid Stenosis; Female; Humans; Male; Mass Screening; Middle Aged; Prevalence; Severity of Illness Index; Sex Factors

Prospective study of obstructive sleep apnea and incident coronary heart disease and heart failure: the sleep heart health study. - Gottlieb, Daniel J; Yenokyan, Gayane; Newman, Anne B; O'Connor, George T; Punjabi, Naresh M; Quan, Stuart F; Redline, Susan; Resnick, Helaine E; Tong, Elisa K; Diener-West, Marie; Shahar, Eyal (Circulation, 2010)
BACKGROUND: Clinic-based observational studies in men have reported that obstructive sleep apnea is associated with an increased incidence of coronary heart disease. The objective of this study was to assess the relation of obstructive sleep apnea to incident coronary heart disease and heart failure in a general community sample of adult men and women. METHODS AND RESULTS: A total of 1927 men and 2495 women > or =40 years of age and free of coronary heart disease and heart failure at the time of baseline polysomnography were followed up for a median of 8.7 years in this prospective longitudinal epidemiological study. After adjustment for multiple risk factors, obstructive sleep apnea was a significant predictor of incident coronary heart disease (myocardial infarction, revascularization procedure, or coronary heart disease death) only in men < or =70 years of age (adjusted hazard ratio 1.10 [95% confidence interval 1.00 to 1.21] per 10-unit increase in apnea-hypopnea index [AHI]) but not in older men or in women of any age. Among men 40 to 70 years old, those with AHI > or =30 were 68% more likely to develop coronary heart disease than those with AHI <5. Obstructive sleep apnea predicted incident heart failure in men but not in women (adjusted hazard ratio 1.13 [95% confidence interval 1.02 to 1.26] per 10-unit increase in AHI). Men with AHI > or =30 were 58% more likely to develop heart failure than those with AHI <5. CONCLUSIONS: Obstructive sleep apnea is associated with an increased risk of incident heart failure in community-dwelling middle-aged and older men; its association with incident coronary heart disease in this sample is equivocal.
Keywords: Adult; Aged; Coronary Disease; Female; Heart Failure; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Proportional Hazards Models; Prospective Studies; Sleep Apnea, Obstructive; Survival Analysis

Reproductive history, hormone replacement, and incidence of venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology. - Ohira, Tetsuya; Folsom, Aaron R; Cushman, Mary; White, Richard H; Hannan, Peter J; Rosamond, Wayne D; Heckbert, Susan R (Br J Haematol, 2010)
Numerous studies have established that hormone replacement therapy increases the risk of venous thromboembolism (VTE), but an association of endogenous oestrogen exposure with the incidence of VTE is not fully established. Using a prospective design combining the Atherosclerosis Risk in Communities and the Cardiovascular Health Study cohort, we studied the 12-year risk of VTE in relation to hormone replacement therapy use, age at menopause, parity number, and type of menopause in 8236 post-menopausal women. There were no significant associations of age at menopause, parity number, or type of menopause with incidence of VTE. Women currently using hormone replacement had a 1.6-times higher multivariate-adjusted rate ratio (RR) of VTE compared with those without hormone use in the time-dependent model (RR=1.60, 95% confidence interval [CI], 1.06-2.36; Population attributable fraction=6.7%, 95%CI, 1.0-10.3). When we excluded women with 1-year or more duration of hormone therapy at baseline, the association was stronger (RR=2.02, 95%CI, 1.31-3.12). The multivariate-adjusted RRs of VTE for current users tended to be higher in those with idiopathic VTE (RR=2.40, 95%CI, 1.40-4.12) than those with secondary VTE (RR=1.08, 95%CI, 0.63-1.85). Hormone replacement therapy is associated with increased risk of VTE, but reproductive history markers of endogenous oestrogen exposure were not associated with VTE.
Keywords: Age Factors; Aged; Epidemiologic Methods; Estrogen Replacement Therapy; Female; Humans; Male; Middle Aged; Parity; Pregnancy; Reproductive History; United States; Venous Thromboembolism

Serum albumin and risk of venous thromboembolism. - Folsom, Aaron R; Lutsey, Pamela L; Heckbert, Susan R; Cushman, Mary (Thromb Haemost, 2010)
The incidence of venous thromboembolism (VTE) is increased in patients with albuminuria. However, whether a low serum albumin concentration is associated with increased risk of VTE has been a matter of controversy. We determined the association of serum albumin with VTE incidence in two large, prospective, population-based cohorts: the Atherosclerosis Risk in Communities (ARIC) Study (n = 15,300) and the Cardiovascular Health Study (CHS) (n = 5,400). Validated VTE occurrence (n = 462 in ARIC and n = 174 in CHS) was ascertained during follow-up. In both studies, after adjustment for age, sex, race, use of hormone replacement therapy, estimated glomerular filtration rate, history of cancer, and diabetes, serum albumin tended to be associated inversely with VTE. The adjusted hazard ratio per standard deviation lower albumin was 1.18 (95% confidence interval [CI] = 1.08, 1.31) in ARIC and 1.10 (95% CI = 0.94, 1.29) in CHS. The hazard ratio for albumin below (vs. above) the fifth percentile was 1.28 (95% CI = 0.90, 1.84) in ARIC and 1.80 (95% CI = 1.11, 2.93) in CHS. In conclusion, low serum albumin was a modest marker of increased VTE risk. The observed association likely does not reflect cause and effect, but rather that low serum albumin reflects a hyperinflammatory or hypercoagulable state. Whether this association has clinical relevance warrants further study.
Keywords: Aged; Biomarkers; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Risk Factors; Serum Albumin; United States; Venous Thromboembolism

Significance of the amyloidogenic transthyretin Val 122 Ile allele in African Americans in the Arteriosclerosis Risk in Communities (ARIC) and Cardiovascular Health (CHS) Studies. - Buxbaum, Joel; Alexander, Alice; Koziol, James; Tagoe, Clement; Fox, Ervin; Kitzman, Dalane (Am Heart J, 2010)
BACKGROUND: Many African Americans carry an amyloidogenic transthyretin mutation (TTR V122I), with a high risk for cardiac TTR amyloid deposition after the age of 65 years. We wished to determine the allele frequency and its clinical penetrance in community-dwelling African Americans. METHODS: Five thousand consenting African Americans, aged 41 to 93 years, in 2 community studies of cardiovascular risk (CHS and ARIC) were included in the study. The following were performed: genotyping of banked DNA for TTR V122I allele status and review of cardiovascular and demographic parameters in CHS and ARIC databases, with statistical comparisons of the frequency of congestive heart failure, survival, and occurrence of features of cardiac amyloidosis in carriers of the amyloidogenic allele and controls. RESULTS: One hundred nineteen (3.23%) of 3,712 ARIC and 17 (2.12%) of 805 CHS African Americans carried TTR V122I. After the age of 65 years (CHS), the frequencies of congestive heart failure (38% vs 15%, relative risk 2.62, P = .04) and mortality (76% vs 53%, relative risk 1.46, P = .08) were higher in V122I allele carriers than in age-, gender- and ethnically matched controls. In ARIC (all subjects <65 years old), there were no differences between carriers and noncarriers in mortality, frequency of congestive heart failure, or findings consistent with cardiac amyloidosis. CONCLUSIONS: Heterozygosity for the amyloidogenic TTR V122I mutation is relatively common in community-dwelling African Americans. Before the age of 65 years, the allele has no discernible impact on cardiac function or mortality. After the age of 70 years, carriers show a higher frequency of congestive failure and greater mortality with more echocardiographic evidence suggestive of cardiac amyloidosis, findings consistent with age-dependent clinical penetrance of this autosomal dominant gene.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Amyloidosis; Female; Gene Frequency; Heart Diseases; Humans; Isoleucine; Kaplan-Meier Estimate; Male; Middle Aged; Mutation; Prealbumin; Ultrasonography; Valine

Sleep disturbances, quality of life, and ethnicity: the Sleep Heart Health Study. - Baldwin, Carol M; Ervin, Ann-Margret; Mays, Mary Z; Robbins, John; Shafazand, Shirin; Walsleben, Joyce; Weaver, Terri (J Clin Sleep Med, 2010)
STUDY OBJECTIVES: To compare health-related quality of life (HR-QOL) across subgroups defined by sleep disturbances and ethnicity. METHODS: Men (47%) and women (53%) Sleep Heart Health Study participants age 40 and older (N = 5237) underwent overnight polysomnography and completed self-report questionnaires on symptoms of sleep disturbances. The physical and mental composite scales (PCS and MCS) of the Medical Outcomes Study 36-item short form survey assessed HR-QOL and were compared to sleep data. RESULTS: Participants self-identified as Caucasian/White (n = 4482, 86%), African American/Black (n = 490, 9%), or Hispanic/Mexican American (n = 265, 5%). The prevalence of obstructive sleep apnea (OSA) was 17%, frequent snoring was 34%, difficulty initiating or maintaining sleep (DIMS; insomnia symptoms) was 30%, and excessive daytime sleepiness (EDS) was 25%. African American participants with frequent snoring, insomnia symptoms, or EDS had significantly poorer physical health compared to Caucasians (p < 0.001). Hispanics with frequent snoring, insomnia symptoms, or EDS had significantly poorer mental health than Caucasian participants (p <0.001). Neither PCS nor MCS scores differed significantly across ethnic subgroups for participants with moderate to severe OSA (respiratory disturbance index > 15, 4% desaturation). CONCLUSIONS: Across ethnic/racial subgroups, sleep disturbances are associated with worse physical and better mental HR-QOL than the U.S. norm, but this relationship may be moderated by comorbid health conditions. This study replicates and extends prior research indicating differences among minority and non-minority participants and highlights the need for future studies of sleep disturbances with larger samples of minorities that control for comorbid health conditions.
Keywords: African Americans; Cohort Studies; Ethnic Groups; European Continental Ancestry Group; Female; Health Status; Heart Diseases; Hispanic Americans; Humans; Longitudinal Studies; Male; Mental Health; Middle Aged; Polysomnography; Prevalence; Quality of Life; Sleep Apnea, Obstructive; Sleep Initiation and Maintenance Disorders; Sleep Wake Disorders; Snoring; Surveys and Questionnaires; United States

Sleepiness, quality of life, and sleep maintenance in REM versus non-REM sleep-disordered breathing. - Chami, Hassan A; Baldwin, Carol M; Silverman, Angela; Zhang, Ying; Rapoport, David; Punjabi, Naresh M; Gottlieb, Daniel J (Am J Respir Crit Care Med, 2010)
RATIONALE: The impact of REM-predominant sleep-disordered breathing (SDB) on sleepiness, quality of life (QOL), and sleep maintenance is uncertain. OBJECTIVE: To evaluate the association of SDB during REM sleep with daytime sleepiness, health-related QOL, and difficulty maintaining sleep, in comparison to their association with SDB during non-REM sleep in a community-based cohort. METHODS: Cross-sectional analysis of 5,649 Sleep Heart Health Study participants (mean age 62.5 [SD = 10.9], 52.6% women, 22.6% ethnic minorities). SDB during REM and non-REM sleep was quantified using polysomnographically derived apnea-hypopnea index in REM (AHI(REM)) and non-REM (AHI(NREM)) sleep. Sleepiness, sleep maintenance, and QOL were respectively quantified using the Epworth Sleepiness Scale (ESS), the Sleep Heart Health Study Sleep Habit Questionnaire, and the physical and mental composites scales of the Medical Outcomes Study Short Form (SF)-36. MEASUREMENTS AND MAIN RESULTS: AHI(REM) was not associated with the ESS scores or the physical and mental components scales scores of the SF-36 after adjusting for demographics, body mass index, and AHI(NREM) x AHI(REM) was not associated with frequent difficulty maintaining sleep or early awakening from sleep. AHI(NREM) was associated with the ESS score (beta = 0.25; 95% confidence interval [CI], 0.16 to 0.34) and the physical (beta = -0.12; 95% CI, -0.42 to -0.01) and mental (beta = -0.20; 95% CI, -0.20 to -0.01) components scores of the SF-36 adjusting for demographics, body mass index, and AHI(REM). CONCLUSIONS: In a community-based sample of middle-aged and older adults, REM-predominant SDB is not independently associated with daytime sleepiness, impaired health-related QOL, or self-reported sleep disruption.
Keywords: Aged; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Quality of Life; Sleep; Sleep Apnea Syndromes; Sleep, REM

Study of the relationship between the interleukin-6 gene and obstructive sleep apnea. - Larkin, Emma K; Patel, Sanjay R; Zhu, Xiaofeng; Tracy, Russell P; Jenny, Nancy S; Reiner, Alex P; Walston, Jeremy; Redline, Susan (Clin Transl Sci, 2010)
Keywords: Adult; African Americans; Alleles; Female; Humans; Interleukin-6; Male; Middle Aged; Polymorphism, Single Nucleotide; Sleep Apnea, Obstructive

Subclinical hypothyroidism and the risk of coronary heart disease and mortality. - Rodondi, Nicolas; den Elzen, Wendy P J; Bauer, Douglas C; Cappola, Anne R; Razvi, Salman; Walsh, John P; Asvold, Bjørn O; Iervasi, Giorgio; Imaizumi, Misa; Collet, Tinh-Hai; Bremner, Alexandra; Maisonneuve, Patrick; et al. (JAMA, 2010)
CONTEXT: Data regarding the association between subclinical hypothyroidism and cardiovascular disease outcomes are conflicting among large prospective cohort studies. This might reflect differences in participants' age, sex, thyroid-stimulating hormone (TSH) levels, or preexisting cardiovascular disease. OBJECTIVE: To assess the risks of coronary heart disease (CHD) and total mortality for adults with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (1950 to May 31, 2010) were searched without language restrictions for prospective cohort studies with baseline thyroid function and subsequent CHD events, CHD mortality, and total mortality. The reference lists of retrieved articles also were searched. DATA EXTRACTION: Individual data on 55,287 participants with 542,494 person-years of follow-up between 1972 and 2007 were supplied from 11 prospective cohorts in the United States, Europe, Australia, Brazil, and Japan. The risk of CHD events was examined in 25,977 participants from 7 cohorts with available data. Euthyroidism was defined as a TSH level of 0.50 to 4.49 mIU/L. Subclinical hypothyroidism was defined as a TSH level of 4.5 to 19.9 mIU/L with normal thyroxine concentrations. RESULTS: Among 55,287 adults, 3450 had subclinical hypothyroidism (6.2%) and 51,837 had euthyroidism. During follow-up, 9664 participants died (2168 of CHD), and 4470 participants had CHD events (among 7 studies). The risk of CHD events and CHD mortality increased with higher TSH concentrations. In age- and sex-adjusted analyses, the hazard ratio (HR) for CHD events was 1.00 (95% confidence interval [CI], 0.86-1.18) for a TSH level of 4.5 to 6.9 mIU/L (20.3 vs 20.3/1000 person-years for participants with euthyroidism), 1.17 (95% CI, 0.96-1.43) for a TSH level of 7.0 to 9.9 mIU/L (23.8/1000 person-years), and 1.89 (95% CI, 1.28-2.80) for a TSH level of 10 to 19.9 mIU/L (n = 70 events/235; 38.4/1000 person-years; P <.001 for trend). The corresponding HRs for CHD mortality were 1.09 (95% CI, 0.91-1.30; 5.3 vs 4.9/1000 person-years for participants with euthyroidism), 1.42 (95% CI, 1.03-1.95; 6.9/1000 person-years), and 1.58 (95% CI, 1.10-2.27, n = 28 deaths/333; 7.7/1000 person-years; P = .005 for trend). Total mortality was not increased among participants with subclinical hypothyroidism. Results were similar after further adjustment for traditional cardiovascular risk factors. Risks did not significantly differ by age, sex, or preexisting cardiovascular disease. CONCLUSIONS: Subclinical hypothyroidism is associated with an increased risk of CHD events and CHD mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Coronary Disease; Female; Humans; Hypothyroidism; Male; Middle Aged; Mortality; Prospective Studies; Risk; Thyrotropin; Young Adult

Utility of sleep stage transitions in assessing sleep continuity. - Laffan, Alison; Caffo, Brian; Swihart, Bruce J; Punjabi, Naresh M (Sleep, 2010)
STUDY OBJECTIVES: Sleep continuity is commonly assessed with polysomnographic measures such as sleep efficiency, sleep stage percentages, and the arousal index. The aim of this study was to examine whether the transition rate between different sleep stages could be used as an index of sleep continuity to predict self-reported sleep quality independent of other commonly used metrics. DESIGN AND SETTING: Analysis of the Sleep Heart Health Study polysomnographic data. PARTICIPANTS: A community cohort. MEASUREMENTS AND RESULTS: Sleep recordings on 5,684 participants were deemed to be of sufficient quality to allow visual scoring of NREM and REM sleep. For each participant, we tabulated the frequency of transitions between wake, NREM sleep, and REM sleep. An overall transition rate was determined as the number of all transitions per hour sleep. Stage-specific transition rates between wake, NREM sleep, and REM sleep were also determined. A 5-point Likert scale was used to assess the subjective experience of restless and light sleep the morning after the sleep study. Multivariable regression models showed that a high overall sleep stage transition rate was associated with restless and light sleep independent of several covariates including total sleep time, percentages of sleep stages, wake time after sleep onset, and the arousal index. Compared to the lowest quartile of the overall transition rate (<7.76 events/h), the odds ratios for restless sleep were 1.27, 1.42, and 1.38, for the second (7.77-10.10 events/h), third (10.11-13.34 events/h), and fourth (≥13.35 events/h) quartiles, respectively. Analysis of stage-specific transition rates showed that transitions between wake and NREM sleep were also independently associated with restless and light sleep. CONCLUSIONS: Assessing overall and stage-specific transition rates provides a complementary approach for assessing sleep continuity. Incorporating such measures, along with conventional metrics, could yield useful insights into the significance of sleep continuity for clinical outcomes.
Keywords: Age Factors; Aged; Arousal; Body Mass Index; Cohort Studies; Female; Humans; Male; Middle Aged; Polysomnography; Predictive Value of Tests; Risk Factors; Sex Factors; Sleep Stages; Sleep Wake Disorders

Validation of an atrial fibrillation risk algorithm in whites and African Americans. - Schnabel, Renate B; Aspelund, Thor; Li, Guo; Sullivan, Lisa M; Suchy-Dicey, Astrid; Harris, Tamara B; Pencina, Michael J; D'Agostino, Ralph B; Levy, Daniel; Kannel, William B; Wang, Thomas J; Kronmal, Richard A; et al. (Arch Intern Med, 2010)
BACKGROUND: We sought to validate a recently published risk algorithm for incident atrial fibrillation (AF) in independent cohorts and other racial groups. METHODS: We evaluated the performance of a Framingham Heart Study (FHS)-derived risk algorithm modified for 5-year incidence of AF in the FHS (n = 4764 participants) and 2 geographically and racially diverse cohorts in the age range 45 to 95 years: AGES (the Age, Gene/Environment Susceptibility-Reykjavik Study) (n = 4238) and CHS (the Cardiovascular Health Study) (n = 5410, of whom 874 [16.2%] were African Americans). The risk algorithm included age, sex, body mass index, systolic blood pressure, electrocardiographic PR interval, hypertension treatment, and heart failure. RESULTS: We found 1359 incident AF events in 100 074 person-years of follow-up. Unadjusted 5-year event rates differed by cohort (AGES, 12.8 cases/1000 person-years; CHS whites, 22.7 cases/1000 person-years; and FHS, 4.5 cases/1000 person-years) and by race (CHS African Americans, 18.4 cases/1000 person-years). The strongest risk factors in all samples were age and heart failure. The relative risks for incident AF associated with risk factors were comparable across cohorts and race groups. After recalibration for baseline incidence and risk factor distribution, the Framingham algorithm, reported in C statistic, performed reasonably well in all samples: AGES, 0.67 (95% confidence interval [CI], 0.64-0.71); CHS whites, 0.68 (95% CI, 0.66-0.70); and CHS African Americans, 0.66 (95% CI, 0.61-0.71). Risk factors combined in the algorithm explained between 47.0% (AGES) and 63.6% (FHS) of the population-attributable risk. CONCLUSIONS: Risk of incident AF in community-dwelling whites and African Americans can be assessed reliably by routinely available and potentially modifiable clinical variables. Seven risk factors accounted for up to 64% of risk.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Algorithms; Atrial Fibrillation; Blood Pressure; Body Mass Index; Cohort Studies; Electrocardiography; Europe; European Continental Ancestry Group; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Incidence; Kaplan-Meier Estimate; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sex Factors; Systole; United States

Association of eGFR-Related Loci Identified by GWAS with Incident CKD and ESRD. - Böger, Carsten A; Gorski, Mathias; Li, Man; Hoffmann, Michael M; Huang, Chunmei; Yang, Qiong; Teumer, Alexander; Krane, Vera; O'Seaghdha, Conall M; Kutalik, Zoltán; Wichmann, H-Erich; Haak, Thomas; et al. (PLoS Genet, 2011)
Family studies suggest a genetic component to the etiology of chronic kidney disease (CKD) and end stage renal disease (ESRD). Previously, we identified 16 loci for eGFR in genome-wide association studies, but the associations of these single nucleotide polymorphisms (SNPs) for incident CKD or ESRD are unknown. We thus investigated the association of these loci with incident CKD in 26,308 individuals of European ancestry free of CKD at baseline drawn from eight population-based cohorts followed for a median of 7.2 years (including 2,122 incident CKD cases defined as eGFR <60ml/min/1.73m(2) at follow-up) and with ESRD in four case-control studies in subjects of European ancestry (3,775 cases, 4,577 controls). SNPs at 11 of the 16 loci (UMOD, PRKAG2, ANXA9, DAB2, SHROOM3, DACH1, STC1, SLC34A1, ALMS1/NAT8, UBE2Q2, and GCKR) were associated with incident CKD; p-values ranged from p = 4.1e-9 in UMOD to p = 0.03 in GCKR. After adjusting for baseline eGFR, six of these loci remained significantly associated with incident CKD (UMOD, PRKAG2, ANXA9, DAB2, DACH1, and STC1). SNPs in UMOD (OR = 0.92, p = 0.04) and GCKR (OR = 0.93, p = 0.03) were nominally associated with ESRD. In summary, the majority of eGFR-related loci are either associated or show a strong trend towards association with incident CKD, but have modest associations with ESRD in individuals of European descent. Additional work is required to characterize the association of genetic determinants of CKD and ESRD at different stages of disease progression.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Chronic Disease; Creatinine; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Association Studies; Humans; Kidney Diseases; Kidney Failure, Chronic; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptor, Epidermal Growth Factor; Uromodulin

Association of genetic variants and incident coronary heart disease in multiethnic cohorts: the PAGE study. - Franceschini, Nora; Carty, Cara; Bůzková, Petra; Reiner, Alex P; Garrett, Tiana; Lin, Yi; Vöckler, Jens-S; Hindorff, Lucia A; Cole, Shelley A; Boerwinkle, Eric; Lin, Dan-Yu; Bookman, Ebony; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: Genome-wide association studies identified several single nucleotide polymorphisms (SNP) associated with prevalent coronary heart disease (CHD), but less is known of associations with incident CHD. The association of 13 published CHD SNPs was examined in 5 ancestry groups of 4 large US prospective cohorts. METHODS AND RESULTS: The analyses included incident coronary events over an average 9.1 to 15.7 follow-up person-years in up to 26 617 white individuals (6626 events), 8018 black individuals (914 events), 1903 Hispanic individuals (113 events), 3669 American Indian individuals (595 events), and 885 Asian/Pacific Islander individuals (66 events). We used Cox proportional hazards models (with additive mode of inheritance) adjusted for age, sex, and ancestry (as needed). Nine loci were statistically associated with incident CHD events in white participants: 9p21 (rs10757278; P=4.7 × 10(-41)), 16q23.1 (rs2549513; P=0.0004), 6p24.1 (rs499818; P=0.0002), 2q36.3 (rs2943634; P=6.7 × 10(-6)), MTHFD1L (rs6922269, P=5.1 × 10(-10)), APOE (rs429358; P=2.7×10(-18)), ZNF627 (rs4804611; P=5.0 × 10(-8)), CXCL12 (rs501120; P=1.4 × 10(-6)) and LPL (rs268; P=2.7 × 10(-17)). The 9p21 region showed significant between-study heterogeneity, with larger effects in individuals age 55 years or younger and in women. Inclusion of coronary revascularization procedures among the incident CHD events introduced heterogeneity. The SNPs were not associated with CHD in black participants, and associations varied in other US minorities. CONCLUSIONS: Prospective analyses of white participants replicated several reported cross-sectional CHD-SNP associations.
Keywords: Aged; Aged, 80 and over; Continental Population Groups; Coronary Disease; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Association of genetic variation with systolic and diastolic blood pressure among African Americans: the Candidate Gene Association Resource study. - Fox, Ervin R; Young, J Hunter; Li, Yali; Dreisbach, Albert W; Keating, Brendan J; Musani, Solomon K; Liu, Kiang; Morrison, Alanna C; Ganesh, Santhi; Kutlar, Abdullah; Ramachandran, Vasan S; Polak, Josef F; et al. (Hum Mol Genet, 2011)
The prevalence of hypertension in African Americans (AAs) is higher than in other US groups; yet, few have performed genome-wide association studies (GWASs) in AA. Among people of European descent, GWASs have identified genetic variants at 13 loci that are associated with blood pressure. It is unknown if these variants confer susceptibility in people of African ancestry. Here, we examined genome-wide and candidate gene associations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) using the Candidate Gene Association Resource (CARe) consortium consisting of 8591 AAs. Genotypes included genome-wide single-nucleotide polymorphism (SNP) data utilizing the Affymetrix 6.0 array with imputation to 2.5 million HapMap SNPs and candidate gene SNP data utilizing a 50K cardiovascular gene-centric array (ITMAT-Broad-CARe [IBC] array). For Affymetrix data, the strongest signal for DBP was rs10474346 (P= 3.6 × 10(-8)) located near GPR98 and ARRDC3. For SBP, the strongest signal was rs2258119 in C21orf91 (P= 4.7 × 10(-8)). The top IBC association for SBP was rs2012318 (P= 6.4 × 10(-6)) near SLC25A42 and for DBP was rs2523586 (P= 1.3 × 10(-6)) near HLA-B. None of the top variants replicated in additional AA (n = 11 882) or European-American (n = 69 899) cohorts. We replicated previously reported European-American blood pressure SNPs in our AA samples (SH2B3, P= 0.009; TBX3-TBX5, P= 0.03; and CSK-ULK3, P= 0.0004). These genetic loci represent the best evidence of genetic influences on SBP and DBP in AAs to date. More broadly, this work supports that notion that blood pressure among AAs is a trait with genetic underpinnings but also with significant complexity.
Keywords: Adult; African Americans; Aged; Blood Pressure; Cohort Studies; Diastole; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

Association of genomic loci from a cardiovascular gene SNP array with fibrinogen levels in European Americans and African-Americans from six cohort studies: the Candidate Gene Association Resource (CARe). - Wassel, Christina L; Lange, Leslie A; Keating, Brendan J; Taylor, Kira C; Johnson, Andrew D; Palmer, Cameron; Ho, Lindsey A; Smith, Nicholas L; Lange, Ethan M; Li, Yun; Yang, Qiong; Delaney, Joseph A; et al. (Blood, 2011)
Several common genomic loci, involving various immunity- and metabolism-related genes, have been associated with plasma fibrinogen in European Americans (EAs). The genetic determinants of fibrinogen in African Americans (AAs) are poorly characterized. Using a vascular gene-centric array in 23,634 EA and 6657 AA participants from 6 studies comprising the Candidate Gene Association Resource project, we examined the association of 47,539 common and lower frequency variants with fibrinogen concentration. We identified a rare Pro265Leu variant in FGB (rs6054) associated with lower fibrinogen. Common fibrinogen gene single nucleotide polymorphisms (FGB rs1800787 and FGG rs2066861) significantly associated with fibrinogen in EAs were prevalent in AAs and showed consistent associations. Several fibrinogen locus single nucleotide polymorphism associated with lower fibrinogen were exclusive to AAs; these include a newly reported association with FGA rs10050257. For IL6R, IL1RN, and NLRP3 inflammatory gene loci, associations with fibrinogen were concordant between EAs and AAs, but not at other loci (CPS1, PCCB, and SCL22A5-IRF1). The association of FGG rs2066861 with fibrinogen differed according to assay type used to measure fibrinogen. Further characterization of common and lower-frequency genetic variants that contribute to interpopulation differences in fibrinogen phenotype may help refine our understanding of the contribution of hemostasis and inflammation to atherothrombotic risk.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Association of HSP70 and its co-chaperones with Alzheimer's disease. - Broer, Linda; Ikram, Mohammad Arfan; Schuur, Maaike; DeStefano, Anita L; Bis, Joshua C; Liu, Fan; Rivadeneira, Fernando; Uitterlinden, André G; Beiser, Alexa S; Longstreth, William T; Hofman, Albert; Aulchenko, Yurii; et al. (J Alzheimers Dis, 2011)
The heat shock protein (HSP) 70 family has been implicated in the pathology of Alzheimer's disease (AD). In this study, we examined common genetic variations in the 80 genes encoding HSP70 and its co-chaperones. We conducted a study in a series of 462 patients and 5238 unaffected participants derived from the Rotterdam Study, a population-based study including 7983 persons aged 55 years and older. We genotyped a total of 12,053 Single Nucleotide Polymorphisms (SNPs) using the HumanHap550K Genotyping BeadChip from Illumina. Replication was performed in two independent cohort studies, the Framingham Heart study (FHS; n = 806) and Cardiovascular Health Study (CHS; n = 2150). When adjusting for multiple testing, we found a small but consistent, though not significant effect of rs12118313 located 32 kb from PFDN2, with an OR of 1.19 (p-value from meta-analysis = 0.003). However this SNP was in the intron of another gene, suggesting it is unlikely this SNP reflects the effect of PFDN2. In a formal pathway analysis we found nominally significant evidence for an association of BAG, DNAJA and prefoldin with AD. These findings corroborate with those of a study of 2032 AD patients and 5328 controls, in which several members of the prefoldin family showed evidence for association to AD. Our study did not reveal evidence for a genetic variant if the HSP70 family with a major effect on AD. However, our findings of the single SNP analysis and pathway analysis suggest that multiple genetic variants in prefoldin are associated with AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Genetic Association Studies; Genetic Variation; HSP70 Heat-Shock Proteins; Humans; Middle Aged; Molecular Chaperones; Polymorphism, Single Nucleotide

Association of incident cardiovascular disease with progression of sleep-disordered breathing. - Chami, Hassan A; Resnick, Helaine E; Quan, Stuart F; Gottlieb, Daniel J (Circulation, 2011)
BACKGROUND: Prospective data suggest that sleep-disordered breathing enhances risk for incident and recurrent cardiovascular disease (CVD). However, a reverse causal pathway whereby incident CVD causes or worsens sleep-disordered breathing has not been studied. METHODS AND RESULTS: A total of 2721 Sleep Heart Health Study participants (mean age 62, standard deviation=10 years; 57% women; 23% minority) without CVD at baseline underwent 2 polysomnograms 5 years apart. Incident CVD events, including myocardial infarction, congestive heart failure, and stroke, were ascertained and adjudicated. The relation of incident CVD to change in apnea-hypopnea index between the 2 polysomnograms was tested with general linear models, with adjustment for age, sex, race, study center, history of diabetes mellitus, change in body mass index, change in neck circumference, percent sleep time spent in supine sleep, and time between the 2 polysomnograms. Incident CVD occurred in 95 participants between the first and second polysomnograms. Compared with participants without incident CVD, those with incident CVD experienced larger increases in apnea-hypopnea index between polysomnograms. The difference in adjusted mean apnea-hypopnea index change between subjects with and without incident CVD was 2.75 events per hour (95% confidence interval, 0.26 to 5.24; P=0.032). This association persisted after subjects with central sleep apnea were excluded. Compared with participants without incident CVD, participants with incident CVD had greater increases in both mean obstructive and central apnea indices, by 1.75 events per hour (95% confidence interval, 0.10 to 1.75; P=0.04) and by 1.07 events per hour (95% confidence interval, 0.40 to 1.74; P=0.001), respectively. CONCLUSIONS: In a diverse, community-based sample of middle-aged and older adults, incident CVD was associated with worsening sleep-disordered breathing over 5 years.
Keywords: Aged; Cardiovascular Diseases; Disease Progression; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Polysomnography; Risk Factors; Sleep Apnea Syndromes

Association of polymorphisms in the hepatocyte growth factor gene promoter with keratoconus. - Burdon, Kathryn P; Macgregor, Stuart; Bykhovskaya, Yelena; Javadiyan, Sharhbanou; Li, Xiaohui; Laurie, Kate J; Muszynska, Dorota; Lindsay, Richard; Lechner, Judith; Haritunians, Talin; Henders, Anjali K; Dash, Durga; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: Keratoconus is a progressive disorder of the cornea that can lead to severe visual impairment or blindness. Although several genomic regions have been linked to rare familial forms of keratoconus, no genes have yet been definitively identified for common forms of the disease. METHODS: Two genome-wide association scans were undertaken in parallel. The first used pooled DNA from an Australian cohort, followed by typing of top-ranked single-nucleotide polymorphisms (SNPs) in individual DNA samples. The second was conducted in individually genotyped patients, and controls from the USA. Tag SNPs around the hepatocyte growth factor (HGF) gene were typed in three additional replication cohorts. Serum levels of HGF protein in normal individuals were assessed with ELISA and correlated with genotype. RESULTS: The only SNP observed to be associated in both the pooled discovery and primary replication cohort was rs1014091, located upstream of the HGF gene. The nearby SNP rs3735520 was found to be associated in the individually typed discovery cohort (P = 6.1 × 10(-7)). Genotyping of tag SNPs around HGF revealed association at rs3735520 and rs17501108/rs1014091 in four of the five cohorts. Meta-analysis of all five datasets together yielded suggestive P values for rs3735520 (P = 9.9 × 10(-7)) and rs17501108 (P = 9.9 × 10(-5)). In addition, SNP rs3735520 was found to be associated with serum HGF level in normal individuals (P = 0.036). CONCLUSIONS: Taken together, these results implicate genetic variation at the HGF locus with keratoconus susceptibility.
Keywords: Adult; Aged; Chromosomes, Human, Pair 7; Corneal Topography; Enzyme-Linked Immunosorbent Assay; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hepatocyte Growth Factor; Humans; Keratoconus; Middle Aged; Nucleic Acid Hybridization; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Tagged Sites

A bivariate genome-wide approach to metabolic syndrome: STAMPEED consortium. - Kraja, Aldi T; Vaidya, Dhananjay; Pankow, James S; Goodarzi, Mark O; Assimes, Themistocles L; Kullo, Iftikhar J; Sovio, Ulla; Mathias, Rasika A; Sun, Yan V; Franceschini, Nora; Absher, Devin; Li, Guo; et al. (Diabetes, 2011)
OBJECTIVE The metabolic syndrome (MetS) is defined as concomitant disorders of lipid and glucose metabolism, central obesity, and high blood pressure, with an increased risk of type 2 diabetes and cardiovascular disease. This study tests whether common genetic variants with pleiotropic effects account for some of the correlated architecture among five metabolic phenotypes that define MetS. RESEARCH DESIGN AND METHODS Seven studies of the STAMPEED consortium, comprising 22,161 participants of European ancestry, underwent genome-wide association analyses of metabolic traits using a panel of ∼2.5 million imputed single nucleotide polymorphisms (SNPs). Phenotypes were defined by the National Cholesterol Education Program (NCEP) criteria for MetS in pairwise combinations. Individuals exceeding the NCEP thresholds for both traits of a pair were considered affected. RESULTS Twenty-nine common variants were associated with MetS or a pair of traits. Variants in the genes LPL, CETP, APOA5 (and its cluster), GCKR (and its cluster), LIPC, TRIB1, LOC100128354/MTNR1B, ABCB11, and LOC100129150 were further tested for their association with individual qualitative and quantitative traits. None of the 16 top SNPs (one per gene) associated simultaneously with more than two individual traits. Of them 11 variants showed nominal associations with MetS per se. The effects of 16 top SNPs on the quantitative traits were relatively small, together explaining from ∼9% of the variance in triglycerides, 5.8% of high-density lipoprotein cholesterol, 3.6% of fasting glucose, and 1.4% of systolic blood pressure. CONCLUSIONS Qualitative and quantitative pleiotropic tests on pairs of traits indicate that a small portion of the covariation in these traits can be explained by the reported common genetic variants.
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Meta-Analysis as Topic; Metabolic Syndrome; Middle Aged; Phenotype; Polymorphism, Single Nucleotide

Carotid intima-media thickness, electrocardiographic left ventricular hypertrophy, and incidence of intracerebral hemorrhage. - Folsom, Aaron R; Yatsuya, Hiroshi; Psaty, Bruce M; Shahar, Eyal; Longstreth, W T (Stroke, 2011)
BACKGROUND AND PURPOSE: Carotid intima-media thickness and electrocardiographic left ventricular hypertrophy are 2 subclinical cardiovascular disease measures associated with increased risk of total and ischemic strokes. Increased intima-media thickness and electrocardiographic left ventricular hypertrophy also may reflect end-organ hypertensive effects. Information is scant on the associations of these subclinical measures with intracerebral hemorrhage (ICH). We hypothesized that greater carotid intima-media thickness and the presence of electrocardiographic left ventricular hypertrophy would be independently associated with increased ICH incidence. METHODS: Among 18,155 participants initially free of stroke in the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS), we assessed carotid intima-media thickness, carotid plaque, and electrocardiographic left ventricular hypertrophy. Over a median of 18 years of follow-up, 162 incident ICH events occurred. RESULTS: After adjustment for other ICH risk factors, carotid intima-media thickness was associated positively with incidence of ICH in both ARIC and CHS. The risk was lowest in study-specific Quartile 1, elevated 1.6- to 2.6-fold in Quartiles 2 to 3, and elevated 2.5 to 3.7-fold in Quartile 4 (P<0.05 for both studies). In CHS, having a carotid plaque was associated with a 2-fold (95% CI, 1.1-3.4) greater ICH risk than having no plaque, but only 1.2-fold (95% CI, 0.76-2.0) greater ICH risk in ARIC. Electrocardiographic left ventricular hypertrophy carried a hazard ratio of ICH of 1.7 (95% CI, 0.77-3.7) in CHS and 2.8 (95% CI, 1.2-6.4) in ARIC. CONCLUSIONS: Our data suggest that people with carotid atherosclerosis and possibly left ventricular hypertrophy are at increased risk not only of ischemic stroke, but also of ICH.
Keywords: Carotid Intima-Media Thickness; Cerebral Hemorrhage; Cohort Studies; Electrocardiography; Female; Follow-Up Studies; Humans; Hypertrophy, Left Ventricular; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors

Cerivastatin, genetic variants, and the risk of rhabdomyolysis. - Marciante, Kristin D; Durda, Jon P; Heckbert, Susan R; Lumley, Thomas; Rice, Ken; McKnight, Barbara; Totah, Rheem A; Tamraz, Bani; Kroetz, Deanna L; Fukushima, Hisayo; Kaspera, Rüdiger; Bis, Joshua C; et al. (Pharmacogenet Genomics, 2011)
OBJECTIVE: The withdrawal of cerivastatin involved an uncommon but serious adverse reaction, rhabdomyolysis. The bimodal response, rhabdomyolysis in a small proportion of users, points to genetic factors as a potential cause. We conducted a case-control study to evaluate genetic markers for cerivastatin-associated rhabdomyolysis. METHODS: This study had two components: a candidate gene study to evaluate variants in CYP2C8, UGT1A1, UGT1A3, and SLCO1B1; and a genome-wide association study to identify risk factors in other regions of the genome. A total of 185 rhabdomyolysis cases were frequency matched to statin-using controls from the Cardiovascular Health Study (n=374) and the Heart and Vascular Health Study (n=358). Validation relied on functional studies. RESULTS: Permutation test results suggested an association between cerivastatin-associated rhabdomyolysis and variants in SLCO1B1 (P=0.002), but not variants in CYP2C8 (P=0.073) or UGTs (P=0.523). An additional copy of the minor allele of SLCO1B1 rs4149056 (p.Val174Ala) was associated with the risk of rhabdomyolysis (odds ratio: 1.89; 95% confidence interval: 1.40-2.56). In transfected cells, this variant reduced cerivastatin transport by 40% compared with the reference transporter (P<0.001). The genome-wide association study identified an intronic variant (rs2819742) in the ryanodine receptor 2 gene (RYR2) as significant (P=1.74E-07). An additional copy of the minor allele of the RYR2 variant was associated with a reduced risk of rhabdomyolysis (odds ratio: 0.48; 95% confidence interval: 0.36-0.63). CONCLUSION: We identified modest genetic risk factors for an extreme response to cerivastatin. Disabling genetic variants in the candidate genes were not responsible for the bimodal response to cerivastatin.
Keywords: Adult; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Female; Genetic Variation; Genome-Wide Association Study; Glucuronosyltransferase; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Organic Anion Transporters; Polymorphism, Single Nucleotide; Pyridines; Rhabdomyolysis; Risk; Ryanodine Receptor Calcium Release Channel; Solute Carrier Organic Anion Transporter Family Member 1b1

Cystatin C identifies chronic kidney disease patients at higher risk for complications. - Peralta, Carmen A; Katz, Ronit; Sarnak, Mark J; Ix, Joachim; Fried, Linda F; de Boer, Ian; Palmas, Walter; Siscovick, David; Levey, Andrew S; Shlipak, Michael G (J Am Soc Nephrol, 2011)
Although cystatin C is a stronger predictor of clinical outcomes associated with CKD than creatinine, the clinical role for cystatin C is unclear. We included 11,909 participants from the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS) and assessed risks for death, cardiovascular events, heart failure, and ESRD among persons categorized into mutually exclusive groups on the basis of the biomarkers that supported a diagnosis of CKD (eGFR <60 ml/min per 1.73 m(2)): creatinine only, cystatin C only, both, or neither. We used CKD-EPI equations to estimate GFR from these biomarkers. In MESA, 9% had CKD by the creatinine-based equation only, 2% had CKD by the cystatin C-based equation only, and 4% had CKD by both equations; in CHS, these percentages were 12, 4, and 13%, respectively. Compared with those without CKD, the adjusted hazard ratios (HR) for mortality in MESA were: 0.80 (95% CI 0.50 to 1.26) for CKD by creatinine only; 3.23 (95% CI 1.84 to 5.67) for CKD by cystatin C only; and 1.93 (95% CI 1.27 to 2.92) for CKD by both; in CHS, the adjusted HR were 1.09 (95% CI 0.98 to 1.21), 1.78 (95% CI 1.53 to 2.08), and 1.74 (95% CI 1.58 to 1.93), respectively. The pattern was similar for cardiovascular disease (CVD), heart failure, and kidney failure outcomes. In conclusion, among adults diagnosed with CKD using the creatinine-based CKD-EPI equation, the adverse prognosis is limited to the subset who also have CKD according to the cystatin C-based equation. Cystatin C may have a role in identifying persons with CKD who have the highest risk for complications.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Chronic Disease; Creatinine; Cystatin C; Disease Progression; Female; Glomerular Filtration Rate; Heart Failure; Humans; Kidney Diseases; Kidney Failure, Chronic; Male; Middle Aged; Predictive Value of Tests; Retrospective Studies; Risk Factors

Diabetes mellitus, fasting glucose, and risk of cause-specific death. - Rao Kondapally Seshasai, Sreenivasa; Kaptoge, Stephen; Thompson, Alexander; Di Angelantonio, Emanuele; Gao, Pei; Sarwar, Nadeem; Whincup, Peter H; Mukamal, Kenneth J; Gillum, Richard F; Holme, Ingar; Njølstad, Inger; Fletcher, Astrid; et al. (N Engl J Med, 2011)
BACKGROUND: The extent to which diabetes mellitus or hyperglycemia is related to risk of death from cancer or other nonvascular conditions is uncertain. METHODS: We calculated hazard ratios for cause-specific death, according to baseline diabetes status or fasting glucose level, from individual-participant data on 123,205 deaths among 820,900 people in 97 prospective studies. RESULTS: After adjustment for age, sex, smoking status, and body-mass index, hazard ratios among persons with diabetes as compared with persons without diabetes were as follows: 1.80 (95% confidence interval [CI], 1.71 to 1.90) for death from any cause, 1.25 (95% CI, 1.19 to 1.31) for death from cancer, 2.32 (95% CI, 2.11 to 2.56) for death from vascular causes, and 1.73 (95% CI, 1.62 to 1.85) for death from other causes. Diabetes (vs. no diabetes) was moderately associated with death from cancers of the liver, pancreas, ovary, colorectum, lung, bladder, and breast. Aside from cancer and vascular disease, diabetes (vs. no diabetes) was also associated with death from renal disease, liver disease, pneumonia and other infectious diseases, mental disorders, nonhepatic digestive diseases, external causes, intentional self-harm, nervous-system disorders, and chronic obstructive pulmonary disease. Hazard ratios were appreciably reduced after further adjustment for glycemia measures, but not after adjustment for systolic blood pressure, lipid levels, inflammation or renal markers. Fasting glucose levels exceeding 100 mg per deciliter (5.6 mmol per liter), but not levels of 70 to 100 mg per deciliter (3.9 to 5.6 mmol per liter), were associated with death. A 50-year-old with diabetes died, on average, 6 years earlier than a counterpart without diabetes, with about 40% of the difference in survival attributable to excess nonvascular deaths. CONCLUSIONS: In addition to vascular disease, diabetes is associated with substantial premature death from several cancers, infectious diseases, external causes, intentional self-harm, and degenerative disorders, independent of several major risk factors. (Funded by the British Heart Foundation and others.).
Keywords: Blood Glucose; Cause of Death; Diabetes Mellitus; Female; Humans; Hyperglycemia; Life Expectancy; Male; Middle Aged; Risk; Survival Analysis

Electrocardiographic and clinical predictors separating atherosclerotic sudden cardiac death from incident coronary heart disease. - Soliman, Elsayed Z; Prineas, Ronald J; Case, L Douglas; Russell, Gregory; Rosamond, Wayne; Rea, Thomas; Sotoodehnia, Nona; Post, Wendy S; Siscovick, David; Psaty, Bruce M; Burke, Gregory L (Heart, 2011)
OBJECTIVE: To identify specific ECG and clinical predictors that separate atherosclerotic sudden cardiac death (SCD) from incident coronary heart disease (CHD) (non-fatal events and non-sudden death) in the combined cohorts of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. METHODS: This analysis included 18,497 participants (58% females, 24% black individuals, mean age 58 years) who were initially free of clinical CHD. A competing risk analysis was conducted to examine the prognostic significance of baseline clinical characteristics and an extensive electronic database of ECG measurements for prediction of 229 cases of SCD as a first event versus 2297 incident CHD cases (2122 non-fatal events and 175 non-sudden death) that occurred during a median follow-up time of 13 years in the Cardiovascular Health Study and 14 years in the Atherosclerosis Risk in Communities study. RESULTS: After adjusting for common CHD risk factors, a number of clinical characteristics and ECG measurements were independently predictive of SCD and CHD. However, the risk of SCD versus incident CHD was significantly different for race/ethnicity, hypertension, body mass index (BMI), heart rate, QTc, abnormally inverted T wave in any ECG lead group and level of ST elevation in V2. Black race/ethnicity (compared to non-black) was predictive of high SCD risk but less risk of incident CHD (p value for differences in the risk (HR) for SCD versus CHD <0.0001). Hypertension, increased heart rate, prolongation of QTc and abnormally inverted T wave were stronger predictors of high SCD risk compared to CHD (p value=0.0460, 0.0398, 0.0158 and 0.0265, respectively). BMI was not predictive of incident CHD but was predictive of high SCD risk in a quadratic fashion (p value=0.0220). On the other hand, elevated ST height as measured at the J point and that measured at 60 ms after the J point in V2 were not predictive of SCD but were predictive of high incident CHD risk (p value=0.0251 and 0.0155, respectively). CONCLUSIONS: SCD and CHD have many risk factors in common. Hypertension, race/ethnicity, BMI, heart rate, QTc, abnormally inverted T wave in any ECG lead group and level of ST elevation in V2 have the potential to separate between the risks of SCD and CHD. These results need to be validated in another cohort.
Keywords: Adult; Aged; Aged, 80 and over; Body Mass Index; Continental Population Groups; Coronary Disease; Death, Sudden, Cardiac; Electrocardiography; Ethnic Groups; Female; Heart Rate; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Adjustment; Risk Factors; Time Factors; United States

A gene-centric association scan for Coagulation Factor VII levels in European and African Americans: the Candidate Gene Association Resource (CARe) Consortium. - Taylor, Kira C; Lange, Leslie A; Zabaneh, Delilah; Lange, Ethan; Keating, Brendan J; Tang, Weihong; Smith, Nicholas L; Delaney, Joseph A; Kumari, Meena; Hingorani, Aroon; North, Kari E; Kivimaki, Mika; et al. (Hum Mol Genet, 2011)
Polymorphisms in several distinct genomic regions, including the F7 gene, were recently associated with factor VII (FVII) levels in European Americans (EAs). The genetic determinants of FVII in African Americans (AAs) are unknown. We used a 50,000 single nucleotide polymorphism (SNP) gene-centric array having dense coverage of over 2,000 candidate genes for cardiovascular disease (CVD) pathways in a community-based sample of 16,324 EA and 3898 AA participants from the Candidate Gene Association Resource (CARe) consortium. Our aim was the discovery of new genomic loci and more detailed characterization of existing loci associated with FVII levels. In EAs, we identified three new loci associated with FVII, of which APOA5 on chromosome 11q23 and HNF4A on chromosome 20q12-13 were replicated in a sample of 4289 participants from the Whitehall II study. We confirmed four previously reported FVII-associated loci (GCKR, MS4A6A, F7 and PROCR) in CARe EA samples. In AAs, the F7 and PROCR regions were significantly associated with FVII. Several of the FVII-associated regions are known to be associated with lipids and other cardiovascular-related traits. At the F7 locus, there was evidence of at least five independently associated SNPs in EAs and three independent signals in AAs. Though the variance in FVII explained by the existing loci is substantial (20% in EA and 10% in AA), larger sample sizes and investigation of lower frequency variants may be required to identify additional FVII-associated loci in EAs and AAs and further clarify the relationship between FVII and other CVD risk factors.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; European Continental Ancestry Group; Factor VII; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Genetic association for renal traits among participants of African ancestry reveals new loci for renal function. - Liu, Ching-Ti; Garnaas, Maija K; Tin, Adrienne; Köttgen, Anna; Franceschini, Nora; Peralta, Carmen A; de Boer, Ian H; Lu, Xiaoning; Atkinson, Elizabeth; Ding, Jingzhong; Nalls, Michael; Shriner, Daniel; et al. (PLoS Genet, 2011)
Chronic kidney disease (CKD) is an increasing global public health concern, particularly among populations of African ancestry. We performed an interrogation of known renal loci, genome-wide association (GWA), and IBC candidate-gene SNP association analyses in African Americans from the CARe Renal Consortium. In up to 8,110 participants, we performed meta-analyses of GWA and IBC array data for estimated glomerular filtration rate (eGFR), CKD (eGFR <60 mL/min/1.73 m(2)), urinary albumin-to-creatinine ratio (UACR), and microalbuminuria (UACR >30 mg/g) and interrogated the 250 kb flanking region around 24 SNPs previously identified in European Ancestry renal GWAS analyses. Findings were replicated in up to 4,358 African Americans. To assess function, individually identified genes were knocked down in zebrafish embryos by morpholino antisense oligonucleotides. Expression of kidney-specific genes was assessed by in situ hybridization, and glomerular filtration was evaluated by dextran clearance. Overall, 23 of 24 previously identified SNPs had direction-consistent associations with eGFR in African Americans, 2 of which achieved nominal significance (UMOD, PIP5K1B). Interrogation of the flanking regions uncovered 24 new index SNPs in African Americans, 12 of which were replicated (UMOD, ANXA9, GCKR, TFDP2, DAB2, VEGFA, ATXN2, GATM, SLC22A2, TMEM60, SLC6A13, and BCAS3). In addition, we identified 3 suggestive loci at DOK6 (p-value = 5.3×10(-7)) and FNDC1 (p-value = 3.0×10(-7)) for UACR, and KCNQ1 with eGFR (p = 3.6×10(-6)). Morpholino knockdown of kcnq1 in the zebrafish resulted in abnormal kidney development and filtration capacity. We identified several SNPs in association with eGFR in African Ancestry individuals, as well as 3 suggestive loci for UACR and eGFR. Functional genetic studies support a role for kcnq1 in glomerular development in zebrafish.
Keywords: Adaptor Proteins, Vesicular Transport; Adult; African Continental Ancestry Group; Aged; Animals; Female; Gene Knockdown Techniques; Genetic Association Studies; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; KCNQ1 Potassium Channel; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Zebrafish

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants of the NOTCH3 gene in the elderly and magnetic resonance imaging correlates of age-related cerebral small vessel disease. - Schmidt, Helena; Zeginigg, Marion; Wiltgen, Marco; Freudenberger, Paul; Petrovic, Katja; Cavalieri, Margherita; Gider, Pierre; Enzinger, Christian; Fornage, Myriam; Debette, Stephanie; Rotter, Jerome I; Ikram, Mohammad A; et al. (Brain, 2011)
Cerebral small vessel disease-related brain lesions such as white matter lesions and lacunes are common findings of magnetic resonance imaging in the elderly. These lesions are thought to be major contributors to disability in old age, and risk factors that include age and hypertension have been established. The radiological, histopathologic and clinical phenotypes of age-related cerebral small vessel disease remarkably resemble autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy, which is caused by mutations in NOTCH3. We hypothesized that genetic variations in NOTCH3 also play a role in age-related cerebral small vessel disease. We directly sequenced all 33 exons, the promoter and 3'-untranslated region of NOTCH3 in 195 participants with either coalescent white matter lesions or lacunes and compared the results to 82 randomly selected participants with no focal changes on magnetic resonance images in the Austrian Stroke Prevention Study. We detected nine common and 33 rare single nucleotide polymorphisms, of which 20 were novel. All common single nucleotide polymorphisms were genotyped in the entire cohort (n = 888), and four of them, rs1043994, rs10404382, rs10423702 and rs1043997, were associated significantly with both the presence and progression of white matter lesions. The association was confined to hypertensives, a result which we replicated in the Cohorts for Heart and Ageing Research in Genomic Epidemiology Consortium on an independent sample of 4773 stroke-free hypertensive elderly individuals of European descent (P = 0.04). The 33 rare single nucleotide polymorphisms were scattered over the NOTCH3 gene with three being located in the promoter region, 24 in exons (18 non-synonymous), three in introns and three in the 3'-untranslated region. None of the single nucleotide polymorphisms affected a cysteine residue. Sorting Intolerant From Tolerant, PolyPhen2 analyses and protein structure simulation consistently predicted six of the non-synonymous single nucleotide polymorphisms (H170R, P496L, V1183M, L1518M, D1823N and V1952M) to be functional, with four being exclusively or mainly detected in subjects with severe white matter lesions. In four individuals with rare non-synonymous single nucleotide polymorphisms, we noted anterior temporal lobe hyperintensity, hyperintensity in the external capsule, lacunar infarcts or subcortical lacunar lesions. None of the observed abnormalities were specific to cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy. This is the first comprehensive study investigating (i) the frequency of NOTCH3 variations in community-dwelling elderly and (ii) their effect on cerebral small vessel disease related magnetic resonance imaging phenotypes. We show that the NOTCH3 gene is highly variable with both common and rare single nucleotide polymorphisms spreading across the gene, and that common variants at the NOTCH3 gene increase the risk of age-related white matter lesions in hypertensives. Additional investigations are required to explore the biological mechanisms underlying the observed association.
Keywords: Aged; Aged, 80 and over; Alleles; Brain; Cerebral Small Vessel Diseases; Exons; Female; Follow-Up Studies; Genetic Association Studies; Genotype; Humans; Hypertension; Magnetic Resonance Imaging; Male; Middle Aged; Phenotype; Promoter Regions, Genetic; Prospective Studies; Receptor, Notch3; Receptors, Notch

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Genome-wide association study for serum urate concentrations and gout among African Americans identifies genomic risk loci and a novel URAT1 loss-of-function allele. - Tin, Adrienne; Woodward, Owen M; Kao, Wen Hong Linda; Liu, Ching-Ti; Lu, Xiaoning; Nalls, Michael A; Shriner, Daniel; Semmo, Mariam; Akylbekova, Ermeg L; Wyatt, Sharon B; Hwang, Shih-Jen; Yang, Qiong; et al. (Hum Mol Genet, 2011)
Serum urate concentrations are highly heritable and elevated serum urate is a key risk factor for gout. Genome-wide association studies (GWAS) of serum urate in African American (AA) populations are lacking. We conducted a meta-analysis of GWAS of serum urate levels and gout among 5820 AA and a large candidate gene study among 6890 AA and 21 708 participants of European ancestry (EA) within the Candidate Gene Association Resource Consortium. Findings were tested for replication among 1996 independent AA individuals, and evaluated for their association among 28 283 EA participants of the CHARGE Consortium. Functional studies were conducted using (14)C-urate transport assays in mammalian Chinese hamster ovary cells. In the discovery GWAS of serum urate, three loci achieved genome-wide significance (P< 5.0 × 10(-8)): a novel locus near SGK1/SLC2A12 on chromosome 6 (rs9321453, P= 1.0 × 10(-9)), and two loci previously identified in EA participants, SLC2A9 (P= 3.8 × 10(-32)) and SLC22A12 (P= 2.1 × 10(-10)). A novel rare non-synonymous variant of large effect size in SLC22A12, rs12800450 (minor allele frequency 0.01, G65W), was identified and replicated (beta -1.19 mg/dl, P= 2.7 × 10(-16)). (14)C-urate transport assays showed reduced urate transport for the G65W URAT1 mutant. Finally, in analyses of 11 loci previously associated with serum urate in EA individuals, 10 of 11 lead single-nucleotide polymorphisms showed direction-consistent association with urate among AA. In summary, we identified and replicated one novel locus in association with serum urate levels and experimentally characterize the novel G65W variant in URAT1 as a functional allele. Our data support the importance of multi-ethnic GWAS in the identification of novel risk loci as well as functional variants.
Keywords: Adult; African Americans; Aged; Animals; CHO Cells; Cricetinae; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Gout; Humans; Loss of Heterozygosity; Male; Middle Aged; Organic Anion Transporters; Organic Cation Transport Proteins; Polymorphism, Single Nucleotide; Uric Acid; Young Adult

Health and function of participants in the Long Life Family Study: A comparison with other cohorts. - Newman, Anne B; Glynn, Nancy W; Taylor, Christopher A; Sebastiani, Paola; Perls, Thomas T; Mayeux, Richard; Christensen, Kaare; Zmuda, Joseph M; Barral, Sandra; Lee, Joseph H; Simonsick, Eleanor M; Walston, Jeremy D; et al. (Aging (Albany NY), 2011)
Individuals from families recruited for the Long Life Family Study (LLFS) (n= 4559) were examined and compared to individuals from other cohorts to determine whether the recruitment targeting longevity resulted in a cohort of individuals with better health and function. Other cohorts with similar data included the Cardiovascular Health Study, the Framingham Heart Study, and the New England Centenarian Study. Diabetes, chronic pulmonary disease and peripheral artery disease tended to be less common in LLFS probands and offspring compared to similar aged persons in the other cohorts. Pulse pressure and triglycerides were lower, high density lipids were higher, and a perceptual speed task and gait speed were better in LLFS. Age-specific comparisons showed differences that would be consistent with a higher peak, later onset of decline or slower rate of change across age in LLFS participants. These findings suggest several priority phenotypes for inclusion in future genetic analysis to identify loci contributing to exceptional survival.
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Female; Gait; Humans; Longevity; Male; Middle Aged; Psychomotor Performance; Research Design

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

Identification of patients with sleep disordered breathing: comparing the four-variable screening tool, STOP, STOP-Bang, and Epworth Sleepiness Scales. - Silva, Graciela E; Vana, Kimberly D; Goodwin, James L; Sherrill, Duane L; Quan, Stuart F (J Clin Sleep Med, 2011)
STUDY OBJECTIVE: The Epworth Sleepiness Scale (ESS) has been used to detect patients with potential sleep disordered breathing (SDB). Recently, a 4-Variable screening tool was proposed to identify patients with SDB, in addition to the STOP and STOP-Bang questionnaires. This study evaluated the abilities of the 4-Variable screening tool, STOP, STOP-Bang, and ESS questionnaires in identifying subjects at risk for SDB. METHODS: A total of 4,770 participants who completed polysomnograms in the baseline evaluation of the Sleep Heart Health Study (SHHS) were included. Subjects with RDIs ≥ 15 and ≥ 30 were considered to have moderate-to-severe or severe SDB, respectively. Variables were constructed to approximate those in the questionnaires. The risk of SDB was calculated by the 4-Variable screening tool according to Takegami et al. The STOP and STOP-Bang questionnaires were evaluated including variables for snoring, tiredness/sleepiness, observed apnea, blood pressure, body mass index, age, neck circumference, and gender. Sleepiness was evaluated using the ESS questionnaire and scores were dichotomized into < 11 and ≥ 11. RESULTS: The STOP-Bang questionnaire had higher sensitivity to predict moderate-to-severe (87.0%) and severe (70.4%) SDB, while the 4-Variable screening tool had higher specificity to predict moderate-to-severe and severe SDB (93.2% for both). CONCLUSIONS: In community populations such as the SHHS, high specificities may be more useful in excluding low-risk patients, while avoiding false positives. However, sleep clinicians may prefer to use screening tools with high sensitivities, like the STOP-Bang, in order to avoid missing cases that may lead to adverse health consequences and increased healthcare costs.
Keywords: Blood Pressure; Body Mass Index; Cohort Studies; Female; Humans; Male; Mass Screening; Middle Aged; Polysomnography; Predictive Value of Tests; Prospective Studies; Risk; ROC Curve; Sensitivity and Specificity; Severity of Illness Index; Sleep Apnea Syndromes; Snoring; Surveys and Questionnaires

Kidney function decline in the elderly: impact of lipoprotein-associated phospholipase A(2). - Peralta, Carmen A; Katz, Ronit; Shlipak, Michael; Dubin, Ruth; DeBoer, Ian; Jenny, Nancy; Fitzpatrick, Annette; Koro, Carol; Kestenbaum, Bryan; Ix, Joachim; Sarnak, Mark; Cushman, Mary (Am J Nephrol, 2011)
BACKGROUND: Whether lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) levels are associated with kidney function decline has not been well studied. METHODS: We investigated associations of Lp-PLA(2) antigen and activity with kidney function decline and rapid decline over 5.7 years in the Cardiovascular Health Study (n = 4,359). We estimated kidney function by cystatin C (eGFRcys) in repeated measures, and defined rapid decline as ≥3 ml/min/1.73 m(2) per year. We stratified by baseline preserved GFR (≥60 ml/min/1.73 m(2)). RESULTS: Mean age was 72 ± 5 years. Average eGFRcys decline was -1.79 ml/min/1.73 m(2) (SD = 2.60) per year. Among persons with preserved GFR, compared to the lowest quartile of Lp-PLA(2) antigen, eGFRcys decline was faster among persons in the second, β -0.31 (95% CI -0.52, -0.10), third -0.19 (-0.41, 0.02) and fourth quartiles -0.26 (-0.48, -0.04) after full adjustment. Persons in the highest quartile of Lp-PLA(2) antigen had increased odds of rapid decline 1.34 (1.03, 1.75), compared to the lowest. There was no significant association between levels of Lp-PLA(2) activity and eGFRcys decline or rapid decline. Associations were not statistically significant among persons with low eGFR (<60 ml/min/1.73 m(2)) at baseline. CONCLUSION: Higher levels of Lp-PLA(2) antigen but not activity were significantly associated with faster rates of kidney function decline. These findings may suggest a novel vascular pathway for kidney disease progression.
Keywords: Aged; Cardiovascular Diseases; Creatinine; Cystatin C; Disease Progression; Female; Geriatrics; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Middle Aged; Phospholipases A2; Risk Factors; Treatment Outcome

Large-scale candidate gene analysis in whites and African Americans identifies IL6R polymorphism in relation to atrial fibrillation: the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe) project. - Schnabel, Renate B; Kerr, Kathleen F; Lubitz, Steven A; Alkylbekova, Ermeg L; Marcus, Gregory M; Sinner, Moritz F; Magnani, Jared W; Wolf, Philip A; Deo, Rajat; Lloyd-Jones, Donald M; Lunetta, Kathryn L; Mehra, Reena; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: The genetic background of atrial fibrillation (AF) in whites and African Americans is largely unknown. Genes in cardiovascular pathways have not been systematically investigated. METHODS AND RESULTS: We examined a panel of approximately 50,000 common single-nucleotide polymorphisms (SNPs) in 2095 cardiovascular candidate genes and AF in 3 cohorts with participants of European (n=18,524; 2260 cases) or African American descent (n=3662; 263 cases) in the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource. Results in whites were followed up in the German Competence Network for AF (n=906, 468 cases). The top result was assessed in relation to incident ischemic stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology Stroke Consortium (n=19,602 whites, 1544 incident strokes). SNP rs4845625 in the IL6R gene was associated with AF (relative risk [RR] C allele, 0.90; 95% confidence interval [CI], 0.85-0.95; P=0.0005) in whites but did not reach statistical significance in African Americans (RR, 0.86; 95% CI, 0.72-1.03; P=0.09). The results were comparable in the German AF Network replication, (RR, 0.71; 95% CI, 0.57-0.89; P=0.003). No association between rs4845625 and stroke was observed in whites. The known chromosome 4 locus near PITX2 in whites also was associated with AF in African Americans (rs4611994; hazard ratio, 1.40; 95% CI, 1.16-1.69; P=0.0005). CONCLUSIONS: In a community-based cohort meta-analysis, we identified genetic association in IL6R with AF in whites. Additionally, we demonstrated that the chromosome 4 locus known from recent genome-wide association studies in whites is associated with AF in African Americans.
Keywords: African Americans; Aged; Alleles; Atrial Fibrillation; Chromosomes, Human, Pair 4; Cohort Studies; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; Stroke; United States

Longer legs are associated with greater risk of incident venous thromboembolism independent of total body height. The Longitudinal Study of Thromboembolism Etiology (LITE). - Lutsey, Pamela L; Cushman, Mary; Heckbert, Susan R; Tang, Weihong; Folsom, Aaron R (Thromb Haemost, 2011)
Several studies have reported that taller individuals are at greater risk of venous thromboembolism (VTE). We hypothesised that longer leg length would be positively associated with incident VTE, and would explain the height association. LITE ascertained VTE in a prospective population-based sample of 21,860 individuals aged 45 and older. Leg length was measured as standing height minus torso length. Cox regression models were adjusted for age, race, sex, waist circumference, diabetes, and factor VIII. To evaluate whether leg length was associated with VTE risk independent of height, we standardised leg length and height per 1 standard deviation (SD), and then included them simultaneously in Cox regression models. A total of 641 incident VTE cases accrued over a median follow-up of 16 years. Participants in the highest quintile of leg length were at 59% (95% CI: 22%-108%) greater risk of VTE, relative to the lowest quintile. For height, risk was 45% (12%-88%) greater for those in the highest quintile, compared to the lowest. When leg length and height were modelled simultaneously leg length remained associated with VTE risk (HR per 1 SD: 1.21 (1.04-1.40) while height was unrelated (HR per 1 SD: 1.00 (0.86-1.16). To conclude, participants with longer legs were at greater risk of incident VTE, and leg length explained the relation of height to VTE. It remains to be established whether this finding is due to greater venous surface area, a larger number of venous valves, or greater hydrostatic pressure among individuals with longer legs.
Keywords: Adult; Aged; Anthropometry; Body Height; Female; Follow-Up Studies; Humans; Leg; Male; Middle Aged; Population Groups; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Lower estimated GFR and higher albuminuria are associated with adverse kidney outcomes. A collaborative meta-analysis of general and high-risk population cohorts. - Gansevoort, Ron T; Matsushita, Kunihiro; van der Velde, Marije; Astor, Brad C; Woodward, Mark; Levey, Andrew S; de Jong, Paul E; Coresh, Josef (Kidney Int, 2011)
Both a low estimated glomerular filtration rate (eGFR) and albuminuria are known risk factors for end-stage renal disease (ESRD). To determine their joint contribution to ESRD and other kidney outcomes, we performed a meta-analysis of nine general population cohorts with 845,125 participants and an additional eight cohorts with 173,892 patients, the latter selected because of their high risk for chronic kidney disease (CKD). In the general population, the risk for ESRD was unrelated to eGFR at values between 75 and 105 ml/min per 1.73 m(2) but increased exponentially at lower levels. Hazard ratios for eGFRs averaging 60, 45, and 15 were 4, 29, and 454, respectively, compared with an eGFR of 95, after adjustment for albuminuria and cardiovascular risk factors. Log albuminuria was linearly associated with log ESRD risk without thresholds. Adjusted hazard ratios at albumin-to-creatinine ratios of 30, 300, and 1000 mg/g were 5, 13, and 28, respectively, compared with an albumin-to-creatinine ratio of 5. Albuminuria and eGFR were associated with ESRD, without evidence for multiplicative interaction. Similar associations were found for acute kidney injury and progressive CKD. In high-risk cohorts, the findings were generally comparable. Thus, lower eGFR and higher albuminuria are risk factors for ESRD, acute kidney injury and progressive CKD in both general and high-risk populations, independent of each other and of cardiovascular risk factors.
Keywords: Aged; Albuminuria; Cohort Studies; Creatinine; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Prognosis; Proportional Hazards Models; Risk Factors

Measures of adiposity and future risk of ischemic stroke and coronary heart disease in older men and women. - Kizer, Jorge R; Biggs, Mary L; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; de Boer, Ian H; Mozaffarian, Dariush; Barzilay, Joshua I; Strotmeyer, Elsa S; Luchsinger, José A; Elkind, Mitchell S V; Longstreth, W T; et al. (Am J Epidemiol, 2011)
The relation between measures of general and central adiposity and individual cardiovascular endpoints remains understudied in older adults. This study investigated the association of measures of body size and composition with incident ischemic stroke or coronary heart disease (1989-2007) in 3,754 community-dwelling US adults aged 65-100 years. Standardized anthropometry and bioelectric impedance measurements were obtained at baseline. Body mass index at age 50 years (BMI50) was calculated on the basis of recalled weight. Although only waist/hip ratio was significantly associated with ischemic stroke in quintile analysis in women, dichotomized body mass index (BMI) (≥ 30 kg/m²) was the only significant predictor in men. For coronary heart disease, there were significant positive adjusted associations for all adiposity measures, without interaction by sex. This was true for both quintiles and conventional cutpoints for obesity, although BMI-defined overweight (25-29.9 kg/m² was significant at midlife but not at baseline. Strengths of association for extreme quintiles (quintile 5 vs. quintile 1) were broadly comparable, but the highest effect estimates were for waist/hip ratio (hazard ratio = 1.56, 95% confidence interval: 1.25, 1.94) and BMI50 (hazard ratio = 1.71, 95% confidence interval: 1.37, 2.14), both of which remained significant after adjustment for mediators, BMI, or each other. Whether these differences translate to better risk prediction will require meta-analytical approaches, as will determination of prognostic cutpoints.
Keywords: Adiposity; Age Factors; Aged; Aged, 80 and over; Brain Ischemia; Coronary Disease; Female; Humans; Incidence; Male; Middle Aged; Obesity; Prevalence; Retrospective Studies; Risk Factors; Sex Factors; United States

Meta-analysis of gene-environment interaction: joint estimation of SNP and SNP × environment regression coefficients. - Manning, Alisa K; LaValley, Michael; Liu, Ching-Ti; Rice, Kenneth; An, Ping; Liu, Yongmei; Miljkovic, Iva; Rasmussen-Torvik, Laura; Harris, Tamara B; Province, Michael A; Borecki, Ingrid B; Florez, Jose C; et al. (Genet Epidemiol, 2011)
INTRODUCTION: Genetic discoveries are validated through the meta-analysis of genome-wide association scans in large international consortia. Because environmental variables may interact with genetic factors, investigation of differing genetic effects for distinct levels of an environmental exposure in these large consortia may yield additional susceptibility loci undetected by main effects analysis. We describe a method of joint meta-analysis (JMA) of SNP and SNP by Environment (SNP × E) regression coefficients for use in gene-environment interaction studies. METHODS: In testing SNP × E interactions, one approach uses a two degree of freedom test to identify genetic variants that influence the trait of interest. This approach detects both main and interaction effects between the trait and the SNP. We propose a method to jointly meta-analyze the SNP and SNP × E coefficients using multivariate generalized least squares. This approach provides confidence intervals of the two estimates, a joint significance test for SNP and SNP × E terms, and a test of homogeneity across samples. RESULTS: We present a simulation study comparing this method to four other methods of meta-analysis and demonstrate that the JMA performs better than the others when both main and interaction effects are present. Additionally, we implemented our methods in a meta-analysis of the association between SNPs from the type 2 diabetes-associated gene PPARG and log-transformed fasting insulin levels and interaction by body mass index in a combined sample of 19,466 individuals from five cohorts.
Keywords: Adult; Aged; Body Mass Index; Confidence Intervals; Diabetes Mellitus, Type 2; Environment; Fasting; Female; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Insulin; Least-Squares Analysis; Male; Mathematical Computing; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; PPAR gamma

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

N-terminal pro-B-type natriuretic peptide is associated with sudden cardiac death risk: the Cardiovascular Health Study. - Patton, Kristen K; Sotoodehnia, Nona; DeFilippi, Christopher; Siscovick, David S; Gottdiener, John S; Kronmal, Richard A (Heart Rhythm, 2011)
BACKGROUND: Sudden cardiac death (SCD), the cause of 250,000-450,000 deaths per year, is a major public health problem. The majority of those affected do not have a prior cardiovascular diagnosis. Elevated B-type natriuretic peptide levels have been associated with the risk of heart failure and mortality as well as with sudden death in women. OBJECTIVE: The purpose of this study was to examine the relationship between N-terminal pro-B-type natriuretic peptide (NT-proBNP) and SCD in the Cardiovascular Health Study population. METHODS: The risk of SCD associated with baseline NT-proBNP was examined in 5,447 participants. Covariate-adjusted Cox model regressions were used to estimate the hazard ratios of developing SCD as a function of baseline NT-proBNP. RESULTS: Over a median follow-up of 12.5 years (maximum 16), there were 289 cases of SCD. Higher NT-proBNP levels were strongly associated with SCD, with an unadjusted hazard ratio of 4.2 (95% confidence interval [2.9, 6.1]; P <.001) in the highest quintile compared with in the lowest. NT-proBNP remained associated with SCD even after adjustment for numerous clinical characteristics and risk factors (age, sex, race, and other associated conditions), with an adjusted hazard ratio for the fifth versus the first quintile of 2.5 (95% confidence interval [1.6, 3.8]; P <.001). CONCLUSION: NT-proBNP provides information regarding the risk of SCD in a community-based population of older adults, beyond other traditional risk factors. This biomarker may ultimately prove useful in targeting the population at risk with aggressive medical management of comorbid conditions.
Keywords: Age Distribution; Aged; Biomarkers; Cardiovascular Diseases; Cohort Studies; Confidence Intervals; Death, Sudden, Cardiac; Female; Humans; Incidence; Kaplan-Meier Estimate; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Assessment; Sex Distribution; Time Factors; United States

Separate and combined associations of body-mass index and abdominal adiposity with cardiovascular disease: collaborative analysis of 58 prospective studies. - Wormser, David; Kaptoge, Stephen; Di Angelantonio, Emanuele; Wood, Angela M; Pennells, Lisa; Thompson, Alex; Sarwar, Nadeem; Kizer, Jorge R; Lawlor, Debbie A; Nordestgaard, Børge G; Ridker, Paul; Salomaa, Veikko; et al. (Lancet, 2011)
BACKGROUND: Guidelines differ about the value of assessment of adiposity measures for cardiovascular disease risk prediction when information is available for other risk factors. We studied the separate and combined associations of body-mass index (BMI), waist circumference, and waist-to-hip ratio with risk of first-onset cardiovascular disease. METHODS: We used individual records from 58 cohorts to calculate hazard ratios (HRs) per 1 SD higher baseline values (4.56 kg/m(2) higher BMI, 12.6 cm higher waist circumference, and 0.083 higher waist-to-hip ratio) and measures of risk discrimination and reclassification. Serial adiposity assessments were used to calculate regression dilution ratios. RESULTS: Individual records were available for 221,934 people in 17 countries (14,297 incident cardiovascular disease outcomes; 1.87 million person-years at risk). Serial adiposity assessments were made in up to 63,821 people (mean interval 5.7 years [SD 3.9]). In people with BMI of 20 kg/m(2) or higher, HRs for cardiovascular disease were 1.23 (95% CI 1.17-1.29) with BMI, 1.27 (1.20-1.33) with waist circumference, and 1.25 (1.19-1.31) with waist-to-hip ratio, after adjustment for age, sex, and smoking status. After further adjustment for baseline systolic blood pressure, history of diabetes, and total and HDL cholesterol, corresponding HRs were 1.07 (1.03-1.11) with BMI, 1.10 (1.05-1.14) with waist circumference, and 1.12 (1.08-1.15) with waist-to-hip ratio. Addition of information on BMI, waist circumference, or waist-to-hip ratio to a cardiovascular disease risk prediction model containing conventional risk factors did not importantly improve risk discrimination (C-index changes of -0.0001, -0.0001, and 0.0008, respectively), nor classification of participants to categories of predicted 10-year risk (net reclassification improvement -0.19%, -0.05%, and -0.05%, respectively). Findings were similar when adiposity measures were considered in combination. Reproducibility was greater for BMI (regression dilution ratio 0.95, 95% CI 0.93-0.97) than for waist circumference (0.86, 0.83-0.89) or waist-to-hip ratio (0.63, 0.57-0.70). INTERPRETATION: BMI, waist circumference, and waist-to-hip ratio, whether assessed singly or in combination, do not importantly improve cardiovascular disease risk prediction in people in developed countries when additional information is available for systolic blood pressure, history of diabetes, and lipids. FUNDING: British Heart Foundation and UK Medical Research Council.
Keywords: Age Factors; Blood Pressure; Body Mass Index; Cardiovascular Diseases; Cholesterol; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Middle Aged; Obesity, Abdominal; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Factors; Smoking; Systole; Waist Circumference; Waist-Hip Ratio

Vitamin D, parathyroid hormone, and sudden cardiac death: results from the Cardiovascular Health Study. - Deo, Rajat; Katz, Ronit; Shlipak, Michael G; Sotoodehnia, Nona; Psaty, Bruce M; Sarnak, Mark J; Fried, Linda F; Chonchol, Michel; de Boer, Ian H; Enquobahrie, Daniel; Siscovick, David; Kestenbaum, Bryan (Hypertension, 2011)
Recent studies have demonstrated greater risks of cardiovascular events and mortality among persons who have lower 25-hydroxyvitamin D (25-OHD) and higher parathyroid hormone (PTH) levels. We sought to evaluate the association between markers of mineral metabolism and sudden cardiac death (SCD) among the 2312 participants from the Cardiovascular Health Study who were free of clinical cardiovascular disease at baseline. We estimated associations of baseline 25-OHD and PTH concentrations individually and in combination with SCD using Cox proportional hazards models after adjustment for demographics, cardiovascular risk factors, and kidney function. During a median follow-up of 14 years, there were 73 adjudicated SCD events. The annual incidence of SCD was greater among subjects who had lower 25-OHD concentrations, 2 events per 1000 for 25-OHD ≥20 ng/mL and 4 events per 1000 for 25-OHD <20 ng/mL. Similarly, SCD incidence was greater among subjects who had higher PTH concentrations, 2 events per 1000 for PTH <65 pg/mL and 4 events per 1000 for PTH ≥65 pg/mL. Multivariate adjustment attenuated associations of 25-OHD and PTH with SCD. Finally, 267 participants (11.7% of the cohort) had high PTH and low 25-OHD concentrations. This combination was associated with a >2-fold risk of SCD after adjustment (hazard ratio: 2.19 [95% CI: 1.17-4.10]; P=0.017) compared with participants with normal levels of PTH and 25-OHD. The combination of lower 25-OHD and higher PTH concentrations appears to be associated independently with SCD risk among older adults without cardiovascular disease.
Keywords: Aged; Cardiovascular Diseases; Comorbidity; Death, Sudden, Cardiac; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Kidney; Male; Middle Aged; Minerals; Parathyroid Hormone; Proportional Hazards Models; Risk Factors; Socioeconomic Factors; United States; Vitamin D

Age and association of kidney measures with mortality and end-stage renal disease. - Hallan, Stein I; Matsushita, Kunihiro; Sang, Yingying; Mahmoodi, Bakhtawar K; Black, Corri; Ishani, Areef; Kleefstra, Nanne; Naimark, David; Roderick, Paul; Tonelli, Marcello; Wetzels, Jack F M; Astor, Brad C; et al. (JAMA, 2012)
CONTEXT: Chronic kidney disease (CKD) is prevalent in older individuals, but the risk implications of low estimated glomerular filtration rate (eGFR) and high albuminuria across the full age range are controversial. OBJECTIVE: To evaluate possible effect modification (interaction) by age of the association of eGFR and albuminuria with clinical risk, examining both relative and absolute risks. DESIGN, SETTING, AND PARTICIPANTS: Individual-level meta-analysis including 2,051,244 participants from 33 general population or high-risk (of vascular disease) cohorts and 13 CKD cohorts from Asia, Australasia, Europe, and North/South America, conducted in 1972-2011 with a mean follow-up time of 5.8 years (range, 0-31 years). MAIN OUTCOME MEASURES: Hazard ratios (HRs) of mortality and end-stage renal disease (ESRD) according to eGFR and albuminuria were meta-analyzed across age categories after adjusting for sex, race, cardiovascular disease, diabetes, systolic blood pressure, cholesterol, body mass index, and smoking. Absolute risks were estimated using HRs and average incidence rates. RESULTS: Mortality (112,325 deaths) and ESRD (8411 events) risks were higher at lower eGFR and higher albuminuria in every age category. In general and high-risk cohorts, relative mortality risk for reduced eGFR decreased with increasing age; eg, adjusted HRs at an eGFR of 45 mL/min/1.73 m2 vs 80 mL/min/1.73 m2 were 3.50 (95% CI, 2.55-4.81), 2.21 (95% CI, 2.02-2.41), 1.59 (95% CI, 1.42-1.77), and 1.35 (95% CI, 1.23-1.48) in age categories 18-54, 55-64, 65-74, and ≥75 years, respectively (P <.05 for age interaction). Absolute risk differences for the same comparisons were higher at older age (9.0 [95% CI, 6.0-12.8], 12.2 [95% CI, 10.3-14.3], 13.3 [95% CI, 9.0-18.6], and 27.2 [95% CI, 13.5-45.5] excess deaths per 1000 person-years, respectively). For increased albuminuria, reduction of relative risk with increasing age was less evident, while differences in absolute risk were higher in older age categories (7.5 [95% CI, 4.3-11.9], 12.2 [95% CI, 7.9-17.6], 22.7 [95% CI, 15.3-31.6], and 34.3 [95% CI, 19.5-52.4] excess deaths per 1000 person-years, respectively by age category, at an albumin-creatinine ratio of 300 mg/g vs 10 mg/g). In CKD cohorts, adjusted relative hazards of mortality did not decrease with age. In all cohorts, ESRD relative risks and absolute risk differences at lower eGFR or higher albuminuria were comparable across age categories. CONCLUSIONS: Both low eGFR and high albuminuria were independently associated with mortality and ESRD regardless of age across a wide range of populations. Mortality showed lower relative risk but higher absolute risk differences at older age.
Keywords: Adolescent; Adult; Age Factors; Aged; Albuminuria; Cohort Studies; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Risk; Young Adult

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

Association of genetic loci with sleep apnea in European Americans and African-Americans: the Candidate Gene Association Resource (CARe). - Patel, Sanjay R; Goodloe, Robert; De, Gourab; Kowgier, Matthew; Weng, Jia; Buxbaum, Sarah G; Cade, Brian; Fulop, Tibor; Gharib, Sina A; Gottlieb, Daniel J; Hillman, David; Larkin, Emma K; et al. (PLoS One, 2012)
Although obstructive sleep apnea (OSA) is known to have a strong familial basis, no genetic polymorphisms influencing apnea risk have been identified in cross-cohort analyses. We utilized the National Heart, Lung, and Blood Institute (NHLBI) Candidate Gene Association Resource (CARe) to identify sleep apnea susceptibility loci. Using a panel of 46,449 polymorphisms from roughly 2,100 candidate genes on a customized Illumina iSelect chip, we tested for association with the apnea hypopnea index (AHI) as well as moderate to severe OSA (AHI≥15) in 3,551 participants of the Cleveland Family Study and two cohorts participating in the Sleep Heart Health Study.Among 647 African-Americans, rs11126184 in the pleckstrin (PLEK) gene was associated with OSA while rs7030789 in the lysophosphatidic acid receptor 1 (LPAR1) gene was associated with AHI using a chip-wide significance threshold of p-value<2×10(-6). Among 2,904 individuals of European ancestry, rs1409986 in the prostaglandin E2 receptor (PTGER3) gene was significantly associated with OSA. Consistency of effects between rs7030789 and rs1409986 in LPAR1 and PTGER3 and apnea phenotypes were observed in independent clinic-based cohorts.Novel genetic loci for apnea phenotypes were identified through the use of customized gene chips and meta-analyses of cohort data with replication in clinic-based samples. The identified SNPs all lie in genes associated with inflammation suggesting inflammation may play a role in OSA pathogenesis.
Keywords: Adult; African Americans; Aged; Alleles; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Polysomnography; Sleep Apnea, Obstructive

Association of mild to moderate chronic kidney disease with venous thromboembolism: pooled analysis of five prospective general population cohorts. - Mahmoodi, Bakhtawar K; Gansevoort, Ron T; Næss, Inger Anne; Lutsey, Pamela L; Brækkan, Sigrid K; Veeger, Nic J G M; Brodin, Ellen E; Meijer, Karina; Sang, Yingying; Matsushita, Kunihiro; Hallan, Stein I; Hammerstrøm, Jens; et al. (Circulation, 2012)
BACKGROUND: Recent findings suggest that chronic kidney disease (CKD) may be associated with an increased risk of venous thromboembolism (VTE). Given the high prevalence of mild-to-moderate CKD in the general population, in depth analysis of this association is warranted. METHODS AND RESULTS: We pooled individual participant data from 5 community-based cohorts from Europe (second Nord-Trøndelag Health Study [HUNT2], Prevention of Renal and Vascular End-stage Disease [PREVEND], and the Tromsø study) and the United States (Atherosclerosis Risks in Communities [ARIC] and Cardiovascular Health Study [CHS]) to assess the association of estimated glomerular filtration rate (eGFR), albuminuria, and CKD with objectively verified VTE. To estimate adjusted hazard ratios for VTE, categorical and continuous spline models were fit by using Cox regression with shared-frailty or random-effect meta-analysis. A total of 1178 VTE events occurred over 599 453 person-years follow-up. Relative to eGFR 100 mL/min per 1.73 m(2), hazard ratios for VTE were 1.29 (95% confidence interval, 1.04-1.59) for eGFR 75, 1.31 (1.00-1.71) for eGFR 60, 1.82 (1.27-2.60) for eGFR 45, and 1.95 (1.26-3.01) for eGFR 30 mL/min per 1.73 m(2). In comparison with an albumin-to-creatinine ratio (ACR) of 5.0 mg/g, the hazard ratios for VTE were 1.34 (1.04-1.72) for ACR 30 mg/g, 1.60 (1.08-2.36) for ACR 300 mg/g, and 1.92 (1.19-3.09) for ACR 1000 mg/g. There was no interaction between clinical categories of eGFR and ACR (P=0.20). The adjusted hazard ratio for CKD, defined as eGFR <60 mL/min per 1.73 m(2) or albuminuria ≥30 mg/g, (versus no CKD) was 1.54 (95% confidence interval, 1.15-2.06). Associations were consistent in subgroups according to age, sex, and comorbidities, and for unprovoked versus provoked VTE, as well. CONCLUSIONS: Both eGFR and ACR are independently associated with increased risk of VTE in the general population, even across the normal eGFR and ACR ranges.
Keywords: Aged; Cohort Studies; Europe; Female; Humans; Incidence; Male; Middle Aged; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Severity of Illness Index; Venous Thromboembolism

Association of weight status with mortality in adults with incident diabetes. - Carnethon, Mercedes R; De Chavez, Peter John D; Biggs, Mary L; Lewis, Cora E; Pankow, James S; Bertoni, Alain G; Golden, Sherita H; Liu, Kiang; Mukamal, Kenneth J; Campbell-Jenkins, Brenda; Dyer, Alan R (JAMA, 2012)
CONTEXT: Type 2 diabetes in normal-weight adults (body mass index [BMI] <25) is a representation of the metabolically obese normal-weight phenotype with unknown mortality consequences. OBJECTIVE: To test the association of weight status with mortality in adults with new-onset diabetes in order to minimize the influence of diabetes duration and voluntary weight loss on mortality. DESIGN, SETTING, AND PARTICIPANTS: Pooled analysis of 5 longitudinal cohort studies: Atherosclerosis Risk in Communities study, 1990-2006; Cardiovascular Health Study, 1992-2008; Coronary Artery Risk Development in Young Adults, 1987-2011; Framingham Offspring Study, 1979-2007; and Multi-Ethnic Study of Atherosclerosis, 2002-2011. A total of 2625 participants with incident diabetes contributed 27,125 person-years of follow-up. Included were men and women (age >40 years) who developed incident diabetes based on fasting glucose 126 mg/dL or greater or newly initiated diabetes medication and who had concurrent measurements of BMI. Participants were classified as normal weight if their BMI was 18.5 to 24.99 or overweight/obese if BMI was 25 or greater. MAIN OUTCOME MEASURES: Total, cardiovascular, and noncardiovascular mortality. RESULTS: The proportion of adults who were normal weight at the time of incident diabetes ranged from 9% to 21% (overall 12%). During follow-up, 449 participants died: 178 from cardiovascular causes and 253 from noncardiovascular causes (18 were not classified). The rates of total, cardiovascular, and noncardiovascular mortality were higher in normal-weight participants (284.8, 99.8, and 198.1 per 10,000 person-years, respectively) than in overweight/obese participants (152.1, 67.8, and 87.9 per 10,000 person-years, respectively). After adjustment for demographic characteristics and blood pressure, lipid levels, waist circumference, and smoking status, hazard ratios comparing normal-weight participants with overweight/obese participants for total, cardiovascular, and noncardiovascular mortality were 2.08 (95% CI, 1.52-2.85), 1.52 (95% CI, 0.89-2.58), and 2.32 (95% CI, 1.55-3.48), respectively. CONCLUSION: Adults who were normal weight at the time of incident diabetes had higher mortality than adults who are overweight or obese.
Keywords: Adult; Aged; Aged, 80 and over; Body Mass Index; Body Weight; Cardiovascular Diseases; Cause of Death; Diabetes Mellitus, Type 2; Female; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Overweight; United States

Associations between incident ischemic stroke events and stroke and cardiovascular disease-related genome-wide association studies single nucleotide polymorphisms in the Population Architecture Using Genomics and Epidemiology study. - Carty, Cara L; Bůzková, Petra; Fornage, Myriam; Franceschini, Nora; Cole, Shelley; Heiss, Gerardo; Hindorff, Lucia A; Howard, Barbara V; Mann, Sue; Martin, Lisa W; Zhang, Ying; Matise, Tara C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genome-wide association studies (GWAS) have identified loci associated with ischemic stroke (IS) and cardiovascular disease (CVD) in European-descent individuals, but their replication in different populations has been largely unexplored. METHODS AND RESULTS: Nine single nucleotide polymorphisms (SNPs) selected from GWAS and meta-analyses of stroke, and 86 SNPs previously associated with myocardial infarction and CVD risk factors, including blood lipids (high density lipoprotein [HDL], low density lipoprotein [LDL], and triglycerides), type 2 diabetes, and body mass index (BMI), were investigated for associations with incident IS in European Americans (EA) N=26 276, African-Americans (AA) N=8970, and American Indians (AI) N=3570 from the Population Architecture using Genomics and Epidemiology Study. Ancestry-specific fixed effects meta-analysis with inverse variance weighting was used to combine study-specific log hazard ratios from Cox proportional hazards models. Two of 9 stroke SNPs (rs783396 and rs1804689) were significantly associated with [corrected] IS hazard in AA; none were significant in this large EA cohort. Of 73 CVD risk factor SNPs tested in EA, 2 (HDL and triglycerides SNPs) were associated with IS. In AA, SNPs associated with LDL, HDL, and BMI were significantly associated with IS (3 of 86 SNPs tested). Out of 58 SNPs tested in AI, 1 LDL SNP was significantly associated with IS. CONCLUSIONS: Our analyses showing lack of replication in spite of reasonable power for many stroke SNPs and differing results by ancestry highlight the need to follow up on GWAS findings and conduct genetic association studies in diverse populations. We found modest IS associations with BMI and lipids SNPs, though these findings require confirmation.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Female; Genetics, Population; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Triglycerides

Associations of kidney disease measures with mortality and end-stage renal disease in individuals with and without diabetes: a meta-analysis. - Fox, Caroline S; Matsushita, Kunihiro; Woodward, Mark; Bilo, Henk J G; Chalmers, John; Heerspink, Hiddo J Lambers; Lee, Brian J; Perkins, Robert M; Rossing, Peter; Sairenchi, Toshimi; Tonelli, Marcello; Vassalotti, Joseph A; et al. (Lancet, 2012)
BACKGROUND: Chronic kidney disease is characterised by low estimated glomerular filtration rate (eGFR) and high albuminuria, and is associated with adverse outcomes. Whether these risks are modified by diabetes is unknown. METHODS: We did a meta-analysis of studies selected according to Chronic Kidney Disease Prognosis Consortium criteria. Data transfer and analyses were done between March, 2011, and June, 2012. We used Cox proportional hazards models to estimate the hazard ratios (HR) of mortality and end-stage renal disease (ESRD) associated with eGFR and albuminuria in individuals with and without diabetes. FINDINGS: We analysed data for 1,024,977 participants (128,505 with diabetes) from 30 general population and high-risk cardiovascular cohorts and 13 chronic kidney disease cohorts. In the combined general population and high-risk cohorts with data for all-cause mortality, 75,306 deaths occurred during a mean follow-up of 8·5 years (SD 5·0). In the 23 studies with data for cardiovascular mortality, 21,237 deaths occurred from cardiovascular disease during a mean follow-up of 9·2 years (SD 4·9). In the general and high-risk cohorts, mortality risks were 1·2-1·9 times higher for participants with diabetes than for those without diabetes across the ranges of eGFR and albumin-to-creatinine ratio (ACR). With fixed eGFR and ACR reference points in the diabetes and no diabetes groups, HR of mortality outcomes according to lower eGFR and higher ACR were much the same in participants with and without diabetes (eg, for all-cause mortality at eGFR 45 mL/min per 1·73 m(2) [vs 95 mL/min per 1·73 m(2)], HR 1·35; 95% CI 1·18-1·55; vs 1·33; 1·19-1·48 and at ACR 30 mg/g [vs 5 mg/g], 1·50; 1·35-1·65 vs 1·52; 1·38-1·67). The overall interactions were not significant. We identified much the same findings for ESRD in the chronic kidney disease cohorts. INTERPRETATION: Despite higher risks for mortality and ESRD in diabetes, the relative risks of these outcomes by eGFR and ACR are much the same irrespective of the presence or absence of diabetes, emphasising the importance of kidney disease as a predictor of clinical outcomes. FUNDING: US National Kidney Foundation.
Keywords: Aged; Albuminuria; Cardiovascular Diseases; Cause of Death; Diabetic Nephropathies; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Risk Factors

Automated recognition of obstructive sleep apnea syndrome using support vector machine classifier. - Al-Angari, Haitham M; Sahakian, Alan V (IEEE Trans Inf Technol Biomed, 2012)
Obstructive sleep apnea (OSA) is a common sleep disorder that causes pauses of breathing due to repetitive obstruction of the upper airways of the respiratory system. The effect of this phenomenon can be observed in other physiological signals like the heart rate variability, oxygen saturation, and the respiratory effort signals. In this study, features from these signals were extracted from 50 control and 50 OSA patients from the Sleep Heart Health Study database and implemented for minute and subject classifications. A support vector machine (SVM) classifier was used with linear and second-order polynomial kernels. For the minute classification, the respiratory features had the highest sensitivity while the oxygen saturation gave the highest specificity. The polynomial kernel always had better performance and the highest accuracy of 82.4% (Sen: 69.9%, Spec: 91.4%) was achieved using the combined-feature classifier. For subject classification, the polynomial kernel had a clear improvement in the oxygen saturation accuracy as the highest accuracy of 95% was achieved by both the oxygen saturation (Sen: 100%, Spec: 90.2%) and the combined-feature (Sen: 91.8%, Spec: 98.0%). Further analysis of the SVM with other kernel types might be useful for optimizing the classifier with the appropriate features for an OSA automated detection algorithm.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Heart Rate; Humans; Middle Aged; Oximetry; Oxygen; Pattern Recognition, Automated; Polysomnography; Respiratory Rate; Sleep Apnea, Obstructive; Support Vector Machine

Common genetic variants differentially influence the transition from clinically defined states of fasting glucose metabolism. - Walford, G A; Green, T; Neale, B; Isakova, T; Rotter, J I; Grant, S F A; Fox, C S; Pankow, J S; Wilson, J G; Meigs, J B; Siscovick, D S; Bowden, D W; et al. (Diabetologia, 2012)
AIMS/HYPOTHESIS: Common genetic variants have been associated with type 2 diabetes. We hypothesised that a subset of these variants may have different effects on the transition from normal fasting glucose (NFG) to impaired fasting glucose (IFG) than on that from IFG to diabetes. METHODS: We identified 16 type 2 diabetes risk variants from the Illumina Broad Candidate-gene Association Resource (CARe) array genotyped in 26,576 CARe participants. Participants were categorised at baseline as NFG, IFG or type 2 diabetic (n = 16,465, 8,017 or 2,291, respectively). Using Cox proportional hazards and likelihood ratio tests (LRTs), we compared rates of progression by genotype for 4,909 (NFG to IFG) and 1,518 (IFG to type 2 diabetes) individuals, respectively. We then performed multinomial regression analyses at baseline, comparing the risk of assignment to the NFG, IFG or diabetes groups by genotype. RESULTS: The rate of progression from NFG to IFG was significantly greater in participants carrying the risk allele at MTNR1B (p = 1 × 10(-4)), nominally greater at GCK and SLC30A8 (p < 0.05) and nominally smaller at IGF2BP2 (p = 0.01) than the rate of progression from IFG to diabetes by the LRT. Results of the baseline, multinomial regression model were consistent with these findings. CONCLUSIONS/INTERPRETATION: Common genetic risk variants at GCK, SLC30A8, IGF2BP2 and MTNR1B influence to different extents the development of IFG and the transition from IFG to type 2 diabetes. Our findings may have implications for understanding the genetic contribution of these variants to the development of IFG and type 2 diabetes.
Keywords: Adult; Aged; Blood Glucose; Cohort Studies; Diabetes Mellitus, Type 2; Disease Progression; Fasting; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Proportional Hazards Models; Regression Analysis; Risk

Comparison of risk prediction using the CKD-EPI equation and the MDRD study equation for estimated glomerular filtration rate. - Matsushita, Kunihiro; Mahmoodi, Bakhtawar K; Woodward, Mark; Emberson, Jonathan R; Jafar, Tazeen H; Jee, Sun Ha; Polkinghorne, Kevan R; Shankar, Anoop; Smith, David H; Tonelli, Marcello; Warnock, David G; Wen, Chi-Pang; et al. (JAMA, 2012)
CONTEXT: The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation more accurately estimates glomerular filtration rate (GFR) than the Modification of Diet in Renal Disease (MDRD) Study equation using the same variables, especially at higher GFR, but definitive evidence of its risk implications in diverse settings is lacking. OBJECTIVE: To evaluate risk implications of estimated GFR using the CKD-EPI equation compared with the MDRD Study equation in populations with a broad range of demographic and clinical characteristics. DESIGN, SETTING, AND PARTICIPANTS: A meta-analysis of data from 1.1 million adults (aged ≥ 18 years) from 25 general population cohorts, 7 high-risk cohorts (of vascular disease), and 13 CKD cohorts. Data transfer and analyses were conducted between March 2011 and March 2012. MAIN OUTCOME MEASURES: All-cause mortality (84,482 deaths from 40 cohorts), cardiovascular mortality (22,176 events from 28 cohorts), and end-stage renal disease (ESRD) (7644 events from 21 cohorts) during 9.4 million person-years of follow-up; the median of mean follow-up time across cohorts was 7.4 years (interquartile range, 4.2-10.5 years). RESULTS: Estimated GFR was classified into 6 categories (≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m(2)) by both equations. Compared with the MDRD Study equation, 24.4% and 0.6% of participants from general population cohorts were reclassified to a higher and lower estimated GFR category, respectively, by the CKD-EPI equation, and the prevalence of CKD stages 3 to 5 (estimated GFR <60 mL/min/1.73 m(2)) was reduced from 8.7% to 6.3%. In estimated GFR of 45 to 59 mL/min/1.73 m(2) by the MDRD Study equation, 34.7% of participants were reclassified to estimated GFR of 60 to 89 mL/min/1.73 m(2) by the CKD-EPI equation and had lower incidence rates (per 1000 person-years) for the outcomes of interest (9.9 vs 34.5 for all-cause mortality, 2.7 vs 13.0 for cardiovascular mortality, and 0.5 vs 0.8 for ESRD) compared with those not reclassified. The corresponding adjusted hazard ratios were 0.80 (95% CI, 0.74-0.86) for all-cause mortality, 0.73 (95% CI, 0.65-0.82) for cardiovascular mortality, and 0.49 (95% CI, 0.27-0.88) for ESRD. Similar findings were observed in other estimated GFR categories by the MDRD Study equation. Net reclassification improvement based on estimated GFR categories was significantly positive for all outcomes (range, 0.06-0.13; all P < .001). Net reclassification improvement was similarly positive in most subgroups defined by age (<65 years and ≥65 years), sex, race/ethnicity (white, Asian, and black), and presence or absence of diabetes and hypertension. The results in the high-risk and CKD cohorts were largely consistent with the general population cohorts. CONCLUSION: The CKD-EPI equation classified fewer individuals as having CKD and more accurately categorized the risk for mortality and ESRD than did the MDRD Study equation across a broad range of populations.
Keywords: African Continental Ancestry Group; Aged; Algorithms; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Decision Support Techniques; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Models, Theoretical; Risk Assessment; Sex Factors

Consistent directions of effect for established type 2 diabetes risk variants across populations: the population architecture using Genomics and Epidemiology (PAGE) Consortium. - Haiman, Christopher A; Fesinmeyer, Megan D; Spencer, Kylee L; Bůzková, Petra; Voruganti, V Saroja; Wan, Peggy; Haessler, Jeff; Franceschini, Nora; Monroe, Kristine R; Howard, Barbara V; Jackson, Rebecca D; Florez, Jose C; et al. (Diabetes, 2012)
Common genetic risk variants for type 2 diabetes (T2D) have primarily been identified in populations of European and Asian ancestry. We tested whether the direction of association with 20 T2D risk variants generalizes across six major racial/ethnic groups in the U.S. as part of the Population Architecture using Genomics and Epidemiology Consortium (16,235 diabetes case and 46,122 control subjects of European American, African American, Hispanic, East Asian, American Indian, and Native Hawaiian ancestry). The percentage of positive (odds ratio [OR] >1 for putative risk allele) associations ranged from 69% in American Indians to 100% in European Americans. Of the nine variants where we observed significant heterogeneity of effect by racial/ethnic group (P(heterogeneity) < 0.05), eight were positively associated with risk (OR >1) in at least five groups. The marked directional consistency of association observed for most genetic variants across populations implies a shared functional common variant in each region. Fine-mapping of all loci will be required to reveal markers of risk that are important within and across populations.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Metagenomics; Middle Aged; Population Groups; Risk; Risk Factors

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

Fine-mapping and initial characterization of QT interval loci in African Americans. - Avery, Christy L; Sethupathy, Praveen; Buyske, Steven; He, Qianchuan; Lin, Dan-Yu; Arking, Dan E; Carty, Cara L; Duggan, David; Fesinmeyer, Megan D; Hindorff, Lucia A; Jeff, Janina M; Klein, Liviu; et al. (PLoS Genet, 2012)
The QT interval (QT) is heritable and its prolongation is a risk factor for ventricular tachyarrhythmias and sudden death. Most genetic studies of QT have examined European ancestral populations; however, the increased genetic diversity in African Americans provides opportunities to narrow association signals and identify population-specific variants. We therefore evaluated 6,670 SNPs spanning eleven previously identified QT loci in 8,644 African American participants from two Population Architecture using Genomics and Epidemiology (PAGE) studies: the Atherosclerosis Risk in Communities study and Women's Health Initiative Clinical Trial. Of the fifteen known independent QT variants at the eleven previously identified loci, six were significantly associated with QT in African American populations (P≤1.20×10(-4)): ATP1B1, PLN1, KCNQ1, NDRG4, and two NOS1AP independent signals. We also identified three population-specific signals significantly associated with QT in African Americans (P≤1.37×10(-5)): one at NOS1AP and two at ATP1B1. Linkage disequilibrium (LD) patterns in African Americans assisted in narrowing the region likely to contain the functional variants for several loci. For example, African American LD patterns showed that 0 SNPs were in LD with NOS1AP signal rs12143842, compared with European LD patterns that indicated 87 SNPs, which spanned 114.2 Kb, were in LD with rs12143842. Finally, bioinformatic-based characterization of the nine African American signals pointed to functional candidates located exclusively within non-coding regions, including predicted binding sites for transcription factors such as TBX5, which has been implicated in cardiac structure and conductance. In this detailed evaluation of QT loci, we identified several African Americans SNPs that better define the association with QT and successfully narrowed intervals surrounding established loci. These results demonstrate that the same loci influence variation in QT across multiple populations, that novel signals exist in African Americans, and that the SNPs identified as strong candidates for functional evaluation implicate gene regulatory dysfunction in QT prolongation.
Keywords: African Americans; Aged; Computational Biology; Electrocardiography; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors; Tachycardia; United States

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genetic variation in F3 (tissue factor) and the risk of incident venous thrombosis: meta-analysis of eight studies. - Smith, N L; Heit, J A; Tang, W; Teichert, M; Chasman, D I; Morange, P-E (J Thromb Haemost, 2012)
Keywords: Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; Incidence; Male; Middle Aged; Phenotype; Regression Analysis; Risk Assessment; Risk Factors; Thromboplastin; Venous Thrombosis

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Hemoglobin A1c and arterial and ventricular stiffness in older adults. - Zieman, Susan J; Kamineni, Aruna; Ix, Joachim H; Barzilay, Joshua; Djoussé, Luc; Kizer, Jorge R; Biggs, Mary L; de Boer, Ian H; Chonchol, Michel; Gottdiener, John S; Selvin, Elizabeth; Newman, Anne B; et al. (PLoS One, 2012)
OBJECTIVE: Arterial and ventricular stiffening are characteristics of diabetes and aging which confer significant morbidity and mortality; advanced glycation endproducts (AGE) are implicated in this stiffening pathophysiology. We examined the association between HbA(1c), an AGE, with arterial and ventricular stiffness measures in older individuals without diabetes. RESEARCH DESIGN & METHODS: Baseline HbA(1c) was measured in 830 participants free of diabetes defined by fasting glucose or medication use in the Cardiovascular Health Study, a population-based cohort study of adults aged ≥ 65 years. We performed cross-sectional analyses using baseline exam data including echocardiography, ankle and brachial blood pressure measurement, and carotid ultrasonography. We examined the adjusted associations between HbA(1c) and multiple arterial and ventricular stiffness measures by linear regression models and compared these results to the association of fasting glucose (FG) with like measures. RESULTS: HbA(1c) was correlated with fasting and 2-hour postload glucose levels (r = 0.21; p<0.001 for both) and positively associated with greater body-mass index and black race. In adjusted models, HbA(1c) was not associated with any measure of arterial or ventricular stiffness, including pulse pressure (PP), carotid intima-media thickness, ankle-brachial index, end-arterial elastance, or left ventricular mass (LVM). FG levels were positively associated with systolic, diastolic and PP and LVM. CONCLUSIONS: In this sample of older adults without diabetes, HbA(1c) was not associated with arterial or ventricular stiffness measures, whereas FG levels were. The role of AGE in arterial and ventricular stiffness in older adults may be better assessed using alternate AGE markers.
Keywords: Adult; African Continental Ancestry Group; Aged; Ankle Brachial Index; Arteries; Blood Glucose; Blood Pressure; Body Mass Index; Cross-Sectional Studies; Fasting; Female; Genetic Association Studies; Glycated Hemoglobin A; Glycation End Products, Advanced; Heart Ventricles; Humans; Male; Middle Aged; Ultrasonography; Vascular Stiffness

Impact of ancestry and common genetic variants on QT interval in African Americans. - Smith, J Gustav; Avery, Christy L; Evans, Daniel S; Nalls, Michael A; Meng, Yan A; Smith, Erin N; Palmer, Cameron; Tanaka, Toshiko; Mehra, Reena; Butler, Anne M; Young, Taylor; Buxbaum, Sarah G; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Ethnic differences in cardiac arrhythmia incidence have been reported, with a particularly high incidence of sudden cardiac death and low incidence of atrial fibrillation in individuals of African ancestry. We tested the hypotheses that African ancestry and common genetic variants are associated with prolonged duration of cardiac repolarization, a central pathophysiological determinant of arrhythmia, as measured by the electrocardiographic QT interval. METHODS AND RESULTS: First, individual estimates of African and European ancestry were inferred from genome-wide single-nucleotide polymorphism (SNP) data in 7 population-based cohorts of African Americans (n=12,097) and regressed on measured QT interval from ECGs. Second, imputation was performed for 2.8 million SNPs, and a genome-wide association study of QT interval was performed in 10 cohorts (n=13,105). There was no evidence of association between genetic ancestry and QT interval (P=0.94). Genome-wide significant associations (P<2.5 × 10(-8)) were identified with SNPs at 2 loci, upstream of the genes NOS1AP (rs12143842, P=2 × 10(-15)) and ATP1B1 (rs1320976, P=2 × 10(-10)). The most significant SNP in NOS1AP was the same as the strongest SNP previously associated with QT interval in individuals of European ancestry. Low probability values (P<10(-5)) were observed for SNPs at several other loci previously identified in genome-wide association studies in individuals of European ancestry, including KCNQ1, KCNH2, LITAF, and PLN. CONCLUSIONS: We observed no difference in duration of cardiac repolarization with global genetic indices of African American ancestry. In addition, our genome-wide association study extends the association of polymorphisms at several loci associated with repolarization in individuals of European ancestry to include individuals of African ancestry.
Keywords: Adult; African Americans; Aged; Electrocardiography; European Continental Ancestry Group; Female; Genealogy and Heraldry; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Impact of blood pressure and blood pressure change during middle age on the remaining lifetime risk for cardiovascular disease: the cardiovascular lifetime risk pooling project. - Allen, Norrina; Berry, Jarett D; Ning, Hongyan; Van Horn, Linda; Dyer, Alan; Lloyd-Jones, Donald M (Circulation, 2012)
BACKGROUND: Prior estimates of lifetime risk (LTR) for cardiovascular disease (CVD) examined the impact of blood pressure (BP) at the index age and did not account for changes in BP over time. We examined how changes in BP during middle age affect LTR for CVD, coronary heart disease, and stroke. METHODS AND RESULTS: Data from 7 diverse US cohort studies were pooled. Remaining LTRs for CVD, coronary heart disease, and stroke were estimated for white and black men and women with death free of CVD as a competing event. LTRs for CVD by BP strata and by changes in BP over an average of 14 years were estimated. Starting at 55 years of age, we followed up 61 585 men and women for 700 000 person-years. LTR for CVD was 52.5% (95% confidence interval, 51.3-53.7) for men and 39.9% (95% confidence interval, 38.7-41.0) for women. LTR for CVD was higher for blacks and increased with increasing BP at index age. Individuals who maintained or decreased their BP to normal levels had the lowest remaining LTR for CVD, 22% to 41%, compared with individuals who had or developed hypertension by 55 years of age, 42% to 69%, suggesting a dose-response effect for the length of time at high BP levels. CONCLUSIONS: Individuals who experience increases or decreases in BP in middle age have associated higher and lower remaining LTR for CVD. Prevention efforts should continue to emphasize the importance of lowering BP and avoiding or delaying the incidence of hypertension to reduce the LTR for CVD.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Humans; Hypertension; Life Tables; Longitudinal Studies; Male; Middle Aged; Risk Factors

Leukocyte telomere length is associated with noninvasively measured age-related disease: The Cardiovascular Health Study. - Sanders, Jason L; Fitzpatrick, Annette L; Boudreau, Robert M; Arnold, Alice M; Aviv, Abraham; Kimura, Masayuki; Fried, Linda F; Harris, Tamara B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2012)
BACKGROUND: Most studies of leukocyte telomere length (LTL) focus on diagnosed disease in one system. A more encompassing depiction of health is disease burden, defined here as the sum of noninvasively measured markers of structure or function in different organ systems. We determined if (a) shorter LTL is associated with greater age-related disease burden and (b) shorter LTL is less strongly associated with disease in individual systems or diagnosed chronic conditions (cardiovascular disease, stroke, pulmonary disease, diabetes, kidney disease, arthritis, or depression). METHODS: LTL was measured by Southern blots of terminal restriction fragment length. Age-related disease was measured noninvasively and included carotid intima-media thickness, lung vital capacity, white matter grade, cystatin-C, and fasting glucose; each graded 0 (best tertile), 1 (middle tertile), or 2 (worst tertile) and summed (0 to 10) to estimate disease burden. Of 419 participants randomly selected for LTL measurement, 236 had disease burden assessed (mean [SD] age 74.2 [4.9] years, 42.4% male, 86.8% white, and 13.2% black). RESULTS: Mean (SD) LTL was 6,312 (615) bp, and disease score was 4.7 (2.1) points. An SD higher disease score (β [SE] = -132 [47] bp, p < .01), age (β [SE] = -107 [46], p = .02) or carotid thickness (β [SE] = -95 [40] bp, p = .02) was associated with shorter LTL, but diagnosed conditions or number of conditions were not associated with LTL. Disease score attenuated the effect of age on LTL by 35%. CONCLUSION: LTL was associated with a characterization of age-related disease burden across multiple physiologic systems, which was comparable to, but independent of, its association with age.
Keywords: African Americans; Aged; Aged, 80 and over; Cardiovascular Diseases; Carotid Intima-Media Thickness; Chronic Disease; Cystatin C; European Continental Ancestry Group; Female; Humans; Leukocytes; Lung; Male; Middle Aged; Telomere Homeostasis

Lifetime risk and years lived free of total cardiovascular disease. - Wilkins, John T; Ning, Hongyan; Berry, Jarett; Zhao, Lihui; Dyer, Alan R; Lloyd-Jones, Donald M (JAMA, 2012)
CONTEXT: Estimates of lifetime risk for total cardiovascular disease (CVD) may provide projections of the future population burden of CVD and may assist in clinician-patient risk communication. To date, no lifetime risk estimates of total CVD have been reported. OBJECTIVES: To calculate lifetime risk estimates of total CVD by index age (45, 55, 65, 75 years) and risk factor strata and to estimate years lived free of CVD across risk factor strata. DESIGN, SETTING, AND PARTICIPANTS: Pooled survival analysis of as many as 905,115 person-years of data from 1964 through 2008 from 5 National Heart, Lung, and Blood Institute-funded community-based cohorts: Framingham Heart Study, Framingham Offspring Study, Atherosclerosis Risk in Communities Study, Chicago Heart Association Detection Project in Industry Study, and Cardiovascular Health Study. All participants were free of CVD at baseline with risk factor data (blood pressure [BP], total cholesterol [TC], diabetes, and smoking status) and total CVD outcome data. MAIN OUTCOME MEASURES: Any total CVD event (including fatal and nonfatal coronary heart disease, all forms of stroke, congestive heart failure, and other CVD deaths). RESULTS: At an index age of 45 years, overall lifetime risk for total CVD was 60.3% (95% CI, 59.3%-61.2%) for men and 55.6% (95% CI, 54.5%-56.7%) for women. Men had higher lifetime risk estimates than women across all index ages. At index ages 55 and 65 years, men and women with at least 1 elevated risk factor (BP, 140-149/90-99 mm Hg; or TC, 200-239 mg/dL; but no diabetes or smoking), 1 major risk factor, or at least 2 major risk factors (BP, ≥160/100 mm Hg or receiving treatment; TC, ≥240 mg/dL or receiving treatment; diabetes mellitus; or current smoking) had lifetime risk estimates to age 95 years that exceeded 50%. Despite an optimal risk factor profile (BP, <120/80 mm Hg; TC, <180 mg/dL; and no smoking or diabetes), men and women at the index age of 55 years had lifetime risks (through 85 years of age) for total CVD of greater than 40% and 30%, respectively. Compared with participants with at least 2 major risk factors, those with an optimal risk factor profile lived up to 14 years longer free of total CVD. CONCLUSIONS: Lifetime risk estimates for total CVD were high (>30%) for all individuals, even those with optimal risk factors in middle age. However, maintenance of optimal risk factor levels in middle age was associated with substantially longer morbidity-free survival.
Keywords: Adult; Aged; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Forecasting; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Morbidity; Risk; Risk Factors; Smoking

Lifetime risks of cardiovascular disease. - Berry, Jarett D; Dyer, Alan; Cai, Xuan; Garside, Daniel B; Ning, Hongyan; Thomas, Avis; Greenland, Philip; Van Horn, Linda; Tracy, Russell P; Lloyd-Jones, Donald M (N Engl J Med, 2012)
BACKGROUND: The lifetime risks of cardiovascular disease have not been reported across the age spectrum in black adults and white adults. METHODS: We conducted a meta-analysis at the individual level using data from 18 cohort studies involving a total of 257,384 black men and women and white men and women whose risk factors for cardiovascular disease were measured at the ages of 45, 55, 65, and 75 years. Blood pressure, cholesterol level, smoking status, and diabetes status were used to stratify participants according to risk factors into five mutually exclusive categories. The remaining lifetime risks of cardiovascular events were estimated for participants in each category at each age, with death free of cardiovascular disease treated as a competing event. RESULTS: We observed marked differences in the lifetime risks of cardiovascular disease across risk-factor strata. Among participants who were 55 years of age, those with an optimal risk-factor profile (total cholesterol level, <180 mg per deciliter [4.7 mmol per liter]; blood pressure, <120 mm Hg systolic and 80 mm Hg diastolic; nonsmoking status; and nondiabetic status) had substantially lower risks of death from cardiovascular disease through the age of 80 years than participants with two or more major risk factors (4.7% vs. 29.6% among men, 6.4% vs. 20.5% among women). Those with an optimal risk-factor profile also had lower lifetime risks of fatal coronary heart disease or nonfatal myocardial infarction (3.6% vs. 37.5% among men, <1% vs. 18.3% among women) and fatal or nonfatal stroke (2.3% vs. 8.3% among men, 5.3% vs. 10.7% among women). Similar trends within risk-factor strata were observed among blacks and whites and across diverse birth cohorts. CONCLUSIONS: Differences in risk-factor burden translate into marked differences in the lifetime risk of cardiovascular disease, and these differences are consistent across race and birth cohorts. (Funded by the National Heart, Lung, and Blood Institute.).
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Effect; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Risk; Risk Assessment; Risk Factors; United States

Lipid-related markers and cardiovascular disease prediction. - Di Angelantonio, Emanuele; Gao, Pei; Pennells, Lisa; Kaptoge, Stephen; Caslake, Muriel; Thompson, Alexander; Butterworth, Adam S; Sarwar, Nadeem; Wormser, David; Saleheen, Danish; Ballantyne, Christie M; Psaty, Bruce M; et al. (JAMA, 2012)
CONTEXT: The value of assessing various emerging lipid-related markers for prediction of first cardiovascular events is debated. OBJECTIVE: To determine whether adding information on apolipoprotein B and apolipoprotein A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 to total cholesterol and high-density lipoprotein cholesterol (HDL-C) improves cardiovascular disease (CVD) risk prediction. DESIGN, SETTING, AND PARTICIPANTS: Individual records were available for 165,544 participants without baseline CVD in 37 prospective cohorts (calendar years of recruitment: 1968-2007) with up to 15,126 incident fatal or nonfatal CVD outcomes (10,132 CHD and 4994 stroke outcomes) during a median follow-up of 10.4 years (interquartile range, 7.6-14 years). MAIN OUTCOME MEASURES: Discrimination of CVD outcomes and reclassification of participants across predicted 10-year risk categories of low (<10%), intermediate (10%-<20%), and high (≥20%) risk. RESULTS: The addition of information on various lipid-related markers to total cholesterol, HDL-C, and other conventional risk factors yielded improvement in the model's discrimination: C-index change, 0.0006 (95% CI, 0.0002-0.0009) for the combination of apolipoprotein B and A-I; 0.0016 (95% CI, 0.0009-0.0023) for lipoprotein(a); and 0.0018 (95% CI, 0.0010-0.0026) for lipoprotein-associated phospholipase A2 mass. Net reclassification improvements were less than 1% with the addition of each of these markers to risk scores containing conventional risk factors. We estimated that for 100,000 adults aged 40 years or older, 15,436 would be initially classified at intermediate risk using conventional risk factors alone. Additional testing with a combination of apolipoprotein B and A-I would reclassify 1.1%; lipoprotein(a), 4.1%; and lipoprotein-associated phospholipase A2 mass, 2.7% of people to a 20% or higher predicted CVD risk category and, therefore, in need of statin treatment under Adult Treatment Panel III guidelines. CONCLUSION: In a study of individuals without known CVD, the addition of information on the combination of apolipoprotein B and A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 mass to risk scores containing total cholesterol and HDL-C led to slight improvement in CVD prediction.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cholesterol, HDL; Cohort Studies; Female; Humans; Lipoproteins; Male; Middle Aged; Risk Assessment

Lipoprotein-associated phospholipase A2 (Lp-PLA2) and future risk of type 2 diabetes: results from the Cardiovascular Health Study. - Nelson, T L; Biggs, M L; Kizer, J R; Cushman, M; Hokanson, J E; Furberg, C D; Mukamal, K J (J Clin Endocrinol Metab, 2012)
INTRODUCTION: Lipoprotein-associated phospholipase A2 (Lp-PLA(2)) has been consistently associated with cardiovascular disease (CVD) risk factors and predictive of CVD outcomes; furthermore, it is consistently higher among type 2 diabetics than nondiabetics. However, the relationships of circulating Lp-PLA(2) mass and activity with incident type 2 diabetes mellitus have not been examined. Therefore, the purpose of this study was to determine the association of Lp-PLA(2) mass and activity with type 2 diabetes among older adults. METHODS: We conducted analyses of Lp-PLA(2) and prevalent and incident diabetes among 5474 men and women from the Cardiovascular Health Study (1989-2007). Lp-PLA(2) mass and activity were measured in baseline plasma. Diabetes status was ascertained annually with medication inventories and repeated blood glucose measurements. Generalized linear and Cox proportional hazards models were used to adjust for confounding factors including body mass index and inflammation. RESULTS: At baseline, the top two quintiles of Lp-PLA(2) activity were significantly associated with prevalent type 2 diabetes with a multivariable relative risk = 1.35 [95% confidence interval (CI) = 1.11-1.63] for quintile 4, and relative risk = 1.33 (95% CI = 1.07-1.66) for quintile 5. Among participants free of diabetes at baseline, we found a significant positive association with both the homeostatic model assessment for insulin resistance and β-cell function per SD increase in Lp-PLA(2) activity (P values for both <0.01). In prospective analyses, the risk of incident type 2 diabetes was significantly higher among those in the highest quintile of Lp-PLA(2) activity [multivariable hazard ratio = 1.45 (95% CI = 1.01-2.07)] compared with the lowest quintile. Lp-PLA(2) mass was not significantly associated with incident type 2 diabetes. DISCUSSION: Lp-PLA(2) activity is positively associated with insulin resistance and predicts incident type 2 diabetes among older adults independent of multiple factors associated with diabetes pathogenesis.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Aged, 80 and over; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Insulin Resistance; Male; Middle Aged; Predictive Value of Tests; Prevalence; Prospective Studies; Risk; Risk Factors

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Nocturia, sleep-disordered breathing, and cardiovascular morbidity in a community-based cohort. - Parthasarathy, Sairam; Fitzgerald, MaryPat; Goodwin, James L; Unruh, Mark; Guerra, Stefano; Quan, Stuart F (PLoS One, 2012)
BACKGROUND: Nocturia has been independently associated with cardiovascular morbidity and all-cause mortality, but such studies did not adjust for sleep-disordered breathing (SDB), which may have mediated such a relationship. Our aims were to determine whether an association between nocturia and cardiovascular morbidity exists that is independent of SDB. We also determined whether nocturia is independently associated with SDB. METHODOLOGY/PRINCIPAL FINDINGS: In order to accomplish these aims we performed a cross-sectional analysis of the Sleep Heart Health Study that contained information regarding SDB, nocturia, and cardiovascular morbidity in a middle-age to elderly community-based population. In 6342 participants (age 63±11 [SD] years, 53% women), after adjusting for known confounders such as age, body mass index, diuretic use, diabetes mellitus, alpha-blocker use, nocturia was independently associated with SDB (measured as Apnea Hypopnea index >15 per hour; OR 1.3; 95%CI, 1.2-1.5). After adjusting for SDB and other known confounders, nocturia was independently associated with prevalent hypertension (OR 1.23; 95%CI 1.08-1.40; P = 0.002), cardiovascular disease (OR 1.26; 95%CI 1.05-1.52; P = 0.02) and stroke (OR 1.62; 95%CI 1.14-2.30; P = 0.007). Moreover, nocturia was also associated with adverse objective alterations of sleep as measured by polysomnography and self-reported excessive daytime sleepiness (P<0.05). CONCLUSIONS/SIGNIFICANCE: Nocturia is independently associated with sleep-disordered breathing. After adjusting for SDB, there remained an association between nocturia and cardiovascular morbidity. Such results support screening for SDB in patients with nocturia, but the mechanisms underlying the relationship between nocturia and cardiovascular morbidity requires further study. MeSH terms: Nocturia, sleep-disordered breathing, obstructive sleep apnea, sleep apnea, polysomnography, hypertension.
Keywords: Aged; Cardiovascular Diseases; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Nocturia; Polysomnography; Sleep Apnea Syndromes

Novel circulating fatty acid patterns and risk of cardiovascular disease: the Cardiovascular Health Study. - Imamura, Fumiaki; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Lichtenstein, Alice H; Matthan, Nirupa R; Herrington, David M; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2012)
BACKGROUND: Complex interplays of diet and metabolism influence circulating fatty acids (FAs), possibly constituting FA patterns related to cardiovascular disease (CVD) risk. OBJECTIVES: We aimed to derive FA patterns from circulating FAs, relate the patterns to CVD incidence, and extend the derived patterns to atherosclerosis progression in another independent cohort. DESIGN: We used principal component analysis (PCA) to derive FA patterns from 38 plasma phospholipid FAs in 2972 older adults in the Cardiovascular Health Study (CHS). Identified patterns were evaluated for prospective associations with 14-y incidence of CVD [ischemic heart disease (IHD) or stroke]. In another independent cohort of postmenopausal women with IHD, we evaluated associations of the CHS-derived patterns with 3.2-y progression of angiographically defined coronary atherosclerosis. RESULTS: Three distinct patterns were identified, characterized by higher proportions of trans FAs, de novo lipogenesis (DNL) FAs, and long-chain MUFAs (LCMUFAs). During 32,265 person-years, 780 incident CVD events occurred. The trans FA pattern was associated with higher CVD risk (multivariable-adjusted HR for the highest compared with the lowest quintiles = 1.58; 95% CI: 1.17, 2.12; P-trend = 0.006), primarily attributable to higher risk of stroke (HR: 2.46; 95% CI: 1.54, 3.92; P-trend = 0.005). The DNL and LCMUFA patterns were not associated with CVD incidence or with IHD or stroke (P-trend > 0.11 each). In the second cohort, the trans FA pattern, but not the other 2 patterns, was positively associated with progression of coronary atherosclerosis (P-trend < 0.05). CONCLUSIONS: PCA appears to provide informative circulating FA patterns. A pattern driven mainly by trans FA levels related to greater CVD risk in older adults and coronary atherosclerosis progression in women with IHD.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Disease Progression; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Myocardial Ischemia; Principal Component Analysis; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; Trans Fatty Acids; United States

Novel loci associated with PR interval in a genome-wide association study of 10 African American cohorts. - Butler, Anne M; Yin, Xiaoyan; Evans, Daniel S; Nalls, Michael A; Smith, Erin N; Tanaka, Toshiko; Li, Guo; Buxbaum, Sarah G; Whitsel, Eric A; Alonso, Alvaro; Arking, Dan E; Benjamin, Emelia J; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: The PR interval, as measured by the resting, standard 12-lead ECG, reflects the duration of atrial/atrioventricular nodal depolarization. Substantial evidence exists for a genetic contribution to PR, including genome-wide association studies that have identified common genetic variants at 9 loci influencing PR in populations of European and Asian descent. However, few studies have examined loci associated with PR in African Americans. METHODS AND RESULTS: We present results from the largest genome-wide association study to date of PR in 13 415 adults of African descent from 10 cohorts. We tested for association between PR (ms) and ≈2.8 million genotyped and imputed single-nucleotide polymorphisms. Imputation was performed using HapMap 2 YRI and CEU panels. Study-specific results, adjusted for global ancestry and clinical correlates of PR, were meta-analyzed using the inverse variance method. Variation in genome-wide test statistic distributions was noted within studies (λ range: 0.9-1.1), although not after genomic control correction was applied to the overall meta-analysis (λ: 1.008). In addition to generalizing previously reported associations with MEIS1, SCN5A, ARHGAP24, CAV1, and TBX5 to African American populations at the genome-wide significance level (P<5.0 × 10(-8)), we also identified a novel locus: ITGA9, located in a region previously implicated in SCN5A expression. The 3p21 region harboring SCN5A also contained 2 additional independent secondary signals influencing PR (P<5.0 × 10(-8)). CONCLUSIONS: This study demonstrates the ability to map novel loci in African Americans as well as the generalizability of loci associated with PR across populations of African, European, and Asian descent.
Keywords: Adult; African Americans; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide

Racial differences in risks for first cardiovascular events and noncardiovascular death: the Atherosclerosis Risk in Communities study, the Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. - Feinstein, Matthew; Ning, Hongyan; Kang, Joseph; Bertoni, Alain; Carnethon, Mercedes; Lloyd-Jones, Donald M (Circulation, 2012)
BACKGROUND: No studies have compared first cardiovascular disease (CVD) events and non-CVD death between races in a competing risks framework, which examines risks for numerous events simultaneously. METHODS AND RESULTS: We used competing Cox models to estimate hazards for first CVD events and non-CVD death within and between races in 3 multicenter, National Heart, Lung, and Blood Institute-sponsored cohorts. Of 14 569 Atherosclerosis Risk in Communities (ARIC) study participants aged 45 to 64 years with mean follow-up of 10.5 years, 11.6% had CVD and 5.0% had non-CVD death as first events; among 4237 Cardiovascular Health Study (CHS) study participants aged 65 to 84 years and followed for 8.5 years, these figures were 43.2% and 15.7%, respectively. Middle-aged blacks were significantly more likely than whites to experience any CVD as a first event; this disparity disappeared by older adulthood and after adjustment for CVD risk factors. The pattern of results was similar for Multi-Ethnic Study of Atherosclerosis (MESA) participants. Traditional Cox and competing risks models yielded different results for coronary heart disease risk. Black men appeared somewhat more likely than white men to experience coronary heart disease with use of a standard Cox model (hazard ratio 1.06; 95% CI 0.90, 1.26), whereas they appeared less likely than white men to have a first coronary heart disease event with use of a competing risks model (hazard ratio, 0.77; 95% CI, 0.60, 1.00). CONCLUSIONS: CVD affects blacks at an earlier age than whites; this may be attributable in part to elevated CVD risk factor levels among blacks. Racial disparities in first CVD incidence disappear by older adulthood. Competing risks analyses may yield somewhat different results than traditional Cox models and provide a complementary approach to examining risks for first CVD events.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Continental Population Groups; Ethnic Groups; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Residence Characteristics; Risk Factors

Risk of intraparenchymal hemorrhage with magnetic resonance imaging-defined leukoaraiosis and brain infarcts. - Folsom, Aaron R; Yatsuya, Hiroshi; Mosley, Thomas H; Psaty, Bruce M; Longstreth, W T (Ann Neurol, 2012)
OBJECTIVE: To determine whether the burden of leukoaraiosis and the number of brain infarcts, defined by magnetic resonance imaging (MRI), are prospectively and independently associated with intraparenchymal hemorrhage (IPH) incidence in a pooled population-based study. METHODS: Among 4,872 participants initially free of clinical stroke in the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study, we assessed white matter grade (range, 0-9), reflecting increasing leukoaraiosis, and brain infarcts using MRI. Over a median of 13 years of follow-up, 71 incident, spontaneous IPH events occurred. RESULTS: After adjustment for other IPH risk factors, the hazard ratios (95% confidence intervals) across white matter grades 0 to 1, 2, 3, and 4 to 9 were 1.00, 1.68 (0.86-3.30), 3.52 (1.80-6.89), and 3.96 (1.90-8.27), respectively (p for trend <0.0001). These hazard ratios were weakened only modestly (p for trend = 0.0003) with adjustment for MRI-defined brain infarcts. The IPH hazard ratios for 0, 1, 2, or ≥3 MRI-defined brain infarcts were 1.00, 1.97 (1.10-3.54), 2.00 (0.83-4.78), and 3.12 (1.31-7.43) (p for trend = 0.002), but these were substantially attenuated when adjusted for white matter grade (p for trend = 0.049). INTERPRETATION: Greater MRI-defined burden of leukoaraiosis is a risk factor for spontaneous IPH. Spontaneous IPH should be added to the growing list of potential poor outcomes in people with leukoaraiosis.
Keywords: Cerebral Infarction; Cohort Studies; Female; Humans; Incidence; Intracranial Hemorrhages; Leukoaraiosis; Magnetic Resonance Imaging; Male; Middle Aged; Risk Factors

Sleep-disordered breathing and caffeine consumption: results of a community-based study. - Aurora, R Nisha; Crainiceanu, Ciprian; Caffo, Brian; Punjabi, Naresh M (Chest, 2012)
BACKGROUND: Sleepiness is one of the most burdensome symptoms of sleep-disordered breathing (SDB). While caffeine is frequently used to avert sleepiness, the association between SDB and caffeine use has not been thoroughly explored. The current study examined whether SDB is associated with caffeine consumption and if factors such as sex, age, and daytime sleepiness explain or modify the association. METHODS: Data from the Sleep Heart Health Study, a community-based study on the consequences of SDB, were used to characterize the association between SDB and caffeine intake. SDB was assessed with full-montage polysomnography. Caffeine use was quantified as the number of cans of soda or the cups of coffee or tea consumed daily. The Epworth Sleepiness Scale was used to assess daytime sleepiness. Multivariable negative binomial regression models were used to characterize the independent association between SDB and caffeine use. RESULTS: Caffeinated soda, but not tea or coffee, intake was independently associated with SDB severity. Compared with participants without SDB, the relative ratios for caffeinated soda consumption in women with mild, moderate, and severe SDB were 1.20 (CI, 1.03-1.41), 1.46 (CI, 1.14-1.87), and 1.73 (CI, 1.23-2.42), respectively. For men, an association was only noted with severe SDB and caffeinated soda use. Age did not modify the SDB-caffeine association, and sleepiness could not explain the observed associations. CONCLUSIONS: SDB is independently associated with caffeinated soda use in the general community. Identifying excessive caffeine used in SDB has potential significance given the cardiovascular effects of caffeine and untreated SDB.
Keywords: Age Factors; Aged; Caffeine; Carbonated Beverages; Coffee; Data Collection; Drinking Behavior; Female; Humans; Male; Middle Aged; Polysomnography; Prevalence; Retrospective Studies; Sex Factors; Sleep Apnea Syndromes; Tea

Subclinical hyperthyroidism and the risk of coronary heart disease and mortality. - Collet, Tinh-Hai; Gussekloo, Jacobijn; Bauer, Douglas C; den Elzen, Wendy P J; Cappola, Anne R; Balmer, Philippe; Iervasi, Giorgio; Asvold, Bjørn O; Sgarbi, José A; Völzke, Henry; Gencer, Bariş; Maciel, Rui M B; et al. (Arch Intern Med, 2012)
BACKGROUND: Data from prospective cohort studies regarding the association between subclinical hyperthyroidism and cardiovascular outcomes are conflicting.We aimed to assess the risks of total and coronary heart disease (CHD) mortality, CHD events, and atrial fibrillation (AF) associated with endogenous subclinical hyperthyroidism among all available large prospective cohorts. METHODS: Individual data on 52 674 participants were pooled from 10 cohorts. Coronary heart disease events were analyzed in 22 437 participants from 6 cohorts with available data, and incident AF was analyzed in 8711 participants from 5 cohorts. Euthyroidism was defined as thyrotropin level between 0.45 and 4.49 mIU/L and endogenous subclinical hyperthyroidism as thyrotropin level lower than 0.45 mIU/L with normal free thyroxine levels, after excluding those receiving thyroid-altering medications. RESULTS: Of 52 674 participants, 2188 (4.2%) had subclinical hyperthyroidism. During follow-up, 8527 participants died (including 1896 from CHD), 3653 of 22 437 had CHD events, and 785 of 8711 developed AF. In age- and sex-adjusted analyses, subclinical hyperthyroidism was associated with increased total mortality (hazard ratio[HR], 1.24, 95% CI, 1.06-1.46), CHD mortality (HR,1.29; 95% CI, 1.02-1.62), CHD events (HR, 1.21; 95%CI, 0.99-1.46), and AF (HR, 1.68; 95% CI, 1.16-2.43).Risks did not differ significantly by age, sex, or preexisting cardiovascular disease and were similar after further adjustment for cardiovascular risk factors, with attributable risk of 14.5% for total mortality to 41.5% forAF in those with subclinical hyperthyroidism. Risks for CHD mortality and AF (but not other outcomes) were higher for thyrotropin level lower than 0.10 mIU/L compared with thyrotropin level between 0.10 and 0.44 mIU/L(for both, P value for trend, .03). CONCLUSION: Endogenous subclinical hyperthyroidism is associated with increased risks of total, CHD mortality, and incident AF, with highest risks of CHD mortality and AF when thyrotropin level is lower than 0.10 mIU/L.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Atrial Fibrillation; Cause of Death; Cohort Studies; Coronary Artery Disease; Female; Humans; Hyperthyroidism; Male; Middle Aged; Prognosis; Prospective Studies; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Analysis; Switzerland; Thyroid Function Tests; Thyrotropin; Young Adult

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Adhesion molecules, endothelin-1 and lung function in seven population-based cohorts. - Oelsner, E C; Pottinger, T D; Burkart, K M; Allison, M; Buxbaum, S G; Hansel, N N; Kumar, R; Larkin, E K; Lange, L A; Loehr, L R; London, S J; O'Connor, G T; et al. (Biomarkers, 2013)
CONTEXT: Endothelial function is abnormal in chronic obstructive pulmonary disease (COPD); whether endothelial dysfunction causes COPD is unknown. OBJECTIVE: Test associations of endothelial biomarkers with FEV1 using instrumental variables. METHODS: Among 26 907 participants with spirometry, ICAM-1, P-selectin, E-selectin and endothelin-1 were measured in subsets. RESULTS: ICAM-1 and P-selectin were inversely associated with FEV1 among European-Americans (-29 mL and -34 mL per standard deviation of log-transformed biomarker, p < 0.001), as was endothelin-1 among African-Americans (-22 mL, p = 0.008). Genetically-estimated ICAM-1 and P-selectin were not significantly associated with FEV1. The instrumental variable for endothelin-1 was non-informative. CONCLUSION: Although ICAM-1, P-selectin and endothelin-1 were inversely associated with FEV1, associations for ICAM-1 and P-selectin do not appear causal.
Keywords: African Continental Ancestry Group; Biomarkers; Cohort Studies; E-Selectin; Endothelin-1; Endothelium, Vascular; European Continental Ancestry Group; Female; Gene Expression; Humans; Intercellular Adhesion Molecule-1; Lung; Male; Middle Aged; P-Selectin; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests; Spirometry

Association of functional polymorphism rs2231142 (Q141K) in the ABCG2 gene with serum uric acid and gout in 4 US populations: the PAGE Study. - Zhang, Lili; Spencer, Kylee L; Voruganti, V Saroja; Jorgensen, Neal W; Fornage, Myriam; Best, Lyle G; Brown-Gentry, Kristin D; Cole, Shelley A; Crawford, Dana C; Deelman, Ewa; Franceschini, Nora; Gaffo, Angelo L; et al. (Am J Epidemiol, 2013)
A loss-of-function mutation (Q141K, rs2231142) in the ATP-binding cassette, subfamily G, member 2 gene (ABCG2) has been shown to be associated with serum uric acid levels and gout in Asians, Europeans, and European and African Americans; however, less is known about these associations in other populations. Rs2231142 was genotyped in 22,734 European Americans, 9,720 African Americans, 3,849 Mexican Americans, and 3,550 American Indians in the Population Architecture using Genomics and Epidemiology (PAGE) Study (2008-2012). Rs2231142 was significantly associated with serum uric acid levels (P = 2.37 × 10(-67), P = 3.98 × 10(-5), P = 6.97 × 10(-9), and P = 5.33 × 10(-4) in European Americans, African Americans, Mexican Americans, and American Indians, respectively) and gout (P = 2.83 × 10(-10), P = 0.01, and P = 0.01 in European Americans, African Americans, and Mexican Americans, respectively). Overall, the T allele was associated with a 0.24-mg/dL increase in serum uric acid level (P = 1.37 × 10(-80)) and a 1.75-fold increase in the odds of gout (P = 1.09 × 10(-12)). The association between rs2231142 and serum uric acid was significantly stronger in men, postmenopausal women, and hormone therapy users compared with their counterparts. The association with gout was also significantly stronger in men than in women. These results highlight a possible role of sex hormones in the regulation of ABCG2 urate transporter and its potential implications for the prevention, diagnosis, and treatment of hyperuricemia and gout.
Keywords: Adult; African Americans; Age Distribution; ATP-Binding Cassette Transporters; Comorbidity; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Gout; Hormone Replacement Therapy; Humans; Indians, North American; Male; Mexican Americans; Middle Aged; Neoplasm Proteins; Polymorphism, Genetic; Postmenopause; Sex Distribution; United States; Uric Acid

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: African Continental Ancestry Group; Atherosclerosis; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T

Atrial fibrillation and the risk of sudden cardiac death: the atherosclerosis risk in communities study and cardiovascular health study. - Chen, Lin Y; Sotoodehnia, Nona; Bůzková, Petra; Lopez, Faye L; Yee, Laura M; Heckbert, Susan R; Prineas, Ronald; Soliman, Elsayed Z; Adabag, Selcuk; Konety, Suma; Folsom, Aaron R; Siscovick, David; et al. (JAMA Intern Med, 2013)
BACKGROUND: It is unknown whether atrial fibrillation (AF) is associated with an increased risk of sudden cardiac death (SCD) in the general population. This association was examined in 2 population-based cohorts. METHODS: In the Atherosclerosis Risk in Communities (ARIC) Study, we analyzed data from 15 439 participants (baseline age, 45-64 years; 55.2% women; and 26.6% black) from baseline (1987-1989) through December 31, 2001. In the Cardiovascular Health Study (CHS), we analyzed data from 5479 participants (baseline age, ≥65 years; 58.2% women; and 15.4% black) from baseline (first cohort, 1989-1990; second cohort, 1992-1993) through December 31, 2006. The main outcome was physician-adjudicated SCD, defined as death from a sudden, pulseless condition presumed to be due to a ventricular tachyarrhythmia. The secondary outcome was non-SCD (NSCD), defined as coronary heart disease death not meeting SCD criteria. We used Cox proportional hazards models to assess the association between AF and SCD/NSCD, adjusting for baseline demographic and cardiovascular risk factors. RESULTS: In the ARIC Study, 894 AF, 269 SCD, and 233 NSCD events occurred during follow-up (median, 13.1 years). The crude incidence rates of SCD were 2.89 per 1000 person-years (with AF) and 1.30 per 1000 person-years (without AF). The multivariable hazard ratios (HRs) (95% CIs) of AF for SCD and NSCD were 3.26 (2.17-4.91) and 2.43 (1.60-3.71), respectively. In the CHS, 1458 AF, 292 SCD, and 581 NSCD events occurred during follow-up (median, 13.1 years). The crude incidence rates of SCD were 12.00 per 1000 person-years (with AF) and 3.82 per 1000 person-years (without AF). The multivariable HRs (95% CIs) of AF for SCD and NSCD were 2.14 (1.60-2.87) and 3.10 (2.58-3.72), respectively. The meta-analyzed HRs (95% CIs) of AF for SCD and NSCD were 2.47 (1.95-3.13) and 2.98 (2.52-3.53), respectively. CONCLUSIONS: Incident AF is associated with an increased risk of SCD and NSCD in the general population. Additional research to identify predictors of SCD in patients with AF is warranted.
Keywords: Aged; Atrial Fibrillation; Cardiovascular Diseases; Death, Sudden, Cardiac; Demography; Ethnic Groups; Female; Humans; Incidence; Male; Middle Aged; Proportional Hazards Models; Risk Assessment; Risk Factors; Sex Factors; United States

Cardiomyocyte injury assessed by a highly sensitive troponin assay and sudden cardiac death in the community: the Cardiovascular Health Study. - Hussein, Ayman A; Gottdiener, John S; Bartz, Traci M; Sotoodehnia, Nona; DeFilippi, Christopher; Dickfeld, Timm; Deo, Rajat; Siscovick, David; Stein, Phyllis K; Lloyd-Jones, Donald (J Am Coll Cardiol, 2013)
OBJECTIVES: This study sought to determine the association between markers of cardiomyocyte injury in ambulatory subjects and sudden cardiac death (SCD). BACKGROUND: The pathophysiology of SCD is complex but is believed to be associated with an abnormal cardiac substrate in most cases. The association between biomarkers of cardiomyocyte injury in ambulatory subjects and SCD has not been investigated. METHODS: Levels of cardiac troponin T, a biomarker of cardiomyocyte injury, were measured by a highly sensitive assay (hsTnT) in 4,431 ambulatory participants in the Cardiovascular Health Study, a longitudinal community-based prospective cohort study. Serial measures were obtained in 3,089 subjects. All deaths, including SCD, were adjudicated by a central events committee. RESULTS: Over a median follow-up of 13.1 years, 246 participants had SCD. Baseline levels of hsTnT were significantly associated with SCD (hazard ratio [HR] for +1 log(hsTnT): 2.04, 95% confidence interval [CI]: 1.78 to 2.34]. This association persisted in covariate-adjusted Cox analyses accounting for baseline risk factors (HR: 1.30, 95% CI: 1.05 to 1.62), as well as for incident heart failure and myocardial infarction (HR: 1.26, 95% CI: 1.01 to 1.57). The population was also categorized into 3 groups based on baseline hsTnT levels and SCD risk [fully adjusted HR: 1.89 vs. 1.55 vs. 1 (reference group) for hsTnT ≥12.10 vs. 5.01 to 12.09 vs. ≤ 5.00 pg/ml, respectively; p trend = 0.005]. On serial measurements, change in hsTnT levels was also associated with SCD risk (fully adjusted HR for +1 pg/ml per year increase from baseline: 1.03, 95% CI: 1.01 to 1.06). CONCLUSIONS: The findings suggest an association between cardiomyocyte injury in ambulatory subjects and SCD risk beyond that of traditional risk factors.
Keywords: Aged; Ambulatory Care; Biomarkers; Death, Sudden, Cardiac; Female; Heart Arrest; Humans; Longitudinal Studies; Male; Middle Aged; Myocardium; Myocytes, Cardiac; Proportional Hazards Models; Risk Assessment; Troponin T

Circulating 25-hydroxyvitamin D is associated with insulin resistance cross-sectionally but not longitudinally in older adults: The Cardiovascular Health Study. - Danziger, John; Biggs, Mary L; Niemi, Matt; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; de Boer, Ian H; Siscovick, David S; Kestenbaum, Bryan; Mukamal, Kenneth J (Metabolism, 2013)
BACKGROUND: Despite extensive study, the role of vitamin D in insulin resistance and secretion remains unclear. OBJECTIVE: To examine the cross-sectional and longitudinal relationships between 25-hydroxyvitamin D (25(OH)D) concentrations and indices of insulin resistance and secretion in older adults. METHODS AND RESULTS: Among 2134 participants of the Cardiovascular Health Study who were free from cardiovascular disease, we measured serum 25(OH)D concentrations in samples collected in 1992-1993. We examined insulin resistance and secretion using Homeostasis Model Assessment (HOMA) estimates cross-sectionally and among 1469 participants who had repeated HOMA measures four years later (1996-1997). In cross-sectional analysis, each 10 ng/mL increment in 25(OH)D concentration was associated with a 0.09 lower adjusted HOMA-IR [95% CI (-0.17, -0.02), p=0.01]. However, baseline 25(OH)D concentrations were not associated with change in HOMA-IR over 4 years of follow up (p=0.48). 25(OH)D concentrations were not associated with insulin secretion, as determined by HOMA-β, in either cross-sectional or longitudinal analysis. CONCLUSIONS: Circulating 25(OH)D concentrations are associated with lower insulin resistance in cross-sectional but not longitudinal analyses. Whether this reflects residual confounding in cross-sectional analyses or the short-term nature of the relationship between vitamin D and insulin sensitivity will require trials with repeated measures of these factors.
Keywords: Adiposity; Aged; Anthropometry; Cardiovascular Diseases; Cross-Sectional Studies; Exercise; Female; Humans; Hydroxycholecalciferols; Inflammation; Insulin; Insulin Resistance; Longitudinal Studies; Male; Middle Aged; Obesity; Risk Factors; Surveys and Questionnaires

Common genetic variation near the connexin-43 gene is associated with resting heart rate in African Americans: a genome-wide association study of 13,372 participants. - Deo, R; Nalls, M A; Avery, C L; Smith, J G; Evans, D S; Keller, M F; Butler, A M; Buxbaum, S G; Li, G; Miguel Quibrera, P; Smith, E N; Tanaka, T; et al. (Heart Rhythm, 2013)
BACKGROUND: Genome-wide association studies have identified several genetic loci associated with variation in resting heart rate in European and Asian populations. No study has evaluated genetic variants associated with heart rate in African Americans. OBJECTIVE: To identify novel genetic variants associated with resting heart rate in African Americans. METHODS: Ten cohort studies participating in the Candidate-gene Association Resource and Continental Origins and Genetic Epidemiology Network consortia performed genome-wide genotyping of single nucleotide polymorphisms (SNPs) and imputed 2,954,965 SNPs using HapMap YRI and CEU panels in 13,372 participants of African ancestry. Each study measured the RR interval (ms) from 10-second resting 12-lead electrocardiograms and estimated RR-SNP associations using covariate-adjusted linear regression. Random-effects meta-analysis was used to combine cohort-specific measures of association and identify genome-wide significant loci (P≤2.5×10(-8)). RESULTS: Fourteen SNPs on chromosome 6q22 exceeded the genome-wide significance threshold. The most significant association was for rs9320841 (+13 ms per minor allele; P = 4.98×10(-15)). This SNP was approximately 350 kb downstream of GJA1, a locus previously identified as harboring SNPs associated with heart rate in Europeans. Adjustment for rs9320841 also attenuated the association between the remaining 13 SNPs in this region and heart rate. In addition, SNPs in MYH6, which have been identified in European genome-wide association study, were associated with similar changes in the resting heart rate as this population of African Americans. CONCLUSIONS: An intergenic region downstream of GJA1 (the gene encoding connexin 43, the major protein of the human myocardial gap junction) and an intragenic region within MYH6 are associated with variation in resting heart rate in African Americans as well as in populations of European and Asian origin.
Keywords: Adult; African Americans; Aged; Arrhythmias, Cardiac; Connexin 43; Electrocardiography; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Rate; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Rest; United States

Effects of smoking on the genetic risk of obesity: the population architecture using genomics and epidemiology study. - Fesinmeyer, Megan D; North, Kari E; Lim, Unhee; Bůzková, Petra; Crawford, Dana C; Haessler, Jeffrey; Gross, Myron D; Fowke, Jay H; Goodloe, Robert; Love, Shelley-Ann; Graff, Misa; Carlson, Christopher S; et al. (BMC Med Genet, 2013)
BACKGROUND: Although smoking behavior is known to affect body mass index (BMI), the potential for smoking to influence genetic associations with BMI is largely unexplored. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE)' Consortium, we investigated interaction between genetic risk factors associated with BMI and smoking for 10 single nucleotide polymorphisms (SNPs) previously identified in genome-wide association studies. We included 6 studies with a total of 56,466 subjects (16,750 African Americans (AA) and 39,716 European Americans (EA)). We assessed effect modification by testing an interaction term for each SNP and smoking (current vs. former/never) in the linear regression and by stratified analyses. RESULTS: We did not observe strong evidence for interactions and only observed two interactions with p-values <0.1: for rs6548238/TMEM18, the risk allele (C) was associated with BMI only among AA females who were former/never smokers (β = 0.018, p = 0.002), vs. current smokers (β = 0.001, p = 0.95, p(interaction) = 0.10). For rs9939609/FTO, the A allele was more strongly associated with BMI among current smoker EA females (β = 0.017, p = 3.5 x 10(-5)), vs. former/never smokers (β = 0.006, p = 0.05, p(interaction) = 0.08). CONCLUSIONS: These analyses provide limited evidence that smoking status may modify genetic effects of previously identified genetic risk factors for BMI. Larger studies are needed to follow up our results. CLINICAL TRIAL REGISTRATION: NCT00000611.
Keywords: Adolescent; Adult; African Americans; Aged; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Mass Index; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Smoking; Young Adult

Epidemiology and long-term clinical and biologic risk factors for pneumonia in community-dwelling older Americans: analysis of three cohorts. - Yende, Sachin; Alvarez, Karina; Loehr, Laura; Folsom, Aaron R; Newman, Anne B; Weissfeld, Lisa A; Wunderink, Richard G; Kritchevsky, Stephen B; Mukamal, Kenneth J; London, Stephanie J; Harris, Tamara B; Bauer, Doug C; et al. (Chest, 2013)
BACKGROUND: Preventing pneumonia requires better understanding of incidence, mortality, and long-term clinical and biologic risk factors, particularly in younger individuals. METHODS: This was a cohort study in three population-based cohorts of community-dwelling individuals. A derivation cohort (n = 16,260) was used to determine incidence and survival and develop a risk prediction model. The prediction model was validated in two cohorts (n = 8,495). The primary outcome was 10-year risk of pneumonia hospitalization. RESULTS: The crude and age-adjusted incidences of pneumonia were 6.71 and 9.43 cases/1,000 person-years (10-year risk was 6.15%). The 30-day and 1-year mortality were 16.5% and 31.5%. Although age was the most important risk factor (range of crude incidence rates, 1.69-39.13 cases/1,000 person-years for each 5-year increment from 45-85 years), 38% of pneumonia cases occurred in adults < 65 years of age. The 30-day and 1-year mortality were 12.5% and 25.7% in those < 65 years of age. Although most comorbidities were associated with higher risk of pneumonia, reduced lung function was the most important risk factor (relative risk = 6.61 for severe reduction based on FEV1 by spirometry). A clinical risk prediction model based on age, smoking, and lung function predicted 10-year risk (area under curve [AUC] = 0.77 and Hosmer-Lemeshow [HL] C statistic = 0.12). Model discrimination and calibration were similar in the internal validation cohort (AUC = 0.77; HL C statistic, 0.65) but lower in the external validation cohort (AUC = 0.62; HL C statistic, 0.45). The model also calibrated well in blacks and younger adults. C-reactive protein and IL-6 were associated with higher pneumonia risk but did not improve model performance. CONCLUSIONS: Pneumonia hospitalization is common and associated with high mortality, even in younger healthy adults. Long-term risk of pneumonia can be predicted in community-dwelling adults with a simple clinical risk prediction model.
Keywords: Age Factors; Aged; Aged, 80 and over; Community-Acquired Infections; Comorbidity; Female; Follow-Up Studies; Hospitalization; Humans; Incidence; Male; Middle Aged; Pneumonia; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors

Exome sequencing and genome-wide linkage analysis in 17 families illustrate the complex contribution of TTN truncating variants to dilated cardiomyopathy. - Norton, Nadine; Li, Duanxiang; Rampersaud, Evadnie; Morales, Ana; Martin, Eden R; Zuchner, Stephan; Guo, Shengru; Gonzalez, Michael; Hedges, Dale J; Robertson, Peggy D; Krumm, Niklas; Nickerson, Deborah A; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Familial dilated cardiomyopathy (DCM) is a genetically heterogeneous disease with >30 known genes. TTN truncating variants were recently implicated in a candidate gene study to cause 25% of familial and 18% of sporadic DCM cases. METHODS AND RESULTS- We used an unbiased genome-wide approach using both linkage analysis and variant filtering across the exome sequences of 48 individuals affected with DCM from 17 families to identify genetic cause. Linkage analysis ranked the TTN region as falling under the second highest genome-wide multipoint linkage peak, multipoint logarithm of odds, 1.59. We identified 6 TTN truncating variants carried by individuals affected with DCM in 7 of 17 DCM families (logarithm of odds, 2.99); 2 of these 7 families also had novel missense variants that segregated with disease. Two additional novel truncating TTN variants did not segregate with DCM. Nucleotide diversity at the TTN locus, including missense variants, was comparable with 5 other known DCM genes. The average number of missense variants in the exome sequences from the DCM cases or the ≈5400 cases from the Exome Sequencing Project was ≈23 per individual. The average number of TTN truncating variants in the Exome Sequencing Project was 0.014 per individual. We also identified a region (chr9q21.11-q22.31) with no known DCM genes with a maximum heterogeneity logarithm of odds score of 1.74. CONCLUSIONS- These data suggest that TTN truncating variants contribute to DCM cause. However, the lack of segregation of all identified TTN truncating variants illustrates the challenge of determining variant pathogenicity even with full exome sequencing.
Keywords: Adolescent; Adult; Aged; Cardiomyopathy, Dilated; Chromosomes, Human, Pair 9; Connectin; Exome; Female; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genome, Human; Humans; Male; Middle Aged; Muscle Proteins; Mutation, Missense; Odds Ratio; Pedigree; Protein Kinases; Sequence Analysis, DNA; Young Adult

Exploring psychosocial pathways between neighbourhood characteristics and stroke in older adults: the cardiovascular health study. - Yan, Tingjian; Escarce, José J; Liang, Li-Jung; Longstreth, W T; Merkin, Sharon Stein; Ovbiagele, Bruce; Vassar, Stefanie D; Seeman, Teresa; Sarkisian, Catherine; Brown, Arleen F (Age Ageing, 2013)
OBJECTIVES: to investigate whether psychosocial pathways mediate the association between neighbourhood socioeconomic disadvantage and stroke. METHODS: prospective cohort study with a follow-up of 11.5 years. SETTING: the Cardiovascular Health Study, a longitudinal population-based cohort study of older adults ≥65 years. MEASUREMENTS: the primary outcome was adjudicated incident ischaemic stroke. Neighbourhood socioeconomic status (NSES) was measured using a composite of six census-tract variables. Psychosocial factors were assessed with standard measures for depression, social support and social networks. RESULTS: of the 3,834 white participants with no prior stroke, 548 had an incident ischaemic stroke over the 11.5-year follow-up. Among whites, the incident stroke hazard ratio (HR) associated with living in the lowest relative to highest NSES quartile was 1.32 (95% CI = 1.01-1.73), in models adjusted for individual SES. Additional adjustment for psychosocial factors had a minimal effect on hazard of incident stroke (HR = 1.31, CI = 1.00-1.71). Associations between NSES and stroke incidence were not found among African-Americans (n = 785) in either partially or fully adjusted models. CONCLUSIONS: psychosocial factors played a minimal role in mediating the effect of NSES on stroke incidence among white older adults.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Aging; Brain Ischemia; Depression; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Linear Models; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Assessment; Risk Factors; Social Support; Socioeconomic Factors; Stroke; Time Factors; United States; Vulnerable Populations

Fibroblast growth factor 23, bone mineral density, and risk of hip fracture among older adults: the cardiovascular health study. - Jovanovich, Anna; Bůzková, Petra; Chonchol, Michel; Robbins, John; Fink, Howard A; de Boer, Ian H; Kestenbaum, Bryan; Katz, Ronit; Carbone, Laura; Lee, Jennifer; Laughlin, Gail A; Mukamal, Kenneth J; et al. (J Clin Endocrinol Metab, 2013)
CONTEXT: Fibroblast growth factor 23 (FGF23) is a phosphaturic hormone that also inhibits calcitriol synthesis. OBJECTIVE: Our objective was to evaluate the relationships of plasma FGF23 concentrations with bone mineral density (BMD) and hip fracture in community-dwelling older adults. DESIGN AND SETTING: Linear regression and Cox proportional hazard models were used to examine the associations of plasma FGF23 concentrations with BMD and incident hip fracture, respectively. Analyses were also stratified by chronic kidney disease. PARTICIPANTS: Participants included 2008 women and 1329 men ≥65 years from the 1996 to 1997 Cardiovascular Health Study visit. MAIN OUTCOME MEASURES: Dual x-ray absorptiometry measured total hip (TH) and lumbar spine (LS) BMD in 1291 participants. Hip fracture incidence was assessed prospectively through June 30, 2008 by hospitalization records in all participants. RESULTS: Women had higher plasma FGF23 concentrations than men (75 [56-107] vs 66 [interquartile range = 52-92] relative units/mL; P < .001). After adjustment, higher FGF23 concentrations were associated with greater total hip and lumbar spine BMD in men only (β per doubling of FGF23 = 0.02, with 95% confidence interval [CI] = 0.001-0.04 g/cm(2), and 0.03 with 95% CI = 0.01-0.06 g/cm(2)). During 9.6 ± 5.1-11.0 years of follow-up, 328 hip fractures occurred. Higher FGF23 concentrations were not associated with hip fracture risk in women or men (adjusted hazard ratio = 0.95, with 95% CI = 0.78-1.15, and 1.09 with 95% CI = 0.82-1.46 per doubling of FGF23). Results did not differ by chronic kidney disease status (P > .4 for interactions). CONCLUSIONS: In this large prospective cohort of community-dwelling older adults, higher FGF23 concentrations were weakly associated with greater lumbar spine and total hip BMD but not with hip fracture risk.
Keywords: Aged; Aged, 80 and over; Bone Density; Female; Fibroblast Growth Factors; Hip Fractures; Humans; Longitudinal Studies; Male; Middle Aged; Prospective Studies; Risk; Spinal Fractures

Fine Mapping and Identification of BMI Loci in African Americans. - Gong, Jian; Schumacher, Fredrick; Lim, Unhee; Hindorff, Lucia A; Haessler, Jeff; Buyske, Steven; Carlson, Christopher S; Rosse, Stephanie; Bůzková, Petra; Fornage, Myriam; Gross, Myron; Pankratz, Nathan; et al. (Am J Hum Genet, 2013)
Genome-wide association studies (GWASs) primarily performed in European-ancestry (EA) populations have identified numerous loci associated with body mass index (BMI). However, it is still unclear whether these GWAS loci can be generalized to other ethnic groups, such as African Americans (AAs). Furthermore, the putative functional variant or variants in these loci mostly remain under investigation. The overall lower linkage disequilibrium in AA compared to EA populations provides the opportunity to narrow in or fine-map these BMI-related loci. Therefore, we used the Metabochip to densely genotype and evaluate 21 BMI GWAS loci identified in EA studies in 29,151 AAs from the Population Architecture using Genomics and Epidemiology (PAGE) study. Eight of the 21 loci (SEC16B, TMEM18, ETV5, GNPDA2, TFAP2B, BDNF, FTO, and MC4R) were found to be associated with BMI in AAs at 5.8 × 10(-5). Within seven out of these eight loci, we found that, on average, a substantially smaller number of variants was correlated (r(2) > 0.5) with the most significant SNP in AA than in EA populations (16 versus 55). Conditional analyses revealed GNPDA2 harboring a potential additional independent signal. Moreover, Metabochip-wide discovery analyses revealed two BMI-related loci, BRE (rs116612809, p = 3.6 × 10(-8)) and DHX34 (rs4802349, p = 1.2 × 10(-7)), which were significant when adjustment was made for the total number of SNPs tested across the chip. These results demonstrate that fine mapping in AAs is a powerful approach for both narrowing in on the underlying causal variants in known loci and discovering BMI-related loci.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Body Mass Index; Female; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Young Adult

Genetic analysis of a population heavy drinking phenotype identifies risk variants in whites. - Hamidovic, Ajna; Goodloe, Robert J; Young, Taylor R; Styn, Mindi A; Mukamal, Kenneth J; Choquet, Helene; Kasberger, Jay L; Buxbaum, Sarah G; Papanicolaou, George J; White, Wendy; Volcik, Kelly; Spring, Bonnie; et al. (J Clin Psychopharmacol, 2013)
Genetic association studies thus far have used detailed diagnoses of alcoholism to identify loci associated with risk. This proof-of-concept analysis examined whether population data of lifetime heaviest alcohol consumption may be used to identify genetic loci that modulate risk. We conducted a genetic association study in European Americans between variants in approximately 2100 genes and alcohol consumption as part of the Candidate gene Association Resource project. We defined cases as individuals with a history of drinking 5 or more drinks per day almost every day of the week and controls as current light drinkers (1-5 drinks per week). We cross-validated identified single nucleotide polymorphisms in a meta-analysis of 2 cohorts of unrelated individuals--Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health Study (CHS)--and in a separate cohort of related individuals--Framingham Heart Study (FHS). The most significant variant in the meta-analysis of ARIC and CHS was rs6933598 in methylenetetrahydrofolate dehydrogenase (P = 7.46 × 10(-05)) with a P value in FHS of 0.042. The top variants in FHS were rs12249562 in cubulin (P = 3.03 × 10(-05)) and rs9839267 near cholecystokinin (P = 3.05 × 10(-05)) with a P value of 0.019 for rs9839267 in CHS. We have here shown feasibility in evaluating lifetime incidence of heavy alcohol drinking from population-based studies for the purpose of conducting genetic association analyses.
Keywords: Aged; Alcohol Drinking; Alcoholism; Case-Control Studies; European Continental Ancestry Group; Feasibility Studies; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Humans; Incidence; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk

Genetic association of COL5A1 variants in keratoconus patients suggests a complex connection between corneal thinning and keratoconus. - Li, Xiaohui; Bykhovskaya, Yelena; Canedo, Ana Laura Caiado; Haritunians, Talin; Siscovick, David; Aldave, Anthony J; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Rotter, Jerome I; Taylor, Kent D; Rabinowitz, Yaron S (Invest Ophthalmol Vis Sci, 2013)
PURPOSE: Single nucleotide polymorphisms (SNPs) located near or within the COL5A1 gene, at 9q34.2-q34.3 chromosomal region have been reported in association with central corneal thickness (CCT). Using family linkage analysis, we identified a keratoconus susceptibility locus at 9q34. These findings led us to perform an association study between COL5A1 variation and keratoconus susceptibility. METHODS: A Caucasian case-control cohort of 222 keratoconus patients and 3324 controls was selected as the discovery panel. An independent case-control panel of 304 cases and 518 controls and a family panel of 186 subjects were replicated for genotyping and association. Forty-four SNPs (21 for discovery and 23 for fine-mapping) spanning 300 kilobases in and around COL5A1 were genotyped and tested for genetic association. Logistic regression models implemented in PLINK were used to test for association in case controls. Generalized estimating equation models accounting for familial correlations implemented in genome-wide interaction analyses with family data were used for association testing in families. RESULTS: Two CCT associated SNPs (rs1536482 and rs7044529 near and within COL5A1) were identified in the keratoconus discovery cohort (P values of 6.5 × 10(-3) and 7.4 × 10(-3)). SNP rs1536482 was replicated in the second case-control sample (P = 0.02), and SNP rs7044529 was replicated in a keratoconus family panel (P = 0.03). Meta P values of rs1536482 and rs7044529 in the keratoconus cohorts were 1.5 × 10(-4) (odds ratio [OR] = 1.30) and 2.9 × 10(-3) (OR = 1.39). After Bonferroni correction, the association of SNP rs1536482 remained significant (P = 6.5 × 10(-3)). CONCLUSIONS: SNPs in the COL5A1 region, which regulate normal variation in CCT, may play a role in the thinning associated with keratoconus.
Keywords: Adult; Aged; Collagen Type V; Cornea; Corneal Topography; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Keratoconus; Male; Microscopy, Acoustic; Middle Aged; Polymorphism, Single Nucleotide; Tomography, Optical Coherence

Genetic loci for retinal arteriolar microcirculation. - Sim, Xueling; Jensen, Richard A; Ikram, M Kamran; Cotch, Mary Frances; Li, Xiaohui; Macgregor, Stuart; Xie, Jing; Smith, Albert Vernon; Boerwinkle, Eric; Mitchell, Paul; Klein, Ronald; Klein, Barbara E K; et al. (PLoS One, 2013)
Narrow arterioles in the retina have been shown to predict hypertension as well as other vascular diseases, likely through an increase in the peripheral resistance of the microcirculatory flow. In this study, we performed a genome-wide association study in 18,722 unrelated individuals of European ancestry from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium and the Blue Mountain Eye Study, to identify genetic determinants associated with variations in retinal arteriolar caliber. Retinal vascular calibers were measured on digitized retinal photographs using a standardized protocol. One variant (rs2194025 on chromosome 5q14 near the myocyte enhancer factor 2C MEF2C gene) was associated with retinal arteriolar caliber in the meta-analysis of the discovery cohorts at genome-wide significance of P-value <5×10(-8). This variant was replicated in an additional 3,939 individuals of European ancestry from the Australian Twins Study and Multi-Ethnic Study of Atherosclerosis (rs2194025, P-value = 2.11×10(-12) in combined meta-analysis of discovery and replication cohorts). In independent studies of modest sample sizes, no significant association was found between this variant and clinical outcomes including coronary artery disease, stroke, myocardial infarction or hypertension. In conclusion, we found one novel loci which underlie genetic variation in microvasculature which may be relevant to vascular disease. The relevance of these findings to clinical outcomes remains to be determined.
Keywords: Aged; Aged, 80 and over; Arterioles; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Male; MEF2 Transcription Factors; Microcirculation; Middle Aged; Models, Genetic; Retinal Vessels

Genetic variants associated with fasting glucose and insulin concentrations in an ethnically diverse population: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Fesinmeyer, Megan D; Meigs, James B; North, Kari E; Schumacher, Fredrick R; Bůzková, Petra; Franceschini, Nora; Haessler, Jeffrey; Goodloe, Robert; Spencer, Kylee L; Voruganti, Venkata Saroja; Howard, Barbara V; Jackson, Rebecca; et al. (BMC Med Genet, 2013)
BACKGROUND: Multiple genome-wide association studies (GWAS) within European populations have implicated common genetic variants associated with insulin and glucose concentrations. In contrast, few studies have been conducted within minority groups, which carry the highest burden of impaired glucose homeostasis and type 2 diabetes in the U.S. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we investigated the association of up to 10 GWAS-identified single nucleotide polymorphisms (SNPs) in 8 genetic regions with glucose or insulin concentrations in up to 36,579 non-diabetic subjects including 23,323 European Americans (EA) and 7,526 African Americans (AA), 3,140 Hispanics, 1,779 American Indians (AI), and 811 Asians. We estimated the association between each SNP and fasting glucose or log-transformed fasting insulin, followed by meta-analysis to combine results across PAGE sites. RESULTS: Overall, our results show that 9/9 GWAS SNPs are associated with glucose in EA (p = 0.04 to 9 × 10-15), versus 3/9 in AA (p= 0.03 to 6 × 10-5), 3/4 SNPs in Hispanics, 2/4 SNPs in AI, and 1/2 SNPs in Asians. For insulin we observed a significant association with rs780094/GCKR in EA, Hispanics and AI only. CONCLUSIONS: Generalization of results across multiple racial/ethnic groups helps confirm the relevance of some of these loci for glucose and insulin metabolism. Lack of association in non-EA groups may be due to insufficient power, or to unique patterns of linkage disequilibrium.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Genomics; Hispanic Americans; Humans; Indians, North American; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

Genome-wide association study identifies novel loci associated with concentrations of four plasma phospholipid fatty acids in the de novo lipogenesis pathway: results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortiu - Wu, Jason H Y; Lemaitre, Rozenn N; Manichaikul, Ani; Guan, Weihua; Tanaka, Toshiko; Foy, Millennia; Kabagambe, Edmond K; Djoussé, Luc; Siscovick, David; Fretts, Amanda M; Johnson, Catherine; King, Irena B; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1n-7), and oleic acid (18:1n-9) are major saturated and monounsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis and are the main saturated and monounsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes mellitus and coronary heart disease. METHODS AND RESULTS- Genome-wide association studies were conducted in 5 population-based cohorts comprising 8961 participants of European ancestry to investigate the association of common genetic variation with plasma levels of these 4 fatty acids. We identified polymorphisms in 7 novel loci associated with circulating levels of ≥1 of these fatty acids. ALG14 (asparagine-linked glycosylation 14 homolog) polymorphisms were associated with higher 16:0 (P=2.7×10(-11)) and lower 18:0 (P=2.2×10(-18)). FADS1 and FADS2 (desaturases) polymorphisms were associated with higher 16:1n-7 (P=6.6×10(-13)) and 18:1n-9 (P=2.2×10(-32)) and lower 18:0 (P=1.3×10(-20)). LPGAT1 (lysophosphatidylglycerol acyltransferase) polymorphisms were associated with lower 18:0 (P=2.8×10(-9)). GCKR (glucokinase regulator; P=9.8×10(-10)) and HIF1AN (factor inhibiting hypoxia-inducible factor-1; P=5.7×10(-9)) polymorphisms were associated with higher 16:1n-7, whereas PKD2L1 (polycystic kidney disease 2-like 1; P=5.7×10(-15)) and a locus on chromosome 2 (not near known genes) were associated with lower 16:1n-7 (P=4.1×10(-8)). CONCLUSIONS- Our findings provide novel evidence that common variations in genes with diverse functions, including protein-glycosylation, polyunsaturated fatty acid metabolism, phospholipid modeling, and glucose- and oxygen-sensing pathways, are associated with circulating levels of 4 fatty acids in the de novo lipogenesis pathway. These results expand our knowledge of genetic factors relevant to de novo lipogenesis and fatty acid biology.
Keywords: Adult; Aged; Chromosomes, Human, Pair 2; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Lipogenesis; Male; Middle Aged; Oleic Acid; Palmitic Acid; Polymorphism, Single Nucleotide; Stearic Acids

Genome-wide association study of cardiac structure and systolic function in African Americans: the Candidate Gene Association Resource (CARe) study. - Fox, Ervin R; Musani, Solomon K; Barbalic, Maja; Lin, Honghuang; Yu, Bing; Ogunyankin, Kofo O; Smith, Nicholas L; Kutlar, Abdullah; Glazer, Nicole L; Post, Wendy S; Paltoo, Dina N; Dries, Daniel L; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: Using data from 4 community-based cohorts of African Americans, we tested the association between genome-wide markers (single-nucleotide polymorphisms) and cardiac phenotypes in the Candidate-gene Association Resource study. METHODS AND RESULTS: Among 6765 African Americans, we related age, sex, height, and weight-adjusted residuals for 9 cardiac phenotypes (assessed by echocardiogram or magnetic resonance imaging) to 2.5 million single-nucleotide polymorphisms genotyped using Genome-wide Affymetrix Human SNP Array 6.0 (Affy6.0) and the remainder imputed. Within the cohort, genome-wide association analysis was conducted, followed by meta-analysis across cohorts using inverse variance weights (genome-wide significance threshold=4.0 ×10(-7)). Supplementary pathway analysis was performed. We attempted replication in 3 smaller cohorts of African ancestry and tested lookups in 1 consortium of European ancestry (EchoGEN). Across the 9 phenotypes, variants in 4 genetic loci reached genome-wide significance: rs4552931 in UBE2V2 (P=1.43×10(-7)) for left ventricular mass, rs7213314 in WIPI1 (P=1.68×10(-7)) for left ventricular internal diastolic diameter, rs1571099 in PPAPDC1A (P=2.57×10(-8)) for interventricular septal wall thickness, and rs9530176 in KLF5 (P=4.02×10(-7)) for ejection fraction. Associated variants were enriched in 3 signaling pathways involved in cardiac remodeling. None of the 4 loci replicated in cohorts of African ancestry was confirmed in lookups in EchoGEN. CONCLUSIONS: In the largest genome-wide association study of cardiac structure and function to date in African Americans, we identified 4 genetic loci related to left ventricular mass, interventricular septal wall thickness, left ventricular internal diastolic diameter, and ejection fraction, which reached genome-wide significance. Replication results suggest that these loci may be unique to individuals of African ancestry. Additional large-scale studies are warranted for these complex phenotypes.
Keywords: African Americans; Aged; Cohort Studies; Diastole; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD. - Hansel, Nadia N; Ruczinski, Ingo; Rafaels, Nicholas; Sin, Don D; Daley, Denise; Malinina, Alla; Huang, Lili; Sandford, Andrew; Murray, Tanda; Kim, Yoonhee; Vergara, Candelaria; Heckbert, Susan R; et al. (Hum Genet, 2013)
Accelerated lung function decline is a key COPD phenotype; however, its genetic control remains largely unknown. We performed a genome-wide association study using the Illumina Human660W-Quad v.1_A BeadChip. Generalized estimation equations were used to assess genetic contributions to lung function decline over a 5-year period in 4,048 European American Lung Health Study participants with largely mild COPD. Genotype imputation was performed using reference HapMap II data. To validate regions meeting genome-wide significance, replication of top SNPs was attempted in independent cohorts. Three genes (TMEM26, ANK3 and FOXA1) within the regions of interest were selected for tissue expression studies using immunohistochemistry. Two intergenic SNPs (rs10761570, rs7911302) on chromosome 10 and one SNP on chromosome 14 (rs177852) met genome-wide significance after Bonferroni. Further support for the chromosome 10 region was obtained by imputation, the most significantly associated imputed SNPs (rs10761571, rs7896712) being flanked by observed markers rs10761570 and rs7911302. Results were not replicated in four general population cohorts or a smaller cohort of subjects with moderate to severe COPD; however, we show novel expression of genes near regions of significantly associated SNPS, including TMEM26 and FOXA1 in airway epithelium and lung parenchyma, and ANK3 in alveolar macrophages. Levels of expression were associated with lung function and COPD status. We identified two novel regions associated with lung function decline in mild COPD. Genes within these regions were expressed in relevant lung cells and their expression related to airflow limitation suggesting they may represent novel candidate genes for COPD susceptibility.
Keywords: Adult; Ankyrins; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 14; Cohort Studies; Female; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-alpha; Humans; Linkage Disequilibrium; Lung; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Height and risk of incident intraparenchymal hemorrhage: Atherosclerosis Risk in Communities and Cardiovascular Health study cohorts. - Smith, Lindsay G; Yatsuya, Hiroshi; Psaty, Bruce M; Longstreth, W T; Folsom, Aaron R (J Stroke Cerebrovasc Dis, 2013)
BACKGROUND: Height is inversely associated with incident coronary disease and total stroke, but few studies have examined the association between height and intraparenchymal hemorrhage (IPH). We hypothesized that height would be inversely associated with incident IPH in the combined cohorts of the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. METHODS: Data on Caucasian and African American participants were used to estimate the association of height at baseline with incident IPH verified by clinician review of medical records and imaging reports. Sex-specific Cox proportional hazards regression models were used to calculate hazard ratios. RESULTS: A total of 20,983 participants initially free of stroke (11,788 women and 9195 men) were followed for an average of 15.9 years (standard deviation [SD] 5.1 years). Incident IPH occurred in 115 women and 73 men. Sex, but not age, race, study, or blood pressure, modified the association (P = .03). After adjustment for risk factors (age, systolic blood pressure, triglycerides, low-density lipoprotein cholesterol, fibrinogen, and race), among women, height was significantly inversely associated with incident IPH (hazard ratio [HR] per SD [6.3 cm] was 0.81; 95% confidence interval [CI] 0.66-0.99; P = .04). The HR for tertile 3 vs 1 in women was 0.63 (95% CI 0.37-1.08). Among men, height was not linearly associated with incident IPH (HR per SD [6.7 cm] was 1.09; 95% CI 0.84-1.40; P = .52). CONCLUSIONS: This large prospective study provides evidence that shorter height may be a risk factor for incident IPH in women.
Keywords: African Americans; Aged; Body Height; Cerebral Hemorrhage; European Continental Ancestry Group; Female; Humans; Incidence; Male; Middle Aged; Multivariate Analysis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States

Impact of inflammatory biomarkers on relation of high density lipoprotein-cholesterol with incident coronary heart disease: cardiovascular Health Study. - Tehrani, David M; Gardin, Julius M; Yanez, David; Hirsch, Calvin H; Lloyd-Jones, Donald M; Stein, Phyllis K; Wong, Nathan D (Atherosclerosis, 2013)
BACKGROUND: Inflammatory factors and low HDL-C relate to CHD risk, but whether inflammation attenuates any protective association of high HDL-C is unknown. OBJECTIVE: Investigate inflammatory markers' individual and collective impact on the association of HDL-C with incident coronary heart disease (CHD). METHODS: In 3888 older adults without known cardiovascular disease (CVD), we examined if the inflammatory markers C-reactive protein (CRP), interleukin-6 (IL-6), and lipoprotein-associated phospholipase A2 (Lp-PLA₂) modify the relation of HDL-C with CHD. HDL-C, CRP, IL-6, and Lp-PLA₂ values were grouped as using gender-specific tertiles. Also, an inflammation index of z-score sums for CRP, IL-6, and Lp-PLA₂ was categorized into tertiles. We calculated CHD incidence for each HDL-C/inflammation group and performed Cox regression, adjusted for standard CVD risk factors and triglycerides to examine the relationship of combined HDL-C-inflammation groups with incident events. RESULTS: CHD incidence (per 1000 person years) was higher for higher levels of CRP, IL-6, and the index, and lower for higher levels of HDL-C. Compared to high HDL-C/low-inflammation categories (referent), adjusted HRs for incident CHD were increased for those with high HDL-C and high CRP (HR = 1.50, p < 0.01) or highest IL-6 tertile (HR = 1.40, p < 0.05), but not with highest Lp-PLA₂ tertile. Higher CHD incidence was similarly seen for those with intermediate or low HDL-C accompanied by high CRP, high IL-6, or a high inflammatory index. CONCLUSION: The protective relation of high HDL-C for incident CHD appears to be attenuated by greater inflammation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Inflammation; Interleukin-6; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Factors

The influence of obesity-related single nucleotide polymorphisms on BMI across the life course: the PAGE study. - Graff, Mariaelisa; Gordon-Larsen, Penny; Lim, Unhee; Fowke, Jay H; Love, Shelly-Ann; Fesinmeyer, Megan; Wilkens, Lynne R; Vertilus, Shawyntee; Ritchie, Marilyn D; Prentice, Ross L; Pankow, Jim; Monroe, Kristine; et al. (Diabetes, 2013)
Evidence is limited as to whether heritable risk of obesity varies throughout adulthood. Among >34,000 European Americans, aged 18-100 years, from multiple U.S. studies in the Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we examined evidence for heterogeneity in the associations of five established obesity risk variants (near FTO, GNPDA2, MTCH2, TMEM18, and NEGR1) with BMI across four distinct epochs of adulthood: 1) young adulthood (ages 18-25 years), adulthood (ages 26-49 years), middle-age adulthood (ages 50-69 years), and older adulthood (ages ≥70 years); or 2) by menopausal status in women and stratification by age 50 years in men. Summary-effect estimates from each meta-analysis were compared for heterogeneity across the life epochs. We found heterogeneity in the association of the FTO (rs8050136) variant with BMI across the four adulthood epochs (P = 0.0006), with larger effects in young adults relative to older adults (β [SE] = 1.17 [0.45] vs. 0.09 [0.09] kg/m², respectively, per A allele) and smaller intermediate effects. We found no evidence for heterogeneity in the association of GNPDA2, MTCH2, TMEM18, and NEGR1 with BMI across adulthood. Genetic predisposition to obesity may have greater effects on body weight in young compared with older adulthood for FTO, suggesting changes by age, generation, or secular trends. Future research should compare and contrast our findings with results using longitudinal data.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Body Mass Index; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Genetic Association Studies; Health Surveys; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; United States; Young Adult

Insulin resistance and risk of incident heart failure: Cardiovascular Health Study. - Banerjee, Dipanjan; Biggs, Mary L; Mercer, Laina; Mukamal, Kenneth; Kaplan, Robert; Barzilay, Joshua; Kuller, Lewis; Kizer, Jorge R; Djoussé, Luc; Tracy, Russell; Zieman, Susan; Lloyd-Jones, Donald; et al. (Circ Heart Fail, 2013)
BACKGROUND: Patients with heart failure (HF) have higher fasting insulin levels and a higher prevalence of insulin resistance as compared with matched controls. Insulin resistance leads to structural abnormalities in the heart, such as increased left atrial size, left ventricular mass, and alterations in transmitral velocity that can precede the diagnosis of HF. It is not known whether insulin resistance precedes the development of HF or whether the relationship between insulin resistance and HF is present among adults with HF caused by nonischemic heart disease. METHODS AND RESULTS: We examined 4425 participants (60% women) from the Cardiovascular Health Study after excluding those with HF, myocardial infarction, or treated diabetes mellitus at baseline. We used Cox proportional hazards models to estimate the relative risk of incident HF associated with fasting insulin measured at study entry. There were 1216 cases of incident HF (1103 without antecedent myocardial infarction) during a median follow-up of 12 years (maximum, 19 years). Fasting insulin levels were positively associated with the risk of incident HF (hazard ratio, 1.10; 95% confidence interval, 1.05-1.15, per SD change) when adjusted for age, sex, race, field center, physical activity, smoking, alcohol intake, high-density lipoprotein-cholesterol, total cholesterol, systolic blood pressure, and waist circumference. The association between fasting insulin levels and incident HF was similar for HF without antecedent myocardial infarction (hazard ratio, 1.10; 95% confidence interval, 1.05-1.15). Measures of left atrial size, left ventricular mass, and peak A velocity at baseline were associated both with fasting insulin levels and with HF; however, additional statistical adjustment for these parameters did not completely attenuate the insulin-HF estimate (hazard ratio, 1.08; 95% confidence interval, 1.03-1.14 per 1-SD increase in fasting insulin). CONCLUSIONS: Fasting insulin was positively associated with adverse echocardiographic features and risk of subsequent HF in Cardiovascular Health Study participants, including those without an antecedent myocardial infarction. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Female; Heart Atria; Heart Failure; Heart Ventricles; Humans; Incidence; Insulin; Insulin Resistance; Male; Middle Aged; Myocardial Infarction; Organ Size; Proportional Hazards Models; Prospective Studies

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

Lack of associations of ten candidate coronary heart disease risk genetic variants and subclinical atherosclerosis in four US populations: the Population Architecture using Genomics and Epidemiology (PAGE) study. - Zhang, Lili; Bůzková, Petra; Wassel, Christina L; Roman, Mary J; North, Kari E; Crawford, Dana C; Boston, Jonathan; Brown-Gentry, Kristin D; Cole, Shelley A; Deelman, Ewa; Goodloe, Robert; Wilson, Sarah; et al. (Atherosclerosis, 2013)
BACKGROUND: A number of genetic variants have been discovered by recent genome-wide association studies for their associations with clinical coronary heart disease (CHD). However, it is unclear whether these variants are also associated with the development of CHD as measured by subclinical atherosclerosis phenotypes, ankle brachial index (ABI), carotid artery intima-media thickness (cIMT) and carotid plaque. METHODS: Ten CHD risk single nucleotide polymorphisms (SNPs) were genotyped in individuals of European American (EA), African American (AA), American Indian (AI), and Mexican American (MA) ancestry in the Population Architecture using Genomics and Epidemiology (PAGE) study. In each individual study, we performed linear or logistic regression to examine population-specific associations between SNPs and ABI, common and internal cIMT, and plaque. The results from individual studies were meta-analyzed using a fixed effect inverse variance weighted model. RESULTS: None of the ten SNPs was significantly associated with ABI and common or internal cIMT, after Bonferroni correction. In the sample of 13,337 EA, 3809 AA, and 5353 AI individuals with carotid plaque measurement, the GCKR SNP rs780094 was significantly associated with the presence of plaque in AI only (OR = 1.32, 95% confidence interval: 1.17, 1.49, P = 1.08 × 10(-5)), but not in the other populations (P = 0.90 in EA and P = 0.99 in AA). A 9p21 region SNP, rs1333049, was nominally associated with plaque in EA (OR = 1.07, P = 0.02) and in AI (OR = 1.10, P = 0.05). CONCLUSIONS: We identified a significant association between rs780094 and plaque in AI populations, which needs to be replicated in future studies. There was little evidence that the index CHD risk variants identified through genome-wide association studies in EA influence the development of CHD through subclinical atherosclerosis as assessed by cIMT and ABI across ancestries.
Keywords: African Americans; Aged; Ankle Brachial Index; Asymptomatic Diseases; Carotid Artery Diseases; Carotid Intima-Media Thickness; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Indians, North American; Linear Models; Logistic Models; Male; Mexican Americans; Middle Aged; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

Lifetime risk for heart failure among white and black Americans: cardiovascular lifetime risk pooling project. - Huffman, Mark D; Berry, Jarett D; Ning, Hongyan; Dyer, Alan R; Garside, Daniel B; Cai, Xuan; Daviglus, Martha L; Lloyd-Jones, Donald M (J Am Coll Cardiol, 2013)
OBJECTIVES: This study sought to estimate lifetime risk for heart failure (HF) by sex and race. BACKGROUND: Prior estimates of lifetime risk for developing HF range from 20% to 33% in predominantly white cohorts. Short-term risks for HF appear higher for blacks than whites, but only limited comparisons of lifetime risk for HF have been made. METHODS: Using public-release and internal datasets from National Heart, Lung, and Blood Institute-sponsored cohorts, we estimated lifetime risks for developing HF to age 95 years, with death free of HF as the competing event, among participants in the CHA (Chicago Heart Association Detection Project in Industry), ARIC (Atherosclerosis Risk in Communities), and CHS (Cardiovascular Health Study) cohorts. RESULTS: There were 39,578 participants (33,652 [85%] white; 5,926 [15%] black) followed for 716,976 person-years; 5,983 participants developed HF. At age 45 years, lifetime risks for HF through age 95 years in CHA and CHS were 30% to 42% in white men, 20% to 29% in black men, 32% to 39% in white women, and 24% to 46% in black women. Results for ARIC demonstrated similar lifetime risks for HF in blacks and whites through age 75 years (limit of follow-up). Lifetime risk for HF was higher with higher blood pressure and body mass index at all ages in both blacks and whites, and did not diminish substantially with advancing index age. CONCLUSIONS: These are among the first data to compare lifetime risks for HF between blacks and whites. Lifetime risks for HF are high and appear similar for black and white women, yet are somewhat lower for black compared with white men due to competing risks.
Keywords: Adolescent; Adult; African Americans; Age Factors; Aged; Anthropometry; Body Mass Index; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Health Surveys; Heart Failure; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Predictive Value of Tests; Prognosis; Risk Assessment; Severity of Illness Index; Sex Factors; Survival Analysis; Time Factors; United States; Young Adult

Lipoprotein receptor-related protein 1 variants and dietary fatty acids: meta-analysis of European origin and African American studies. - Smith, C E; Ngwa, J; Tanaka, T; Qi, Q; Wojczynski, M K; Lemaitre, R N; Anderson, J S; Manichaikul, A; Mikkilä, V; van Rooij, F J A; Ye, Z; Bandinelli, S; et al. (Int J Obes (Lond), 2013)
OBJECTIVE: Low-density lipoprotein-related receptor protein 1 (LRP1) is a multi-functional endocytic receptor and signaling molecule that is expressed in adipose and the hypothalamus. Evidence for a role of LRP1 in adiposity is accumulating from animal and in vitro models, but data from human studies are limited. The study objectives were to evaluate (i) relationships between LRP1 genotype and anthropometric traits, and (ii) whether these relationships were modified by dietary fatty acids. DESIGN AND METHODS: We conducted race/ethnic-specific meta-analyses using data from 14 studies of US and European whites and 4 of African Americans to evaluate associations of dietary fatty acids and LRP1 genotypes with body mass index (BMI), waist circumference and hip circumference, as well as interactions between dietary fatty acids and LRP1 genotypes. Seven single-nucleotide polymorphisms (SNPs) of LRP1 were evaluated in whites (N up to 42 000) and twelve SNPs in African Americans (N up to 5800). RESULTS: After adjustment for age, sex and population substructure if relevant, for each one unit greater intake of percentage of energy from saturated fat (SFA), BMI was 0.104 kg m(-2) greater, waist was 0.305 cm larger and hip was 0.168 cm larger (all P<0.0001). Other fatty acids were not associated with outcomes. The association of SFA with outcomes varied by genotype at rs2306692 (genotyped in four studies of whites), where the magnitude of the association of SFA intake with each outcome was greater per additional copy of the T allele: 0.107 kg m(-2) greater for BMI (interaction P=0.0001), 0.267 cm for waist (interaction P=0.001) and 0.21 cm for hip (interaction P=0.001). No other significant interactions were observed. CONCLUSION: Dietary SFA and LRP1 genotype may interactively influence anthropometric traits. Further exploration of this, and other diet x genotype interactions, may improve understanding of interindividual variability in the relationships of dietary factors with anthropometric traits.
Keywords: Adipose Tissue; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Body Mass Index; Europe; European Continental Ancestry Group; Fatty Acids; Female; Gene Frequency; Gene-Environment Interaction; Genetic Predisposition to Disease; Genotype; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Obesity; Phenotype; Polymorphism, Single Nucleotide; Prevalence; United States

Long-chain monounsaturated Fatty acids and incidence of congestive heart failure in 2 prospective cohorts. - Imamura, Fumiaki; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Steffen, Lyn M; Folsom, Aaron R; Siscovick, David S; Mozaffarian, Dariush (Circulation, 2013)
BACKGROUND: Decades-old animal experiments suggested that dietary long-chain monounsaturated fatty acids (LCMUFAs) caused cardiotoxicity, leading, for example, development of Canola oil (Canadian oil low in erucic acid) from rapeseed. However, potential cardiotoxicity in humans and contemporary dietary sources of LCMUFAs are unknown. METHODS AND RESULTS: We prospectively investigated the associations of plasma phospholipid LCMUFAs (20:1, 22:1, and 24:1), assessed as objective biomarkers of exposure, with incidence congestive heart failure in 2 independent cohorts: 3694 older adults (mean age, 75.2±5.2 years) in the Cardiovascular Health Study (CHS; 1992-2006) and 3577 middle-aged adults (mean age, 54.1±5.8 years) in the Atherosclerosis Risk in Communities Study, Minnesota subcohort (ARIC; 1987-2008). We further examined dietary correlates of circulating LCMUFAs in CHS and ARIC and US dietary sources of LCMUFAs in the 2003-2010 National Health and Nutrition Examination Survey (NHANES). In CHS, 997 congestive heart failure events occurred during 39 238 person-years; in ARIC, 330 events congestive heart failure events occurred during 64 438 person-years. After multivariable adjustment, higher levels of 22:1 and 24:1 were positively associated with greater incident congestive heart failure in both CHS and ARIC; hazard ratios were 1.34 (95% confidence interval, 1.02-1.76) and 1.57 (95% confidence interval, 1.11-2.23) for highest versus lowest quintiles of 22:1, respectively, and 1.75 (95% confidence interval, 1.23-2.50) and 1.92 (95% confidence interval, 1.22-3.03) for 24:1, respectively (P for trend ≤0.03 each). A variety of foods were related to circulating LCMUFAs in CHS and ARIC, consistent with food sources of LCMUFAs in NHANES, including fish, poultry, meats, whole grains, and mustard. CONCLUSIONS: Higher circulating levels of 22:1 and 24:1, with apparently diverse dietary sources, were associated with incident congestive heart failure in 2 independent cohorts, suggesting possible cardiotoxicity of LCMUFAs in humans.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Dietary Fats; Fatty Acids, Monounsaturated; Feeding Behavior; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Nutrition Surveys; Prospective Studies; Risk Factors; Stroke

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Post-genome-wide association study challenges for lipid traits: describing age as a modifier of gene-lipid associations in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Ann Hum Genet, 2013)
Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age-dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre- or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age-specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 (FADS1) and LDL-C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E-03, I(2) = 89.8), with a significant association in older males (P = 1.39E-06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP-trait associations despite large sample sizes.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

The QT interval and risk of incident atrial fibrillation. - Mandyam, Mala C; Soliman, Elsayed Z; Alonso, Alvaro; Dewland, Thomas A; Heckbert, Susan R; Vittinghoff, Eric; Cummings, Steven R; Ellinor, Patrick T; Chaitman, Bernard R; Stocke, Karen; Applegate, William B; Arking, Dan E; et al. (Heart Rhythm, 2013)
BACKGROUND: Abnormal atrial repolarization is important in the development of atrial fibrillation (AF), but no direct measurement is available in clinical medicine. OBJECTIVE: To determine whether the QT interval, a marker of ventricular repolarization, could be used to predict incident AF. METHODS: We examined a prolonged QT interval corrected by using the Framingham formula (QT(Fram)) as a predictor of incident AF in the Atherosclerosis Risk in Communities (ARIC) study. The Cardiovascular Health Study (CHS) and Health, Aging, and Body Composition (ABC) study were used for validation. Secondary predictors included QT duration as a continuous variable, a short QT interval, and QT intervals corrected by using other formulas. RESULTS: Among 14,538 ARIC study participants, a prolonged QT(Fram) predicted a roughly 2-fold increased risk of AF (hazard ratio [HR] 2.05; 95% confidence interval [CI] 1.42-2.96; P < .001). No substantive attenuation was observed after adjustment for age, race, sex, study center, body mass index, hypertension, diabetes, coronary disease, and heart failure. The findings were validated in Cardiovascular Health Study and Health, Aging, and Body Composition study and were similar across various QT correction methods. Also in the ARIC study, each 10-ms increase in QT(Fram) was associated with an increased unadjusted (HR 1.14; 95% CI 1.10-1.17; P < .001) and adjusted (HR 1.11; 95% CI 1.07-1.14; P < .001) risk of AF. Findings regarding a short QT interval were inconsistent across cohorts. CONCLUSIONS: A prolonged QT interval is associated with an increased risk of incident AF.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Humans; Incidence; Long QT Syndrome; Male; Middle Aged; Risk Factors

Relation of vitamin D and parathyroid hormone to cardiac biomarkers and to left ventricular mass (from the Cardiovascular Health Study). - van Ballegooijen, Adriana J; Visser, Marjolein; Kestenbaum, Bryan; Siscovick, David S; de Boer, Ian H; Gottdiener, John S; deFilippi, Christopher R; Brouwer, Ingeborg A (Am J Cardiol, 2013)
Vitamin D and parathyroid hormone (PTH) may affect cardiovascular health in patients with kidney disease and in the general population. The aim of this study was to investigate associations of serum 25-hydroxyvitamin D (25(OH)D) and PTH concentrations with a comprehensive set of biochemical, electrocardiographic, and echocardiographic measurements of cardiac structure and function in the Cardiovascular Health Study. A total of 2,312 subjects who were free of cardiovascular disease at baseline were studied. Serum 25(OH)D and intact PTH concentrations were measured using mass spectrometry and a 2-site immunoassay. Outcomes were N-terminal pro-B-type natriuretic peptide, cardiac troponin T, electrocardiographic measures of conduction, and echocardiographic measures of left ventricular mass and diastolic dysfunction. At baseline, subjects had a mean age of 73.9 ± 4.9 years, 69.7% were women, and 21% had chronic kidney disease (glomerular filtration rate <60 ml/min). Mean 25(OH)D was 25.2 ± 10.2 ng/ml, and median PTH was 51 pg/ml (range 39 to 65). After adjustment, 25(OH)D was not associated with any of the biochemical, conduction, or echocardiographic outcomes. Serum PTH levels ≥65 pg/ml were associated with greater N-terminal pro-B-type natriuretic peptide, cardiac troponin T, and left ventricular mass in patients with chronic kidney disease. The regression coefficients were: 120 pg/ml (95% confidence interval 36.1 to 204), 5.2 pg/ml (95% confidence interval 3.0 to 7.4), and 17 g (95% confidence interval 6.2 to 27.8) (p <0.001). In subjects with normal kidney function, PTH was not associated with the outcomes. In conclusion, in older adults with chronic kidney disease, PTH excess is associated with higher N-terminal pro-B-type natriuretic peptide, cardiac troponin T, and left ventricular mass. These findings suggest a role for PTH in cardiovascular health and the prevention of cardiac diseases.
Keywords: Adult; Aged; Biomarkers; Cardiovascular Diseases; Echocardiography; Electrocardiography; Female; Follow-Up Studies; Heart Ventricles; Humans; Incidence; Male; Mass Spectrometry; Middle Aged; Parathyroid Hormone; Prospective Studies; United States; Vitamin D

Resequencing and clinical associations of the 9p21.3 region: a comprehensive investigation in the Framingham heart study. - Johnson, Andrew D; Hwang, Shih-Jen; Voorman, Arend; Morrison, Alanna; Peloso, Gina M; Hsu, Yi-Hsiang; Thanassoulis, George; Newton-Cheh, Christopher; Rogers, Ian S; Hoffmann, Udo; Freedman, Jane E; Fox, Caroline S; et al. (Circulation, 2013)
BACKGROUND: 9p21.3 is among the most strongly replicated regions for cardiovascular disease. There are few reports of sequencing the associated 9p21.3 interval. We set out to sequence the 9p21.3 region followed by a comprehensive study of genetic associations with clinical and subclinical cardiovascular disease and its risk factors, as well as with copy number variation and gene expression, in the Framingham Heart Study (FHS). METHODS AND RESULTS: We sequenced 281 individuals (94 with myocardial infarction, 94 with high coronary artery calcium levels, and 93 control subjects free of elevated coronary artery calcium or myocardial infarction), followed by genotyping and association in >7000 additional FHS individuals. We assessed genetic associations with clinical and subclinical cardiovascular disease, risk factor phenotypes, and gene expression levels of the protein-coding genes CDKN2A and CDKN2B and the noncoding gene ANRIL in freshly harvested leukocytes and platelets. Within this large sample, we found strong associations of 9p21.3 variants with increased risk for myocardial infarction, higher coronary artery calcium levels, and larger abdominal aorta diameters and no evidence for association with traditional cardiovascular disease risk factors. No common protein-coding variation, variants in splice donor or acceptor sites, or copy number variation events were observed. By contrast, strong associations were observed between genetic variants and gene expression, particularly for a short isoform of ANRIL and for CDKN2B. CONCLUSIONS: Our thorough genomic characterization of 9p21.3 suggests common variants likely account for observed disease associations and provides further support for the hypothesis that complex regulatory variation affecting ANRIL and CDKN2B gene expression may contribute to increased risk for clinically apparent and subclinical coronary artery disease and aortic disease.
Keywords: Calcinosis; Chromosomes, Human, Pair 9; Coronary Artery Disease; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Longitudinal Studies; Male; Massachusetts; Middle Aged; Myocardial Infarction; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; RNA, Long Noncoding; Sequence Analysis, DNA

Simple risk model predicts incidence of atrial fibrillation in a racially and geographically diverse population: the CHARGE-AF consortium. - Alonso, Alvaro; Krijthe, Bouwe P; Aspelund, Thor; Stepas, Katherine A; Pencina, Michael J; Moser, Carlee B; Sinner, Moritz F; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; et al. (J Am Heart Assoc, 2013)
BACKGROUND: Tools for the prediction of atrial fibrillation (AF) may identify high-risk individuals more likely to benefit from preventive interventions and serve as a benchmark to test novel putative risk factors. METHODS AND RESULTS: Individual-level data from 3 large cohorts in the United States (Atherosclerosis Risk in Communities [ARIC] study, the Cardiovascular Health Study [CHS], and the Framingham Heart Study [FHS]), including 18 556 men and women aged 46 to 94 years (19% African Americans, 81% whites) were pooled to derive predictive models for AF using clinical variables. Validation of the derived models was performed in 7672 participants from the Age, Gene and Environment-Reykjavik study (AGES) and the Rotterdam Study (RS). The analysis included 1186 incident AF cases in the derivation cohorts and 585 in the validation cohorts. A simple 5-year predictive model including the variables age, race, height, weight, systolic and diastolic blood pressure, current smoking, use of antihypertensive medication, diabetes, and history of myocardial infarction and heart failure had good discrimination (C-statistic, 0.765; 95% CI, 0.748 to 0.781). Addition of variables from the electrocardiogram did not improve the overall model discrimination (C-statistic, 0.767; 95% CI, 0.750 to 0.783; categorical net reclassification improvement, -0.0032; 95% CI, -0.0178 to 0.0113). In the validation cohorts, discrimination was acceptable (AGES C-statistic, 0.664; 95% CI, 0.632 to 0.697 and RS C-statistic, 0.705; 95% CI, 0.664 to 0.747) and calibration was adequate. CONCLUSION: A risk model including variables readily available in primary care settings adequately predicted AF in diverse populations from the United States and Europe.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cohort Studies; Diabetes Mellitus; European Continental Ancestry Group; Female; Heart Failure; Humans; Hypertension; Iceland; Incidence; Male; Middle Aged; Myocardial Infarction; Netherlands; Proportional Hazards Models; Risk Assessment; Smoking; United States

A systematic mapping approach of 16q12.2/FTO and BMI in more than 20,000 African Americans narrows in on the underlying functional variation: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Peters, Ulrike; North, Kari E; Sethupathy, Praveen; Buyske, Steve; Haessler, Jeff; Jiao, Shuo; Fesinmeyer, Megan D; Jackson, Rebecca D; Kuller, Lew H; Rajkovic, Aleksandar; Lim, Unhee; Cheng, Iona; et al. (PLoS Genet, 2013)
Genetic variants in intron 1 of the fat mass- and obesity-associated (FTO) gene have been consistently associated with body mass index (BMI) in Europeans. However, follow-up studies in African Americans (AA) have shown no support for some of the most consistently BMI-associated FTO index single nucleotide polymorphisms (SNPs). This is most likely explained by different race-specific linkage disequilibrium (LD) patterns and lower correlation overall in AA, which provides the opportunity to fine-map this region and narrow in on the functional variant. To comprehensively explore the 16q12.2/FTO locus and to search for second independent signals in the broader region, we fine-mapped a 646-kb region, encompassing the large FTO gene and the flanking gene RPGRIP1L by investigating a total of 3,756 variants (1,529 genotyped and 2,227 imputed variants) in 20,488 AAs across five studies. We observed associations between BMI and variants in the known FTO intron 1 locus: the SNP with the most significant p-value, rs56137030 (8.3 × 10(-6)) had not been highlighted in previous studies. While rs56137030was correlated at r(2)>0.5 with 103 SNPs in Europeans (including the GWAS index SNPs), this number was reduced to 28 SNPs in AA. Among rs56137030 and the 28 correlated SNPs, six were located within candidate intronic regulatory elements, including rs1421085, for which we predicted allele-specific binding affinity for the transcription factor CUX1, which has recently been implicated in the regulation of FTO. We did not find strong evidence for a second independent signal in the broader region. In summary, this large fine-mapping study in AA has substantially reduced the number of common alleles that are likely to be functional candidates of the known FTO locus. Importantly our study demonstrated that comprehensive fine-mapping in AA provides a powerful approach to narrow in on the functional candidate(s) underlying the initial GWAS findings in European populations.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Aged, 80 and over; Alleles; Body Mass Index; Chromosome Mapping; Continental Population Groups; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Obesity; Proteins

ADAM19 and HTR4 variants and pulmonary function: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - London, Stephanie J; Gao, Wei; Gharib, Sina A; Hancock, Dana B; Wilk, Jemma B; House, John S; Gibbs, Richard A; Muzny, Donna M; Lumley, Thomas; Franceschini, Nora; North, Kari E; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The pulmonary function measures of forced expiratory volume in 1 second (FEV1) and its ratio to forced vital capacity (FVC) are used in the diagnosis and monitoring of lung diseases and predict cardiovascular mortality in the general population. Genome-wide association studies (GWASs) have identified numerous loci associated with FEV1 and FEV1/FVC, but the causal variants remain uncertain. We hypothesized that novel or rare variants poorly tagged by GWASs may explain the significant associations between FEV1/FVC and 2 genes: ADAM19 and HTR4. METHODS AND RESULTS: We sequenced ADAM19 and its promoter region along with the ≈21-kb portion of HTR4 harboring GWAS single-nucleotide polymorphisms for pulmonary function and analyzed associations with FEV1/FVC among 3983 participants of European ancestry from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Meta-analysis of common variants in each region identified statistically significant associations (316 tests; P<1.58×10(-4)) with FEV1/FVC for 14 ADAM19 single-nucleotide polymorphisms and 24 HTR4 single-nucleotide polymorphisms. After conditioning on the sentinel GWASs hit in each gene (ADAM19 rs1422795, minor allele frequency=0.33 and HTR4 rs11168048, minor allele frequency=0.40], 1 single-nucleotide polymorphism remained statistically significant (ADAM19 rs13155908, minor allele frequency=0.12; P=1.56×10(-4)). Analysis of rare variants (minor allele frequency <1%) using sequence kernel association test did not identify associations with either region. CONCLUSIONS: Sequencing identified 1 common variant associated with FEV1/FVC independent of the sentinel ADAM19 GWAS hit and supports the original HTR4 GWAS findings. Rare variants do not seem to underlie GWAS associations with pulmonary function for common variants in ADAM19 and HTR4.
Keywords: ADAM Proteins; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Age- and sex-dependent upper reference limits for the high-sensitivity cardiac troponin T assay. - Gore, M Odette; Seliger, Stephen L; deFilippi, Christopher R; Nambi, Vijay; Christenson, Robert H; Hashim, Ibrahim A; Hoogeveen, Ron C; Ayers, Colby R; Sun, Wensheng; McGuire, Darren K; Ballantyne, Christie M; de Lemos, James A (J Am Coll Cardiol, 2014)
OBJECTIVES: The study sought to determine the 99th percentile upper reference limit for the high-sensitivity cardiac troponin T assay (hs-cTnT) in 3 large independent cohorts. BACKGROUND: The presently recommended 14 ng/l cut point for the diagnosis of myocardial infarction using the hs-cTnT assay was derived from small studies of presumably healthy individuals, with relatively little phenotypic characterization. METHODS: Data were included from 3 well-characterized population-based studies: the Dallas Heart Study (DHS), the Atherosclerosis Risk in Communities (ARIC) Study, and the Cardiovascular Health Study (CHS). Within each cohort, reference subcohorts were defined excluding individuals with recent hospitalization, overt cardiovascular disease, and kidney disease (subcohort 1), and further excluding those with subclinical structural heart disease (subcohort 2). Data were analyzed stratified by age, sex, and race. RESULTS: The 99th percentile values for the hs-cTnT assay in DHS, ARIC, and CHS were 18, 22, and 36 ng/l (subcohort 1) and 14, 21, and 28 ng/l (subcohort 2), respectively. These differences in 99th percentile values paralleled age differences across cohorts. Analyses within sex/age strata yielded similar results between cohorts. Within each cohort, 99th percentile values increased with age and were higher in men. More than 10% of men 65 to 74 years of age with no cardiovascular disease in our study had cardiac troponin T values above the current myocardial infarction threshold. CONCLUSIONS: Use of a uniform 14 ng/l cutoff for the hs-cTnT assay may lead to over-diagnosis of myocardial infarction, particularly in men and the elderly. Clinical validation is needed of new age- and sex-specific cutoff values for this assay.
Keywords: Adult; Age Factors; Aged; Biological Assay; Biomarkers; Blood Chemical Analysis; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Myocardial Infarction; Reference Values; Risk Assessment; Sensitivity and Specificity; Severity of Illness Index; Sex Factors; Troponin T

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association between the metabolic syndrome, its individual components, and unprovoked venous thromboembolism: results of a patient-level meta-analysis. - Ageno, Walter; Di Minno, Matteo N D; Ay, Cihan; Jang, Moon Ju; Hansen, John-Bjarne; Steffen, Lyn M; Vaya, Amparo; Rattazzi, Marcello; Pabinger, Ingrid; Oh, Doyeun; Di Minno, Giovanni; Braekkan, Sigrid K; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: The metabolic syndrome (MetS) may contribute to the pathogenesis of venous thromboembolism (VTE), but this association requires additional investigation. APPROACH AND RESULTS: We performed a patient-level meta-analysis of case-control and cohort studies that evaluated the role of MetS and risk of unprovoked VTE. For case-control studies, odds ratios and 95% confidence intervals were calculated using logistic regression analysis to estimate the influence of individual variables on the risk of VTE; χ(2) tests for trend were used to investigate the effect of increasing number of components of MetS on the risk of VTE and to explore the influence of abdominal obesity on this relationship. For cohort studies, hazard ratios and 95% confidence interval were calculated using multivariable Cox regression analysis. Six case-control studies were included (908 cases with unprovoked VTE and 1794 controls): in multivariate analysis, MetS was independently associated with VTE (odds ratio, 1.91; 95% confidence interval, 1.57-2.33), and both MetS and abdominal obesity were better predictors of unprovoked VTE than obesity defined by the body mass index. Two prospective cohort studies were included (26,531 subjects and 289 unprovoked VTE events): age, obesity, and abdominal obesity, but not MetS were associated with VTE. CONCLUSIONS: Case-control but not prospective cohort studies support an association between MetS and VTE. Abdominal adiposity is a strong risk factor for VTE.
Keywords: Adult; Aged; Case-Control Studies; Cohort Studies; Female; Humans; Logistic Models; Male; Metabolic Syndrome; Middle Aged; Obesity, Abdominal; Risk Factors; Venous Thromboembolism

Association of a cystatin C gene variant with cystatin C levels, CKD, and risk of incident cardiovascular disease and mortality. - O'Seaghdha, Conall M; Tin, Adrienne; Yang, Qiong; Katz, Ronit; Liu, Yongmei; Harris, Tamara; Astor, Brad; Coresh, Josef; Fox, Caroline S; Kao, W H Linda; Shlipak, Michael G (Am J Kidney Dis, 2014)
BACKGROUND: Carriers of the T allele of the single-nucleotide polymorphism rs13038305 tend to have lower cystatin C levels and higher cystatin C-based estimated glomerular filtration rate (eGFRcys). Adjusting for this genetic effect on cystatin C concentrations may improve GFR estimation, reclassify cases of chronic kidney disease (CKD), and strengthen risk estimates for cardiovascular disease (CVD) and mortality. STUDY DESIGN: Observational. SETTING & POPULATION: 4 population-based cohorts: Atherosclerosis Risk in Communities (ARIC), Cardiovascular Health (CHS), Framingham Heart (FHS), and Health, Aging, and Body Composition (Health ABC) studies. PREDICTORS: We estimated the association of rs13038305 with eGFRcys and serum creatinine-based eGFR (eGFRcr) and performed longitudinal analyses of the associations of eGFRcys with mortality and cardiovascular events following adjustment for rs13038305. OUTCOMES: We assessed reclassification by genotype-adjusted eGFRcys across CKD categories: <45, 45-59, 60-89, and ≥ 90 mL/min/1.73 m(2). We compared mortality and CVD outcomes in those reclassified to a worse eGFRcys category with those unaffected. Results were combined using fixed-effect inverse-variance meta-analysis. RESULTS: In 14,645 participants, each copy of the T allele of rs13038305 (frequency, 21%) was associated with a 6.4% lower cystatin C concentration, 5.5-mL/min/1.73 m(2) higher eGFRcys, and 36% [95% CI, 29%-41%] lower odds of CKD. Associations with CVD (HR, 1.17; 95% CI, 1.14-1.20) and mortality (HR, 1.22; 95% CI, 1.19-1.24) per 10-mL/min/1.73 m(2) lower eGFRcys were similar with or without rs13038305 adjustment. 1,134 (7.7%) participants were reclassified to a worse CKD category following rs13038305 adjustment, and rates of CVD and mortality were higher in individuals who were reclassified. However, the overall net reclassification index was not significant for either outcome, at 0.009 (95% CI, -0.003 to 0.022) for mortality and 0.014 (95% CI, 0.0 to 0.028) for CVD. LIMITATIONS: rs13038305 explains only a small proportion of cystatin C variation. CONCLUSIONS: Statistical adjustment can correct a genetic bias in GFR estimates based on cystatin C in carriers of the T allele of rs13038305 and result in changes in disease classification. However, on a population level, the effects on overall reclassification of CKD status are modest.
Keywords: Aged; Bias; Biomarkers; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Genetic Variation; Glomerular Filtration Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Risk Assessment; Risk Factors; Severity of Illness Index; Statistics as Topic; Survival Rate

Association of kidney disease measures with ischemic versus hemorrhagic strokes: pooled analyses of 4 prospective community-based cohorts. - Mahmoodi, Bakhtawar K; Yatsuya, Hiroshi; Matsushita, Kunihiro; Sang, Yinying; Gottesman, Rebecca F; Astor, Brad C; Woodward, Mark; Longstreth, W T; Psaty, Bruce M; Shlipak, Michael G; Folsom, Aaron R; Gansevoort, Ron T; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Although low glomerular filtration rate (GFR) and albuminuria are associated with increased risk of stroke, few studies compared their contribution to risk of ischemic versus hemorrhagic stroke separately. We contrasted the association of these kidney measures with ischemic versus hemorrhagic stroke. METHODS: We pooled individual participant data from 4 community-based cohorts: 3 from the United States and 1 from The Netherlands. GFR was estimated using both creatinine and cystatin C, and albuminuria was quantified by urinary albumin-to-creatinine ratio (ACR). Associations of estimated GFR and ACR were compared for each stroke type (ischemic versus intraparenchymal hemorrhagic) using study-stratified Cox regression. RESULTS: Among 29,595 participants (mean age, 61 [SD 12.5] years; 46% men; 17% black), 1261 developed stroke (12% hemorrhagic) during 280,549 person-years. Low estimated GFR was significantly associated with increased risk of ischemic stroke, but not hemorrhagic stroke, whereas high ACR was associated with both stroke types. Adjusted hazard ratios for ischemic and hemorrhagic stroke at estimated GFR of 45 (versus 95) mL/min per 1.73 m2 were 1.30 (95% confidence interval, 1.01-1.68) and 0.92 (0.47-1.81), respectively. In contrast, the corresponding hazard ratios for ACR of 300 (versus 5) mg/g were 1.62 (1.27-2.07) for ischemic and 2.57 (1.37-4.83) for hemorrhagic stroke, with significantly stronger association with hemorrhagic stroke (P=0.04). For hemorrhagic stroke, the association of elevated ACR was of similar magnitude as that of elevated systolic blood pressure. CONCLUSIONS: Whereas albuminuria showed significant association with both stroke types, the association of decreased estimated GFR was only significant for ischemic stroke. The strong association of albuminuria with both stroke types warrants clinical attention and further investigations.
Keywords: Aged; Albuminuria; Brain Ischemia; Comorbidity; Female; Glomerular Filtration Rate; Humans; Intracranial Hemorrhages; Kidney Diseases; Male; Middle Aged; Netherlands; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Association of sick sinus syndrome with incident cardiovascular disease and mortality: the Atherosclerosis Risk in Communities study and Cardiovascular Health Study. - Alonso, Alvaro; Jensen, Paul N; Lopez, Faye L; Chen, Lin Y; Psaty, Bruce M; Folsom, Aaron R; Heckbert, Susan R (PLoS One, 2014)
BACKGROUND: Sick sinus syndrome (SSS) is a common indication for pacemaker implantation. Limited information exists on the association of sick sinus syndrome (SSS) with mortality and cardiovascular disease (CVD) in the general population. METHODS: We studied 19,893 men and women age 45 and older in the Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS), two community-based cohorts, who were without a pacemaker or atrial fibrillation (AF) at baseline. Incident SSS cases were validated by review of medical charts. Incident CVD and mortality were ascertained using standardized protocols. Multivariable Cox models were used to estimate the association of incident SSS with selected outcomes. RESULTS: During a mean follow-up of 17 years, 213 incident SSS events were identified and validated (incidence, 0.6 events per 1,000 person-years). After adjustment for confounders, SSS incidence was associated with increased mortality (hazard ratio [HR] 1.39, 95% confidence interval [CI] 1.14-1.70), coronary heart disease (HR 1.72, 95%CI 1.11-2.66), heart failure (HR 2.87, 95%CI 2.17-3.80), stroke (HR 1.56, 95%CI 0.99-2.46), AF (HR 5.75, 95%CI 4.43-7.46), and pacemaker implantation (HR 53.7, 95%CI 42.9-67.2). After additional adjustment for other incident CVD during follow-up, SSS was no longer associated with increased mortality, coronary heart disease, or stroke, but remained associated with higher risk of heart failure (HR 2.00, 95%CI 1.51-2.66), AF (HR 4.25, 95%CI 3.28-5.51), and pacemaker implantation (HR 25.2, 95%CI 19.8-32.1). CONCLUSION: Individuals who develop SSS are at increased risk of death and CVD. The mechanisms underlying these associations warrant further investigation.
Keywords: Age Distribution; Atherosclerosis; Cohort Studies; Continental Population Groups; Female; Humans; Incidence; Male; Middle Aged; Residence Characteristics; Risk; Sex Distribution; Sick Sinus Syndrome

The challenges of genome-wide interaction studies: lessons to learn from the analysis of HDL blood levels. - van Leeuwen, Elisabeth M; Smouter, Françoise A S; Kam-Thong, Tony; Karbalai, Nazanin; Smith, Albert V; Harris, Tamara B; Launer, Lenore J; Sitlani, Colleen M; Li, Guo; Brody, Jennifer A; Bis, Joshua C; White, Charles C; et al. (PLoS One, 2014)
Genome-wide association studies (GWAS) have revealed 74 single nucleotide polymorphisms (SNPs) associated with high-density lipoprotein cholesterol (HDL) blood levels. This study is, to our knowledge, the first genome-wide interaction study (GWIS) to identify SNP×SNP interactions associated with HDL levels. We performed a GWIS in the Rotterdam Study (RS) cohort I (RS-I) using the GLIDE tool which leverages the massively parallel computing power of Graphics Processing Units (GPUs) to perform linear regression on all genome-wide pairs of SNPs. By performing a meta-analysis together with Rotterdam Study cohorts II and III (RS-II and RS-III), we were able to filter 181 interaction terms with a p-value<1 · 10-8 that replicated in the two independent cohorts. We were not able to replicate any of these interaction term in the AGES, ARIC, CHS, ERF, FHS and NFBC-66 cohorts (Ntotal = 30,011) when adjusting for multiple testing. Our GWIS resulted in the consistent finding of a possible interaction between rs774801 in ARMC8 (ENSG00000114098) and rs12442098 in SPATA8 (ENSG00000185594) being associated with HDL levels. However, p-values do not reach the preset Bonferroni correction of the p-values. Our study suggest that even for highly genetically determined traits such as HDL the sample sizes needed to detect SNP×SNP interactions are large and the 2-step filtering approaches do not yield a solution. Here we present our analysis plan and our reservations concerning GWIS.
Keywords: Cholesterol, HDL; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Common carotid intima-media thickness measurements do not improve cardiovascular risk prediction in individuals with elevated blood pressure: the USE-IMT collaboration. - Bots, Michiel L; Groenewegen, Karlijn A; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; Hedblad, Bo; Hofman, Albert; Holewijn, Suzanne; et al. (Hypertension, 2014)
Carotid intima-media thickness (CIMT) is a marker of cardiovascular risk. It is unclear whether measurement of mean common CIMT improves 10-year risk prediction of first-time myocardial infarction or stroke in individuals with elevated blood pressure. We performed an analysis among individuals with elevated blood pressure (i.e., a systolic blood pressure ≥140 mm Hg and a diastolic blood pressure ≥ 90 mm Hg) in USE-IMT, a large ongoing individual participant data meta-analysis. We refitted the risk factors of the Framingham Risk Score on asymptomatic individuals (baseline model) and expanded this model with mean common CIMT (CIMT model) measurements. From both models, 10-year risks to develop a myocardial infarction or stroke were estimated. In individuals with elevated blood pressure, we compared discrimination and calibration of the 2 models and calculated the net reclassification improvement (NRI). We included 17 254 individuals with elevated blood pressure from 16 studies. During a median follow-up of 9.9 years, 2014 first-time myocardial infarctions or strokes occurred. The C-statistics of the baseline and CIMT models were similar (0.73). NRI with the addition of mean common CIMT was small and not significant (1.4%; 95% confidence intervals, -1.1 to 3.7). In those at intermediate risk (n=5008, 10-year absolute risk of 10% to 20%), the NRI was 5.6% (95% confidence intervals, 1.6-10.4). There is no added value of measurement of mean common CIMT in individuals with elevated blood pressure for improving cardiovascular risk prediction. For those at intermediate risk, the addition of mean common CIMT to an existing cardiovascular risk score is small but statistically significant.
Keywords: Adult; Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Carotid Artery, Common; Carotid Intima-Media Thickness; Cohort Studies; Female; Humans; Hypertension; Male; Meta-Analysis as Topic; Middle Aged; Risk Assessment; Risk Factors

A common SCN5A variant is associated with PR interval and atrial fibrillation among African Americans. - Ilkhanoff, Leonard; Arking, Dan E; Lemaitre, Rozenn N; Alonso, Alvaro; Chen, Lin Y; Durda, Peter; Hesselson, Stephanie E; Kerr, Kathleen F; Magnani, Jared W; Marcus, Gregory M; Schnabel, Renate B; Smith, J Gustav; et al. (J Cardiovasc Electrophysiol, 2014)
OBJECTIVE: We examined the association of rs7626962 (S1103Y) or rs7629265, a variant in high linkage disequilibrium with S1103Y (r(2) = 0.87 - 1), with sudden cardiac death (SCD) and atrial fibrillation (AF) among African Americans. BACKGROUND: The SCN5A missense variant S1103Y has been associated with SCD among African Americans in small case-control studies, but larger population-based studies are needed to validate these findings. The association of this variant with AF has not been fully explored. METHODS: Using genotyping data on over 7,000 African Americans from 5 cohorts (Atherosclerosis Risk in Communities [ARIC], Cleveland Family Study [CFS], Jackson Heart Study [JHS], Multi-Ethnic Study of Atherosclerosis [MESA], Cardiovascular Health Study [CHS]), we examined the association of rs7629265 with electrocardiographic PR, QRS, and QT intervals, and with incident AF and SCD. We examined association of S1103Y (rs7626962) with SCD using a population-based case-control study of SCD Cardiac Arrest Blood Study (CABS). RESULTS: Meta-analyses across 5 cohorts demonstrated that rs7629265 was significantly associated with PR duration (β = -4.1 milliseconds; P = 2.2×10(-6) ), but not significantly associated with QRS or QT intervals. In meta-analyses of prospectively followed ARIC and CHS participants (n = 3,656), rs7629265 was associated with increased AF risk (n = 299 AF cases; HR = 1.74, P = 1.9 × 10(-4) ). By contrast, rs7629265 was not significantly associated with SCD risk in ARIC (n = 83 SCD cases; P = 0.30) or CHS (n = 54 SCD cases; P = 0.47). Similarly, S1103Y was not significantly associated with SCD risk in CABS (n = 225 SCD cases; P = 0.29). CONCLUSION: The common SCN5A variant, rs7629265, is associated with increased AF risk and shorter PR interval among African Americans. In contrast to prior reports, we found no evidence of association of rs7629265 or rs7626962 (S1103Y) with SCD risk in the general population.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Female; Genetic Variation; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Prospective Studies; Risk Factors; Single-Blind Method

Coronary heart disease risks associated with high levels of HDL cholesterol. - Wilkins, John T; Ning, Hongyan; Stone, Neil J; Criqui, Michael H; Zhao, Lihui; Greenland, Philip; Lloyd-Jones, Donald M (J Am Heart Assoc, 2014)
BACKGROUND: The association between high-density lipoprotein cholesterol (HDL-C) and coronary heart disease (CHD) events is not well described in individuals with very high levels of HDL-C (>80 mg/dL). METHODS AND RESULTS: Using pooled data from 6 community-based cohorts we examined CHD and total mortality risks across a broad range of HDL-C, including values in excess of 80 mg/dL. We used Cox proportional hazards models with penalized splines to assess multivariable, adjusted, sex-stratified associations of HDL-C with the hazard for CHD events and total mortality, using HDL-C 45 mg/dL and 55 mg/dL as the referent in men and women, respectively. Analyses included 11 515 men and 12 925 women yielding 307 245 person-years of follow-up. In men, the association between HDL-C and CHD events was inverse and linear across most HDL-C values; however at HDL-C values >90 mg/dL there was a plateau effect in the pattern of association. In women, the association between HDL-C and CHD events was inverse and linear across lower values of HDL-C, however at HDL-C values >75 mg/dL there were no further reductions in the hazard ratio point estimates for CHD. In unadjusted models there were increased total mortality risks in men with very high HDL-C, however mortality risks observed in participants with very high HDL-C were attenuated after adjustment for traditional risk factors. CONCLUSIONS: We did not observe further reductions in CHD risk with HDL-C values higher than 90 mg/dL in men and 75 mg/dL in women.
Keywords: Aged; Biomarkers; Cholesterol, HDL; Coronary Disease; Female; Humans; Linear Models; Male; Middle Aged; Multivariate Analysis; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Decline in estimated glomerular filtration rate and subsequent risk of end-stage renal disease and mortality. - Coresh, Josef; Turin, Tanvir Chowdhury; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Appel, Lawrence J; Arima, Hisatomi; Chadban, Steven J; Cirillo, Massimo; Djurdjev, Ognjenka; Green, Jamie A; Heine, Gunnar H; et al. (JAMA, 2014)
IMPORTANCE: The established chronic kidney disease (CKD) progression end point of end-stage renal disease (ESRD) or a doubling of serum creatinine concentration (corresponding to a change in estimated glomerular filtration rate [GFR] of −57% or greater) is a late event. OBJECTIVE: To characterize the association of decline in estimated GFR with subsequent progression to ESRD with implications for using lesser declines in estimated GFR as potential alternative end points for CKD progression. Because most people with CKD die before reaching ESRD, mortality risk also was investigated. DATA SOURCES AND STUDY SELECTION: Individual meta-analysis of 1.7 million participants with 12,344 ESRD events and 223,944 deaths from 35 cohorts in the CKD Prognosis Consortium with a repeated measure of serum creatinine concentration over 1 to 3 years and outcome data. DATA EXTRACTION AND SYNTHESIS: Transfer of individual participant data or standardized analysis of outputs for random-effects meta-analysis conducted between July 2012 and September 2013, with baseline estimated GFR values collected from 1975 through 2012. MAIN OUTCOMES AND MEASURES: End-stage renal disease (initiation of dialysis or transplantation) or all-cause mortality risk related to percentage change in estimated GFR over 2 years, adjusted for potential confounders and first estimated GFR. RESULTS: The adjusted hazard ratios (HRs) of ESRD and mortality were higher with larger estimated GFR decline. Among participants with baseline estimated GFR of less than 60 mL/min/1.73 m2, the adjusted HRs for ESRD were 32.1 (95% CI, 22.3-46.3) for changes of −57% in estimated GFR and 5.4 (95% CI, 4.5-6.4) for changes of −30%. However, changes of −30% or greater (6.9% [95% CI, 6.4%-7.4%] of the entire consortium) were more common than changes of −57% (0.79% [95% CI, 0.52%-1.06%]). This association was strong and consistent across the length of the baseline period (1 to 3 years), baseline estimated GFR, age, diabetes status, or albuminuria. Average adjusted 10-year risk of ESRD (in patients with a baseline estimated GFR of 35 mL/min/1.73 m2) was 99% (95% CI, 95%-100%) for estimated GFR change of −57%, was 83% (95% CI, 71%-93%) for estimated GFR change of −40%, and was 64% (95% CI, 52%-77%) for estimated GFR change of −30% vs 18% (95% CI, 15%-22%) for estimated GFR change of 0%. Corresponding mortality risks were 77% (95% CI, 71%-82%), 60% (95% CI, 56%-63%), and 50% (95% CI, 47%-52%) vs 32% (95% CI, 31%-33%), showing a similar but weaker pattern. CONCLUSIONS AND RELEVANCE: Declines in estimated GFR smaller than a doubling of serum creatinine concentration occurred more commonly and were strongly and consistently associated with the risk of ESRD and mortality, supporting consideration of lesser declines in estimated GFR (such as a 30% reduction over 2 years) as an alternative end point for CKD progression.
Keywords: Adult; Aged; Aged, 80 and over; Cohort Studies; Creatinine; Disease Progression; Endpoint Determination; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Reference Values; Risk

Development and validation of an ankle brachial index risk model for the prediction of cardiovascular events. - Fowkes, F G R; Murray, G D; Butcher, I; Folsom, A R; Hirsch, A T; Couper, D J; deBacker, G; Kornitzer, M; Newman, A B; Sutton-Tyrrell, K C; Cushman, M; Lee, A J; et al. (Eur J Prev Cardiol, 2014)
BACKGROUND: The ankle brachial index (ABI) is related to risk of cardiovascular events independent of the Framingham risk score (FRS). The aim of this study was to develop and evaluate a risk model for cardiovascular events incorporating the ABI and FRS. DESIGN: An analysis of participant data from 18 cohorts in which 24,375 men and 20,377 women free of coronary heart disease had ABI measured and were followed up for events. METHODS: Subjects were divided into a development and internal validation dataset and an external validation dataset. Two models, comprising FRS and FRS + ABI, were fitted for the primary outcome of major coronary events. RESULTS: In predicting events in the external validation dataset, C-index for the FRS was 0.672 (95% CI 0.599 to 0.737) in men and 0.578 (95% CI 0.492 to 0.661) in women. The FRS + ABI led to a small increase in C-index in men to 0.685 (95% CI 0.612 to 0.749) and large increase in women to 0.690 (95% CI 0.605 to 0.764) with net reclassification improvement (NRI) of 4.3% (95% CI 0.0 to 7.6%, p = 0.050) and 9.6% (95% CI 6.1 to 16.4%, p < 0.001), respectively. Restricting the FRS + ABI model to those with FRS intermediate 10-year risk of 10 to 19% resulted in higher NRI of 15.9% (95% CI 6.1 to 20.6%, p < 0.001) in men and 23.3% (95% CI 13.8 to 62.5%, p = 0.002) in women. However, incorporating ABI in an improved newly fitted risk factor model had a nonsignificant effect: NRI 2.0% (95% CI 2.3 to 4.2%, p = 0.567) in men and 1.1% (95% CI 1.9 to 4.0%, p = 0.483) in women. CONCLUSIONS: An ABI risk model may improve prediction especially in individuals at intermediate risk and when performance of the base risk factor model is modest.
Keywords: Adult; Aged; Aged, 80 and over; Ankle Brachial Index; Cardiovascular Diseases; Europe; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Prognosis; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States; Young Adult

The effect of widowhood on husbands' and wives' physical activity: the Cardiovascular Health Study. - Stahl, Sarah T; Schulz, Richard (J Behav Med, 2014)
This prospective study examined the effect of widowhood on physical activity by comparing widowed elders to health status-, age-, and sex-matched married controls. Participants included 396 married controls and 396 widows/widowers age 64-91 (M age = 72.7 years) who experienced the death of their spouse while participating in the Cardiovascular Health Study. Compared to married controls, widowed men, but not women, were more likely to increase their physical activity following the death of their spouse. However, this increased level of activity was not sustained and declines as time since spousal death passes. Moreover, during the year before spousal death, soon-to-be widowed men, but not women, increase their physical activity. Our results suggest that widowed men experience significant changes in physical activity and that the transition to widowhood contribute to these changes.
Keywords: Aged; Aged, 80 and over; Cardiovascular System; Female; Health Surveys; Humans; Male; Middle Aged; Motor Activity; Prospective Studies; Sex Characteristics; Spouses; Time Factors; Widowhood

Estimated GFR and circulating 24,25-dihydroxyvitamin D3 concentration: a participant-level analysis of 5 cohort studies and clinical trials. - de Boer, Ian H; Sachs, Michael C; Chonchol, Michel; Himmelfarb, Jonathan; Hoofnagle, Andrew N; Ix, Joachim H; Kremsdorf, Robin A; Lin, Yvonne S; Mehrotra, Rajnish; Robinson-Cohen, Cassianne; Siscovick, David S; Steffes, Michael W; et al. (Am J Kidney Dis, 2014)
BACKGROUND: Decreased glomerular filtration rate (GFR) leads to reduced production of 1,25-dihydroxyvitamin D3 from 25-hydroxyvitamin D3 (25[OH]D3). Effects of low GFR on vitamin D catabolism are less well understood. We tested associations of estimated GFR (eGFR) with the circulating concentration of 24,25-dihydroxyvitamin D3 (24,25[OH]2D3), the most abundant product of 25(OH)D3 catabolism, across populations with a wide range of GFRs. STUDY DESIGN: Cross-sectional study. SETTING & PARTICIPANTS: 9,596 participants in 5 cohort studies and clinical trials: the Diabetes Control and Complications Trial (N=1,193), Multi-Ethnic Study of Atherosclerosis (N=6,470), Cardiovascular Health Study (N=932), Seattle Kidney Study (N=289), and Hemodialysis Study (N=712). PREDICTOR: eGFR. OUTCOME: Circulating 24,25(OH)2D3 concentration. MEASUREMENTS: GFR was estimated from serum creatinine using the Chronic Kidney Disease Epidemiology Collaboration equation. Vitamin D metabolites were measured by mass spectrometry. RESULTS: Circulating 24,25(OH)2D3 concentration was correlated with circulating 25(OH)D3 concentration (Pearson r range, 0.64-0.88). This correlation was weaker with lower eGFRs. Moreover, the increment in 24,25(OH)2D3 concentration associated with higher 25(OH)D3 concentration (slope) was lower with lower eGFRs: 2.06 (95% CI, 2.01-2.10), 1.77 (95% CI, 1.74-1.81), 1.55 (95% CI, 1.48-1.62), 1.17 (95% CI, 1.05-1.29), 0.92 (95% CI, 0.74-1.10), 0.61 (95% CI, 0.22-1.00), and 0.37 (95% CI, 0.35-0.39) ng/mL of 24,25(OH)2D3 per 10 ng/mL of 25(OH)D3 for eGFRs≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m2 and end-stage renal disease treated with hemodialysis, respectively. As a result, at a 25(OH)D3 concentration of 20 ng/mL, mean 24,25(OH)2D3 concentrations were 2.92 (95% CI, 2.87-2.96), 2.68 (95% CI, 2.64-2.72), 2.35 (95% CI, 2.26-2.45), 1.92 (95% CI, 1.74-2.10), 1.69 (95% CI, 1.43-1.95), 1.14 (95% CI, 0.62-1.66), and 1.04 (95% CI,1.02-1.07) ng/mL for each category, respectively. This interaction was independent of other relevant clinical characteristics. Race, diabetes, urine albumin excretion, and circulating parathyroid hormone and fibroblast growth factor 23 concentrations more modestly modified the association of 24,25(OH)2D3 with 25(OH)D3. LIMITATIONS: Lack of direct pharmacokinetic measurements of vitamin D catabolism. CONCLUSIONS: Lower eGFR is associated strongly with reduced vitamin D catabolism, as measured by circulating 24,25(OH)2D3 concentration.
Keywords: 24,25-Dihydroxyvitamin D 3; Adult; Aged; Aged, 80 and over; Biomarkers; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Observational Studies as Topic; Randomized Controlled Trials as Topic; Young Adult

Evidence of heterogeneity by race/ethnicity in genetic determinants of QT interval. - Seyerle, Amanda A; Young, Alicia M; Jeff, Janina M; Melton, Phillip E; Jorgensen, Neal W; Lin, Yi; Carty, Cara L; Deelman, Ewa; Heckbert, Susan R; Hindorff, Lucia A; Jackson, Rebecca D; Martin, Lisa W; et al. (Epidemiology, 2014)
BACKGROUND: QT interval (QT) prolongation is an established risk factor for ventricular tachyarrhythmia and sudden cardiac death. Previous genome-wide association studies in populations of the European descent have identified multiple genetic loci that influence QT, but few have examined these loci in ethnically diverse populations. METHODS: Here, we examine the direction, magnitude, and precision of effect sizes for 21 previously reported SNPs from 12 QT loci, in populations of European (n = 16,398), African (n = 5,437), American Indian (n = 5,032), Hispanic (n = 1,143), and Asian (n = 932) descent as part of the Population Architecture using Genomics and Epidemiology (PAGE) study. Estimates obtained from linear regression models stratified by race/ethnicity were combined using inverse-variance weighted meta-analysis. Heterogeneity was evaluated using Cochran's Q test. RESULTS: Of 21 SNPs, 7 showed consistent direction of effect across all 5 populations, and an additional 9 had estimated effects that were consistent across 4 populations. Despite consistent direction of effect, 9 of 16 SNPs had evidence (P < 0.05) of heterogeneity by race/ethnicity. For these 9 SNPs, linkage disequilibrium plots often indicated substantial variation in linkage disequilibrium patterns among the various racial/ethnic groups, as well as possible allelic heterogeneity. CONCLUSIONS: These results emphasize the importance of analyzing racial/ethnic groups separately in genetic studies. Furthermore, they underscore the possible utility of trans-ethnic studies to pinpoint underlying casual variants influencing heritable traits such as QT.
Keywords: Aged; Continental Population Groups; Electrocardiography; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long QT Syndrome; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Extreme deep white matter hyperintensity volumes are associated with African American race. - Nyquist, Paul A; Bilgel, Murat S; Gottesman, Rebecca; Yanek, Lisa R; Moy, Taryn F; Becker, Lewis C; Cuzzocreo, Jennifer; Prince, Jerry; Yousem, David M; Becker, Diane M; Kral, Brian G; Vaidya, Dhananjay (Cerebrovasc Dis, 2014)
BACKGROUND: African Americans (AAs) have a higher prevalence of extreme ischemic white matter hyperintensities (WMHs) on magnetic resonance imaging (MRI) than do European Americans (EAs) based on the Cardiovascular Health Study (CHS) score. Ischemic white matter disease, limited to the deep white matter, may be biologically distinct from disease in other regions and may reflect a previously observed trend toward an increased risk of subcortical lacunar infarcts in AAs. We hypothesized that extreme deep WMH volume (DWMV) or periventricular volume (PV) may also have a higher prevalence in AAs. Thus, we studied extreme CHS scores and extreme DWMV and PV in a healthy population enriched for cardiovascular disease risk factors. METHODS: We imaged the brains of 593 subjects who were first-degree relatives of probands with early onset coronary disease prior to 60 years of age. WMHs were manually delineated on 3-tesla cranial MRI by a trained radiology reader; the location and volume of lesions were characterized using automated software. DWMV and PV were measured directly with automated software, and the CHS score was determined by a neuroradiologist. Volumes were characterized as being in the upper 25% versus lower 75% of total lesion volume. Volumes in the upper versus the remaining quartiles were examined for AA versus EA race using multiple logistic regression (generalized estimating equations adjusted for family relatedness) and adjusted for major vascular disease risk factors including age ≥55 years versus <55, sex, current smoking, obesity, hypertension, diabetes and low-density lipoprotein >160 mg/dl. RESULTS: Participants were 58% women and 37% AAs, with a mean age of 51.5 ± 11.0 years (range, 29-74 years). AAs had significantly higher odds of having extreme DWMVs (odds ratio, OR, 1.8; 95% confidence interval, CI, 1.2-2.9; p = 0.0076) independently of age, sex, hypertension and all other risk factors. AAs also had significantly higher odds of having extreme CHS scores ≥3 (OR, 1.3; 95% CI, 1.1-3.6; p = 0.025). Extreme PV was not significantly associated with AA race (OR, 1.3; 95% CI, 0.81-2.1; p = 0.26). CONCLUSIONS: AAs from families with early-onset cardiovascular disease are more likely to have extreme DWMVs (a subclinical form of cerebrovascular disease) and an extreme CHS score, but not extreme PV, independently of age and other cardiovascular disease risk factors. These findings suggest that this AA population is at an increased risk for DWMV and may be at an increased risk for future subcortical stroke. Longitudinal studies are required to see if DWMV is predictive of symptomatic subcortical strokes in this population.
Keywords: Adult; African Americans; Age Factors; Aged; Cerebrovascular Disorders; European Continental Ancestry Group; Female; Humans; Hypertension; Magnetic Resonance Imaging; Male; Middle Aged; Prevalence; Risk Factors; White Matter

Fibroblast growth factor-23 and incident atrial fibrillation: the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS). - Mathew, Jehu S; Sachs, Michael C; Katz, Ronit; Patton, Kristen K; Heckbert, Susan R; Hoofnagle, Andrew N; Alonso, Alvaro; Chonchol, Michel; Deo, Rajat; Ix, Joachim H; Siscovick, David S; Kestenbaum, Bryan; et al. (Circulation, 2014)
BACKGROUND: Fibroblast growth factor-23 (FGF-23) is a hormone that promotes urinary phosphate excretion and regulates vitamin D metabolism. Circulating FGF-23 concentrations increase markedly in chronic kidney disease and are associated with increased risk of clinical cardiovascular events. FGF-23 may promote atrial fibrillation (AF) by inducing left ventricular hypertrophy and diastolic and left atrial dysfunction. METHODS AND RESULTS: We tested the associations of circulating FGF-23 concentration with incident AF among 6398 participants in the Multi-Ethnic Study of Atherosclerosis (MESA) and 1350 participants in the Cardiovascular Health Study (CHS), all free of clinical cardiovascular disease at baseline. Over a median of 7.7 and 8.0 years of follow-up, we observed 291 and 229 incident AF events in MESA and CHS, respectively. In multivariable Cox proportional hazards models, each 2-fold-higher FGF-23 concentration was associated with a 41% higher risk of incident AF in MESA (hazard ratio, 1.41; 95% confidence interval, 1.13-1.76; P=0.003) and a 30% higher risk of incident AF in CHS (hazard ratio, 1.30; 95% confidence interval, 1.05-1.61; P=0.016) after adjustment for potential confounding characteristics, including kidney disease. Serum phosphate concentration was significantly associated with incident AF in MESA (hazard ratio, 1.15 per 0.5 mg/dL; 95% confidence interval, 1.02-1.31; P=0.023) but not CHS. In MESA, an association of low estimated glomerular filtration rate with incident AF was partially attenuated by adjustment for FGF-23. CONCLUSION: Higher circulating FGF-23 concentration is associated with incident AF and may, in part, explain the link between chronic kidney disease and AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Comorbidity; Ethnic Groups; Female; Fibroblast Growth Factor 3; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Hypertrophy, Left Ventricular; Male; Middle Aged; Phosphates; Proportional Hazards Models; Renal Insufficiency, Chronic; Risk Factors; United States; Ventricular Dysfunction, Left; Ventricular Remodeling; Vitamin D

FTO genetic variants, dietary intake and body mass index: insights from 177,330 individuals. - Qi, Qibin; Kilpeläinen, Tuomas O; Downer, Mary K; Tanaka, Toshiko; Smith, Caren E; Sluijs, Ivonne; Sonestedt, Emily; Chu, Audrey Y; Renstrom, Frida; Lin, Xiaochen; Ängquist, Lars H; Huang, Jinyan; et al. (Hum Mol Genet, 2014)
FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the association between the FTO-rs9939609 variant (or a proxy single-nucleotide polymorphism) and total energy and macronutrient intake and (ii) the interaction between the FTO variant and dietary intake on BMI. The minor allele (A-allele) of the FTO-rs9939609 variant was associated with higher BMI in Whites (effect per allele = 0.34 [0.31, 0.37] kg/m(2), P = 1.9 × 10(-105)), and all participants (0.30 [0.30, 0.35] kg/m(2), P = 3.6 × 10(-107)). The BMI-increasing allele of the FTO variant showed a significant association with higher dietary protein intake (effect per allele = 0.08 [0.06, 0.10] %, P = 2.4 × 10(-16)), and relative weak associations with lower total energy intake (-6.4 [-10.1, -2.6] kcal/day, P = 0.001) and lower dietary carbohydrate intake (-0.07 [-0.11, -0.02] %, P = 0.004). The associations with protein (P = 7.5 × 10(-9)) and total energy (P = 0.002) were attenuated but remained significant after adjustment for BMI. We did not find significant interactions between the FTO variant and dietary intake of total energy, protein, carbohydrate or fat on BMI. Our findings suggest a positive association between the BMI-increasing allele of FTO variant and higher dietary protein intake and offer insight into potential link between FTO, dietary protein intake and adiposity.
Keywords: Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Female; Gene Frequency; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins

Gender and telomere length: systematic review and meta-analysis. - Gardner, Michael; Bann, David; Wiley, Laura; Cooper, Rachel; Hardy, Rebecca; Nitsch, Dorothea; Martin-Ruiz, Carmen; Shiels, Paul; Sayer, Avan Aihie; Barbieri, Michelangela; Bekaert, Sofie; Bischoff, Claus; et al. (Exp Gerontol, 2014)
BACKGROUND: It is widely believed that females have longer telomeres than males, although results from studies have been contradictory. METHODS: We carried out a systematic review and meta-analyses to test the hypothesis that in humans, females have longer telomeres than males and that this association becomes stronger with increasing age. Searches were conducted in EMBASE and MEDLINE (by November 2009) and additional datasets were obtained from study investigators. Eligible observational studies measured telomeres for both females and males of any age, had a minimum sample size of 100 and included participants not part of a diseased group. We calculated summary estimates using random-effects meta-analyses. Heterogeneity between studies was investigated using sub-group analysis and meta-regression. RESULTS: Meta-analyses from 36 cohorts (36,230 participants) showed that on average females had longer telomeres than males (standardised difference in telomere length between females and males 0.090, 95% CI 0.015, 0.166; age-adjusted). There was little evidence that these associations varied by age group (p=1.00) or cell type (p=0.29). However, the size of this difference did vary by measurement methods, with only Southern blot but neither real-time PCR nor Flow-FISH showing a significant difference. This difference was not associated with random measurement error. CONCLUSIONS: Telomere length is longer in females than males, although this difference was not universally found in studies that did not use Southern blot methods. Further research on explanations for the methodological differences is required.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Female; Humans; Male; Middle Aged; Sex Factors; Telomere

Gene-age interactions in blood pressure regulation: a large-scale investigation with the CHARGE, Global BPgen, and ICBP Consortia. - Simino, Jeannette; Shi, Gang; Bis, Joshua C; Chasman, Daniel I; Ehret, Georg B; Gu, Xiangjun; Guo, Xiuqing; Hwang, Shih-Jen; Sijbrands, Eric; Smith, Albert V; Verwoert, Germaine C; Bragg-Gresham, Jennifer L; et al. (Am J Hum Genet, 2014)
Although age-dependent effects on blood pressure (BP) have been reported, they have not been systematically investigated in large-scale genome-wide association studies (GWASs). We leveraged the infrastructure of three well-established consortia (CHARGE, GBPgen, and ICBP) and a nonstandard approach (age stratification and metaregression) to conduct a genome-wide search of common variants with age-dependent effects on systolic (SBP), diastolic (DBP), mean arterial (MAP), and pulse (PP) pressure. In a two-staged design using 99,241 individuals of European ancestry, we identified 20 genome-wide significant (p ≤ 5 × 10(-8)) loci by using joint tests of the SNP main effect and SNP-age interaction. Nine of the significant loci demonstrated nominal evidence of age-dependent effects on BP by tests of the interactions alone. Index SNPs in the EHBP1L1 (DBP and MAP), CASZ1 (SBP and MAP), and GOSR2 (PP) loci exhibited the largest age interactions, with opposite directions of effect in the young versus the old. The changes in the genetic effects over time were small but nonnegligible (up to 1.58 mm Hg over 60 years). The EHBP1L1 locus was discovered through gene-age interactions only in whites but had DBP main effects replicated (p = 8.3 × 10(-4)) in 8,682 Asians from Singapore, indicating potential interethnic heterogeneity. A secondary analysis revealed 22 loci with evidence of age-specific effects (e.g., only in 20 to 29-year-olds). Age can be used to select samples with larger genetic effect sizes and more homogenous phenotypes, which may increase statistical power. Age-dependent effects identified through novel statistical approaches can provide insight into the biology and temporal regulation underlying BP associations.
Keywords: Adolescent; Adult; Age Factors; Aged; Blood Pressure; Cohort Studies; Humans; Middle Aged; Young Adult

Gene-centric meta-analyses for central adiposity traits in up to 57 412 individuals of European descent confirm known loci and reveal several novel associations. - Yoneyama, Sachiko; Guo, Yiran; Lanktree, Matthew B; Barnes, Michael R; Elbers, Clara C; Karczewski, Konrad J; Padmanabhan, Sandosh; Bauer, Florianne; Baumert, Jens; Beitelshees, Amber; Berenson, Gerald S; Boer, Jolanda M A; et al. (Hum Mol Genet, 2014)
Waist circumference (WC) and waist-to-hip ratio (WHR) are surrogate measures of central adiposity that are associated with adverse cardiovascular events, type 2 diabetes and cancer independent of body mass index (BMI). WC and WHR are highly heritable with multiple susceptibility loci identified to date. We assessed the association between SNPs and BMI-adjusted WC and WHR and unadjusted WC in up to 57 412 individuals of European descent from 22 cohorts collaborating with the NHLBI's Candidate Gene Association Resource (CARe) project. The study population consisted of women and men aged 20-80 years. Study participants were genotyped using the ITMAT/Broad/CARE array, which includes ∼50 000 cosmopolitan tagged SNPs across ∼2100 cardiovascular-related genes. Each trait was modeled as a function of age, study site and principal components to control for population stratification, and we conducted a fixed-effects meta-analysis. No new loci for WC were observed. For WHR analyses, three novel loci were significantly associated (P < 2.4 × 10(-6)). Previously unreported rs2811337-G near TMCC1 was associated with increased WHR (β ± SE, 0.048 ± 0.008, P = 7.7 × 10(-9)) as was rs7302703-G in HOXC10 (β = 0.044 ± 0.008, P = 2.9 × 10(-7)) and rs936108-C in PEMT (β = 0.035 ± 0.007, P = 1.9 × 10(-6)). Sex-stratified analyses revealed two additional novel signals among females only, rs12076073-A in SHC1 (β = 0.10 ± 0.02, P = 1.9 × 10(-6)) and rs1037575-A in ATBDB4 (β = 0.046 ± 0.01, P = 2.2 × 10(-6)), supporting an already established sexual dimorphism of central adiposity-related genetic variants. Functional analysis using ENCODE and eQTL databases revealed that several of these loci are in regulatory regions or regions with differential expression in adipose tissue.
Keywords: Adiposity; Adult; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Waist Circumference; Waist-Hip Ratio; Young Adult

A genetic association study of D-dimer levels with 50K SNPs from a candidate gene chip in four ethnic groups. - Weng, Lu-Chen; Tang, Weihong; Rich, Stephen S; Smith, Nicholas L; Redline, Susan; O'Donnell, Christopher J; Basu, Saonli; Reiner, Alexander P; Delaney, Joseph A; Tracy, Russell P; Palmer, Cameron D; Young, Taylor; et al. (Thromb Res, 2014)
INTRODUCTION: D-dimer, a fibrin degradation product, is related to risk of cardiovascular disease and venous thromboembolism. Genetic determinants of D-dimer are not well characterized; notably, few data have been reported for African American (AA), Asian, and Hispanic populations. MATERIALS AND METHODS: We conducted a large-scale candidate gene association study to identify variants in genes associated with D-dimer levels in multi-ethnic populations. Four cohorts, comprising 6,848 European Americans (EAs), 2,192 AAs, 670 Asians, and 1,286 Hispanics in the National Heart, Lung, and Blood Institute Candidate Gene Association Resource consortium, were assembled. Approximately 50,000 genotyped single nucleotide polymorphisms (SNPs) in 2,000 cardiovascular disease gene loci were analyzed by linear regression, adjusting for age, sex, study site, and principal components in each cohort and ethnic group. Results across studies were combined within each ethnic group by meta-analysis. RESULTS: Twelve SNPs in coagulation factor V (F5) and 3 SNPs in the fibrinogen alpha chain (FGA) were significantly associated with D-dimer level in EAs with p<2.0×10(-6). The signal for the most associated SNP in F5 (rs6025, factor V Leiden) was replicated in Hispanics (p=0.023), while that for the top functional SNP in FGA (rs6050) was replicated in AAs (p=0.006). No additional SNPs were significantly associated with D-dimer. CONCLUSIONS: Our study replicated previously reported associations of D-dimer with SNPs in F5 and FGA in EAs; we demonstrated replication of the association of D-dimer with FGA rs6050 in AAs and the factor V Leiden variant in Hispanics.
Keywords: Adult; Aged; Cardiovascular Diseases; Ethnic Groups; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic determinants of age-related macular degeneration in diverse populations from the PAGE study. - Restrepo, Nicole A; Spencer, Kylee L; Goodloe, Robert; Garrett, Tiana A; Heiss, Gerardo; Bůzková, Petra; Jorgensen, Neal; Jensen, Richard A; Matise, Tara C; Hindorff, Lucia A; Klein, Barbara E K; Klein, Ronald; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Substantial progress has been made in identifying susceptibility variants for AMD in European populations; however, few studies have been conducted to understand the role these variants play in AMD risk in diverse populations. The present study aims to examine AMD risk across diverse populations in known and suspected AMD complement factor and lipid-related loci. METHODS: Targeted genotyping was performed across study sites for AMD and lipid trait-associated single nucleotide polymorphism (SNPs). Genetic association tests were performed at individual sites and then meta-analyzed using logistic regression assuming an additive genetic model stratified by self-described race/ethnicity. Participants included cases with early or late AMD and controls with no signs of AMD as determined by fundus photography. Populations included in this study were European Americans, African Americans, Mexican Americans, and Singaporeans from the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: Index variants of AMD, rs1061170 (CFH) and rs10490924 (ARMS2), were associated with AMD at P=3.05×10(-8) and P=6.36×10(-6), respectively, in European Americans. In general, none of the major AMD index variants generalized to our non-European populations with the exception of rs10490924 in Mexican Americans at an uncorrected P value<0.05. Four lipid-associated SNPS (LPL rs328, TRIB1 rs6987702, CETP rs1800775, and KCTD10/MVK rs2338104) were associated with AMD in African Americans and Mexican Americans (P<0.05), but these associations did not survive strict corrections for multiple testing. CONCLUSIONS: While most associations did not generalize in the non-European populations, variants within lipid-related genes were found to be associated with AMD. This study highlights the need for larger well-powered studies in non-European populations.
Keywords: Adult; Aged; Aged, 80 and over; Complement Factor H; DNA; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Macular Degeneration; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Proteins; Risk Factors; United States

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine. - Lüneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M; Xanthakis, Vanessa; Glazer, Nicole L; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers. METHODS AND RESULTS: This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. CONCLUSIONS: These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
Keywords: Adult; Aged; Amidohydrolases; Arginine; Binding Sites; Cohort Studies; Female; Genetic Loci; Genome-Wide Association Study; Genotype; HEK293 Cells; Humans; Male; Mediator Complex; Middle Aged; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Risk Factors; Stroke; Substrate Specificity; Transaminases

Genome-wide association study of plasma N6 polyunsaturated fatty acids within the cohorts for heart and aging research in genomic epidemiology consortium. - Guan, Weihua; Steffen, Brian T; Lemaitre, Rozenn N; Wu, Jason H Y; Tanaka, Toshiko; Manichaikul, Ani; Foy, Millennia; Rich, Stephen S; Wang, Lu; Nettleton, Jennifer A; Tang, Weihong; Gu, Xiangjun; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Omega6 (n6) polyunsaturated fatty acids (PUFAs) and their metabolites are involved in cell signaling, inflammation, clot formation, and other crucial biological processes. Genetic components, such as variants of fatty acid desaturase (FADS) genes, determine the composition of n6 PUFAs. METHODS AND RESULTS: To elucidate undiscovered biological pathways that may influence n6 PUFA composition, we conducted genome-wide association studies and meta-analyses of associations of common genetic variants with 6 plasma n6 PUFAs in 8631 white adults (55% women) across 5 prospective studies. Plasma phospholipid or total plasma fatty acids were analyzed by similar gas chromatography techniques. The n6 fatty acids linoleic acid (LA), γ-linolenic acid (GLA), dihomo-GLA, arachidonic acid, and adrenic acid were expressed as percentage of total fatty acids. We performed linear regression with robust SEs to test for single-nucleotide polymorphism-fatty acid associations, with pooling using inverse-variance-weighted meta-analysis. Novel regions were identified on chromosome 10 associated with LA (rs10740118; P=8.1×10(-9); near NRBF2), on chromosome 16 with LA, GLA, dihomo-GLA, and arachidonic acid (rs16966952; P=1.2×10(-15), 5.0×10(-11), 7.6×10(-65), and 2.4×10(-10), respectively; NTAN1), and on chromosome 6 with adrenic acid after adjustment for arachidonic acid (rs3134950; P=2.1×10(-10); AGPAT1). We confirmed previous findings of the FADS cluster on chromosome 11 with LA and arachidonic acid, and further observed novel genome-wide significant association of this cluster with GLA, dihomo-GLA, and adrenic acid (P=2.3×10(-72), 2.6×10(-151), and 6.3×10(-140), respectively). CONCLUSIONS: Our findings suggest that along with the FADS gene cluster, additional genes may influence n6 PUFA composition.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 6; Fatty Acid Desaturases; Fatty Acids, Omega-6; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Height and risk of sudden cardiac death: the Atherosclerosis Risk in Communities and Cardiovascular Health studies. - Rosenberg, Michael A; Lopez, Faye L; Bůzková, Petra; Adabag, Selcuk; Chen, Lin Y; Sotoodehnia, Nona; Kronmal, Richard A; Siscovick, David S; Alonso, Alvaro; Buxton, Alfred; Folsom, Aaron R; Mukamal, Kenneth J (Ann Epidemiol, 2014)
PURPOSE: Sudden cardiac death (SCD) is an important cause of mortality in the adult population. Height has been associated with cardiac hypertrophy and an increased risk of arrhythmias but also with decreased risk of coronary heart disease, suggesting a complex association with SCD. METHODS: We examined the association of adult height with the risk of physician-adjudicated SCD in two large population-based cohorts: the Cardiovascular Health Study and the Atherosclerosis Risk in Communities study. RESULTS: Over an average follow-up time of 11.7 years in Cardiovascular Health Study, there were 199 (3.6%) cases of SCD among 5556 participants. In Atherosclerosis Risk in Communities study, over 12.6 years, there were 227 (1.5%) cases of SCD among 15,633 participants. In both cohorts, there was a trend toward decreased SCD with taller height. In fixed effects meta-analysis, the pooled hazard ratio per 10 cm of height was 0.84; 95% confidence interval, 0.73-0.98; P = .03. The association of increased height with lower risk of SCD was slightly attenuated after inclusion of risk factors associated with height, such as hypertension and left ventricular hypertrophy. The association appeared stronger among men than women in both cohorts. CONCLUSIONS: In two population-based prospective cohorts of different ages, greater height was associated with lower risk of SCD.
Keywords: Adult; Aged; Atherosclerosis; Body Height; Coronary Disease; Death, Sudden, Cardiac; Female; Humans; Hypertension; Incidence; Male; Middle Aged; Population Surveillance; Prospective Studies; Risk Factors

Incidence of and risk factors for sick sinus syndrome in the general population. - Jensen, Paul N; Gronroos, Noelle N; Chen, Lin Y; Folsom, Aaron R; deFilippi, Chris; Heckbert, Susan R; Alonso, Alvaro (J Am Coll Cardiol, 2014)
BACKGROUND: Little is known about the incidence of and risk factors for sick sinus syndrome (SSS), a common indication for pacemaker implantation. OBJECTIVES: This study sought to describe the epidemiology of SSS. METHODS: This analysis included 20,572 participants (mean baseline age 59 years, 43% male) in the ARIC (Atherosclerosis Risk In Communities) study and the CHS (Cardiovascular Health Study), who at baseline were free of prevalent atrial fibrillation and pacemaker therapy, had a heart rate of ≥ 50 beats/min unless using beta blockers, and were identified as of white or black race. Incident SSS cases were identified by hospital discharge International Classification of Disease-revision 9-Clinical Modification code 427.81 and validated by medical record review. RESULTS: During an average 17 years of follow-up, 291 incident SSS cases were identified (unadjusted rate 0.8 per 1,000 person-years). Incidence increased with age (hazard ratio [HR]: 1.73; 95% confidence interval [CI]: 1.47 to 2.05 per 5-year increment), and blacks had a 41% lower risk of SSS than whites (HR: 0.59; 95% CI: 0.37 to 0.98). Incident SSS was associated with greater baseline body mass index, height, N-terminal pro-B-type natriuretic peptide, and cystatin C, with longer QRS interval, with lower heart rate, and with prevalent hypertension, right bundle branch block, and cardiovascular disease. We project that the annual number of new SSS cases in the United States will increase from 78,000 in 2012 to 172,000 in 2060. CONCLUSIONS: Blacks have a lower risk of SSS than whites, and several cardiovascular risk factors were associated with incident SSS. With the aging of the population, the number of Americans with SSS will increase dramatically over the next 50 years.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Population Surveillance; Prospective Studies; Risk Factors; Sick Sinus Syndrome

Integrating genetic, transcriptional, and functional analyses to identify 5 novel genes for atrial fibrillation. - Sinner, Moritz F; Tucker, Nathan R; Lunetta, Kathryn L; Ozaki, Kouichi; Smith, J Gustav; Trompet, Stella; Bis, Joshua C; Lin, Honghuang; Chung, Mina K; Nielsen, Jonas B; Lubitz, Steven A; Krijthe, Bouwe P; et al. (Circulation, 2014)
BACKGROUND: Atrial fibrillation (AF) affects >30 million individuals worldwide and is associated with an increased risk of stroke, heart failure, and death. AF is highly heritable, yet the genetic basis for the arrhythmia remains incompletely understood. METHODS AND RESULTS: To identify new AF-related genes, we used a multifaceted approach, combining large-scale genotyping in 2 ethnically distinct populations, cis-eQTL (expression quantitative trait loci) mapping, and functional validation. Four novel loci were identified in individuals of European descent near the genes NEURL (rs12415501; relative risk [RR]=1.18; 95% confidence interval [CI], 1.13-1.23; P=6.5×10(-16)), GJA1 (rs13216675; RR=1.10; 95% CI, 1.06-1.14; P=2.2×10(-8)), TBX5 (rs10507248; RR=1.12; 95% CI, 1.08-1.16; P=5.7×10(-11)), and CAND2 (rs4642101; RR=1.10; 95% CI, 1.06-1.14; P=9.8×10(-9)). In Japanese, novel loci were identified near NEURL (rs6584555; RR=1.32; 95% CI, 1.26-1.39; P=2.0×10(-25)) and CUX2 (rs6490029; RR=1.12; 95% CI, 1.08-1.16; P=3.9×10(-9)). The top single-nucleotide polymorphisms or their proxies were identified as cis-eQTLs for the genes CAND2 (P=2.6×10(-19)), GJA1 (P=2.66×10(-6)), and TBX5 (P=1.36×10(-5)). Knockdown of the zebrafish orthologs of NEURL and CAND2 resulted in prolongation of the atrial action potential duration (17% and 45%, respectively). CONCLUSIONS: We have identified 5 novel loci for AF. Our results expand the diversity of genetic pathways implicated in AF and provide novel molecular targets for future biological and pharmacological investigation.
Keywords: Aged; Animals; Atrial Fibrillation; Chromosome Mapping; Connexin 43; Europe; Female; Gene Knockdown Techniques; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Muscle Proteins; Nuclear Proteins; Quantitative Trait Loci; Repressor Proteins; T-Box Domain Proteins; Transcription Factors; Ubiquitin-Protein Ligases; Zebrafish; Zebrafish Proteins

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans. - Ellis, Jaclyn; Lange, Ethan M; Li, Jin; Dupuis, Josée; Baumert, Jens; Walston, Jeremy D; Keating, Brendan J; Durda, Peter; Fox, Ervin R; Palmer, Cameron D; Meng, Yan A; Young, Taylor; et al. (Hum Genet, 2014)
C-reactive protein (CRP) is a heritable biomarker of systemic inflammation and a predictor of cardiovascular disease (CVD). Large-scale genetic association studies for CRP have largely focused on individuals of European descent. We sought to uncover novel genetic variants for CRP in a multiethnic sample using the ITMAT Broad-CARe (IBC) array, a custom 50,000 SNP gene-centric array having dense coverage of over 2,000 candidate CVD genes. We performed analyses on 7,570 African Americans (AA) from the Candidate gene Association Resource (CARe) study and race-combined meta-analyses that included 29,939 additional individuals of European descent from CARe, the Women's Health Initiative (WHI) and KORA studies. We observed array-wide significance (p < 2.2 × 10(-6)) for four loci in AA, three of which have been reported previously in individuals of European descent (IL6R, p = 2.0 × 10(-6); CRP, p = 4.2 × 10(-71); APOE, p = 1.6 × 10(-6)). The fourth significant locus, CD36 (p = 1.6 × 10(-6)), was observed at a functional variant (rs3211938) that is extremely rare in individuals of European descent. We replicated the CD36 finding (p = 1.8 × 10(-5)) in an independent sample of 8,041 AA women from WHI; a meta-analysis combining the CARe and WHI AA results at rs3211938 reached genome-wide significance (p = 1.5 × 10(-10)). In the race-combined meta-analyses, 13 loci reached significance, including ten (CRP, TOMM40/APOE/APOC1, HNF1A, LEPR, GCKR, IL6R, IL1RN, NLRP3, HNF4A and BAZ1B/BCL7B) previously associated with CRP, and one (ARNTL) previously reported to be nominally associated with CRP. Two novel loci were also detected (RPS6KB1, p = 2.0 × 10(-6); CD36, p = 1.4 × 10(-6)). These results highlight both shared and unique genetic risk factors for CRP in AA compared to populations of European descent.
Keywords: Adult; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; CD36 Antigens; Female; Genetic Loci; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Humans; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Leukocyte telomere length and age at menopause. - Gray, Kristen E; Schiff, Melissa A; Fitzpatrick, Annette L; Kimura, Masayuki; Aviv, Abraham; Starr, Jacqueline R (Epidemiology, 2014)
BACKGROUND: Telomere length is a marker of cellular aging that varies with the individual, is inherited, and is highly correlated across somatic cell types within persons. Interindividual variability of telomere length may partly explain differences in reproductive aging rates. We examined whether leukocyte telomere length was associated with menopausal age. METHODS: We evaluated the relationship between leukocyte telomere length and age at natural menopause in 486 white women ≥65 years of age. We fit linear regression models adjusted for age, income, education, body mass index, physical activity, smoking, and alcohol intake. We repeated the analysis in women with surgical menopause. We also performed sensitivity analyses excluding women (1) with unilateral oophorectomy, (2) who were nulliparous, or (3) reporting menopausal age <40 years, among other exclusions. RESULTS: For every 1-kb increase in leukocyte telomere length, average age at natural menopause increased by 10.2 months (95% confidence interval = 1.3 to 19.0). There was no association among 179 women reporting surgical menopause. In all but one sensitivity analysis, the association between leukocyte telomere length and age at menopause became stronger. However, when excluding women with menopausal age <40 years, the association decreased to 7.5 months (-0.4 to 15.5). CONCLUSIONS: Women with the longest leukocyte telomere length underwent menopause 3 years later than those with the shortest leukocyte telomere length. If an artifact, an association would likely also have been observed in women with surgical menopause. If these results are replicated, leukocyte telomere length may prove to be a useful predictor of age at menopause.
Keywords: Adult; Age of Onset; Aged; Aging; Alcohol Drinking; Body Mass Index; Educational Status; European Continental Ancestry Group; Female; Humans; Leukocytes; Linear Models; Menopause; Middle Aged; Motor Activity; Smoking; Telomere

A low-frequency variant in MAPK14 provides mechanistic evidence of a link with myeloperoxidase: a prognostic cardiovascular risk marker. - Waterworth, Dawn M; Li, Li; Scott, Robert; Warren, Liling; Gillson, Christopher; Aponte, Jennifer; Sarov-Blat, Lea; Sprecher, Dennis; Dupuis, Josée; Reiner, Alex; Psaty, Bruce M; Tracy, Russell P; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Genetics can be used to predict drug effects and generate hypotheses around alternative indications. To support Losmapimod, a p38 mitogen-activated protein kinase inhibitor in development for acute coronary syndrome, we characterized gene variation in MAPK11/14 genes by exome sequencing and follow-up genotyping or imputation in participants well-phenotyped for cardiovascular and metabolic traits. METHODS AND RESULTS: Investigation of genetic variation in MAPK11 and MAPK14 genes using additive genetic models in linear or logistic regression with cardiovascular, metabolic, and biomarker phenotypes highlighted an association of RS2859144 in MAPK14 with myeloperoxidase in a dyslipidemic population (Genetic Epidemiology of Metabolic Syndrome Study), P=2.3×10(-6)). This variant (or proxy) was consistently associated with myeloperoxidase in the Framingham Heart Study and Cardiovascular Health Study studies (replication meta-P=0.003), leading to a meta-P value of 9.96×10(-7) in the 3 dyslipidemic groups. The variant or its proxy was then profiled in additional population-based cohorts (up to a total of 58 930 subjects) including Cohorte Lausannoise, Ely, Fenland, European Prospective Investigation of Cancer, London Life Sciences Prospective Population Study, and the Genetics of Obesity Associations study obesity case-control for up to 40 cardiovascular and metabolic traits. Overall analysis identified the same single nucleotide polymorphisms to be nominally associated consistently with glomerular filtration rate (P=0.002) and risk of obesity (body mass index ≥30 kg/m(2), P=0.004). CONCLUSIONS: As myeloperoxidase is a prognostic marker of coronary events, the MAPK14 variant may provide a mechanistic link between p38 map kinase and these events, providing information consistent with current indication of Losmapimod for acute coronary syndrome. If replicated, the association with glomerular filtration rate, along with previous biological findings, also provides support for kidney diseases as alternative indications.
Keywords: Adult; Aged; Cardiovascular Diseases; Dyslipidemias; Exome; Female; Genotype; Humans; Linear Models; Logistic Models; Male; Metabolic Syndrome X; Middle Aged; Mitogen-Activated Protein Kinase 11; Mitogen-Activated Protein Kinase 14; Obesity; Peroxidase; Polymorphism, Single Nucleotide; Prognosis; Risk Factors; Sequence Analysis, DNA

Multiancestral analysis of inflammation-related genetic variants and C-reactive protein in the population architecture using genomics and epidemiology study. - Kocarnik, Jonathan M; Pendergrass, Sarah A; Carty, Cara L; Pankow, James S; Schumacher, Fredrick R; Cheng, Iona; Durda, Peter; Ambite, Jose Luis; Deelman, Ewa; Cook, Nancy R; Liu, Simin; Wactawski-Wende, Jean; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: C-reactive protein (CRP) is a biomarker of inflammation. Genome-wide association studies (GWAS) have identified single-nucleotide polymorphisms (SNPs) associated with CRP concentrations and inflammation-related traits such as cardiovascular disease, type 2 diabetes mellitus, and obesity. We aimed to replicate previous CRP-SNP associations, assess whether these associations generalize to additional race/ethnicity groups, and evaluate inflammation-related SNPs for a potentially pleiotropic association with CRP. METHODS AND RESULTS: We selected and analyzed 16 CRP-associated and 250 inflammation-related GWAS SNPs among 40 473 African American, American Indian, Asian/Pacific Islander, European American, and Hispanic participants from 7 studies collaborating in the Population Architecture using Genomics and Epidemiology (PAGE) study. Fixed-effect meta-analyses combined study-specific race/ethnicity-stratified linear regression estimates to evaluate the association between each SNP and high-sensitivity CRP. Overall, 18 SNPs in 8 loci were significantly associated with CRP (Bonferroni-corrected P<3.1×10(-3) for replication, P<2.0×10(-4) for pleiotropy): Seven of these were specific to European Americans, while 9 additionally generalized to African Americans (1), Hispanics (5), or both (3); 1 SNP was seen only in African Americans and Hispanics. Two SNPs in the CELSR2/PSRC1/SORT1 locus showed a potentially novel association with CRP: rs599839 (P=2.0×10(-6)) and rs646776 (P=3.1×10(-5)). CONCLUSIONS: We replicated 16 SNP-CRP associations, 10 of which generalized to African Americans and/or Hispanics. We also identified potentially novel pleiotropic associations with CRP for two SNPs previously associated with coronary artery disease and/or low-density lipoprotein-cholesterol. These findings demonstrate the benefit of evaluating genotype-phenotype associations in multiple race/ethnicity groups and looking for pleiotropic relationships among SNPs previously associated with related phenotypes.
Keywords: Adult; African Continental Ancestry Group; Aged; Asian Continental Ancestry Group; C-Reactive Protein; Female; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Inflammation; Male; Middle Aged; Polymorphism, Single Nucleotide; United States; Young Adult

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

Novel genetic markers associate with atrial fibrillation risk in Europeans and Japanese. - Lubitz, Steven A; Lunetta, Kathryn L; Lin, Honghuang; Arking, Dan E; Trompet, Stella; Li, Guo; Krijthe, Bouwe P; Chasman, Daniel I; Barnard, John; Kleber, Marcus E; Dörr, Marcus; Ozaki, Kouichi; et al. (J Am Coll Cardiol, 2014)
OBJECTIVES: This study sought to identify nonredundant atrial fibrillation (AF) genetic susceptibility signals and examine their cumulative relations with AF risk. BACKGROUND: AF-associated loci span broad genomic regions that may contain multiple susceptibility signals. Whether multiple signals exist at AF loci has not been systematically explored. METHODS: We performed association testing conditioned on the most significant, independently associated genetic markers at 9 established AF loci using 2 complementary techniques in 64,683 individuals of European ancestry (3,869 incident and 3,302 prevalent AF cases). Genetic risk scores were created and tested for association with AF in Europeans and an independent sample of 11,309 individuals of Japanese ancestry (7,916 prevalent AF cases). RESULTS: We observed at least 4 distinct AF susceptibility signals on chromosome 4q25 upstream of PITX2, but not at the remaining 8 AF loci. A multilocus score comprised 12 genetic markers demonstrated an estimated 5-fold gradient in AF risk. We observed a similar spectrum of risk associated with these markers in Japanese. Regions containing AF signals on chromosome 4q25 displayed a greater degree of evolutionary conservation than the remainder of the locus, suggesting that they may tag regulatory elements. CONCLUSIONS: The chromosome 4q25 AF locus is architecturally complex and harbors at least 4 AF susceptibility signals in individuals of European ancestry. Similar polygenic AF susceptibility exists between Europeans and Japanese. Future work is necessary to identify causal variants, determine mechanisms by which associated loci predispose to AF, and explore whether AF susceptibility signals classify individuals at risk for AF and related morbidity.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; Europe; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factors

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Prediction of asymptomatic carotid artery stenosis in the general population: identification of high-risk groups. - de Weerd, Marjolein; Greving, Jacoba P; Hedblad, Bo; Lorenz, Matthias W; Mathiesen, Ellisiv B; O'Leary, Daniel H; Rosvall, Maria; Sitzer, Matthias; de Borst, Gert Jan; Buskens, Erik; Bots, Michiel L (Stroke, 2014)
BACKGROUND AND PURPOSE: Because of a low prevalence of severe carotid stenosis in the general population, screening for presence of asymptomatic carotid artery stenosis (ACAS) is not warranted. Possibly, for certain subgroups, screening is worthwhile. The present study aims to develop prediction rules for the presence of ACAS (>50% and >70%). METHODS: Individual participant data from 4 population-based cohort studies (Malmö Diet and Cancer Study, Tromsø Study, Carotid Atherosclerosis Progression Study, and Cardiovascular Health Study; totaling 23 706 participants) were pooled. Multivariable logistic regression was performed to determine which variables predict presence of ACAS (>50% and >70%). Calibration and discrimination of the models were assessed, and bootstrapping was used to correct for overfitting. RESULTS: Age, sex, history of vascular disease, systolic and diastolic blood pressure, total cholesterol/high-density lipoprotein ratio, diabetes mellitus, and current smoking were predictors of stenosis (>50% and >70%). The calibration of the model was good confirmed by a nonsignificant Hosmer and Lemeshow test for moderate (P=0.59) and severe stenosis (P=0.07). The models discriminated well between participants with and without stenosis, with an area under the receiver operating characteristic curve corrected for over optimism of 0.82 (95% confidence interval, 0.80-0.84) for moderate stenosis and of 0.87 (95% confidence interval, 0.85-0.90) for severe stenosis. The regression coefficients of the predictors were converted into a score chart to facilitate practical application. CONCLUSIONS: A clinical prediction rule was developed that allows identification of subgroups with high prevalence of moderate (>50%) and severe (>70%) ACAS. When confirmed in comparable cohorts, application of the prediction rule may lead to a reduction in the number needed to screen for ACAS.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Blood Pressure; Carotid Stenosis; Female; Humans; Life Style; Male; Mass Screening; Middle Aged; Prevalence; Registries; Risk; Smoking

Racial and regional differences in venous thromboembolism in the United States in 3 cohorts. - Zakai, Neil A; McClure, Leslie A; Judd, Suzanne E; Safford, Monika M; Folsom, Aaron R; Lutsey, Pamela L; Cushman, Mary (Circulation, 2014)
BACKGROUND: Blacks are thought to have a higher risk of venous thromboembolism (VTE) than whites. However, prior studies are limited to administrative databases that lack specific information on VTE risk factors or have limited geographic scope. METHODS AND RESULTS: We ascertained VTE from 3 prospective studies: the Atherosclerosis Risk in Communities Study (ARIC), the Cardiovascular Health Study (CHS), and the Reasons for Geographic and Racial Differences in Stroke study (REGARDS). We tested the association of race with VTE using Cox proportional hazard models adjusted for VTE risk factors. Over 438 090 person-years, 916 incident VTE events (302 in blacks) occurred in 51 149 individuals (17 318 blacks) who were followed up. In risk factor-adjusted models, blacks had a higher rate of VTE than whites in the CHS (hazard ratio, 1.81; 95% confidence interval, 1.20-2.73) but not ARIC (hazard ratio, 1.21; 95% confidence interval, 0.96-1.54). In REGARDS, there was a significant region-by-race interaction (P=0.01): Blacks in the Southeast had a significantly higher rate of VTE than blacks in the rest of the United States (hazard ratio, 1.63; 95% confidence interval, 1.08-2.48) that was not seen in whites (hazard ratio, 0.83; 95% confidence interval, 0.61-1.14). CONCLUSIONS: The association of race with VTE differed in each cohort, which may reflect the different time periods of the studies or different regional rates of VTE. Further studies of environmental and genetic risk factors for VTE are needed to determine which underlie racial and perhaps regional differences in VTE.
Keywords: African Continental Ancestry Group; Aged; Cohort Studies; European Continental Ancestry Group; Female; Humans; Longitudinal Studies; Male; Middle Aged; Prevalence; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Factors; United States; Venous Thromboembolism

Relative risks of chronic kidney disease for mortality and end-stage renal disease across races are similar. - Wen, Chi Pang; Matsushita, Kunihiro; Coresh, Josef; Iseki, Kunitoshi; Islam, Muhammad; Katz, Ronit; McClellan, William; Peralta, Carmen A; Wang, Haiyan; de Zeeuw, Dick; Astor, Brad C; Gansevoort, Ron T; et al. (Kidney Int, 2014)
Some suggest race-specific cutpoints for kidney measures to define and stage chronic kidney disease (CKD), but evidence for race-specific clinical impact is limited. To address this issue, we compared hazard ratios of estimated glomerular filtration rates (eGFR) and albuminuria across races using meta-regression in 1.1 million adults (75% Asians, 21% Whites, and 4% Blacks) from 45 cohorts. Results came mainly from 25 general population cohorts comprising 0.9 million individuals. The associations of lower eGFR and higher albuminuria with mortality and end-stage renal disease (ESRD) were largely similar across races. For example, in Asians, Whites, and Blacks, the adjusted hazard ratios (95% confidence interval) for eGFR 45-59 versus 90-104 ml/min per 1.73 m(2) were 1.3 (1.2-1.3), 1.1 (1.0-1.2), and 1.3 (1.1-1.7) for all-cause mortality, 1.6 (1.5-1.7), 1.4 (1.2-1.7), and 1.4 (0.7-2.9) for cardiovascular mortality, and 27.6 (11.1-68.7), 11.2 (6.0-20.9), and 4.1 (2.2-7.5) for ESRD, respectively. The corresponding hazard ratios for urine albumin-to-creatinine ratio 30-299 mg/g or dipstick 1+ versus an albumin-to-creatinine ratio under 10 or dipstick negative were 1.6 (1.4-1.8), 1.7 (1.5-1.9), and 1.8 (1.7-2.1) for all-cause mortality, 1.7 (1.4-2.0), 1.8 (1.5-2.1), and 2.8 (2.2-3.6) for cardiovascular mortality, and 7.4 (2.0-27.6), 4.0 (2.8-5.9), and 5.6 (3.4-9.2) for ESRD, respectively. Thus, the relative mortality or ESRD risks of lower eGFR and higher albuminuria were largely similar among three major races, supporting similar clinical approach to CKD definition and staging, across races.
Keywords: Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Albuminuria; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Creatinine; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Renal Insufficiency, Chronic; Risk Factors

A self-report risk index to predict occurrence of dementia in three independent cohorts of older adults: the ANU-ADRI. - Anstey, Kaarin J; Cherbuin, Nicolas; Herath, Pushpani M; Qiu, Chengxuan; Kuller, Lewis H; Lopez, Oscar L; Wilson, Robert S; Fratiglioni, Laura (PLoS One, 2014)
BACKGROUND AND AIMS: The Australian National University AD Risk Index (ANU-ADRI, http://anuadri.anu.edu.au) is a self-report risk index developed using an evidence-based medicine approach to measure risk of Alzheimer's disease (AD). We aimed to evaluate the extent to which the ANU-ADRI can predict the risk of AD in older adults and to compare the ANU-ADRI to the dementia risk index developed from the Cardiovascular Risk Factors, Aging and Dementia (CAIDE) study for middle-aged cohorts. METHODS: This study included three validation cohorts, i.e., the Rush Memory and Aging Study (MAP) (n = 903, age ≥53 years), the Kungsholmen Project (KP) (n = 905, age ≥75 years), and the Cardiovascular Health Cognition Study (CVHS) (n = 2496, age ≥65 years) that were each followed for dementia. Baseline data were collected on exposure to the 15 risk factors included in the ANU-ADRI of which MAP had 10, KP had 8 and CVHS had 9. Risk scores and C-statistics were computed for individual participants for the ANU-ADRI and the CAIDE index. RESULTS: For the ANU-ADRI using available data, the MAP study c-statistic was 0·637 (95% CI 0·596-0·678), for the KP study it was 0·740 (0·712-0·768) and for the CVHS it was 0·733 (0·691-0·776) for predicting AD. When a common set of risk and protective factors were used c-statistics were 0.689 (95% CI 0.650-0.727), 0.666 (0.628-0.704) and 0.734 (0.707-0.761) for MAP, KP and CVHS respectively. Results for CAIDE ranged from c-statistics of 0.488 (0.427-0.554) to 0.595 (0.565-0.625). CONCLUSION: A composite risk score derived from the ANU-ADRI weights including 8-10 risk or protective factors is a valid, self-report tool to identify those at risk of AD and dementia. The accuracy can be further improved in studies including more risk factors and younger cohorts with long-term follow-up.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Female; Humans; Incidence; Male; Middle Aged; Risk; ROC Curve; Self Report

Separate prediction of intracerebral hemorrhage and ischemic stroke. - Ferket, Bart S; van Kempen, Bob J H; Wieberdink, Renske G; Steyerberg, Ewout W; Koudstaal, Peter J; Hofman, Albert; Shahar, Eyal; Gottesman, Rebecca F; Rosamond, Wayne; Kizer, Jorge R; Kronmal, Richard A; Psaty, Bruce M; et al. (Neurology, 2014)
OBJECTIVES: To develop and validate 10-year cumulative incidence functions of intracerebral hemorrhage (ICH) and ischemic stroke (IS). METHODS: We used data on 27,493 participants from 3 population-based cohort studies: the Atherosclerosis Risk in Communities Study, median age 54 years, 45% male, median follow-up 20.7 years; the Rotterdam Study, median age 68 years, 38% male, median follow-up 14.3 years; and the Cardiovascular Health Study, median age 71 years, 41% male, median follow-up 12.8 years. Among these participants, 325 ICH events, 2,559 IS events, and 9,909 nonstroke deaths occurred. We developed 10-year cumulative incidence functions for ICH and IS using stratified Cox regression and competing risks analysis. Basic models including only established nonlaboratory risk factors were extended with diastolic blood pressure, total cholesterol/high-density lipoprotein cholesterol ratio, body mass index, waist-to-hip ratio, and glomerular filtration rate. The cumulative incidence functions' performances were cross-validated in each cohort separately by Harrell C-statistic and calibration plots. RESULTS: High total cholesterol/high-density lipoprotein cholesterol ratio decreased the ICH rates but increased IS rates (p for difference across stroke types <0.001). For both the ICH and IS models, C statistics increased more by model extension in the Atherosclerosis Risk in Communities and Cardiovascular Health Study cohorts. Improvements in C statistics were reproduced by cross-validation. Models were well calibrated in all cohorts. Correlations between 10-year ICH and IS risks were moderate in each cohort. CONCLUSIONS: We developed and cross-validated cumulative incidence functions for separate prediction of 10-year ICH and IS risk. These functions can be useful to further specify an individual's stroke risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Body Mass Index; Brain Ischemia; Cholesterol; Female; Humans; Incidence; Intracranial Hemorrhages; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Risk Assessment; Risk Factors; Stroke

Sequence variation in TMEM18 in association with body mass index: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Liu, Ching-Ti; Young, Kristin L; Brody, Jennifer A; Olden, Matthias; Wojczynski, Mary K; Heard-Costa, Nancy; Li, Guo; Morrison, Alanna C; Muzny, Donna; Gibbs, Richard A; Reid, Jeffrey G; Shao, Yaming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies for body mass index (BMI) previously identified a locus near TMEM18. We conducted targeted sequencing of this region to investigate the role of common, low-frequency, and rare variants influencing BMI. METHODS AND RESULTS: We sequenced TMEM18 and regions downstream of TMEM18 on chromosome 2 in 3976 individuals of European ancestry from 3 community-based cohorts (Atherosclerosis Risk in Communities, Cardiovascular Health Study, and Framingham Heart Study), including 200 adults selected for high BMI. We examined the association between BMI and variants identified in the region from nucleotide position 586 432 to 677 539 (hg18). Rare variants (minor allele frequency, <1%) were analyzed using a burden test and the sequence kernel association test. Results from the 3 cohort studies were meta-analyzed. We estimate that mean BMI is 0.43 kg/m(2) higher for each copy of the G allele of single-nucleotide polymorphism rs7596758 (minor allele frequency, 29%; P=3.46×10(-4)) using a Bonferroni threshold of P<4.6×10(-4). Analyses conditional on previous genome-wide association study single-nucleotide polymorphisms associated with BMI in the region led to attenuation of this signal and uncovered another independent (r(2)<0.2), statistically significant association, rs186019316 (P=2.11×10(-4)). Both rs186019316 and rs7596758 or proxies are located in transcription factor binding regions. No significant association with rare variants was found in either the exons of TMEM18 or the 3' genome-wide association study region. CONCLUSIONS: Targeted sequencing around TMEM18 identified 2 novel BMI variants with possible regulatory function.
Keywords: Adult; Aged; Aging; Body Mass Index; Cohort Studies; Female; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Young Adult

Sequencing of 2 subclinical atherosclerosis candidate regions in 3669 individuals: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Bis, Joshua C; White, Charles C; Franceschini, Nora; Brody, Jennifer; Zhang, Xiaoling; Muzny, Donna; Santibanez, Jireh; Gibbs, Richard; Liu, Xiaoming; Lin, Honghuang; Boerwinkle, Eric; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Atherosclerosis, the precursor to coronary heart disease and stroke, is characterized by an accumulation of fatty cells in the arterial intimal-medial layers. Common carotid intima media thickness (cIMT) and plaque are subclinical atherosclerosis measures that predict cardiovascular disease events. Previously, genome-wide association studies demonstrated evidence for association with cIMT (SLC17A4) and plaque (PIK3CG). METHODS AND RESULTS: We sequenced 120 kb around SLC17A4 (6p22.2) and 251 kb around PIK3CG (7q22.3) among 3669 European ancestry participants from the Atherosclerosis Risk in Communities (ARIC) study, Cardiovascular Health Study (CHS), and Framingham Heart Study (FHS) in Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Primary analyses focused on 438 common variants (minor allele frequency ≥1%), which were independently meta-analyzed. A 3' untranslated region CCDC71L variant (rs2286149), upstream from PIK3CG, was the most significant finding in cIMT (P=0.00033) and plaque (P=0.0004) analyses. A SLC17A4 intronic variant was also associated with cIMT (P=0.008). Both were in low linkage disequilibrium with the genome-wide association study single nucleotide polymorphisms. Gene-based tests including T1 count and sequence kernel association test for rare variants (minor allele frequency <1%) did not yield statistically significant associations. However, we observed nominal associations for rare variants in CCDC71L and SLC17A3 with cIMT and of the entire 7q22 region with plaque (P=0.05). CONCLUSIONS: Common and rare variants in PIK3CG and SLC17A4 regions demonstrated modest association with subclinical atherosclerosis traits. Although not conclusive, these findings may help to understand the genetic architecture of regions previously implicated by genome-wide association studies and identify variants within these regions for further investigation in larger samples.
Keywords: Aged; Aged, 80 and over; Aging; Atherosclerosis; Class Ib Phosphatidylinositol 3-Kinase; Cohort Studies; European Continental Ancestry Group; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Sodium-Phosphate Cotransporter Proteins, Type I

Sequencing of SCN5A identifies rare and common variants associated with cardiac conduction: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Magnani, Jared W; Brody, Jennifer A; Prins, Bram P; Arking, Dan E; Lin, Honghuang; Yin, Xiaoyan; Liu, Ching-Ti; Morrison, Alanna C; Zhang, Feng; Spector, Tim D; Alonso, Alvaro; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The cardiac sodium channel SCN5A regulates atrioventricular and ventricular conduction. Genetic variants in this gene are associated with PR and QRS intervals. We sought to characterize further the contribution of rare and common coding variation in SCN5A to cardiac conduction. METHODS AND RESULTS: In Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study, we performed targeted exonic sequencing of SCN5A (n=3699, European ancestry individuals) and identified 4 common (minor allele frequency >1%) and 157 rare variants. Common and rare SCN5A coding variants were examined for association with PR and QRS intervals through meta-analysis of European ancestry participants from CHARGE, National Heart, Lung, and Blood Institute's Exome Sequencing Project (n=607), and the UK10K (n=1275) and by examining Exome Sequencing Project African ancestry participants (n=972). Rare coding SCN5A variants in aggregate were associated with PR interval in European and African ancestry participants (P=1.3×10(-3)). Three common variants were associated with PR and QRS interval duration among European ancestry participants and one among African ancestry participants. These included 2 well-known missense variants: rs1805124 (H558R) was associated with PR and QRS shortening in European ancestry participants (P=6.25×10(-4) and P=5.2×10(-3), respectively) and rs7626962 (S1102Y) was associated with PR shortening in those of African ancestry (P=2.82×10(-3)). Among European ancestry participants, 2 novel synonymous variants, rs1805126 and rs6599230, were associated with cardiac conduction. Our top signal, rs1805126 was associated with PR and QRS lengthening (P=3.35×10(-7) and P=2.69×10(-4), respectively) and rs6599230 was associated with PR shortening (P=2.67×10(-5)). CONCLUSIONS: By sequencing SCN5A, we identified novel common and rare coding variants associated with cardiac conduction.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Conduction System; Heart Diseases; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Sleep duration does not mediate or modify association of common genetic variants with type 2 diabetes. - Tare, Archana; Lane, Jacqueline M; Cade, Brian E; Grant, Struan F A; Chen, Ting-Hsu; Punjabi, Naresh M; Lauderdale, Diane S; Zee, Phyllis C; Gharib, Sina A; Gottlieb, Daniel J; Scheer, Frank A J L; Redline, Susan; et al. (Diabetologia, 2014)
AIMS/HYPOTHESIS: Short and long sleep duration are associated with increased risk of type 2 diabetes. We aimed to investigate whether genetic variants for fasting glucose or type 2 diabetes associate with short or long sleep duration and whether sleep duration modifies the association of genetic variants with these traits. METHODS: We examined the cross-sectional relationship between self-reported habitual sleep duration and prevalence of type 2 diabetes in individuals of European descent participating in five studies included in the Candidate Gene Association Resource (CARe), totalling 1,474 cases and 8,323 controls. We tested for association of 16 fasting glucose-associated variants, 27 type 2 diabetes-associated variants and aggregate genetic risk scores with continuous and dichotomised (≤5 h or ≥9 h) sleep duration using regression models adjusted for age, sex and BMI. Finally, we tested whether a gene × behaviour interaction of variants with sleep duration had an impact on fasting glucose or type 2 diabetes risk. RESULTS: Short sleep duration was significantly associated with type 2 diabetes in CARe (OR 1.32; 95% CI 1.08, 1.61; p = 0.008). Variants previously associated with fasting glucose or type 2 diabetes and genetic risk scores were not associated with sleep duration. Furthermore, no study-wide significant interaction was observed between sleep duration and these variants on glycaemic traits. Nominal interactions were observed for sleep duration and PPARG rs1801282, CRY2 rs7943320 and HNF1B rs4430796 in influencing risk of type 2 diabetes (p < 0.05). CONCLUSIONS/INTERPRETATION: Our findings suggest that differences in habitual sleep duration do not mediate or modify the relationship between common variants underlying glycaemic traits (including in circadian rhythm genes) and diabetes.
Keywords: Blood Glucose; Body Composition; Body Mass Index; Cross-Sectional Studies; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Fasting; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Glucose Intolerance; Glycated Hemoglobin A; Humans; Insulin Resistance; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sleep; Surveys and Questionnaires; Time Factors; United States

Strategies to design and analyze targeted sequencing data: cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Lin, Honghuang; Wang, Min; Brody, Jennifer A; Bis, Joshua C; Dupuis, Josée; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Sitlani, Colleen M; Reid, Jeffrey G; Bressler, Jan; Liu, Xiaoming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies have identified thousands of genetic variants that influence a variety of diseases and health-related quantitative traits. However, the causal variants underlying the majority of genetic associations remain unknown. Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study aims to follow up genome-wide association study signals and identify novel associations of the allelic spectrum of identified variants with cardiovascular-related traits. METHODS AND RESULTS: The study included 4231 participants from 3 CHARGE cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, and the Framingham Heart Study. We used a case-cohort design in which we selected both a random sample of participants and participants with extreme phenotypes for each of 14 traits. We sequenced and analyzed 77 genomic loci, which had previously been associated with ≥1 of 14 phenotypes. A total of 52 736 variants were characterized by sequencing and passed our stringent quality control criteria. For common variants (minor allele frequency ≥1%), we performed unweighted regression analyses to obtain P values for associations and weighted regression analyses to obtain effect estimates that accounted for the sampling design. For rare variants, we applied 2 approaches: collapsed aggregate statistics and joint analysis of variants using the sequence kernel association test. CONCLUSIONS: We sequenced 77 genomic loci in participants from 3 cohorts. We established a set of filters to identify high-quality variants and implemented statistical and bioinformatics strategies to analyze the sequence data and identify potentially functional variants within genome-wide association study loci.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Research Design; Sequence Analysis, DNA

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Boerwinkle, Eric; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Thyroid antibody status, subclinical hypothyroidism, and the risk of coronary heart disease: an individual participant data analysis. - Collet, Tinh-Hai; Bauer, Douglas C; Cappola, Anne R; Asvold, Bjørn O; Weiler, Stefan; Vittinghoff, Eric; Gussekloo, Jacobijn; Bremner, Alexandra; den Elzen, Wendy P J; Maciel, Rui M B; Vanderpump, Mark P J; Cornuz, Jacques; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Subclinical hypothyroidism has been associated with increased risk of coronary heart disease (CHD), particularly with thyrotropin levels of 10.0 mIU/L or greater. The measurement of thyroid antibodies helps predict the progression to overt hypothyroidism, but it is unclear whether thyroid autoimmunity independently affects CHD risk. OBJECTIVE: The objective of the study was to compare the CHD risk of subclinical hypothyroidism with and without thyroid peroxidase antibodies (TPOAbs). DATA SOURCES AND STUDY SELECTION: A MEDLINE and EMBASE search from 1950 to 2011 was conducted for prospective cohorts, reporting baseline thyroid function, antibodies, and CHD outcomes. DATA EXTRACTION: Individual data of 38 274 participants from six cohorts for CHD mortality followed up for 460 333 person-years and 33 394 participants from four cohorts for CHD events. DATA SYNTHESIS: Among 38 274 adults (median age 55 y, 63% women), 1691 (4.4%) had subclinical hypothyroidism, of whom 775 (45.8%) had positive TPOAbs. During follow-up, 1436 participants died of CHD and 3285 had CHD events. Compared with euthyroid individuals, age- and gender-adjusted risks of CHD mortality in subclinical hypothyroidism were similar among individuals with and without TPOAbs [hazard ratio (HR) 1.15, 95% confidence interval (CI) 0.87-1.53 vs HR 1.26, CI 1.01-1.58, P for interaction = .62], as were risks of CHD events (HR 1.16, CI 0.87-1.56 vs HR 1.26, CI 1.02-1.56, P for interaction = .65). Risks of CHD mortality and events increased with higher thyrotropin, but within each stratum, risks did not differ by TPOAb status. CONCLUSIONS: CHD risk associated with subclinical hypothyroidism did not differ by TPOAb status, suggesting that biomarkers of thyroid autoimmunity do not add independent prognostic information for CHD outcomes.
Keywords: Adult; Aged; Aged, 80 and over; Autoantibodies; Coronary Disease; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Prevalence; Prognosis; Risk Factors; Seroepidemiologic Studies; Severity of Illness Index; Young Adult

Troponin T, NT-proBNP, and venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Lutsey, Pamela L; Nambi, Vijay; deFilippi, Christopher R; Heckbert, Susan R; Cushman, Mary; Ballantyne, Christie M (Vasc Med, 2014)
Increased levels of plasma troponins and natriuretic peptides are markers of cardiac dysfunction associated with increased risk of cardiovascular disease. Little information exists on cardiac dysfunction and occurrence of venous thromboembolism (VTE). In two prospective epidemiological cohorts, we tested the hypothesis that high-sensitivity troponin T (TnT) and N-terminal pro B-type natriuretic peptide (NT-proBNP) are associated positively with VTE occurrence. The Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS) measured plasma TnT and NT-proBNP in 13,719 men or women with no history of venous thrombosis, coronary heart disease, or heart failure and followed them for approximately 10 years for VTE occurrence (n = 348 VTEs). In both ARIC and CHS, TnT was associated positively with incidence of total VTE and provoked VTE, but not with unprovoked VTE: age, race, and sex-adjusted hazard ratios for total VTE in the pooled analysis were 1.00, 0.85, 1.36, 1.51, and 1.98 (p-trend <0.0001) across five categories of TnT. In contrast, the association of NT-proBNP with VTE was positive in ARIC (hazard ratios approximately 2.5-fold for the highest versus lowest NT-proBNP quintiles), but non-existent in CHS.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Factors; Troponin T; Venous Thromboembolism

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association between hospitalization for pneumonia and subsequent risk of cardiovascular disease. - Corrales-Medina, Vicente F; Alvarez, Karina N; Weissfeld, Lisa A; Angus, Derek C; Chirinos, Julio A; Chang, Chung-Chou H; Newman, Anne; Loehr, Laura; Folsom, Aaron R; Elkind, Mitchell S; Lyles, Mary F; Kronmal, Richard A; et al. (JAMA, 2015)
IMPORTANCE: The risk of cardiovascular disease (CVD) after infection is poorly understood. OBJECTIVE: To determine whether hospitalization for pneumonia is associated with an increased short-term and long-term risk of CVD. DESIGN, SETTINGS, AND PARTICIPANTS: We examined 2 community-based cohorts: the Cardiovascular Health Study (CHS, n = 5888; enrollment age, ≥65 years; enrollment period, 1989-1994) and the Atherosclerosis Risk in Communities study (ARIC, n = 15,792; enrollment age, 45-64 years; enrollment period, 1987-1989). Participants were followed up through December 31, 2010. We matched each participant hospitalized with pneumonia to 2 controls. Pneumonia cases and controls were followed for occurrence of CVD over 10 years after matching. We estimated hazard ratios (HRs) for CVD at different time intervals, adjusting for demographics, CVD risk factors, subclinical CVD, comorbidities, and functional status. EXPOSURES: Hospitalization for pneumonia. MAIN OUTCOMES AND MEASURES: Incident CVD (myocardial infarction, stroke, and fatal coronary heart disease). RESULTS: Of 591 pneumonia cases in CHS, 206 had CVD events over 10 years after pneumonia hospitalization. CVD risk after pneumonia was highest in the first year. CVD occurred in 54 cases and 6 controls in the first 30 days (HR, 4.07; 95% CI, 2.86-5.27); 11 cases and 9 controls between 31 and 90 days (HR, 2.94; 95% CI, 2.18-3.70); and 22 cases and 55 controls between 91 days and 1 year (HR, 2.10; 95% CI, 1.59-2.60). Additional CVD risk remained elevated into the tenth year, when 4 cases and 12 controls developed CVD (HR, 1.86; 95% CI, 1.18-2.55). In ARIC, of 680 pneumonia cases, 112 had CVD over 10 years after hospitalization. CVD occurred in 4 cases and 3 controls in the first 30 days (HR, 2.38; 95% CI, 1.12-3.63); 4 cases and 0 controls between 31 and 90 days (HR, 2.40; 95% CI, 1.23-3.47); 11 cases and 8 controls between 91 days and 1 year (HR, 2.19; 95% CI, 1.20-3.19); and 8 cases and 7 controls during the second year (HR, 1.88; 95% CI, 1.10-2.66). After the second year, the HRs were no longer statistically significant. CONCLUSIONS AND RELEVANCE: Hospitalization for pneumonia was associated with increased short-term and long-term risk of CVD, suggesting that pneumonia may be a risk factor for CVD.
Keywords: Aged; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Hospitalization; Humans; Male; Middle Aged; Pneumonia; Risk Factors

Association between left atrial abnormality on ECG and vascular brain injury on MRI in the Cardiovascular Health Study. - Kamel, Hooman; Bartz, Traci M; Longstreth, W T; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Elkind, Mitchell S V; Soliman, Elsayed Z (Stroke, 2015)
BACKGROUND AND PURPOSE: Emerging evidence suggests that atrial disease is associated with vascular brain injury in the absence of atrial fibrillation. METHODS: The Cardiovascular Health Study prospectively enrolled community-dwelling adults aged ≥65 years. Among participants who underwent MRI, we examined associations of ECG left atrial abnormality with brain infarcts and leukoaraiosis. P-wave terminal force in lead V1 was the primary measure of left atrial abnormality; P-wave area and duration were secondary predictors. We excluded participants with atrial fibrillation before or on their index ECG. Primary outcomes were incident infarcts and worsening leukoaraiosis from initial to follow-up scan ≈5 years later. Secondary outcomes were prevalent infarcts and degree of leukoaraiosis on initial MRI. Relative risk (RR) and linear regression models were adjusted for vascular risk factors. RESULTS: Among 3129 participants with ≥1 scan, each SD increase in P-wave terminal force in lead V1 was associated with a 0.05-point (95% confidence interval [CI], 0.0003-0.10) higher baseline white matter grade on a 10-point scale. P-wave terminal force in lead V1 was associated with prevalent infarcts of any type (RR per SD, 1.09; 95% CI, 1.04-1.16) and more so with prevalent nonlacunar infarcts (RR per SD, 1.22; 95% CI, 1.08-1.38). Among 1839 participants with 2 scans, P-wave terminal force in lead V1 was associated with worsening leukoaraiosis (RR per SD, 1.09; 95% CI, 1.01-1.18), but not with incident infarcts (RR per SD, 1.06; 95% CI, 0.93-1.20). Sensitivity analyses adjusting for incident atrial fibrillation found similar results. P-wave area and duration were not associated with outcomes. CONCLUSIONS: ECG left atrial abnormality is associated with vascular brain injury in the absence of documented atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Brain; Brain Infarction; Cardiovascular Diseases; Cerebrovascular Trauma; Electrocardiography; Female; Heart Atria; Heart Diseases; Humans; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Regression Analysis; Risk Factors; Treatment Outcome

Association of 25-Hydroxyvitamin D status and genetic variation in the vitamin D metabolic pathway with FEV1 in the Framingham Heart Study. - Hansen, J G; Gao, W; Dupuis, J; O'Connor, G T; Tang, W; Kowgier, M; Sood, A; Gharib, S A; Palmer, L J; Fornage, M; Heckbert, S R; Psaty, B M; et al. (Respir Res, 2015)
BACKGROUND: Vitamin D is associated with lung function in cross-sectional studies, and vitamin D inadequacy is hypothesized to play a role in the pathogenesis of chronic obstructive pulmonary disease. Further data are needed to clarify the relation between vitamin D status, genetic variation in vitamin D metabolic genes, and cross-sectional and longitudinal changes in lung function in healthy adults. METHODS: We estimated the association between serum 25-hydroxyvitamin D [25(OH)D] and cross-sectional forced expiratory volume in the first second (FEV1) in Framingham Heart Study (FHS) Offspring and Third Generation participants and the association between serum 25(OH)D and longitudinal change in FEV1 in Third Generation participants using linear mixed-effects models. Using a gene-based approach, we investigated the association between 241 SNPs in 6 select vitamin D metabolic genes in relation to longitudinal change in FEV1 in Offspring participants and pursued replication of these findings in a meta-analyzed set of 4 independent cohorts. RESULTS: We found a positive cross-sectional association between 25(OH)D and FEV1 in FHS Offspring and Third Generation participants (P=0.004). There was little or no association between 25(OH)D and longitudinal change in FEV1 in Third Generation participants (P=0.97). In Offspring participants, the CYP2R1 gene, hypothesized to influence usual serum 25(OH)D status, was associated with longitudinal change in FEV1 (gene-based P<0.05). The most significantly associated SNP from CYP2R1 had a consistent direction of association with FEV1 in the meta-analyzed set of replication cohorts, but the association did not reach statistical significance thresholds (P=0.09). CONCLUSIONS: Serum 25(OH)D status was associated with cross-sectional FEV1, but not longitudinal change in FEV1. The inconsistent associations may be driven by differences in the groups studied. CYP2R1 demonstrated a gene-based association with longitudinal change in FEV1 and is a promising candidate gene for further studies.
Keywords: Adult; Aged; Cohort Studies; Cross-Sectional Studies; DNA-Binding Proteins; Female; Genetic Variation; Humans; Longitudinal Studies; Male; Massachusetts; Metabolic Networks and Pathways; Middle Aged; Nuclear Proteins; Polymorphism, Single Nucleotide; Vitamin D

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Dietary fatty acids modulate associations between genetic variants and circulating fatty acids in plasma and erythrocyte membranes: Meta-analysis of nine studies in the CHARGE consortium. - Smith, Caren E; Follis, Jack L; Nettleton, Jennifer A; Foy, Millennia; Wu, Jason H Y; Ma, Yiyi; Tanaka, Toshiko; Manichakul, Ani W; Wu, Hongyu; Chu, Audrey Y; Steffen, Lyn M; Fornage, Myriam; et al. (Mol Nutr Food Res, 2015)
SCOPE: Tissue concentrations of omega-3 fatty acids may reduce cardiovascular disease risk, and genetic variants are associated with circulating fatty acids concentrations. Whether dietary fatty acids interact with genetic variants to modify circulating omega-3 fatty acids is unclear. We evaluated interactions between genetic variants and fatty acid intakes for circulating alpha-linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid. METHODS AND RESULTS: We conducted meta-analyses (N = 11 668) evaluating interactions between dietary fatty acids and genetic variants (rs174538 and rs174548 in FADS1 (fatty acid desaturase 1), rs7435 in AGPAT3 (1-acyl-sn-glycerol-3-phosphate), rs4985167 in PDXDC1 (pyridoxal-dependent decarboxylase domain-containing 1), rs780094 in GCKR (glucokinase regulatory protein), and rs3734398 in ELOVL2 (fatty acid elongase 2)). Stratification by measurement compartment (plasma versus erthyrocyte) revealed compartment-specific interactions between FADS1 rs174538 and rs174548 and dietary alpha-linolenic acid and linoleic acid for docosahexaenoic acid and docosapentaenoic acid. CONCLUSION: Our findings reinforce earlier reports that genetically based differences in circulating fatty acids may be partially due to differences in the conversion of fatty acid precursors. Further, fatty acids measurement compartment may modify gene-diet relationships, and considering compartment may improve the detection of gene-fatty acids interactions for circulating fatty acid outcomes.
Keywords: Acetyltransferases; Acyltransferases; Adaptor Proteins, Signal Transducing; Carboxy-Lyases; Diet; Docosahexaenoic Acids; Eicosapentaenoic Acid; Erythrocyte Membrane; Fatty Acid Desaturases; Fatty Acids; Fatty Acids, Omega-3; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Gene-centric approach identifies new and known loci for FVIII activity and VWF antigen levels in European Americans and African Americans. - Tang, Weihong; Cushman, Mary; Green, David; Rich, Stephen S; Lange, Leslie A; Yang, Qiong; Tracy, Russell P; Tofler, Geoffrey H; Basu, Saonli; Wilson, James G; Keating, Brendan J; Weng, Lu-Chen; et al. (Am J Hematol, 2015)
Coagulation factor VIII and von Willebrand factor (VWF) are key proteins in procoagulant activation. Higher FVIII coagulant activity (FVIII :C) and VWF antigen (VWF :Ag) are risk factors for cardiovascular disease and venous thromboembolism. Beyond associations with ABO blood group, genetic determinants of FVIII and VWF are not well understood, especially in non European-American populations. We performed a genetic association study of FVIII :C and VWF:Ag that assessed 50,000 gene-centric single nucleotide polymorphisms (SNPs) in 18,556 European Americans (EAs) and 5,047 African Americans (AAs) from five population-based cohorts. Previously unreported associations for FVIII :C were identified in both AAs and EAs with KNG1 (most significantly associated SNP rs710446, Ile581Thr, Ile581Thr, P = 5.10 × 10(-7) in EAs and P = 3.88 × 10(-3) in AAs) and VWF rs7962217 (Gly2705Arg,P = 6.30 × 10(-9) in EAs and P = 2.98 × 10(-2) in AAs. Significant associations for FVIII :C were also observed with F8/TMLHE region SNP rs12557310 in EAs (P = 8.02 × 10(-10) ), with VWF rs1800380 in AAs (P = 5.62 × 10(-11) ), and with MAT1A rs2236568 in AAs (P51.69 × 10(-6) ). We replicated previously reported associations of FVIII :C and VWF :Ag with the ABO blood group, VWF rs1063856(Thr789Ala), rs216321 (Ala852Gln), and VWF rs2229446 (Arg2185Gln). Findings from this study expand our understanding of genetic influences for FVIII :C and VWF :Ag in both EAs and AAs.
Keywords: Adult; African Americans; Aged; European Continental Ancestry Group; Factor VIII; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Methionine Adenosyltransferase; Middle Aged; Polymorphism, Single Nucleotide; Venous Thromboembolism; von Willebrand Factor

Gene-Environment Interactions of Circadian-Related Genes for Cardiometabolic Traits. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Garaulet, Marta; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Kiefte-de Jong, Jessica C; Lamon-Fava, Stefania; Scheer, Frank A J L; Bartz, Traci M; et al. (Diabetes Care, 2015)
OBJECTIVE: Common circadian-related gene variants associate with increased risk for metabolic alterations including type 2 diabetes. However, little is known about whether diet and sleep could modify associations between circadian-related variants (CLOCK-rs1801260, CRY2-rs11605924, MTNR1B-rs1387153, MTNR1B-rs10830963, NR1D1-rs2314339) and cardiometabolic traits (fasting glucose [FG], HOMA-insulin resistance, BMI, waist circumference, and HDL-cholesterol) to facilitate personalized recommendations. RESEARCH DESIGN AND METHODS: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations and interactions between dietary intake/sleep duration and selected variants on cardiometabolic traits from 15 cohort studies including up to 28,190 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. RESULTS: We observed significant associations between relative macronutrient intakes and glycemic traits and short sleep duration (<7 h) and higher FG and replicated known MTNR1B associations with glycemic traits. No interactions were evident after accounting for multiple comparisons. However, we observed nominally significant interactions (all P < 0.01) between carbohydrate intake and MTNR1B-rs1387153 for FG with a 0.003 mmol/L higher FG with each additional 1% carbohydrate intake in the presence of the T allele, between sleep duration and CRY2-rs11605924 for HDL-cholesterol with a 0.010 mmol/L higher HDL-cholesterol with each additional hour of sleep in the presence of the A allele, and between long sleep duration (≥9 h) and MTNR1B-rs1387153 for BMI with a 0.60 kg/m(2) higher BMI with long sleep duration in the presence of the T allele relative to normal sleep duration (≥7 to <9 h). CONCLUSIONS: Our results suggest that lower carbohydrate intake and normal sleep duration may ameliorate cardiometabolic abnormalities conferred by common circadian-related genetic variants. Until further mechanistic examination of the nominally significant interactions is conducted, recommendations applicable to the general population regarding diet—specifically higher carbohydrate and lower fat composition—and normal sleep duration should continue to be emphasized among individuals with the investigated circadian-related gene variants.
Keywords: Adult; Alleles; Blood Glucose; Circadian Rhythm Signaling Peptides and Proteins; Cohort Studies; Diabetes Mellitus, Type 2; Diet, Fat-Restricted; European Continental Ancestry Group; Fasting; Female; Gene-Environment Interaction; Humans; Insulin Resistance; Male; Middle Aged; Multicenter Studies as Topic; Observational Studies as Topic; Phenotype; Polymorphism, Single Nucleotide; Sleep; Waist Circumference

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Buchman, Aron S; Deelen, Joris; Evans, Daniel S; Faul, Jessica D; Lunetta, Kathryn L; Sebastiani, Paola; Smith, Jennifer A; Smith, Albert V; Tanaka, Toshiko; Yu, Lei; Arnold, Alice M; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

Habitual sleep duration is associated with BMI and macronutrient intake and may be modified by CLOCK genetic variants. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Cade, Brian E; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Lamon-Fava, Stefania; Richardson, Kris; Saxena, Richa; Scheer, Frank A J L; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Short sleep duration has been associated with greater risks of obesity, hypertension, diabetes, and cardiovascular disease. Also, common genetic variants in the human Circadian Locomotor Output Cycles Kaput (CLOCK) show associations with ghrelin and total energy intake. OBJECTIVES: We examined associations between habitual sleep duration, body mass index (BMI), and macronutrient intake and assessed whether CLOCK variants modify these associations. DESIGN: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations of sleep duration and BMI and macronutrient intake as percentages of total energy as well as interactions with CLOCK variants from 9 cohort studies including up to 14,906 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. RESULTS: We observed a significant association between sleep duration and lower BMI (β ± SE = 0.16 ± 0.04, P < 0.0001) in the overall sample; however, associations between sleep duration and relative macronutrient intake were evident in age- and sex-stratified analyses only. We observed a significant association between sleep duration and lower saturated fatty acid intake in younger (aged 20-64 y) adults (men: 0.11 ± 0.06%, P = 0.03; women: 0.10 ± 0.05%, P = 0.04) and with lower carbohydrate (-0.31 ± 0.12%, P < 0.01), higher total fat (0.18 ± 0.09%, P = 0.05), and higher PUFA (0.05 ± 0.02%, P = 0.02) intakes in older (aged 65-80 y) women. In addition, the following 2 nominally significant interactions were observed: between sleep duration and rs12649507 on PUFA intake and between sleep duration and rs6858749 on protein intake. CONCLUSIONS: Our results indicate that longer habitual sleep duration is associated with lower BMI and age- and sex-specific favorable dietary behaviors. Differences in the relative intake of specific macronutrients associated with short sleep duration could, at least in part, explain previously reported associations between short sleep duration and chronic metabolic abnormalities. In addition, the influence of obesity-associated CLOCK variants on the association between sleep duration and macronutrient intake suggests that longer habitual sleep duration could ameliorate the genetic predisposition to obesity via a favorable dietary profile.
Keywords: Adult; Body Mass Index; CLOCK Proteins; Cohort Studies; Cross-Sectional Studies; Diet; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fatty Acids, Unsaturated; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Sleep; Young Adult

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Mendelian randomization of blood lipids for coronary heart disease. - Holmes, Michael V; Asselbergs, Folkert W; Palmer, Tom M; Drenos, Fotios; Lanktree, Matthew B; Nelson, Christopher P; Dale, Caroline E; Padmanabhan, Sandosh; Finan, Chris; Swerdlow, Daniel I; Tragante, Vinicius; van Iperen, Erik P A; et al. (Eur Heart J, 2015)
AIMS: To investigate the causal role of high-density lipoprotein cholesterol (HDL-C) and triglycerides in coronary heart disease (CHD) using multiple instrumental variables for Mendelian randomization. METHODS AND RESULTS: We developed weighted allele scores based on single nucleotide polymorphisms (SNPs) with established associations with HDL-C, triglycerides, and low-density lipoprotein cholesterol (LDL-C). For each trait, we constructed two scores. The first was unrestricted, including all independent SNPs associated with the lipid trait identified from a prior meta-analysis (threshold P < 2 × 10(-6)); and the second a restricted score, filtered to remove any SNPs also associated with either of the other two lipid traits at P ≤ 0.01. Mendelian randomization meta-analyses were conducted in 17 studies including 62,199 participants and 12,099 CHD events. Both the unrestricted and restricted allele scores for LDL-C (42 and 19 SNPs, respectively) associated with CHD. For HDL-C, the unrestricted allele score (48 SNPs) was associated with CHD (OR: 0.53; 95% CI: 0.40, 0.70), per 1 mmol/L higher HDL-C, but neither the restricted allele score (19 SNPs; OR: 0.91; 95% CI: 0.42, 1.98) nor the unrestricted HDL-C allele score adjusted for triglycerides, LDL-C, or statin use (OR: 0.81; 95% CI: 0.44, 1.46) showed a robust association. For triglycerides, the unrestricted allele score (67 SNPs) and the restricted allele score (27 SNPs) were both associated with CHD (OR: 1.62; 95% CI: 1.24, 2.11 and 1.61; 95% CI: 1.00, 2.59, respectively) per 1-log unit increment. However, the unrestricted triglyceride score adjusted for HDL-C, LDL-C, and statin use gave an OR for CHD of 1.01 (95% CI: 0.59, 1.75). CONCLUSION: The genetic findings support a causal effect of triglycerides on CHD risk, but a causal role for HDL-C, though possible, remains less certain.
Keywords: Case-Control Studies; Cholesterol, HDL; Coronary Artery Disease; Female; Gene Frequency; Genotype; Genotyping Techniques; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk Assessment; Triglycerides

A Meta-analysis of the Association of Estimated GFR, Albuminuria, Age, Race, and Sex With Acute Kidney Injury. - Grams, Morgan E; Sang, Yingying; Ballew, Shoshana H; Gansevoort, Ron T; Kimm, Heejin; Kovesdy, Csaba P; Naimark, David; Oien, Cecilia; Smith, David H; Coresh, Josef; Sarnak, Mark J; Stengel, Bénédicte; et al. (Am J Kidney Dis, 2015)
BACKGROUND: Acute kidney injury (AKI) is a serious global public health problem. We aimed to quantify the risk of AKI associated with estimated glomerular filtration rate (eGFR), albuminuria (albumin-creatinine ratio [ACR]), age, sex, and race (African American and white). STUDY DESIGN: Collaborative meta-analysis. SETTING & POPULATION: 8 general-population cohorts (1,285,049 participants) and 5 chronic kidney disease (CKD) cohorts (79,519 participants). SELECTION CRITERIA FOR STUDIES: Available eGFR, ACR, and 50 or more AKI events. PREDICTORS: Age, sex, race, eGFR, urine ACR, and interactions. OUTCOME: Hospitalized with or for AKI, using Cox proportional hazards models to estimate HRs of AKI and random-effects meta-analysis to pool results. RESULTS: 16,480 (1.3%) general-population cohort participants had AKI over a mean follow-up of 4 years; 2,087 (2.6%) CKD participants had AKI over a mean follow-up of 1 year. Lower eGFR and higher ACR were strongly associated with AKI. Compared with eGFR of 80mL/min/1.73m(2), the adjusted HR of AKI at eGFR of 45mL/min/1.73m(2) was 3.35 (95% CI, 2.75-4.07). Compared with ACR of 5mg/g, the risk of AKI at ACR of 300mg/g was 2.73 (95% CI, 2.18-3.43). Older age was associated with higher risk of AKI, but this effect was attenuated with lower eGFR or higher ACR. Male sex was associated with higher risk of AKI, with a slight attenuation in lower eGFR but not in higher ACR. African Americans had higher AKI risk at higher levels of eGFR and most levels of ACR. LIMITATIONS: Only 2 general-population cohorts could contribute to analyses by race; AKI identified by diagnostic code. CONCLUSIONS: Reduced eGFR and increased ACR are consistent strong risk factors for AKI, whereas associations of AKI with age, sex, and race may be weaker in more advanced stages of CKD.
Keywords: Acute Kidney Injury; Adolescent; Adult; African Americans; Age Distribution; Aged; Albuminuria; Continental Population Groups; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Severity of Illness Index; Sex Distribution; Young Adult

A Meta-analysis of the Association of Estimated GFR, Albuminuria, Diabetes Mellitus, and Hypertension With Acute Kidney Injury. - James, Matthew T; Grams, Morgan E; Woodward, Mark; Elley, C Raina; Green, Jamie A; Wheeler, David C; de Jong, Paul; Gansevoort, Ron T; Levey, Andrew S; Warnock, David G; Sarnak, Mark J (Am J Kidney Dis, 2015)
BACKGROUND: Diabetes mellitus and hypertension are risk factors for acute kidney injury (AKI). Whether estimated glomerular filtration rate (eGFR) and urine albumin-creatinine ratio (ACR) remain risk factors for AKI in the presence and absence of these conditions is uncertain. STUDY DESIGN: Meta-analysis of cohort studies. SETTING & POPULATION: 8 general-population (1,285,045 participants) and 5 chronic kidney disease (CKD; 79,519 participants) cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts participating in the CKD Prognosis Consortium. PREDICTORS: Diabetes and hypertension status, eGFR by the 2009 CKD Epidemiology Collaboration creatinine equation, urine ACR, and interactions. OUTCOME: Hospitalization with AKI, using Cox proportional hazards models to estimate HRs of AKI and random-effects meta-analysis to pool results. RESULTS: During a mean follow-up of 4 years, there were 16,480 episodes of AKI in the general-population and 2,087 episodes in the CKD cohorts. Low eGFRs and high ACRs were associated with higher risks of AKI in individuals with or without diabetes and with or without hypertension. When compared to a common reference of eGFR of 80mL/min/1.73m(2) in nondiabetic patients, HRs for AKI were generally higher in diabetic patients at any level of eGFR. The same was true for diabetic patients at all levels of ACR compared with nondiabetic patients. The risk gradient for AKI with lower eGFRs was greater in those without diabetes than with diabetes, but similar with higher ACRs in those without versus with diabetes. Those with hypertension had a higher risk of AKI at eGFRs>60mL/min/1.73m(2) than those without hypertension. However, risk gradients for AKI with both lower eGFRs and higher ACRs were greater for those without than with hypertension. LIMITATIONS: AKI identified by diagnostic code. CONCLUSIONS: Lower eGFRs and higher ACRs are associated with higher risks of AKI among individuals with or without either diabetes or hypertension.
Keywords: Acute Kidney Injury; Adult; Aged; Comorbidity; Diabetes Mellitus; Disease Progression; Female; Glomerular Filtration Rate; Humans; Hypertension; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Prognosis; Renal Insufficiency, Chronic

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Novel loci associated with usual sleep duration: the CHARGE Consortium Genome-Wide Association Study. - Gottlieb, D J; Hek, K; Chen, T-H; Watson, N F; Eiriksdottir, G; Byrne, E M; Cornelis, M; Warby, S C; Bandinelli, S; Cherkas, L; Evans, D S; Grabe, H J; et al. (Mol Psychiatry, 2015)
Usual sleep duration is a heritable trait correlated with psychiatric morbidity, cardiometabolic disease and mortality, although little is known about the genetic variants influencing this trait. A genome-wide association study (GWAS) of usual sleep duration was conducted using 18 population-based cohorts totaling 47 180 individuals of European ancestry. Genome-wide significant association was identified at two loci. The strongest is located on chromosome 2, in an intergenic region 35- to 80-kb upstream from the thyroid-specific transcription factor PAX8 (lowest P=1.1 × 10(-9)). This finding was replicated in an African-American sample of 4771 individuals (lowest P=9.3 × 10(-4)). The strongest combined association was at rs1823125 (P=1.5 × 10(-10), minor allele frequency 0.26 in the discovery sample, 0.12 in the replication sample), with each copy of the minor allele associated with a sleep duration 3.1 min longer per night. The alleles associated with longer sleep duration were associated in previous GWAS with a more favorable metabolic profile and a lower risk of attention deficit hyperactivity disorder. Understanding the mechanisms underlying these associations may help elucidate biological mechanisms influencing sleep duration and its association with psychiatric, metabolic and cardiovascular disease.
Keywords: Adult; African Americans; Aged; Dyssomnias; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Self Report; Sleep

Plasma Levels of Soluble Interleukin-2 Receptor α: Associations With Clinical Cardiovascular Events and Genome-Wide Association Scan. - Durda, Peter; Sabourin, Jeremy; Lange, Ethan M; Nalls, Mike A; Mychaleckyj, Josyf C; Jenny, Nancy Swords; Li, Jin; Walston, Jeremy; Harris, Tamara B; Psaty, Bruce M; Valdar, William; Liu, Yongmei; et al. (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE: Interleukin (IL) -2 receptor subunit α regulates lymphocyte activation, which plays an important role in atherosclerosis. Associations between soluble IL-2Rα (sIL-2Rα) and cardiovascular disease (CVD) have not been widely studied and little is known about the genetic determinants of sIL-2Rα levels. APPROACH AND RESULTS: We measured baseline levels of sIL-2Rα in 4408 European American (EA) and 766 African American (AA) adults from the Cardiovascular Health Study (CHS) and examined associations with baseline CVD risk factors, subclinical CVD, and incident CVD events. We also performed a genome-wide association study for sIL-2Rα in CHS (2964 EAs and 683 AAs) and further combined CHS EA results with those from two other EA cohorts in a meta-analysis (n=4464 EAs). In age, sex- and race- adjusted models, sIL-2Rα was positively associated with current smoking, type 2 diabetes mellitus, hypertension, insulin, waist circumference, C-reactive protein, IL-6, fibrinogen, internal carotid wall thickness, all-cause mortality, CVD mortality, and incident CVD, stroke, and heart failure. When adjusted for baseline CVD risk factors and subclinical CVD, associations with all-cause mortality, CVD mortality, and heart failure remained significant in both EAs and AAs. In the EA genome-wide association study analysis, we observed 52 single-nucleotide polymorphisms in the chromosome 10p15-14 region, which contains IL2RA, IL15RA, and RMB17, that reached genome-wide significance (P<5×10(-8)). The most significant single-nucleotide polymorphism was rs7911500 (P=1.31×10(-75)). The EA meta-analysis results were highly consistent with CHS-only results. No single-nucleotide polymorphisms reached statistical significance in the AAs. CONCLUSIONS: These results support a role for sIL-2Rα in atherosclerosis and provide evidence for multiple-associated single-nucleotide polymorphisms at chromosome 10p15-14.
Keywords: Adult; African Americans; Age Distribution; Aged; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Incidence; Interleukin-2 Receptor alpha Subunit; Kaplan-Meier Estimate; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution; Survival Analysis

Positive association of tomato consumption with serum urate: support for tomato consumption as an anecdotal trigger of gout flares. - Flynn, Tanya J; Cadzow, Murray; Dalbeth, Nicola; Jones, Peter B; Stamp, Lisa K; Hindmarsh, Jennie Harré; Todd, Alwyn S; Walker, Robert J; Topless, Ruth; Merriman, Tony R (BMC Musculoskelet Disord, 2015)
BACKGROUND: Gout is a consequence of an innate immune reaction to monosodium urate crystals deposited in joints. Acute gout attacks can be triggered by dietary factors that are themselves associated with serum urate levels. Tomato consumption is an anecdotal trigger of gout flares. This study aimed to measure the frequency of tomato consumption as a self-reported trigger of gout attacks in a large New Zealand sample set, and to test the hypothesis that tomato consumption is associated with serum urate levels. METHODS: Two thousand fifty one New Zealanders (of Māori, Pacific Island, European or other ancestry) with clinically-ascertained gout were asked about gout trigger foods. European individuals from the Atherosclerosis Risk In Communities (ARIC; n = 7517) Study, Cardiovascular Health Study (CHS; n = 2151) and Framingham Heart Study (FHS; n = 3052) were used to test, in multivariate-adjusted analyses, for association between serum urate and tomato intake. RESULTS: Seventy one percent of people with gout reported having ≥1 gout trigger food. Of these 20% specifically mentioned tomatoes, the 4(th) most commonly reported trigger food. There was association between tomato intake and serum urate levels in the ARIC, CHS and FHS combined cohort (β = 0.66 μmolL(-1) increase in serum urate per additional serve per week; P = 0.006) - evident in both sexes (men: β = 0.84 μmolL(-1), P = 0.035; women: β = 0.59 μmolL (-1), P = 0.041). CONCLUSIONS: While our descriptive and observational data are unable to support the claim that tomato consumption is a trigger of gout attacks, the positive association between tomato consumption and serum urate levels suggests that the self-reporting of tomatoes as a dietary trigger by people with gout has a biological basis.
Keywords: Adolescent; Adult; Aged; European Continental Ancestry Group; Female; Gout; Humans; Hyperuricemia; Lycopersicon esculentum; Male; Middle Aged; New Zealand; Oceanic Ancestry Group; Surveys and Questionnaires; Uric Acid; Young Adult

Prognostic Significance of High-Sensitivity Cardiac Troponin T Concentrations between the Limit of Blank and Limit of Detection in Community-Dwelling Adults: A Metaanalysis. - Parikh, Ravi H; Seliger, Stephen L; de Lemos, James; Nambi, Vijay; Christenson, Robert; Ayers, Colby; Sun, Wensheng; Gottdiener, John S; Kuller, Lewis H; Ballantyne, Christie; deFilippi, Christopher R (Clin Chem, 2015)
BACKGROUND: There is controversy regarding whether to report concentrations of high-sensitivity cardiac troponin T (hs-cTnT) to the limit of blank (LOB) (3 ng/L) or the limit of detection (LOD) (5 ng/L) of the assay in community-based cohorts. We hypothesized that hs-cTnT concentrations between the LOB and LOD would be associated with poorer cardiovascular outcomes compared to concentrations below the LOB. METHODS: hs-cTnT was analyzed in a total of 10 723 participants from the Cardiovascular Health Study (CHS), Atherosclerosis Risk in Communities (ARIC) study, and Dallas Heart Study (DHS). Participants were divided into 2 groups, those with hs-cTnT concentrations below the limit of blank (LOB) (<3 ng/L) and those with hs-cTnT between the LOB and limit of detection (LOD) (3-4.99 ng/L). Cross-sectional associations with traditional cardiovascular risk factors and cardiac structural measurements, and longitudinal associations with long-term cardiovascular outcomes of incident heart failure and cardiovascular death, were determined. RESULTS: Participants with hs-cTnT between the LOB and LOD for all 3 cohorts were older, more likely to be male, and have a higher burden of cardiovascular risk factors and structural pathology. A metaanalysis of the 3 cohorts showed participants with hs-cTnT between the LOB and LOD were at increased risk of new-onset heart failure (hazard ratio, 1.18; 95% CI, 1.02-1.38) and cardiovascular mortality (hazard ratio, 1.29; 95% CI, 1.06-1.57). CONCLUSIONS: hs-cTnT concentrations between the LOB and LOD (3-4.99 ng/L) are associated with a higher prevalence of traditional risk factors, more cardiac pathology, and worse outcomes than concentrations below the LOB (<3 ng/L).
Keywords: Aged; Atherosclerosis; Biomarkers; Cross-Sectional Studies; Female; Heart Failure; Humans; Independent Living; Limit of Detection; Longitudinal Studies; Male; Middle Aged; Myocardial Infarction; Prognosis; Risk Assessment; Risk Factors; Sex Factors; Troponin T

Prospective study of circulating factor XI and incident venous thromboembolism: The Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Tang, Weihong; Roetker, Nicholas S; Heckbert, Susan R; Cushman, Mary; Pankow, James S (Am J Hematol, 2015)
Elevated plasma concentrations of coagulation factor XI may increase risk of venous thromboembolism (VTE), but prospective data are limited. We studied prospectively the associations of plasma factor XI and a key F11 genetic variant with incident VTE in whites and African-Americans. We measured factor XI in 16,299 participants, initially free of VTE, in two prospective population cohorts. We also measured the F11 single nucleotide polymorphism rs4241824, which a genome-wide association study had linked to factor XI concentration. During follow-up, we identified 606 VTEs. The age, race, sex, and study-adjusted hazard ratio of VTE increased across factor XI quintiles (P < 0.001 for trend), and the hazard ratio was 1.51 (95% CI 1.16, 1.97) for the highest versus lowest quintile overall, and was 1.42 (95% CI 1.03, 1.95) in whites and 1.72 (95% CI 1.08, 2.73) in African-Americans. In whites, the F11 variant was associated with both factor XI concentration and VTE incidence (1.15-fold greater incidence of VTE per risk allele). In African-Americans, these associations were absent. In conclusion, this cohort study documented that an elevated plasma factor XI concentration is a risk factor for VTE over extended follow-up, not only in whites but also in African-Americans. In whites, the association of the F11 genetic variant with VTE suggests a causal relation, but we did not observe this genetic relation in African-Americans.
Keywords: African Americans; Aged; Alleles; European Continental Ancestry Group; Factor XI; Female; Gene Expression; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Race/Ethnic Differences in the Associations of the Framingham Risk Factors with Carotid IMT and Cardiovascular Events. - Gijsberts, Crystel M; Groenewegen, Karlijn A; Hoefer, Imo E; Eijkemans, Marinus J C; Asselbergs, Folkert W; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; et al. (PLoS One, 2015)
BACKGROUND: Clinical manifestations and outcomes of atherosclerotic disease differ between ethnic groups. In addition, the prevalence of risk factors is substantially different. Primary prevention programs are based on data derived from almost exclusively White people. We investigated how race/ethnic differences modify the associations of established risk factors with atherosclerosis and cardiovascular events. METHODS: We used data from an ongoing individual participant meta-analysis involving 17 population-based cohorts worldwide. We selected 60,211 participants without cardiovascular disease at baseline with available data on ethnicity (White, Black, Asian or Hispanic). We generated a multivariable linear regression model containing risk factors and ethnicity predicting mean common carotid intima-media thickness (CIMT) and a multivariable Cox regression model predicting myocardial infarction or stroke. For each risk factor we assessed how the association with the preclinical and clinical measures of cardiovascular atherosclerotic disease was affected by ethnicity. RESULTS: Ethnicity appeared to significantly modify the associations between risk factors and CIMT and cardiovascular events. The association between age and CIMT was weaker in Blacks and Hispanics. Systolic blood pressure associated more strongly with CIMT in Asians. HDL cholesterol and smoking associated less with CIMT in Blacks. Furthermore, the association of age and total cholesterol levels with the occurrence of cardiovascular events differed between Blacks and Whites. CONCLUSION: The magnitude of associations between risk factors and the presence of atherosclerotic disease differs between race/ethnic groups. These subtle, yet significant differences provide insight in the etiology of cardiovascular disease among race/ethnic groups. These insights aid the race/ethnic-specific implementation of primary prevention.
Keywords: Adult; Age Distribution; Aged; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Cholesterol, LDL; Comorbidity; Continental Population Groups; Diabetes Mellitus; Dyslipidemias; Ethnic Groups; Female; Follow-Up Studies; Global Health; Humans; Hypertension; Incidence; Linear Models; Male; Middle Aged; Myocardial Infarction; Prevalence; Proportional Hazards Models; Risk Factors; Smoking; Stroke

Rare and Coding Region Genetic Variants Associated With Risk of Ischemic Stroke: The NHLBI Exome Sequence Project. - Auer, Paul L; Nalls, Mike; Meschia, James F; Worrall, Bradford B; Longstreth, W T; Seshadri, Sudha; Kooperberg, Charles; Burger, Kathleen M; Carlson, Christopher S; Carty, Cara L; Chen, Wei-Min; Cupples, L Adrienne; et al. (JAMA Neurol, 2015)
IMPORTANCE: Stroke is the second leading cause of death and the third leading cause of years of life lost. Genetic factors contribute to stroke prevalence, and candidate gene and genome-wide association studies (GWAS) have identified variants associated with ischemic stroke risk. These variants often have small effects without obvious biological significance. Exome sequencing may discover predicted protein-altering variants with a potentially large effect on ischemic stroke risk. OBJECTIVE: To investigate the contribution of rare and common genetic variants to ischemic stroke risk by targeting the protein-coding regions of the human genome. DESIGN, SETTING, AND PARTICIPANTS: The National Heart, Lung, and Blood Institute (NHLBI) Exome Sequencing Project (ESP) analyzed approximately 6000 participants from numerous cohorts of European and African ancestry. For discovery, 365 cases of ischemic stroke (small-vessel and large-vessel subtypes) and 809 European ancestry controls were sequenced; for replication, 47 affected sibpairs concordant for stroke subtype and an African American case-control series were sequenced, with 1672 cases and 4509 European ancestry controls genotyped. The ESP's exome sequencing and genotyping started on January 1, 2010, and continued through June 30, 2012. Analyses were conducted on the full data set between July 12, 2012, and July 13, 2013. MAIN OUTCOMES AND MEASURES: Discovery of new variants or genes contributing to ischemic stroke risk and subtype (primary analysis) and determination of support for protein-coding variants contributing to risk in previously published candidate genes (secondary analysis). RESULTS: We identified 2 novel genes associated with an increased risk of ischemic stroke: a protein-coding variant in PDE4DIP (rs1778155; odds ratio, 2.15; P = 2.63 × 10(-8)) with an intracellular signal transduction mechanism and in ACOT4 (rs35724886; odds ratio, 2.04; P = 1.24 × 10(-7)) with a fatty acid metabolism; confirmation of PDE4DIP was observed in affected sibpair families with large-vessel stroke subtype and in African Americans. Replication of protein-coding variants in candidate genes was observed for 2 previously reported GWAS associations: ZFHX3 (cardioembolic stroke) and ABCA1 (large-vessel stroke). CONCLUSIONS AND RELEVANCE: Exome sequencing discovered 2 novel genes and mechanisms, PDE4DIP and ACOT4, associated with increased risk for ischemic stroke. In addition, ZFHX3 and ABCA1 were discovered to have protein-coding variants associated with ischemic stroke. These results suggest that genetic variation in novel pathways contributes to ischemic stroke risk and serves as a target for prediction, prevention, and therapy.
Keywords: Aged; Brain Ischemia; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Muscle Proteins; National Heart, Lung, and Blood Institute (U.S.); Nuclear Proteins; Open Reading Frames; Palmitoyl-CoA Hydrolase; Stroke; United States

Sleep Disturbances and Glucose Metabolism in Older Adults: The Cardiovascular Health Study. - Strand, Linn Beate; Carnethon, Mercedes; Biggs, Mary Lou; Djoussé, Luc; Kaplan, Robert C; Siscovick, David S; Robbins, John A; Redline, Susan; Patel, Sanjay R; Janszky, Imre; Mukamal, Kenneth J (Diabetes Care, 2015)
OBJECTIVE: We examined the associations of symptoms of sleep-disordered breathing (SDB), which was defined as loud snoring, stopping breathing for a while during sleep, and daytime sleepiness, and insomnia with glucose metabolism and incident type 2 diabetes in older adults. RESEARCH DESIGN AND METHODS: Between 1989 and 1993, the Cardiovascular Health Study recruited 5,888 participants ≥65 years of age from four U.S. communities. Participants reported SDB and insomnia symptoms yearly through 1989-1994. In 1989-1990, participants underwent an oral glucose tolerance test, from which insulin secretion and insulin sensitivity were estimated. Fasting glucose levels were measured in 1989-1990 and again in 1992-1993, 1994-1995, 1996-1997, and 1998-1999, and medication use was ascertained yearly. We determined the cross-sectional associations of sleep symptoms with fasting glucose levels, 2-h glucose levels, insulin sensitivity, and insulin secretion using generalized estimated equations and linear regression models. We determined the associations of updated and averaged sleep symptoms with incident diabetes in Cox proportional hazards models. We adjusted for sociodemographics, lifestyle factors, and medical history. RESULTS: Observed apnea, snoring, and daytime sleepiness were associated with higher fasting glucose levels, higher 2-h glucose levels, lower insulin sensitivity, and higher insulin secretion. The risk of the development of type 2 diabetes was positively associated with observed apnea (hazard ratio [HR] 1.84 [95% CI 1.19-2.86]), snoring (HR 1.27 [95% CI 0.95-1.71]), and daytime sleepiness (HR 1.54 [95% CI 1.13-2.12]). In contrast, we did not find consistent associations between insomnia symptoms and glucose metabolism or incident type 2 diabetes. CONCLUSIONS: Easily collected symptoms of SDB are strongly associated with insulin resistance and the incidence of type 2 diabetes in older adults. Monitoring glucose metabolism in such patients may prove useful in identifying candidates for lifestyle or pharmacological therapy. Further studies are needed to determine whether insomnia symptoms affect the risk of diabetes in younger adults.
Keywords: Adult; Aged; Blood Glucose; Cardiovascular System; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Glucose Tolerance Test; Humans; Incidence; Insulin; Insulin Resistance; Male; Middle Aged; Sleep Apnea Syndromes; Sleep Initiation and Maintenance Disorders; Snoring; United States

Subclinical thyroid dysfunction and fracture risk: a meta-analysis. - Blum, Manuel R; Bauer, Douglas C; Collet, Tinh-Hai; Fink, Howard A; Cappola, Anne R; da Costa, Bruno R; Wirth, Christina D; Peeters, Robin P; Asvold, Bjørn O; den Elzen, Wendy P J; Luben, Robert N; Imaizumi, Misa; et al. (JAMA, 2015)
IMPORTANCE: Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE: To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION: Individual participant data were obtained from 13 prospective cohorts in the United States, Europe, Australia, and Japan. Levels of thyroid function were defined as euthyroidism (thyroid-stimulating hormone [TSH], 0.45-4.49 mIU/L), subclinical hyperthyroidism (TSH <0.45 mIU/L), and subclinical hypothyroidism (TSH ≥4.50-19.99 mIU/L) with normal thyroxine concentrations. MAIN OUTCOME AND MEASURES: The primary outcome was hip fracture. Any fractures, nonspine fractures, and clinical spine fractures were secondary outcomes. RESULTS: Among 70,298 participants, 4092 (5.8%) had subclinical hypothyroidism and 2219 (3.2%) had subclinical hyperthyroidism. During 762,401 person-years of follow-up, hip fracture occurred in 2975 participants (4.6%; 12 studies), any fracture in 2528 participants (9.0%; 8 studies), nonspine fracture in 2018 participants (8.4%; 8 studies), and spine fracture in 296 participants (1.3%; 6 studies). In age- and sex-adjusted analyses, the hazard ratio (HR) for subclinical hyperthyroidism vs euthyroidism was 1.36 for hip fracture (95% CI, 1.13-1.64; 146 events in 2082 participants vs 2534 in 56,471); for any fracture, HR was 1.28 (95% CI, 1.06-1.53; 121 events in 888 participants vs 2203 in 25,901); for nonspine fracture, HR was 1.16 (95% CI, 0.95-1.41; 107 events in 946 participants vs 1745 in 21,722); and for spine fracture, HR was 1.51 (95% CI, 0.93-2.45; 17 events in 732 participants vs 255 in 20,328). Lower TSH was associated with higher fracture rates: for TSH of less than 0.10 mIU/L, HR was 1.61 for hip fracture (95% CI, 1.21-2.15; 47 events in 510 participants); for any fracture, HR was 1.98 (95% CI, 1.41-2.78; 44 events in 212 participants); for nonspine fracture, HR was 1.61 (95% CI, 0.96-2.71; 32 events in 185 participants); and for spine fracture, HR was 3.57 (95% CI, 1.88-6.78; 8 events in 162 participants). Risks were similar after adjustment for other fracture risk factors. Endogenous subclinical hyperthyroidism (excluding thyroid medication users) was associated with HRs of 1.52 (95% CI, 1.19-1.93) for hip fracture, 1.42 (95% CI, 1.16-1.74) for any fracture, and 1.74 (95% CI, 1.01-2.99) for spine fracture. No association was found between subclinical hypothyroidism and fracture risk. CONCLUSIONS AND RELEVANCE: Subclinical hyperthyroidism was associated with an increased risk of hip and other fractures, particularly among those with TSH levels of less than 0.10 mIU/L and those with endogenous subclinical hyperthyroidism. Further study is needed to determine whether treating subclinical hyperthyroidism can prevent fractures.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Fractures, Bone; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Male; Middle Aged; Risk Factors; Spinal Fractures; Thyrotropin; Young Adult

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

Association of Smoking, Alcohol, and Obesity with Cardiovascular Death and Ischemic Stroke in Atrial Fibrillation: The Atherosclerosis Risk in Communities (ARIC) Study and Cardiovascular Health Study (CHS). - Kwon, Younghoon; Norby, Faye L; Jensen, Paul N; Agarwal, Sunil K; Soliman, Elsayed Z; Lip, Gregory Y H; Longstreth, W T; Alonso, Alvaro; Heckbert, Susan R; Chen, Lin Y (PLoS One, 2016)
Atrial fibrillation (AF) is associated with an increased risk of ischemic stroke and cardiovascular (CV) death. Whether modifiable lifestyle risk factors are associated with these CV outcomes in AF is unknown. Among Atherosclerosis Risk in Communities (ARIC) study and Cardiovascular Health Study (CHS) participants with incident AF, we estimated the risk of composite endpoint of ischemic stroke or CV death associated with candidate modifiable risk factor (smoking, heavy alcohol consumption, or high body mass index [BMI]), and computed the C-statistic, net reclassification improvement (NRI), and integrated discrimination improvement (IDI) of incorporating each factor into the CHA2DS2-VASc. Among 1222 ARIC (mean age: 63.4) and 756 CHS (mean age: 79.1) participants with incident AF, during mean follow-up of 6.9 years and 5.7 years, there were 332 and 335 composite events respectively. Compared with never smokers, current smokers had a higher incidence of the composite endpoint in ARIC [HR: 1.65 (1.21-2.26)] but not in CHS [HR: 1.05 (0.69-1.61)]. In ARIC, the addition of current smoking did not improve risk prediction over and above the CHA2DS2-VASc. No significant associations were observed with alcohol consumption or BMI with CVD outcomes in AF patients from either cohort. Smoking is associated with an increased risk of ischemic stroke or CV death in ARIC, which comprised mostly middle-aged to young-old (65-74 years), but not in CHS, which comprised mostly middle-old or oldest-old (≥75 years) adults with AF. However, addition of smoking to the CHA2DS2-VASc score did not improve risk prediction of these outcomes.
Keywords: Aged; Alcohol Drinking; Atrial Fibrillation; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Obesity; Smoking; Stroke

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

Genome-Wide Association Study for Incident Myocardial Infarction and Coronary Heart Disease in Prospective Cohort Studies: The CHARGE Consortium. - Dehghan, Abbas; Bis, Joshua C; White, Charles C; Smith, Albert Vernon; Morrison, Alanna C; Cupples, L Adrienne; Trompet, Stella; Chasman, Daniel I; Lumley, Thomas; Völker, Uwe; Buckley, Brendan M; Ding, Jingzhong; et al. (PLoS One, 2016)
BACKGROUND: Data are limited on genome-wide association studies (GWAS) for incident coronary heart disease (CHD). Moreover, it is not known whether genetic variants identified to date also associate with risk of CHD in a prospective setting. METHODS: We performed a two-stage GWAS analysis of incident myocardial infarction (MI) and CHD in a total of 64,297 individuals (including 3898 MI cases, 5465 CHD cases). SNPs that passed an arbitrary threshold of 5×10-6 in Stage I were taken to Stage II for further discovery. Furthermore, in an analysis of prognosis, we studied whether known SNPs from former GWAS were associated with total mortality in individuals who experienced MI during follow-up. RESULTS: In Stage I 15 loci passed the threshold of 5×10-6; 8 loci for MI and 8 loci for CHD, for which one locus overlapped and none were reported in previous GWAS meta-analyses. We took 60 SNPs representing these 15 loci to Stage II of discovery. Four SNPs near QKI showed nominally significant association with MI (p-value<8.8×10-3) and three exceeded the genome-wide significance threshold when Stage I and Stage II results were combined (top SNP rs6941513: p = 6.2×10-9). Despite excellent power, the 9p21 locus SNP (rs1333049) was only modestly associated with MI (HR = 1.09, p-value = 0.02) and marginally with CHD (HR = 1.06, p-value = 0.08). Among an inception cohort of those who experienced MI during follow-up, the risk allele of rs1333049 was associated with a decreased risk of subsequent mortality (HR = 0.90, p-value = 3.2×10-3). CONCLUSIONS: QKI represents a novel locus that may serve as a predictor of incident CHD in prospective studies. The association of the 9p21 locus both with increased risk of first myocardial infarction and longer survival after MI highlights the importance of study design in investigating genetic determinants of complex disorders.
Keywords: Aged; Cohort Studies; Cooperative Behavior; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Lifetime Risk of Venous Thromboembolism in Two Cohort Studies. - Bell, Elizabeth J; Lutsey, Pamela L; Basu, Saonli; Cushman, Mary; Heckbert, Susan R; Lloyd-Jones, Donald M; Folsom, Aaron R (Am J Med, 2016)
BACKGROUND: Greater public awareness of venous thromboembolism may be an important next step for optimizing venous thromboembolism prevention and treatment. "Lifetime risk" is an easily interpretable way of presenting risk information. Therefore, we sought to calculate the lifetime risk of venous thromboembolism (deep vein thrombosis or pulmonary embolism) using data from 2 large, prospective cohort studies: the Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) study. METHODS: We followed participants aged 45-64 years in ARIC (n = 14,185) and ≥65 in CHS (n = 5414) at baseline visits (1987-1989 in ARIC, 1989-1990 and 1992-1993 in CHS) for incident venous thromboembolism (n = 728 in ARIC through 2011 and n = 172 in CHS through 2001). We estimated lifetime risks and 95% confidence intervals of incident venous thromboembolism using a modified Kaplan-Meier method, accounting for the competing risk of death from other causes. RESULTS: At age 45 years, the remaining lifetime risk of venous thromboembolism in ARIC was 8.1% (95% confidence interval, 7.1-8.7). High-risk groups were African Americans (11.5% lifetime risk), those with obesity (10.9%), heterozygous for the factor V Leiden (17.1%), or with sickle cell trait or disease (18.2%). Lifetime risk estimates differed by cohort; these differences were explained by differences in time period of venous thromboembolism ascertainment. CONCLUSIONS: At least 1 in 12 middle-aged adults will develop venous thromboembolism in their remaining lifetime. This estimate of lifetime risk may be useful to promote awareness of venous thromboembolism and guide decisions at both clinical and policy levels.
Keywords: African Continental Ancestry Group; Aged; Anemia, Sickle Cell; Cohort Studies; Factor V; Follow-Up Studies; Heterozygote; Humans; Kaplan-Meier Estimate; Middle Aged; Obesity; Risk; Sickle Cell Trait; United States; Venous Thromboembolism

Natriuretic peptides and integrated risk assessment for cardiovascular disease: an individual-participant-data meta-analysis. - Willeit, Peter; Kaptoge, Stephen; Welsh, Paul; Butterworth, Adam; Chowdhury, Rajiv; Spackman, Sarah; Pennells, Lisa; Gao, Pei; Burgess, Stephen; Freitag, Daniel; Sweeting, Michael; Wood, Angela; et al. (Lancet Diabetes Endocrinol, 2016)
BACKGROUND: Guidelines for primary prevention of cardiovascular diseases focus on prediction of coronary heart disease and stroke. We assessed whether or not measurement of N-terminal-pro-B-type natriuretic peptide (NT-proBNP) concentration could enable a more integrated approach than at present by predicting heart failure and enhancing coronary heart disease and stroke risk assessment. METHODS: In this individual-participant-data meta-analysis, we generated and harmonised individual-participant data from relevant prospective studies via both de-novo NT-proBNP concentration measurement of stored samples and collection of data from studies identified through a systematic search of the literature (PubMed, Scientific Citation Index Expanded, and Embase) for articles published up to Sept 4, 2014, using search terms related to natriuretic peptide family members and the primary outcomes, with no language restrictions. We calculated risk ratios and measures of risk discrimination and reclassification across predicted 10 year risk categories (ie, <5%, 5% to <7·5%, and ≥7·5%), adding assessment of NT-proBNP concentration to that of conventional risk factors (ie, age, sex, smoking status, systolic blood pressure, history of diabetes, and total and HDL cholesterol concentrations). Primary outcomes were the combination of coronary heart disease and stroke, and the combination of coronary heart disease, stroke, and heart failure. FINDINGS: We recorded 5500 coronary heart disease, 4002 stroke, and 2212 heart failure outcomes among 95 617 participants without a history of cardiovascular disease in 40 prospective studies. Risk ratios (for a comparison of the top third vs bottom third of NT-proBNP concentrations, adjusted for conventional risk factors) were 1·76 (95% CI 1·56-1·98) for the combination of coronary heart disease and stroke and 2·00 (1·77-2·26) for the combination of coronary heart disease, stroke, and heart failure. Addition of information about NT-proBNP concentration to a model containing conventional risk factors was associated with a C-index increase of 0·012 (0·010-0·014) and a net reclassification improvement of 0·027 (0·019-0·036) for the combination of coronary heart disease and stroke and a C-index increase of 0·019 (0·016-0·022) and a net reclassification improvement of 0·028 (0·019-0·038) for the combination of coronary heart disease, stroke, and heart failure. INTERPRETATION: In people without baseline cardiovascular disease, NT-proBNP concentration assessment strongly predicted first-onset heart failure and augmented coronary heart disease and stroke prediction, suggesting that NT-proBNP concentration assessment could be used to integrate heart failure into cardiovascular disease primary prevention. FUNDING: British Heart Foundation, Austrian Science Fund, UK Medical Research Council, National Institute for Health Research, European Research Council, and European Commission Framework Programme 7.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Assessment

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10-7; replication: N = 7,182, p < 1.6 × 10-3). The replicated methylation sites are heritable (h2 > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Fibroblast Growth Factor 23, Mineral Metabolism, and Adiposity in Normal Kidney Function. - Zaheer, Sarah; de Boer, Ian H; Allison, Matthew; Brown, Jenifer M; Psaty, Bruce M; Robinson-Cohen, Cassianne; Michos, Erin D; Ix, Joachim H; Kestenbaum, Bryan; Siscovick, David; Vaidya, Anand (J Clin Endocrinol Metab, 2017)
Context: Obesity is associated with poor bone mineralization and quality. Fibroblast growth factor 23 (FGF23) plays an important role in skeletal physiology. Objective: To test hypothesis that greater adiposity results in higher FGF23 levels among individuals with normal estimated glomerular filtration rate (eGFR). Design, Setting, Participants: Cross-sectional analyses among participants with eGFR ≥60 mL/min/1.73m2. We assessed the association between crude [body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR); n = 5610] and refined (abdominal adipose tissue area by computed tomography; n = 1313) measures of adiposity and FGF23 using multivariable linear regression. Main Outcome Measure: Serum FGF23. Results: FGF23 was higher across BMI categories (BMI <25: 37.7; BMI 25 to 29.99: 38.7; BMI 30 to 39.99: 39.8; BMI ≥40: 40.9 pg/mL, unadjusted P trend < 0.0001). The association between BMI and FGF23 was independent of known confounders of FGF23 (adjusted β = +7.2% higher FGF23 per 10 kg/m2; P < 0.0001). Similar results were observed using WC and WHR. Abdominal adipose tissue area was also independently associated with higher FGF23 (P < 0.01). Notably, the positive associations between FGF23 and adiposity were observed despite the fact that eGFR did not decline and serum phosphate levels did not increase with adiposity. Conclusion: In a large cohort with normal kidney function, adiposity was associated with higher FGF23 levels independent of known confounders, including eGFR and phosphate. Further studies are needed to evaluate the causes of higher FGF23 in settings of greater adiposity and the potential impact on skeletal health.
Keywords: Adiposity; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Fibroblast Growth Factors; Glomerular Filtration Rate; Humans; Kidney; Male; Middle Aged; Minerals; Renal Insufficiency, Chronic; Risk Factors

Genetically Determined Plasma Lipid Levels and Risk of Diabetic Retinopathy: A Mendelian Randomization Study. - Sobrin, Lucia; Chong, Yong He; Fan, Qiao; Gan, Alfred; Stanwyck, Lynn K; Kaidonis, Georgia; Craig, Jamie E; Kim, Jihye; Liao, Wen-Ling; Huang, Yu-Chuen; Lee, Wen-Jane; Hung, Yi-Jen; et al. (Diabetes, 2017)
Results from observational studies examining dyslipidemia as a risk factor for diabetic retinopathy (DR) have been inconsistent. We evaluated the causal relationship between plasma lipids and DR using a Mendelian randomization approach. We pooled genome-wide association studies summary statistics from 18 studies for two DR phenotypes: any DR (N = 2,969 case and 4,096 control subjects) and severe DR (N = 1,277 case and 3,980 control subjects). Previously identified lipid-associated single nucleotide polymorphisms served as instrumental variables. Meta-analysis to combine the Mendelian randomization estimates from different cohorts was conducted. There was no statistically significant change in odds ratios of having any DR or severe DR for any of the lipid fractions in the primary analysis that used single nucleotide polymorphisms that did not have a pleiotropic effect on another lipid fraction. Similarly, there was no significant association in the Caucasian and Chinese subgroup analyses. This study did not show evidence of a causal role of the four lipid fractions on DR. However, the study had limited power to detect odds ratios less than 1.23 per SD in genetically induced increase in plasma lipid levels, thus we cannot exclude that causal relationships with more modest effect sizes exist.
Keywords: Aged; Diabetic Retinopathy; Female; Genome-Wide Association Study; Humans; Lipids; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk

Genome-wide association meta-analysis of fish and EPA+DHA consumption in 17 US and European cohorts. - Mozaffarian, Dariush; Dashti, Hassan S; Wojczynski, Mary K; Chu, Audrey Y; Nettleton, Jennifer A; Männistö, Satu; Kristiansson, Kati; Reedik, Mägi; Lahti, Jari; Houston, Denise K; Cornelis, Marilyn C; van Rooij, Frank J A; et al. (PLoS One, 2017)
BACKGROUND: Regular fish and omega-3 consumption may have several health benefits and are recommended by major dietary guidelines. Yet, their intakes remain remarkably variable both within and across populations, which could partly owe to genetic influences. OBJECTIVE: To identify common genetic variants that influence fish and dietary eicosapentaenoic acid plus docosahexaenoic acid (EPA+DHA) consumption. DESIGN: We conducted genome-wide association (GWA) meta-analysis of fish (n = 86,467) and EPA+DHA (n = 62,265) consumption in 17 cohorts of European descent from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium Nutrition Working Group. Results from cohort-specific GWA analyses (additive model) for fish and EPA+DHA consumption were adjusted for age, sex, energy intake, and population stratification, and meta-analyzed separately using fixed-effect meta-analysis with inverse variance weights (METAL software). Additionally, heritability was estimated in 2 cohorts. RESULTS: Heritability estimates for fish and EPA+DHA consumption ranged from 0.13-0.24 and 0.12-0.22, respectively. A significant GWA for fish intake was observed for rs9502823 on chromosome 6: each copy of the minor allele (FreqA = 0.015) was associated with 0.029 servings/day (~1 serving/month) lower fish consumption (P = 1.96x10-8). No significant association was observed for EPA+DHA, although rs7206790 in the obesity-associated FTO gene was among top hits (P = 8.18x10-7). Post-hoc calculations demonstrated 95% statistical power to detect a genetic variant associated with effect size of 0.05% for fish and 0.08% for EPA+DHA. CONCLUSIONS: These novel findings suggest that non-genetic personal and environmental factors are principal determinants of the remarkable variation in fish consumption, representing modifiable targets for increasing intakes among all individuals. Genes underlying the signal at rs72838923 and mechanisms for the association warrant further investigation.
Keywords: Adult; Aged; Cohort Studies; Docosahexaenoic Acids; Eicosapentaenoic Acid; Europe; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Seafood; United States

Omega-3 Fatty Acids and Incident Ischemic Stroke and Its Atherothrombotic and Cardioembolic Subtypes in 3 US Cohorts. - Saber, Hamidreza; Yakoob, Mohammad Yawar; Shi, Peilin; Longstreth, W T; Lemaitre, Rozenn N; Siscovick, David; Rexrode, Kathryn M; Willett, Walter C; Mozaffarian, Dariush (Stroke, 2017)
BACKGROUND AND PURPOSE: The associations of individual long-chain n-3 polyunsaturated fatty acids with incident ischemic stroke and its main subtypes are not well established. We aimed to investigate prospectively the relationship of circulating eicosapentaenoic acid, docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) with risk of total ischemic, atherothrombotic, and cardioembolic stroke. METHODS: We measured circulating phospholipid fatty acids at baseline in 3 separate US cohorts: CHS (Cardiovascular Health Study), NHS (Nurses' Health Study), and HPFS (Health Professionals Follow-Up Study). Ischemic strokes were prospectively adjudicated and classified into atherothrombotic (large- and small-vessel infarctions) or cardioembolic by imaging studies and medical records. Risk according to fatty acid levels was assessed using Cox proportional hazards (CHS) or conditional logistic regression (NHS, HPFS) according to study design. Cohort findings were pooled using fixed-effects meta-analysis. RESULTS: A total of 953 incident ischemic strokes were identified (408 atherothrombotic, 256 cardioembolic, and 289 undetermined subtypes) during median follow-up of 11.2 years (CHS) and 8.3 years (pooled, NHS and HPFS). After multivariable adjustment, lower risk of total ischemic stroke was seen with higher DPA (highest versus lowest quartiles; pooled hazard ratio [HR], 0.74; 95% confidence interval [CI], 0.58-0.92) and DHA (HR, 0.80; 95% CI, 0.64-1.00) but not eicosapentaenoic acid (HR, 0.94; 95% CI, 0.77-1.19). DHA was associated with lower risk of atherothrombotic stroke (HR, 0.53; 95% CI, 0.34-0.83) and DPA with lower risk of cardioembolic stroke (HR, 0.58; 95% CI, 0.37-0.92). Findings in each individual cohort were consistent with pooled results. CONCLUSIONS: In 3 large US cohorts, higher circulating levels of DHA were inversely associated with incident atherothrombotic stroke and DPA with cardioembolic stroke. These novel findings suggest differential pathways of benefit for DHA, DPA, and eicosapentaenoic acid.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers; Brain Ischemia; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Incidence; Intracranial Arteriosclerosis; Intracranial Embolism; Intracranial Thrombosis; Male; Middle Aged; Prospective Studies; Random Allocation; Risk Factors; Stroke; United States

Short telomere length is associated with impaired cognitive performance in European ancestry cohorts. - Hägg, S; Zhan, Y; Karlsson, R; Gerritsen, L; Ploner, A; van der Lee, S J; Broer, L; Deelen, J; Marioni, R E; Wong, A; Lundquist, A; Zhu, G; et al. (Transl Psychiatry, 2017)
The association between telomere length (TL) dynamics on cognitive performance over the life-course is not well understood. This study meta-analyses observational and causal associations between TL and six cognitive traits, with stratifications on APOE genotype, in a Mendelian Randomization (MR) framework. Twelve European cohorts (N=17 052; mean age=59.2±8.8 years) provided results for associations between qPCR-measured TL (T/S-ratio scale) and general cognitive function, mini-mental state exam (MMSE), processing speed by digit symbol substitution test (DSST), visuospatial functioning, memory and executive functioning (STROOP). In addition, a genetic risk score (GRS) for TL including seven known genetic variants for TL was calculated, and used in associations with cognitive traits as outcomes in all cohorts. Observational analyses showed that longer telomeres were associated with better scores on DSST (β=0.051 per s.d.-increase of TL; 95% confidence interval (CI): 0.024, 0.077; P=0.0002), and MMSE (β=0.025; 95% CI: 0.002, 0.047; P=0.03), and faster STROOP (β=-0.053; 95% CI: -0.087, -0.018; P=0.003). Effects for DSST were stronger in APOE ɛ4 non-carriers (β=0.081; 95% CI: 0.045, 0.117; P=1.0 × 10-5), whereas carriers performed better in STROOP (β=-0.074; 95% CI: -0.140, -0.009; P=0.03). Causal associations were found for STROOP only (β=-0.598 per s.d.-increase of TL; 95% CI: -1.125, -0.072; P=0.026), with a larger effect in ɛ4-carriers (β=-0.699; 95% CI: -1.330, -0.069; P=0.03). Two-sample replication analyses using CHARGE summary statistics showed causal effects between TL and general cognitive function and DSST, but not with STROOP. In conclusion, we suggest causal effects from longer TL on better cognitive performance, where APOE ɛ4-carriers might be at differential risk.
Keywords: Adult; Aged; Apolipoprotein E4; Cognitive Dysfunction; Cohort Studies; European Continental Ancestry Group; Female; Genetic Carrier Screening; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neuropsychological Tests; Psychometrics; Statistics as Topic; Telomere

Thyroid Function Within the Normal Range, Subclinical Hypothyroidism, and the Risk of Atrial Fibrillation. - Baumgartner, Christine; da Costa, Bruno R; Collet, Tinh-Hai; Feller, Martin; Floriani, Carmen; Bauer, Douglas C; Cappola, Anne R; Heckbert, Susan R; Ceresini, Graziano; Gussekloo, Jacobijn; den Elzen, Wendy P J; Peeters, Robin P; et al. (Circulation, 2017)
BACKGROUND: Atrial fibrillation (AF) is a highly prevalent disorder leading to heart failure, stroke, and death. Enhanced understanding of modifiable risk factors may yield opportunities for prevention. The risk of AF is increased in subclinical hyperthyroidism, but it is uncertain whether variations in thyroid function within the normal range or subclinical hypothyroidism are also associated with AF. METHODS: We conducted a systematic review and obtained individual participant data from prospective cohort studies that measured thyroid function at baseline and assessed incident AF. Studies were identified from MEDLINE and EMBASE databases from inception to July 27, 2016. The euthyroid state was defined as thyroid-stimulating hormone (TSH) 0.45 to 4.49 mIU/L, and subclinical hypothyroidism as TSH 4.5 to 19.9 mIU/L with free thyroxine (fT4) levels within reference range. The association of TSH levels in the euthyroid and subclinical hypothyroid range with incident AF was examined by using Cox proportional hazards models. In euthyroid participants, we additionally examined the association between fT4 levels and incident AF. RESULTS: Of 30 085 participants from 11 cohorts (278 955 person-years of follow-up), 1958 (6.5%) had subclinical hypothyroidism and 2574 individuals (8.6%) developed AF during follow-up. TSH at baseline was not significantly associated with incident AF in euthyroid participants or those with subclinical hypothyroidism. Higher fT4 levels at baseline in euthyroid individuals were associated with increased AF risk in age- and sex-adjusted analyses (hazard ratio, 1.45; 95% confidence interval, 1.26-1.66, for the highest quartile versus the lowest quartile of fT4; P for trend ≤0.001 across quartiles). Estimates did not substantially differ after further adjustment for preexisting cardiovascular disease. CONCLUSIONS: In euthyroid individuals, higher circulating fT4 levels, but not TSH levels, are associated with increased risk of incident AF.
Keywords: Adult; Aged; Aged, 80 and over; Asymptomatic Diseases; Atrial Fibrillation; Biomarkers; Chi-Square Distribution; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Time Factors; Young Adult

Fatty acid biomarkers of dairy fat consumption and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies. - Imamura, Fumiaki; Fretts, Amanda; Marklund, Matti; Ardisson Korat, Andres V; Yang, Wei-Sin; Lankinen, Maria; Qureshi, Waqas; Helmer, Catherine; Chen, Tzu-An; Wong, Kerry; Bassett, Julie K; Murphy, Rachel; et al. (PLoS Med, 2018)
BACKGROUND: We aimed to investigate prospective associations of circulating or adipose tissue odd-chain fatty acids 15:0 and 17:0 and trans-palmitoleic acid, t16:1n-7, as potential biomarkers of dairy fat intake, with incident type 2 diabetes (T2D). METHODS AND FINDINGS: Sixteen prospective cohorts from 12 countries (7 from the United States, 7 from Europe, 1 from Australia, 1 from Taiwan) performed new harmonised individual-level analysis for the prospective associations according to a standardised plan. In total, 63,682 participants with a broad range of baseline ages and BMIs and 15,180 incident cases of T2D over the average of 9 years of follow-up were evaluated. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Prespecified interactions by age, sex, BMI, and race/ethnicity were explored in each cohort and were meta-analysed. Potential heterogeneity by cohort-specific characteristics (regions, lipid compartments used for fatty acid assays) was assessed with metaregression. After adjustment for potential confounders, including measures of adiposity (BMI, waist circumference) and lipogenesis (levels of palmitate, triglycerides), higher levels of 15:0, 17:0, and t16:1n-7 were associated with lower incidence of T2D. In the most adjusted model, the hazard ratio (95% CI) for incident T2D per cohort-specific 10th to 90th percentile range of 15:0 was 0.80 (0.73-0.87); of 17:0, 0.65 (0.59-0.72); of t16:1n7, 0.82 (0.70-0.96); and of their sum, 0.71 (0.63-0.79). In exploratory analyses, similar associations for 15:0, 17:0, and the sum of all three fatty acids were present in both genders but stronger in women than in men (pinteraction < 0.001). Whereas studying associations with biomarkers has several advantages, as limitations, the biomarkers do not distinguish between different food sources of dairy fat (e.g., cheese, yogurt, milk), and residual confounding by unmeasured or imprecisely measured confounders may exist. CONCLUSIONS: In a large meta-analysis that pooled the findings from 16 prospective cohort studies, higher levels of 15:0, 17:0, and t16:1n-7 were associated with a lower risk of T2D.
Keywords: Aged; Australia; Biomarkers; Dairy Products; Diabetes Mellitus, Type 2; Dietary Fats; Europe; Fatty Acids; Fatty Acids, Monounsaturated; Female; Humans; Incidence; Male; Middle Aged; Prospective Studies; Sex Factors; Taiwan; United States

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Protein and glycomic plasma markers for early detection of adenoma and colon cancer. - Rho, Jung-Hyun; Ladd, Jon J; Li, Christopher I; Potter, John D; Zhang, Yuzheng; Shelley, David; Shibata, David; Coppola, Domenico; Yamada, Hiroyuki; Toyoda, Hidenori; Tada, Toshifumi; Kumada, Takashi; et al. (Gut, 2018)
OBJECTIVE: To discover and confirm blood-based colon cancer early-detection markers. DESIGN: We created a high-density antibody microarray to detect differences in protein levels in plasma from individuals diagnosed with colon cancer <3 years after blood was drawn (ie, prediagnostic) and cancer-free, matched controls. Potential markers were tested on plasma samples from people diagnosed with adenoma or cancer, compared with controls. Components of an optimal 5-marker panel were tested via immunoblotting using a third sample set, Luminex assay in a large fourth sample set and immunohistochemistry (IHC) on tissue microarrays. RESULTS: In the prediagnostic samples, we found 78 significantly (t-test) increased proteins, 32 of which were confirmed in the diagnostic samples. From these 32, optimal 4-marker panels of BAG family molecular chaperone regulator 4 (BAG4), interleukin-6 receptor subunit beta (IL6ST), von Willebrand factor (VWF) and CD44 or epidermal growth factor receptor (EGFR) were established. Each panel member and the panels also showed increases in the diagnostic adenoma and cancer samples in independent third and fourth sample sets via immunoblot and Luminex, respectively. IHC results showed increased levels of BAG4, IL6ST and CD44 in adenoma and cancer tissues. Inclusion of EGFR and CD44 sialyl Lewis-A and Lewis-X content increased the panel performance. The protein/glycoprotein panel was statistically significantly higher in colon cancer samples, characterised by a range of area under the curves from 0.90 (95% CI 0.82 to 0.98) to 0.86 (95% CI 0.83 to 0.88), for the larger second and fourth sets, respectively. CONCLUSIONS: A panel including BAG4, IL6ST, VWF, EGFR and CD44 protein/glycomics performed well for detection of early stages of colon cancer and should be further examined in larger studies.
Keywords: Adaptor Proteins, Signal Transducing; Adenoma; Adult; Aged; Aged, 80 and over; Biomarkers, Tumor; CA-19-9 Antigen; Case-Control Studies; Colonic Neoplasms; Cytokine Receptor gp130; Early Detection of Cancer; ErbB Receptors; Female; Humans; Hyaluronan Receptors; Lewis X Antigen; Male; Middle Aged; Oligosaccharides; Protein Array Analysis; von Willebrand Factor

Associations of variants In the hexokinase 1 and interleukin 18 receptor regions with oxyhemoglobin saturation during sleep. - Cade, Brian E; Chen, Han; Stilp, Adrienne M; Louie, Tin; Ancoli-Israel, Sonia; Arens, Raanan; Barfield, Richard; Below, Jennifer E; Cai, Jianwen; Conomos, Matthew P; Evans, Daniel S; Frazier-Wood, Alexis C; et al. (PLoS Genet, 2019)
Sleep disordered breathing (SDB)-related overnight hypoxemia is associated with cardiometabolic disease and other comorbidities. Understanding the genetic bases for variations in nocturnal hypoxemia may help understand mechanisms influencing oxygenation and SDB-related mortality. We conducted genome-wide association tests across 10 cohorts and 4 populations to identify genetic variants associated with three correlated measures of overnight oxyhemoglobin saturation: average and minimum oxyhemoglobin saturation during sleep and the percent of sleep with oxyhemoglobin saturation under 90%. The discovery sample consisted of 8,326 individuals. Variants with p < 1 × 10(-6) were analyzed in a replication group of 14,410 individuals. We identified 3 significantly associated regions, including 2 regions in multi-ethnic analyses (2q12, 10q22). SNPs in the 2q12 region associated with minimum SpO2 (rs78136548 p = 2.70 × 10(-10)). SNPs at 10q22 were associated with all three traits including average SpO2 (rs72805692 p = 4.58 × 10(-8)). SNPs in both regions were associated in over 20,000 individuals and are supported by prior associations or functional evidence. Four additional significant regions were detected in secondary sex-stratified and combined discovery and replication analyses, including a region overlapping Reelin, a known marker of respiratory complex neurons.These are the first genome-wide significant findings reported for oxyhemoglobin saturation during sleep, a phenotype of high clinical interest. Our replicated associations with HK1 and IL18R1 suggest that variants in inflammatory pathways, such as the biologically-plausible NLRP3 inflammasome, may contribute to nocturnal hypoxemia.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cell Adhesion Molecules, Neuronal; Computational Biology; Extracellular Matrix Proteins; Female; Gene Regulatory Networks; Genetic Variation; Genome-Wide Association Study; Hexokinase; Humans; Hypoxia; Interleukin-18 Receptor alpha Subunit; Male; Middle Aged; Nerve Tissue Proteins; NLR Family, Pyrin Domain-Containing 3 Protein; Oxygen; Oxyhemoglobins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Serine Endopeptidases; Sleep; Sleep Apnea Syndromes; Young Adult

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

Discriminative Accuracy of FEV1:FVC Thresholds for COPD-Related Hospitalization and Mortality. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Cassano, Patricia A; Couper, David; Jacobs, David R; Kalhan, Ravi; O'Connor, George T; Yende, Sachin; Sanders, Jason L; Umans, Jason G; Dransfield, Mark T; et al. (JAMA, 2019)
Importance: According to numerous current guidelines, the diagnosis of chronic obstructive pulmonary disease (COPD) requires a ratio of the forced expiratory volume in the first second to the forced vital capacity (FEV1:FVC) of less than 0.70, yet this fixed threshold is based on expert opinion and remains controversial. Objective: To determine the discriminative accuracy of various FEV1:FVC fixed thresholds for predicting COPD-related hospitalization and mortality. Design, Setting, and Participants: The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 4 US general population-based cohorts (Atherosclerosis Risk in Communities Study; Cardiovascular Health Study; Health, Aging, and Body Composition Study; and Multi-Ethnic Study of Atherosclerosis). Participants aged 45 to 102 years were enrolled from 1987 to 2000 and received follow-up longitudinally through 2016. Exposures: Presence of airflow obstruction, which was defined by a baseline FEV1:FVC less than a range of fixed thresholds (0.75 to 0.65) or less than the lower limit of normal as defined by Global Lung Initiative reference equations (LLN). Main Outcomes and Measures: The primary outcome was a composite of COPD hospitalization and COPD-related mortality, defined by adjudication or administrative criteria. The optimal fixed FEV1:FVC threshold was defined by the best discrimination for these COPD-related events as indexed using the Harrell C statistic from unadjusted Cox proportional hazards models. Differences in C statistics were compared with respect to less than 0.70 and less than LLN thresholds using a nonparametric approach. Results: Among 24 207 adults in the pooled cohort (mean [SD] age at enrollment, 63 [10.5] years; 12 990 [54%] women; 16 794 [69%] non-Hispanic white; 15 181 [63%] ever smokers), complete follow-up was available for 11 077 (77%) at 15 years. During a median follow-up of 15 years, 3925 participants experienced COPD-related events over 340 757 person-years of follow-up (incidence density rate, 11.5 per 1000 person-years), including 3563 COPD-related hospitalizations and 447 COPD-related deaths. With respect to discrimination of COPD-related events, the optimal fixed threshold (0.71; C statistic for optimal fixed threshold, 0.696) was not significantly different from the 0.70 threshold (difference, 0.001 [95% CI, -0.002 to 0.004]) but was more accurate than the LLN threshold (difference, 0.034 [95% CI, 0.028 to 0.041]). The 0.70 threshold provided optimal discrimination in the subgroup analysis of ever smokers and in adjusted models. Conclusions and Relevance: Defining airflow obstruction as FEV1:FVC less than 0.70 provided discrimination of COPD-related hospitalization and mortality that was not significantly different or was more accurate than other fixed thresholds and the LLN. These results support the use of FEV1:FVC less than 0.70 to identify individuals at risk of clinically significant COPD.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Forced Expiratory Volume; Hospitalization; Humans; Male; Middle Aged; Prognosis; Proportional Hazards Models; Pulmonary Disease, Chronic Obstructive; Risk Assessment; Vital Capacity

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

Association of Genetic Variation With Keratoconus. - McComish, Bennet J; Sahebjada, Srujana; Bykhovskaya, Yelena; Willoughby, Colin E; Richardson, Andrea J; Tenen, Abi; Charlesworth, Jac C; Macgregor, Stuart; Mitchell, Paul; Lucas, Sionne E M; Mills, Richard A; Mackey, David A; et al. (JAMA Ophthalmol, 2020)
Importance: Keratoconus is a condition in which the cornea progressively thins and protrudes in a conical shape, severely affecting refraction and vision. It is a major indication for corneal transplant. To discover new genetic loci associated with keratoconus and better understand the causative mechanism of this disease, we performed a genome-wide association study on patients with keratoconus. Objective: To identify genetic susceptibility regions for keratoconus in the human genome. Design, Setting, and Participants: This study was conducted with data from eye clinics in Australia, the United States, and Northern Ireland. The discovery cohort of individuals with keratoconus and control participants from Australia was genotyped using the Illumina HumanCoreExome single-nucleotide polymorphism array. After quality control and data cleaning, genotypes were imputed against the 1000 Genomes Project reference panel (phase III; version 5), and association analyses were completed using PLINK version 1.90. Single-nucleotide polymorphisms with P < 1.00 × 10-6 were assessed for replication in 3 additional cohorts. Control participants were drawn from the cohorts of the Blue Mountains Eye Study and a previous study of glaucoma. Replication cohorts were from a previous keratoconus genome-wide association study data set from the United States, a cohort of affected and control participants from Australia and Northern Ireland, and a case-control cohort from Victoria, Australia. Data were collected from January 2006 to March 2019. Main Outcomes and Measures: Associations between keratoconus and 6 252 612 genetic variants were estimated using logistic regression after adjusting for ancestry using the first 3 principal components. Results: The discovery cohort included 522 affected individuals and 655 control participants, while the replication cohorts included 818 affected individuals (222 from the United States, 331 from Australia and Northern Ireland, and 265 from Victoria, Australia) and 3858 control participants (2927 from the United States, 229 from Australia and Northern Ireland, and 702 from Victoria, Australia). Two novel loci reached genome-wide significance (defined as P < 5.00 × 10-8), with a P value of 7.46 × 10-9 at rs61876744 in patatin-like phospholipase domain-containing 2 gene (PNPLA2) on chromosome 11 and a P value of 6.35 × 10-12 at rs138380, 2.2 kb upstream of casein kinase I isoform epsilon gene (CSNK1E) on chromosome 22. One additional locus was identified with a P value less than 1.00 × 10-6 in mastermind-like transcriptional coactivator 2 (MAML2) on chromosome 11 (P = 3.91 × 10-7). The novel locus in PNPLA2 reached genome-wide significance in an analysis of all 4 cohorts (P = 2.45 × 10-8). Conclusions and Relevance: In this relatively large keratoconus genome-wide association study, we identified a genome-wide significant locus for keratoconus in the region of PNPLA2 on chromosome 11.
Keywords: Adult; Female; Fuchs' Endothelial Dystrophy; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Keratoconus; Lipase; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide

Association of Nonobstructive Chronic Bronchitis With Respiratory Health Outcomes in Adults. - Balte, Pallavi P; Chaves, Paulo H M; Couper, David J; Enright, Paul; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard A; Loehr, Laura R; London, Stephanie J; Newman, Anne B; O'Connor, George T; Schwartz, Joseph E; et al. (JAMA Intern Med, 2020)
Importance: Chronic bronchitis has been associated with cigarette smoking as well as with e-cigarette use among young adults, but the association of chronic bronchitis in persons without airflow obstruction or clinical asthma, described as nonobstructive chronic bronchitis, with respiratory health outcomes remains uncertain. Objective: To assess whether nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes in adult ever smokers and never smokers. Design, Setting, and Participants: This prospective cohort study included 22 325 adults without initial airflow obstruction (defined as the ratio of forced expiratory volume in the first second [FEV1] to forced vital capacity [FVC] of <0.70) or clinical asthma at baseline. The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 9 US general population-based cohorts. Thus present study is based on data from 5 of these cohorts. Participants were enrolled from August 1971 through May 2007 and were followed up through December 2018. Exposures: Nonobstructive chronic bronchitis was defined by questionnaire at baseline as both cough and phlegm for at least 3 months for at least 2 consecutive years. Main Outcomes and Measures: Lung function was measured by prebronchodilator spirometry. Hospitalizations and deaths due to chronic lower respiratory disease and respiratory disease-related mortality were defined by events adjudication and administrative criteria. Models were stratified by smoking status and adjusted for anthropometric, sociodemographic, and smoking-related factors. The comparison group was participants without nonobstructive chronic bronchitis. Results: Among 22 325 adults included in the analysis, mean (SD) age was 53.0 (16.3) years (range, 18.0-95.0 years), 58.2% were female, 65.9% were non-Hispanic white, and 49.6% were ever smokers. Among 11 082 ever smokers with 99 869 person-years of follow-up, participants with nonobstructive chronic bronchitis (300 [2.7%]) had accelerated decreases in FEV1 (4.1 mL/y; 95% CI, 2.1-6.1 mL/y) and FVC (4.7 mL/y; 95% CI, 2.2-7.2 mL/y), increased risks of chronic lower respiratory disease-related hospitalization or mortality (hazard ratio [HR], 2.2; 95% CI, 1.7-2.7), and greater respiratory disease-related (HR, 2.0; 95% CI, 1.1-3.8) and all-cause mortality (HR, 1.5; 95% CI, 1.3-1.8) compared with ever smokers without nonobstructive chronic bronchitis. Among 11 243 never smokers with 120 004 person-years of follow-up, participants with nonobstructive chronic bronchitis (151 [1.3%]) had greater rates of chronic lower respiratory disease-related hospitalization or mortality (HR, 3.1; 95% CI, 2.1-4.5) compared with never smokers without nonobstructive chronic bronchitis. Nonobstructive chronic bronchitis was not associated with FEV1:FVC decline or incident airflow obstruction. The presence of at least 1 of the component symptoms of nonobstructive chronic bronchitis (ie, chronic cough or phlegm), which was common in both ever smokers (11.0%) and never smokers (6.7%), was associated with adverse respiratory health outcomes. Conclusions and Relevance: The findings suggest that nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes, particularly in ever smokers, and may be a high-risk phenotype suitable for risk stratification and targeted therapies.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asthma; Bronchitis, Chronic; Female; Humans; Lung; Male; Middle Aged; Prospective Studies; Respiratory Function Tests; Smokers; Smoking; Young Adult

Chronic obstructive pulmonary disease and related phenotypes: polygenic risk scores in population-based and case-control cohorts. - Moll, Matthew; Sakornsakolpat, Phuwanat; Shrine, Nick; Hobbs, Brian D; DeMeo, Dawn L; John, Catherine; Guyatt, Anna L; McGeachie, Michael J; Gharib, Sina A; Obeidat, Ma'en; Lahousse, Lies; Wijnant, Sara R A; et al. (Lancet Respir Med, 2020)
BACKGROUND: Genetic factors influence chronic obstructive pulmonary disease (COPD) risk, but the individual variants that have been identified have small effects. We hypothesised that a polygenic risk score using additional variants would predict COPD and associated phenotypes. METHODS: We constructed a polygenic risk score using a genome-wide association study of lung function (FEV and FEV/forced vital capacity [FVC]) from the UK Biobank and SpiroMeta. We tested this polygenic risk score in nine cohorts of multiple ethnicities for an association with moderate-to-severe COPD (defined as FEV/FVC <0·7 and FEV <80% of predicted). Associations were tested using logistic regression models, adjusting for age, sex, height, smoking pack-years, and principal components of genetic ancestry. We assessed predictive performance of models by area under the curve. In a subset of studies, we also studied quantitative and qualitative CT imaging phenotypes that reflect parenchymal and airway pathology, and patterns of reduced lung growth. FINDINGS: The polygenic risk score was associated with COPD in European (odds ratio [OR] per SD 1·81 [95% CI 1·74-1·88] and non-European (1·42 [1·34-1·51]) populations. Compared with the first decile, the tenth decile of the polygenic risk score was associated with COPD, with an OR of 7·99 (6·56-9·72) in European ancestry and 4·83 (3·45-6·77) in non-European ancestry cohorts. The polygenic risk score was superior to previously described genetic risk scores and, when combined with clinical risk factors (ie, age, sex, and smoking pack-years), showed improved prediction for COPD compared with a model comprising clinical risk factors alone (AUC 0·80 [0·79-0·81] vs 0·76 [0·75-0·76]). The polygenic risk score was associated with CT imaging phenotypes, including wall area percent, quantitative and qualitative measures of emphysema, local histogram emphysema patterns, and destructive emphysema subtypes. The polygenic risk score was associated with a reduced lung growth pattern. INTERPRETATION: A risk score comprised of genetic variants can identify a small subset of individuals at markedly increased risk for moderate-to-severe COPD, emphysema subtypes associated with cigarette smoking, and patterns of reduced lung growth. FUNDING: US National Institutes of Health, Wellcome Trust.
Keywords: Adult; Case-Control Studies; Cohort Studies; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Phenotype; Pulmonary Disease, Chronic Obstructive; Risk Factors; Vital Capacity

A Dyadic Growth Modeling Approach for Examining Associations Between Weight Gain and Lung Function Decline. - Cornelius, Talea; Schwartz, Joseph E; Balte, Pallavi; Bhatt, Surya P; Cassano, Patricia A; Currow, David; Jacobs, David R; Johnson, Miriam; Kalhan, Ravi; Kronmal, Richard; Loehr, Laura; O'Connor, George T; et al. (Am J Epidemiol, 2020)
The relationship between body weight and lung function is complex. Using a dyadic multilevel linear modeling approach, treating body mass index (BMI; weight (kg)/height (m)2) and lung function as paired, within-person outcomes, we tested the hypothesis that persons with more rapid increase in BMI exhibit more rapid decline in lung function, as measured by forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and their ratio (FEV1:FVC). Models included random intercepts and slopes and adjusted for sociodemographic and smoking-related factors. A sample of 9,115 adults with paired measurements of BMI and lung function taken at ≥3 visits were selected from a pooled set of 5 US population-based cohort studies (1983-2018; mean age at baseline = 46 years; median follow-up, 19 years). At age 46 years, average annual rates of change in BMI, FEV1, FVC, and FEV1:FVC ratio were 0.22 kg/m2/year, -25.50 mL/year, -21.99 mL/year, and -0.24%/year, respectively. Persons with steeper BMI increases had faster declines in FEV1 (r = -0.16) and FVC (r = -0.26) and slower declines in FEV1:FVC ratio (r = 0.11) (all P values < 0.0001). Results were similar in subgroup analyses. Residual correlations were negative (P < 0.0001), suggesting additional interdependence between BMI and lung function. Results show that greater rates of weight gain are associated with greater rates of lung function loss.
Keywords: Adult; Aged; Body Mass Index; Cohort Studies; Humans; Linear Models; Lung; Middle Aged; Respiratory Function Tests; Weight Gain

Lung function decline in former smokers and low-intensity current smokers: a secondary data analysis of the NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Folsom, Aaron R; Freedman, Neal D; Jacobs, David R; Kalhan, Ravi; Mathew, Amanda R; Kronmal, Richard A; Loehr, Laura R; et al. (Lancet Respir Med, 2020)
BACKGROUND: Former smokers now outnumber current smokers in many developed countries, and current smokers are smoking fewer cigarettes per day. Some data suggest that lung function decline normalises with smoking cessation; however, mechanistic studies suggest that lung function decline could continue. We hypothesised that former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers, including among those without prevalent lung disease. METHODS: We used data on six US population-based cohorts included in the NHLBI Pooled Cohort Study. We restricted the sample to participants with valid spirometry at two or more exams. Two cohorts recruited younger adults (≥17 years), two recruited middle-aged and older adults (≥45 years), and two recruited only elderly adults (≥65 years) with examinations done between 1983 and 2014. FEV decline in sustained former smokers and current smokers was compared to that of never-smokers by use of mixed models adjusted for sociodemographic and anthropometric factors. Differential FEV decline was also evaluated according to duration of smoking cessation and cumulative (number of pack-years) and current (number of cigarettes per day) cigarette consumption. FINDINGS: 25 352 participants (ages 17-93 years) completed 70 228 valid spirometry exams. Over a median follow-up of 7 years (IQR 3-20), FEV decline at the median age (57 years) was 31·01 mL per year (95% CI 30·66-31·37) in sustained never-smokers, 34·97 mL per year (34·36-35·57) in former smokers, and 39·92 mL per year (38·92-40·92) in current smokers. With adjustment, former smokers showed an accelerated FEV decline of 1·82 mL per year (95% CI 1·24-2·40) compared to never-smokers, which was approximately 20% of the effect estimate for current smokers (9·21 mL per year; 95% CI 8·35-10·08). Compared to never-smokers, accelerated FEV decline was observed in former smokers for decades after smoking cessation and in current smokers with low cumulative cigarette consumption (<10 pack-years). With respect to current cigarette consumption, the effect estimate for FEV decline in current smokers consuming less than five cigarettes per day (7·65 mL per year; 95% CI 6·21-9·09) was 68% of that in current smokers consuming 30 or more cigarettes per day (11·24 mL per year; 9·86-12·62), and around five times greater than in former smokers (1·57 mL per year; 1·00-2·14). Among participants without prevalent lung disease, associations were attenuated but were consistent with the main results. INTERPRETATION: Former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers. These results suggest that all levels of smoking exposure are likely to be associated with lasting and progressive lung damage. FUNDING: National Institutes of Health, National Heart Lung and Blood Institute, and US Environmental Protection Agency.
Keywords: Adult; Aged; Case-Control Studies; Ex-Smokers; Female; Follow-Up Studies; Humans; Lung; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Non-Smokers; Respiratory Physiological Phenomena; Smokers; Smoking; Spirometry; United States; Young Adult

Performance of the Pooled Cohort Equations to Estimate Atherosclerotic Cardiovascular Disease Risk by Body Mass Index. - Khera, Rohan; Pandey, Ambarish; Ayers, Colby R; Carnethon, Mercedes R; Greenland, Philip; Ndumele, Chiadi E; Nambi, Vijay; Seliger, Stephen L; Chaves, Paulo H M; Safford, Monika M; Cushman, Mary; Xanthakis, Vanessa; et al. (JAMA Netw Open, 2020)
Importance: Obesity is a global health challenge and a risk factor for atherosclerotic cardiovascular disease (ASVCD). Performance of the pooled cohort equations (PCE) for ASCVD risk by body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) is unknown. Objective: To assess performance of the PCE across clinical BMI categories. Design, Setting, and Participants: This cohort study used pooled individual-level data from 8 community-based, prospective, longitudinal cohort studies with 10-year ASCVD event follow-up from 1996 to 2016. We included all adults ages 40 to 79 years without baseline ASCVD or statin use, resulting in a sample size of 37 311 participants. Data were analyzed from August 2017 to July 2020. Exposures: Participant BMI category: underweight (<18.5), normal weight (18.5 to <25), overweight (25 to <30), mild obesity (30 to <35), and moderate to severe obesity (≥35). Main Outcomes and Measures: Discrimination (Harrell C statistic) and calibration (Nam-D'Agostino χ2 goodness-of-fit test) of the PCE across BMI categories. Improvement in discrimination and net reclassification with addition of BMI, waist circumference, and high-sensitivity C-reactive protein (hsCRP) to the PCE. Results: Among 37 311 participants (mean [SD] age, 58.6 [11.8] years; 21 897 [58.7%] women), 380 604 person-years of follow-up were conducted. Mean (SD) baseline BMI was 29.0 (6.2), and 360 individuals (1.0%) were in the underweight category, 9937 individuals (26.6%) were in the normal weight category, 13 601 individuals (36.4%) were in the overweight category, 7783 individuals (20.9%) were in the mild obesity category, and 5630 individuals (15.1%) were in the moderate to severe obesity category. Median (interquartile range [IQR]) 10-year estimated ASCVD risk was 7.1% (2.5%-15.4%), and 3709 individuals (9.9%) developed ASCVD over a median (IQR) 10.8 [8.5-12.6] years. The PCE overestimated ASCVD risk in the overall cohort (estimated/observed [E/O] risk ratio, 1.22; 95% CI, 1.18-1.26) and across all BMI categories except the underweight category. Calibration was better near the clinical decision threshold in all BMI groups but worse among individuals with moderate or severe obesity (E/O risk ratio, 1.36; 95% CI, 1.25-1.47) and among those with the highest estimated ASCVD risk ≥20%. The PCE C statistic overall was 0.760 (95% CI, 0.753-0.767), with lower discrimination in the moderate or severe obesity group (C statistic, 0.742; 95% CI, 0.721-0.763) compared with the normal-range BMI group (C statistic, 0.785; 95% CI, 0.772-0.798). Waist circumference (hazard ratio, 1.07 per 1-SD increase; 95% CI, 1.03-1.11) and hsCRP (hazard ratio, 1.07 per 1-SD increase; 95% CI, 1.05-1.09), but not BMI, were associated with increased ASCVD risk when added to the PCE. However, these factors did not improve model performance (C statistic, 0.760; 95% CI, 0.753-0.767) with or without added metrics. Conclusions and Relevance: These findings suggest that the PCE had acceptable model discrimination and were well calibrated at clinical decision thresholds but overestimated risk of ASCVD for individuals in overweight and obese categories, particularly individuals with high estimated risk. Incorporation of the usual clinical measures of obesity did not improve risk estimation of the PCE. Future research is needed to determine whether incorporation of alternative high-risk obesity markers (eg, weight trajectory or measures of visceral or ectopic fat) into the PCE may improve risk prediction.
Keywords: Adult; Aged; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Correlation of Data; Female; Humans; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Association Between Preserved Ratio Impaired Spirometry and Clinical Outcomes in US Adults. - Wan, Emily S; Balte, Pallavi; Schwartz, Joseph E; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Daviglus, Martha L; Dransfield, Mark T; Gharib, Sina A; Jacobs, David R; Kalhan, Ravi; London, Stephanie J; et al. (JAMA, 2021)
Importance: Chronic lung diseases are a leading cause of morbidity and mortality. Unlike chronic obstructive pulmonary disease, clinical outcomes associated with proportional reductions in expiratory lung volumes without obstruction, otherwise known as preserved ratio impaired spirometry (PRISm), are poorly understood. Objective: To examine the prevalence, correlates, and clinical outcomes associated with PRISm in US adults. Design, Setting, and Participants: The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study was a retrospective study with harmonized pooled data from 9 US general population-based cohorts (enrollment, 65 251 participants aged 18 to 102 years of whom 53 701 participants had valid baseline lung function) conducted from 1971-2011 (final follow-up, December 2018). Exposures: Participants were categorized into mutually exclusive groups by baseline lung function. PRISm was defined as the ratio of forced expiratory volume in the first second to forced vital capacity (FEV1:FVC) greater than or equal to 0.70 and FEV1 less than 80% predicted; obstructive spirometry FEV1:FVC ratio of less than 0.70; and normal spirometry FEV1:FVC ratio greater than or equal to 0.7 and FEV1 greater than or equal to 80% predicted. Main Outcomes and Measures: Main outcomes were all-cause mortality, respiratory-related mortality, coronary heart disease (CHD)-related mortality, respiratory-related events (hospitalizations and mortality), and CHD-related events (hospitalizations and mortality) classified by adjudication or validated administrative criteria. Absolute risks were adjusted for age and smoking status. Poisson and Cox proportional hazards models comparing PRISm vs normal spirometry were adjusted for age, sex, race and ethnicity, education, body mass index, smoking status, cohort, and comorbidities. Results: Among all participants (mean [SD] age, 53.2 [15.8] years, 56.4% women, 48.5% never-smokers), 4582 (8.5%) had PRISm. The presence of PRISm relative to normal spirometry was significantly associated with obesity (prevalence, 48.3% vs 31.4%; prevalence ratio [PR], 1.68 [95% CI, 1.55-1.82]), underweight (prevalence, 1.4% vs 1.0%; PR, 2.20 [95% CI, 1.72-2.82]), female sex (prevalence, 60.3% vs 59.0%; PR, 1.07 [95% CI, 1.01-1.13]), and current smoking (prevalence, 25.2% vs 17.5%; PR, 1.33 [95% CI, 1.22-1.45]). PRISm, compared with normal spirometry, was significantly associated with greater all-cause mortality (29.6/1000 person-years vs 18.0/1000 person-years; difference, 11.6/1000 person-years [95% CI, 10.0-13.1]; adjusted hazard ratio [HR], 1.50 [95% CI, 1.42-1.59]), respiratory-related mortality (2.1/1000 person-years vs 1.0/1000 person-years; difference, 1.1/1000 person-years [95% CI, 0.7-1.6]; adjusted HR, 1.95 [95% CI, 1.54-2.48]), CHD-related mortality (5.4/1000 person-years vs 2.6/1000 person-years; difference, 2.7/1000 person-years [95% CI, 2.1-3.4]; adjusted HR, 1.55 [95% CI, 1.36-1.77]), respiratory-related events (12.2/1000 person-years vs 6.0/1000 person-years; difference, 6.2/1000 person-years [95% CI, 4.9-7.5]; adjusted HR, 1.90 [95% CI, 1.69-2.14]), and CHD-related events (11.7/1000 person-years vs 7.0/1000 person-years; difference, 4.7/1000 person-years [95% CI, 3.7-5.8]; adjusted HR, 1.30 [95% CI, 1.18-1.42]). Conclusions and Relevance: In a large, population-based sample of US adults, baseline PRISm, compared with normal spirometry, was associated with a small but statistically significant increased risk for mortality and adverse cardiovascular and respiratory outcomes. Further research is needed to explore whether this association is causal.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Forced Expiratory Volume; Humans; Lung; Lung Diseases; Male; Middle Aged; Prevalence; Retrospective Studies; Spirometry; United States; Vital Capacity

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Cardiovascular Risk Factors Across the Life Course and Cognitive Decline: A Pooled Cohort Study. - Yaffe, Kristine; Vittinghoff, Eric; Hoang, Tina; Matthews, Karen; Golden, Sherita H; Zeki Al Hazzouri, Adina (Neurology, 2021)
OBJECTIVE: Cardiovascular risk factors (CVRFs) are associated with increased risk of cognitive decline, but little is known about how early adult CVRFs and those across the life course might influence late-life cognition. To test the hypothesis that CVRFs across the adult life course are associated with late-life cognitive changes, we pooled data from 4 prospective cohorts (n = 15,001, ages 18-95). METHODS: We imputed trajectories of body mass index (BMI), fasting glucose (FG), systolic blood pressure (SBP), and total cholesterol (TC) for older adults. We used linear mixed models to determine the association of early adult, midlife, and late-life CVRFs with late-life decline on global cognition (Modified Mini-Mental State Examination [3MS]) and processing speed (Digit Symbol Substitution Test [DSST]), adjusting for demographics, education, and cohort. RESULTS: Elevated BMI, FG, and SBP (but not TC) at each time period were associated with greater late-life decline. Early life CVRFs were associated with the greatest change, an approximate doubling of mean 10-year decline (an additional 3-4 points for 3MS or DSST). Late-life CVRFs were associated with declines in early late life (<80 years) but with gains in very late life (≥80 years). After adjusting for CVRF exposures at all time periods, the associations for early adult and late-life CVRFs persisted. CONCLUSIONS: We found that imputed CVRFs across the life course, especially in early adulthood, were associated with greater late-life cognitive decline. Our results suggest that CVRF treatment in early adulthood could benefit late-life cognition, but that treatment in very late life may not be as helpful for these outcomes.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Blood Pressure; Cardiovascular Diseases; Cognition; Cognitive Dysfunction; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Hypertension; Male; Middle Aged; Risk Factors; Young Adult

Depressive Symptoms Imputed Across the Life Course Are Associated with Cognitive Impairment and Cognitive Decline. - Brenowitz, Willa D; Zeki Al Hazzouri, Adina; Vittinghoff, Eric; Golden, Sherita H; Fitzpatrick, Annette L; Yaffe, Kristine (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms may increase risk for dementia, but findings are controversial because late-life depression may be a prodromal dementia symptom. Life course data on depression and dementia risk may clarify this association; however, data is limited. OBJECTIVE: To impute adult depressive symptoms trajectories across adult life stages and estimate the association with cognitive impairment and decline. METHODS: Using a pooled study of 4 prospective cohorts (ages 20-89), we imputed adult life course depressive symptoms trajectories based on Center for Epidemiologic Studies Depression Scale-10 (CESD-10) and calculated time-weighted averages for early adulthood (ages 20-49), mid-life (ages 50-69), and late-life (ages 70-89) for 6,122 older participants. Adjusted pooled logistic and mixed-effects models estimated associations of imputed depressive symptoms with two cognitive outcomes: cognitive impairment defined by established criteria and a composite cognitive score. RESULTS: In separate models, elevated depressive symptoms in each life stage were associated with cognitive outcomes: early adulthood OR for cognitive impairment = 1.59 (95%CI: 1.35,1.87); mid-life OR = 1.94 (95%CI:1.16, 3.26); and late-life OR = 1.77 (95%CI:1.42, 2.21). When adjusted for depressive symptoms in the other life-stages, elevated depressive symptoms in early adulthood (OR = 1.73; 95%CI: 1.42,2.11) and late-life (OR = 1.43; 95%CI: 1.08,1.89) remained associated with cognitive impairment and were also associated with faster rates of cognitive decline (p < 0.05). CONCLUSION: Imputing depressive symptom trajectories from pooled cohorts may help expand data across the life course. Our findings suggest early adulthood depressive symptoms may be a risk factor for cognitive impairment independent of mid- or late-life depressive symptoms.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Cohort Studies; Dementia; Depression; Female; Humans; Male; Middle Aged; Prodromal Symptoms; Risk Factors

Egg consumption, overall diet quality, and risk of type 2 diabetes and coronary heart disease: A pooling project of US prospective cohorts. - Djoussé, Luc; Zhou, Guohai; McClelland, Robyn L; Ma, Nanxun; Zhou, Xia; Kabagambe, Edmond K; Talegawkar, Sameera A; Judd, Suzanne E; Biggs, Mary L; Fitzpatrick, Annette L; Clark, Cheryl R; Gagnon, David R; et al. (Clin Nutr, 2021)
BACKGROUND AND AIMS: Data on the relation of egg consumption with risk of type 2 diabetes (T2D) and coronary heart disease (CHD) are limited and inconsistent. Few studies have controlled for overall dietary patterns in egg-T2D or egg-CHD analyses, and it is unclear whether any observed elevated risks of T2D and CHD with frequent egg consumption is real or due to confounding by dietary habits. We tested the hypothesis that frequent egg consumption is associated with a higher risk of T2D and CHD risk after adjustment for overall dietary patterns among adults. DESIGN: We used prospective cohort design to complete time-to-event analyses. METHODS: We pooled de novo, harmonized, individual-level analyses from nine US cohorts (n = 103,811). Cox regression was used to estimate hazard ratios separately in each cohort adjusting for age, ethnicity, body mass index (BMI), exercise, smoking, alcohol intake, and dietary patterns. We pooled cohort-specific results using an inverse-variance weighted method to estimate summary relative risks. RESULTS: Median age ranged from 25 to 72 years. Median egg consumption was 1 egg per week in most of the cohorts. While egg consumption up to one per week was not associated with T2D risk, consumption of ≥2 eggs per week was associated with elevated risk [27% elevated risk of T2D comparing 7+ eggs/week with none (95% CI: 16%-37%)]. There was little evidence for heterogeneity across cohorts and we observed similar conclusions when stratified by BMI. Overall, egg consumption was not associated with the risk of CHD. However, in a sensitivity analysis, there was a 30% higher risk of CHD (95% CI: 3%-56%) restricted to older adults consuming 5-6 eggs/week. CONCLUSIONS: Our data showed an elevated risk of T2D with egg consumption of ≥2 eggs per week but not with <2 eggs/week. While there was no overall association of egg consumption with CHD risk, the elevated CHD observed with consumption of 5-6 eggs/week in older cohorts merits further investigation.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Diet; Eggs; Humans; Middle Aged; Prospective Studies; Risk Factors; United States

Epigenetic Age and the Risk of Incident Atrial Fibrillation. - Roberts, Jason D; Vittinghoff, Eric; Lu, Ake T; Alonso, Alvaro; Wang, Biqi; Sitlani, Colleen M; Mohammadi-Shemirani, Pedrum; Fornage, Myriam; Kornej, Jelena; Brody, Jennifer A; Arking, Dan E; Lin, Honghuang; et al. (Circulation, 2021)
BACKGROUND: The most prominent risk factor for atrial fibrillation (AF) is chronological age; however, underlying mechanisms are unexplained. Algorithms using epigenetic modifications to the human genome effectively predict chronological age. Chronological and epigenetic predicted ages may diverge in a phenomenon referred to as epigenetic age acceleration (EAA), which may reflect accelerated biological aging. We sought to evaluate for associations between epigenetic age measures and incident AF. METHODS: Measures for 4 epigenetic clocks (Horvath, Hannum, DNA methylation [DNAm] PhenoAge, and DNAm GrimAge) and an epigenetic predictor of PAI-1 (plasminogen activator inhibitor-1) levels (ie, DNAm PAI-1) were determined for study participants from 3 population-based cohort studies. Cox models evaluated for associations with incident AF and results were combined via random-effects meta-analyses. Two-sample summary-level Mendelian randomization analyses evaluated for associations between genetic instruments of the EAA measures and AF. RESULTS: Among 5600 participants (mean age, 65.5 years; female, 60.1%; Black, 50.7%), there were 905 incident AF cases during a mean follow-up of 12.9 years. Unadjusted analyses revealed all 4 epigenetic clocks and the DNAm PAI-1 predictor were associated with statistically significant higher hazards of incident AF, though the magnitudes of their point estimates were smaller relative to the associations observed for chronological age. The pooled EAA estimates for each epigenetic measure, with the exception of Horvath EAA, were associated with incident AF in models adjusted for chronological age, race, sex, and smoking variables. After multivariable adjustment for additional known AF risk factors that could also potentially function as mediators, pooled EAA measures for 2 clocks remained statistically significant. Five-year increases in EAA measures for DNAm GrimAge and DNAm PhenoAge were associated with 19% (adjusted hazard ratio [HR], 1.19 [95% CI, 1.09-1.31]; <0.01) and 15% (adjusted HR, 1.15 [95% CI, 1.05-1.25]; <0.01) higher hazards of incident AF, respectively. Mendelian randomization analyses for the 5 EAA measures did not reveal statistically significant associations with AF. CONCLUSIONS: Our study identified adjusted associations between EAA measures and incident AF, suggesting that biological aging plays an important role independent of chronological age, though a potential underlying causal relationship remains unclear. These aging processes may be modifiable and not constrained by the immutable factor of time.
Keywords: Aged; Aging; Atrial Fibrillation; DNA Methylation; Epigenesis, Genetic; Epigenomics; Female; Follow-Up Studies; Humans; Incidence; Male; Mendelian Randomization Analysis; Middle Aged; Models, Cardiovascular; Models, Genetic

Meta-analyses identify DNA methylation associated with kidney function and damage. - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Adeyemo, Adebowale A; et al. (Nat Commun, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
Keywords: Adult; Aged; CpG Islands; DNA Methylation; Female; Glomerular Filtration Rate; Humans; Interferon Regulatory Factors; Kidney; Kidney Function Tests; LIM Domain Proteins; Male; Membrane Proteins; Middle Aged; Renal Insufficiency, Chronic; Transcription Factors

Sex Differences in Cognitive Decline Among US Adults. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Hingtgen, Stephanie; Elkind, Mitchell S V; Manly, Jennifer J; Gottesman, Rebecca F; et al. (JAMA Netw Open, 2021)
Importance: Sex differences in dementia risk are unclear, but some studies have found greater risk for women. Objective: To determine associations between sex and cognitive decline in order to better understand sex differences in dementia risk. Design, Setting, and Participants: This cohort study used pooled analysis of individual participant data from 5 cohort studies for years 1971 to 2017: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Linear mixed-effects models were used to estimate changes in each continuous cognitive outcome over time by sex. Data analysis was completed from March 2019 to October 2020. Exposure: Sex. Main Outcomes and Measures: The primary outcome was change in global cognition. Secondary outcomes were change in memory and executive function. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition. Results: Among 34 349 participants, 26 088 who self-reported Black or White race, were free of stroke and dementia, and had covariate data at or before the first cognitive assessment were included for analysis. Median (interquartile range) follow-up was 7.9 (5.3-20.5) years. There were 11 775 (44.7%) men (median [interquartile range] age, 58 [51-66] years at first cognitive assessment; 2229 [18.9%] Black) and 14 313 women (median [interquartile range] age, 58 [51-67] years at first cognitive assessment; 3636 [25.4%] Black). Women had significantly higher baseline performance than men in global cognition (2.20 points higher; 95% CI, 2.04 to 2.35 points; P < .001), executive function (2.13 points higher; 95% CI, 1.98 to 2.29 points; P < .001), and memory (1.89 points higher; 95% CI, 1.72 to 2.06 points; P < .001). Compared with men, women had significantly faster declines in global cognition (-0.07 points/y faster; 95% CI, -0.08 to -0.05 points/y; P < .001) and executive function (-0.06 points/y faster; 95% CI, -0.07 to -0.05 points/y; P < .001). Men and women had similar declines in memory (-0.004 points/y faster; 95% CI, -0.023 to 0.014; P = .61). Conclusions and Relevance: The results of this cohort study suggest that women may have greater cognitive reserve but faster cognitive decline than men, which could contribute to sex differences in late-life dementia.
Keywords: Aged; Cognitive Dysfunction; Cognitive Reserve; Cohort Studies; Executive Function; Humans; Memory; Middle Aged; Risk; Sex Factors; Time Factors; United States

Supplemental Association of Clonal Hematopoiesis With Incident Heart Failure. - Yu, Bing; Roberts, Mary B; Raffield, Laura M; Zekavat, Seyedeh Maryam; Nguyen, Ngoc Quynh H; Biggs, Mary L; Brown, Michael R; Griffin, Gabriel; Desai, Pinkal; Correa, Adolfo; Morrison, Alanna C; Shah, Amil M; et al. (J Am Coll Cardiol, 2021)
BACKGROUND: Age-related clonal hematopoiesis of indeterminate potential (CHIP), defined as clonally expanded leukemogenic sequence variations (particularly in DNMT3A, TET2, ASXL1, and JAK2) in asymptomatic individuals, is associated with cardiovascular events, including recurrent heart failure (HF). OBJECTIVES: This study sought to evaluate whether CHIP is associated with incident HF. METHODS: CHIP status was obtained from whole exome or genome sequencing of blood DNA in participants without prevalent HF or hematological malignancy from 5 cohorts. Cox proportional hazards models were performed within each cohort, adjusting for demographic and clinical risk factors, followed by fixed-effect meta-analyses. Large CHIP clones (defined as variant allele frequency >10%), HF with or without baseline coronary heart disease, and left ventricular ejection fraction were evaluated in secondary analyses. RESULTS: Of 56,597 individuals (59% women, mean age 58 years at baseline), 3,406 (6%) had CHIP, and 4,694 developed HF (8.3%) over up to 20 years of follow-up. CHIP was prospectively associated with a 25% increased risk of HF in meta-analysis (hazard ratio: 1.25; 95% confidence interval: 1.13-1.38) with consistent associations across cohorts. ASXL1, TET2, and JAK2 sequence variations were each associated with an increased risk of HF, whereas DNMT3A sequence variations were not associated with HF. Secondary analyses suggested large CHIP was associated with a greater risk of HF (hazard ratio: 1.29; 95% confidence interval: 1.15-1.44), and the associations for CHIP on HF with and without prior coronary heart disease were homogenous. ASXL1 sequence variations were associated with reduced left ventricular ejection fraction. CONCLUSIONS: CHIP, particularly sequence variations in ASXL1, TET2, and JAK2, represents a new risk factor for HF.
Keywords: Aged; Clonal Hematopoiesis; Correlation of Data; Demography; DNA-Binding Proteins; Female; Heart Failure; Humans; Janus Kinase 2; Male; Middle Aged; Mutation; Proportional Hazards Models; Proto-Oncogene Proteins; Repressor Proteins; Risk Factors; Stroke Volume; Ventricular Dysfunction, Left; Whole Exome Sequencing

Total carotenoid intake is associated with reduced loss of grip strength and gait speed over time in adults: The Framingham Offspring Study. - Sahni, Shivani; Dufour, Alyssa B; Fielding, Roger A; Newman, Anne B; Kiel, Douglas P; Hannan, Marian T; Jacques, Paul F (Am J Clin Nutr, 2021)
BACKGROUND: Lower antioxidant serum concentrations have been linked to declines in lean mass and physical function in older adults. Yet population data on the effect of dietary antioxidants on loss of muscle strength and physical function are lacking. OBJECTIVE: We sought to determine the association of antioxidant intake [vitamin C, vitamin E, and total and individual carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lycopene, and lutein + zeaxanthin)] with annualized change in grip strength and gait speed in adults from the Framingham Offspring study. METHODS: This prospective cohort study included participants with a valid FFQ at the index examination and up to 2 prior examinations and at ≥2 measures of primary outcomes: grip strength (n = 2452) and/or gait speed (n = 2422) measured over 3 subsequent examinations. Annualized change in grip strength (kg/y) and change in gait speed (m/s/y) over the follow-up period were used. Linear regression was used to calculate β coefficients and P values, adjusting for covariates. RESULTS: Mean ± SD age of participants was 61 ± 9 y (range: 33-88 y). Median intakes (IQR, mg/d) of vitamin C, vitamin E, and total carotenoid across available examinations were 209.2 (133.1-394.2), 27.1 (7.4-199.0), and 15.3 (10.4-21.3), respectively. The mean follow-up time was ∼12 ± 2 y (range: 4.5-15.4 y). In the sex-combined sample, higher intakes of total carotenoids, lycopene, and lutein + zeaxanthin were associated with increased annualized change in grip strength [β (SE) per 10-mg higher intake/d, range: 0.0316 (0.0146) to 0.1223 (0.0603) kg/y)]. All antioxidants except for vitamin C were associated with faster gait speed [β (SE) per 10-mg higher intake/d, range: 0.00008 (0.00004) to 0.0187 (0.0081) m/s/y]. CONCLUSIONS: Higher antioxidant intake was associated with increase in grip strength and faster gait speed in this cohort of adults. This finding highlights the need for a randomized controlled trial of dietary antioxidants and their effect on muscle strength and physical function.
Keywords: Adult; Aged; Aged, 80 and over; Carotenoids; Cohort Studies; Diet; Female; Hand Strength; Humans; Male; Middle Aged; Prospective Studies; Walking Speed

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Intake and Sources of Dietary Fiber, Inflammation, and Cardiovascular Disease in Older US Adults. - Shivakoti, Rupak; Biggs, Mary L; Djoussé, Luc; Durda, Peter Jon; Kizer, Jorge R; Psaty, Bruce; Reiner, Alex P; Tracy, Russell P; Siscovick, David; Mukamal, Kenneth J (JAMA Netw Open, 2022)
Importance: Higher intake of dietary fiber has been associated with lower inflammation, but whether there are differences in this association by source of dietary fiber (ie, cereal, vegetable, or fruit) has not been studied to date. Objectives: To evaluate the associations of total fiber intake and source (ie, cereal, vegetable, and fruit fiber intake) with inflammation and to evaluate whether inflammation mediates the inverse association between dietary fiber intake and cardiovascular disease (CVD). Design, Setting, and Participants: At the baseline visit (1989-1990) of 4125 adults aged 65 years or older in an ongoing US cohort study, dietary intake was assessed by a food frequency questionnaire among study participants without prevalent CVD (stroke and myocardial infarction) at enrollment. Inflammation was assessed from blood samples collected at baseline with immunoassays for markers of inflammation. Multivariable linear regression models tested the association of dietary fiber intake with inflammation. Also assessed was whether each inflammatory marker and its composite derived from principal component analysis mediated the association of baseline cereal fiber intake with development of CVD (stroke, myocardial infarction, and atherosclerotic cardiovascular death) through June 2015. Data from June 1, 1989, through June 30, 2015, were analyzed. Exposures: Total fiber intake and sources of fiber (cereal, vegetable, and fruit). Main Outcomes and Measures: Systemic markers of inflammation. Cardiovascular disease was the outcome in the mediation analysis. Results: Of 4125 individuals, 0.1% (n = 3) were Asian or Pacific Islander, 4.4% (n = 183) were Black, 0.3% (n = 12) were Native American, 95.0% (n = 3918) were White, and 0.2% (n = 9) were classified as other. Among these 4125 individuals (2473 women [60%]; mean [SD] age, 72.6 [5.5] years; 183 Black individuals [4.4%]; and 3942 individuals of other races and ethnicitites [95.6%] [ie, race and ethnicity other than Black, self-classified by participant]), an increase in total fiber intake of 5 g/d was associated with significantly lower concentrations of C-reactive protein (adjusted mean difference, -0.05 SD; 95% CI, -0.08 to -0.01 SD; P = .007) and interleukin 1 receptor antagonist (adjusted mean difference, -0.04 SD; 95% CI, -0.07 to -0.01 SD; P < .02) but with higher concentrations of soluble CD163 (adjusted mean difference, 0.05 SD; 95% CI, 0.02-0.09 SD; P = .005). Among fiber sources, only cereal fiber was consistently associated with lower inflammation. Similarly, cereal fiber intake was associated with lower CVD incidence (adjusted hazard ratio, 0.90; 95% CI, 0.81-1.00; 1941 incident cases). The proportion of the observed association of cereal fiber with CVD mediated by inflammatory markers ranged from 1.5% for interleukin 18 to 14.2% for C-reactive protein, and 16.1% for their primary principal component. Conclusions and Relevance: Results of this study suggest that cereal fiber intake was associated with lower levels of various inflammatory markers and lower risk of CVD and that inflammation mediated approximately one-sixth of the association between cereal fiber intake and CVD.
Keywords: Adult; Aged; Cardiovascular Diseases; Cohort Studies; Dietary Fiber; Female; Humans; Inflammation; Middle Aged; Risk Factors

Plasma Levels of Advanced Glycation Endproducts and Risk of Cardiovascular Events: Findings From 2 Prospective Cohorts. - Lamprea-Montealegre, Julio A; Arnold, Alice M; McClelland, Robyn L; Mukamal, Kenneth J; Djoussé, Luc; Biggs, Mary L; Siscovick, David S; Tracy, Russell P; Beisswenger, Paul J; Psaty, Bruce M; Ix, Joachim H; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Advanced glycation endproducts (AGEs) have been linked to cardiovascular disease (CVD) in cohorts with and without diabetes. Data are lacking on prospective associations of various α-dicarbonyl-derived AGEs and incident CVD in the general population. We tested the hypothesis that major plasma AGEs are associated with new-onset CVD in 2 population-based cohorts of differing age and comorbidities. Methods and Results Analyses involved a random subcohort (n=466) from the Cardiovascular Health Study and a case-cohort sample (n=1631) from the Multi-Ethnic Study of Atherosclerosis. Five AGEs and 2 oxidative products were measured by liquid chromatography tandem mass spectrometry. Associations with CVD (myocardial infarction and stroke) were evaluated with Cox regression. Participants in the Cardiovascular Health Study were older than the Multi-Ethnic Study of Atherosclerosis, and had more comorbidities, along with higher levels of all AGEs. During median follow-up of 11 years, 439 participants in the Multi-Ethnic Study of Atherosclerosis and 200 in the Cardiovascular Health Study developed CVD. After multivariable adjustment, carboxymethyl-lysine, 3-deoxyglucosone hydroimidazolones and a summary variable of all measured AGEs (principal component 1) were significantly associated with incident CVD in the Cardiovascular Health Study (HRs [95% CI]: 1.20 [1.01, 1.42], 1.45 [1.23, 1.72], and 1.29 [1.06, 1.56], respectively), but not the Multi-Ethnic Study of Atherosclerosis. Oxidative products were not associated with CVD in either cohort. Conclusions We found α-dicarbonyl-derived AGEs to be associated with CVD in an older cohort, but not in a healthier middle-aged/older cohort. Our results suggest that AGEs may exert detrimental cardiovascular effects only under conditions of marked dicarbonyl and oxidative stress. Further investigation of α-dicarbonyl derivatives could lead to potential new strategies for CVD prevention in high-risk older populations.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Glycation End Products, Advanced; Humans; Middle Aged; Risk Factors

Pooled Cohort Probability Score for Subclinical Airflow Obstruction. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Jaeger, Byron C; Cassano, Patricia A; Chaves, Paulo H; Couper, David; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Lloyd-Jones, Donald; Newman, Anne B; et al. (Ann Am Thorac Soc, 2022)
Early detection of chronic obstructive pulmonary disease (COPD) is a public health priority. Airflow obstruction is the single most important risk factor for adverse COPD outcomes, but spirometry is not routinely recommended for screening. To describe the burden of subclinical airflow obstruction (SAO) and to develop a probability score for SAO to inform potential detection and prevention programs. Lung function and clinical data were harmonized and pooled across nine U.S. general population cohorts. Adults with respiratory symptoms, inhaler use, or prior diagnosis of COPD or asthma were excluded. A probability score for prevalent SAO (forced expiratory volume in 1 second/forced vital capacity < 0.70) was developed via hierarchical group-lasso regularization from clinical variables in strata of sex and smoking status, and its discriminative accuracy for SAO was assessed in the pooled cohort as well as in an external validation cohort (NHANES [National Health and Nutrition Examination Survey] 2011-2012). Incident hospitalizations and deaths due to COPD (respiratory events) were defined by adjudication or administrative criteria in four of nine cohorts. Of 33,546 participants (mean age 52 yr, 54% female, 44% non-Hispanic White), 4,424 (13.2%) had prevalent SAO. The incidence of respiratory events ( = 14,024) was threefold higher in participants with SAO versus those without (152 vs. 39 events/10,000 person-years). The probability score, which was based on six commonly available variables (age, sex, race and/or ethnicity, body mass index, smoking status, and smoking pack-years) was well calibrated and showed excellent discrimination in both the testing sample (C-statistic, 0.81; 95% confidence interval [CI], 0.80-0.82) and in NHANES (C-statistic, 0.83; 95% CI, 0.80-0.86). Among participants with predicted probabilities ⩾ 15%, 3.2 would need to undergo spirometry to detect one case of SAO. Adults with SAO demonstrate excess respiratory hospitalization and mortality. A probability score for SAO using commonly available clinical risk factors may be suitable for targeting screening and primary prevention strategies.
Keywords: Adult; Female; Forced Expiratory Volume; Humans; Lung; Male; Middle Aged; Nutrition Surveys; Pulmonary Disease, Chronic Obstructive; Risk Factors; Spirometry; Vital Capacity

Association between 5-year change in cardiovascular risk and the incidence of atherosclerotic cardiovascular diseases: a multi-cohort study. - Yi, Jiayi; Wang, Lili; Guo, Xinli; Ren, Xiangpeng (J Transl Med, 2023)
BACKGROUND: The influence of the historical cardiovascular risk status on future risk of atherosclerotic cardiovascular disease (ASCVD) is poorly understood. We aimed to investigate the association between 5-year changes in cardiovascular risk and ASCVD incidence. METHODS: We analyzed pooled data from seven community-based prospective cohort studies with up to 20 years of follow-up data. The study populations included White or Black participants aged 40-75 years without prevalent ASCVD. Cardiovascular risk was assessed using the pooled cohort equation and was categorized into non-high (< 20%) or high risk (≥ 20%). Changes in cardiovascular disease (CVD) risk over a 5-year interval were recorded. The main outcome was incident ASCVD. RESULTS: Among 11,026 participants (mean [SD] age, 60.0 [8.1] years), 4272 (38.7%) were female and 3127 (28.4%) were Black. During a median follow-up period of 9.9 years, 2560 (23.2%) ASCVD events occurred. In comparison with individuals showing a consistently high CVD risk, participants whose CVD risk changed from non-high to high (hazard ratio [HR], 0.67; 95% confidence interval [CI] 0.59-0.77) or high to non-high (HR, 0.57; 95% CI 0.41-0.80) and those with a consistently non-high risk (HR, 0.33; 95% CI 0.29-0.37) had a lower risk of incident ASCVD. In comparison with individuals showing a consistently non-high CVD risk, participants whose CVD risk changed from high to non-high (HR, 1.74; 95% CI 1.26-2.41) or from non-high to high risk (HR, 2.04; 95% CI 1.84-2.27) and those with a consistently high risk (HR 3.03; 95% CI 2.69-3.42) also showed an increased risk of incident ASCVD. CONCLUSIONS: Individuals with the same current CVD risk status but different historical CVD risks exhibited varying risks of future ASCVD incidents. Dynamic risk evaluation may enable more accurate cardiovascular risk stratification, and decision-making regarding preventive interventions should take the historical risk status into account.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors

Association of Obesity With Cognitive Decline in Black and White Americans. - Quaye, Emmanuel; Galecki, Andrzej T; Tilton, Nicholas; Whitney, Rachael; Briceño, Emily M; Elkind, Mitchell S V; Fitzpatrick, Annette L; Gottesman, Rebecca F; Griswold, Michael; Gross, Alden L; Heckbert, Susan R; Hughes, Timothy M; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: There are disparities in the prevalence of obesity by race, and the relationship between obesity and cognitive decline is unclear. The objective of this study was to determine whether obesity is independently associated with cognitive decline and whether the association between obesity and cognitive decline differs in Black and White adults. We hypothesized that obesity is associated with greater cognitive decline compared with normal weight and that the effect of obesity on cognitive decline is more pronounced in Black adults compared with their White counterparts. METHODS: We pooled data from 28,867 participants free of stroke and dementia (mean, SD: age 61 [10.7] years at the first cognitive assessment, 55% female, 24% Black, and 29% obese) from 6 cohorts. The primary outcome was the annual change in global cognition. We performed linear mixed-effects models with and without time-varying cumulative mean systolic blood pressure (SBP) and fasting plasma glucose (FPG). Global cognition was set to a t-score metric (mean 50, SD 10) at a participant's first cognitive assessment; a 1-point difference represents a 0.1 SD difference in global cognition across the 6 cohorts. The median follow-up was 6.5 years (25th percentile, 75th percentile: 5.03, 20.15). RESULTS: Obese participants had lower baseline global cognition than normal-weight participants (difference in intercepts, -0.36 [95% CI, -0.46 to -0.17]; < 0.001). This difference in baseline global cognition was attenuated but was borderline significant after accounting for SBP and FPG (adjusted differences in intercepts, -0.19 [95% CI, -0.39 to 0.002]; = 0.05). There was no difference in the rate of decline in global cognition between obese and normal-weight participants (difference in slope, 0.009 points/year [95% CI, -0.009 to 0.03]; = 0.32). After accounting for SBP and FPG, obese participants had a slower decline in global cognition (adjusted difference in slope, 0.03 points/year slower [95% CI, 0.01 to 0.05]; < 0.001). There was no evidence that race modified the association between body mass index and global cognitive decline ( = 0.34). DISCUSSION: These results suggest that obesity is associated with lower initial cognitive scores and may potentially attenuate declines in cognition after accounting for BP and FPG.
Keywords: Aged; Black or African American; Cognition; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Obesity; Risk Factors; United States; White

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts. - Ong, Kwok Leung; Marklund, Matti; Huang, Liping; Rye, Kerry-Anne; Hui, Nicholas; Pan, Xiong-Fei; Rebholz, Casey M; Kim, Hyunju; Steffen, Lyn M; van Westing, Anniek C; Geleijnse, Johanna M; Hoogeveen, Ellen K; et al. (BMJ, 2023)
OBJECTIVE: To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). DESIGN: Pooled analysis. DATA SOURCES: A consortium of 19 studies from 12 countries identified up to May 2020. STUDY SELECTION: Prospective studies with measured n-3 PUFA biomarker data and incident CKD based on estimated glomerular filtration rate. DATA EXTRACTION AND SYNTHESIS: Each participating cohort conducted de novo analysis with prespecified and consistent exposures, outcomes, covariates, and models. The results were pooled across cohorts using inverse variance weighted meta-analysis. MAIN OUTCOME MEASURES: Primary outcome of incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m. In a sensitivity analysis, incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m and <75% of baseline rate. RESULTS: 25 570 participants were included in the primary outcome analysis and 4944 (19.3%) developed incident CKD during follow-up (weighted median 11.3 years). In multivariable adjusted models, higher levels of total seafood n-3 PUFAs were associated with a lower incident CKD risk (relative risk per interquintile range 0.92, 95% confidence interval 0.86 to 0.98; P=0.009, I=9.9%). In categorical analyses, participants with total seafood n-3 PUFA level in the highest fifth had 13% lower risk of incident CKD compared with those in the lowest fifth (0.87, 0.80 to 0.96; P=0.005, I=0.0%). Plant derived α linolenic acid levels were not associated with incident CKD (1.00, 0.94 to 1.06; P=0.94, I=5.8%). Similar results were obtained in the sensitivity analysis. The association appeared consistent across subgroups by age (≥60 <60 years), estimated glomerular filtration rate (60-89 ≥90 mL/min/1.73 m), hypertension, diabetes, and coronary heart disease at baseline. CONCLUSIONS: Higher seafood derived n-3 PUFA levels were associated with lower risk of incident CKD, although this association was not found for plant derived n-3 PUFAs. These results support a favourable role for seafood derived n-3 PUFAs in preventing CKD.
Keywords: alpha-Linolenic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Humans; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Boerwinkle, Eric; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Development and Validation of the American Heart Association's PREVENT Equations. - Khan, Sadiya S; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Grams, Morgan E; Surapaneni, Aditya; Blaha, Michael J; Carson, April P; Chang, Alexander R; Ciemins, Elizabeth; Go, Alan S; Gutierrez, Orlando M; et al. (Circulation, 2024)
BACKGROUND: Multivariable equations are recommended by primary prevention guidelines to assess absolute risk of cardiovascular disease (CVD). However, current equations have several limitations. Therefore, we developed and validated the American Heart Association Predicting Risk of CVD EVENTs (PREVENT) equations among US adults 30 to 79 years of age without known CVD. METHODS: The derivation sample included individual-level participant data from 25 data sets (N=3 281 919) between 1992 and 2017. The primary outcome was CVD (atherosclerotic CVD and heart failure). Predictors included traditional risk factors (smoking status, systolic blood pressure, cholesterol, antihypertensive or statin use, and diabetes) and estimated glomerular filtration rate. Models were sex-specific, race-free, developed on the age scale, and adjusted for competing risk of non-CVD death. Analyses were conducted in each data set and meta-analyzed. Discrimination was assessed using the Harrell C-statistic. Calibration was calculated as the slope of the observed versus predicted risk by decile. Additional equations to predict each CVD subtype (atherosclerotic CVD and heart failure) and include optional predictors (urine albumin-to-creatinine ratio and hemoglobin A1c), and social deprivation index were also developed. External validation was performed in 3 330 085 participants from 21 additional data sets. RESULTS: Among 6 612 004 adults included, mean±SD age was 53±12 years, and 56% were women. Over a mean±SD follow-up of 4.8±3.1 years, there were 211 515 incident total CVD events. The median C-statistics in external validation for CVD were 0.794 (interquartile interval, 0.763-0.809) in female and 0.757 (0.727-0.778) in male participants. The calibration slopes were 1.03 (interquartile interval, 0.81-1.16) and 0.94 (0.81-1.13) among female and male participants, respectively. Similar estimates for discrimination and calibration were observed for atherosclerotic CVD- and heart failure-specific models. The improvement in discrimination was small but statistically significant when urine albumin-to-creatinine ratio, hemoglobin A1c, and social deprivation index were added together to the base model to total CVD (ΔC-statistic [interquartile interval] 0.004 [0.004-0.005] and 0.005 [0.004-0.007] among female and male participants, respectively). Calibration improved significantly when the urine albumin-to-creatinine ratio was added to the base model among those with marked albuminuria (>300 mg/g; 1.05 [0.84-1.20] versus 1.39 [1.14-1.65]; =0.01). CONCLUSIONS: PREVENT equations accurately and precisely predicted risk for incident CVD and CVD subtypes in a large, diverse, and contemporary sample of US adults by using routinely available clinical variables.
Keywords: Adult; Aged; Albumins; American Heart Association; Atherosclerosis; Cardiovascular Diseases; Creatinine; Female; Glycated Hemoglobin; Heart Failure; Humans; Male; Middle Aged; Risk Assessment; Risk Factors

Large-Scale Proteomics Identifies Novel Biomarkers and Circulating Risk Factors for Aortic Stenosis. - Shelbaya, Khaled; Arthur, Victoria; Yang, Yimin; Dorbala, Pranav; Buckley, Leo; Claggett, Brian; Skali, Hicham; Dufresne, Line; Yang, Ta-Yu; Engert, James C; Thanassoulis, George; Floyd, James; et al. (J Am Coll Cardiol, 2024)
BACKGROUND: Limited data exist regarding risk factors for aortic stenosis (AS). The plasma proteome is a promising phenotype for discovery of novel biomarkers and potentially causative mechanisms. OBJECTIVES: The aim of this study was to discover novel biomarkers with potentially causal associations with AS. METHODS: We measured 4,877 plasma proteins (SomaScan aptamer-affinity assay) among ARIC (Atherosclerosis Risk In Communities) study participants in mid-life (visit 3 [V3]; n = 11,430; age 60 ± 6 years) and in late-life (V5; n = 4,899; age 76 ± 5 years). We identified proteins cross-sectionally associated with aortic valve (AV) peak velocity (AVmax) and dimensionless index by echocardiography at V5 and with incident AV-related hospitalization after V3 with the use of multivariable linear and Cox proportional hazard regression. We assessed associations of candidate proteins with changes in AVmax over 6 years and with AV calcification with the use of cardiac computed tomography, replicated analysis in an independent sample, performed Mendelian randomization, and evaluated gene expression in explanted human AV tissue. RESULTS: Fifty-two proteins cross-sectionally were associated with AVmax and dimensionless index at V5 and with risk of incident AV-related hospitalization after V3. Among 3,413 participants in the Cardiovascular Health Study, 6 of those proteins were significantly associated with adjudicated moderate or severe AS, including matrix metalloproteinase 12 (MMP12), complement C1q tumor necrosis factor-related protein 1 (C1QTNF1), and growth differentiation factor-15. MMP12 was also associated with greater increase in AVmax over 6 years, greater degree of AV calcification, and greater expression in calcific compared with normal or fibrotic AV tissue. C1QTNF1 had consistent potential causal effects on both AS and AVmax according to Mendelian randomization analysis. CONCLUSIONS: These findings identify MMP12 as a potential novel circulating biomarker of AS risk and C1QTNF1 as a new putative target to prevent AS progression.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Biomarkers; Calcinosis; Humans; Matrix Metalloproteinase 12; Middle Aged; Proteomics; Risk Factors